1,4-bis(5-decyl-2,2′-bithien-5-yl)benzene as new stable organic semiconductor for high performance thin film transistors - Ponomarenko, S.; Kirchmeyer, S.; Halik, Marcus; Klauk, Hagen; Zschieschang, Ute; Schmid, Günter; Karbach, A.; Drechsler, D.; Alpatova, N. M. (Synthetic Metals, 2005)

2D van der Waals Heterojunction of Organic and Inorganic Monolayers for High Responsivity Phototransistors - Zhao, Baolin; Gan, Ziyang; Johnson, Manuel; Najafidehaghani, Emad; Rejek, Tobias; George, Antony; Fink, Rainer; Turchanin, Andrey; Halik, Marcus (Advanced Functional Materials, 2021)
Van der Waals (vdW) heterostructures composing of organic molecules with inorganic 2D crystals open the door to fabricate various promising hybrid devices. Here, a fully ordered organic self-assembled monolayer (SAM) to construct hybrid organic–inorganic vdW heterojunction phototransistors for highly sensitive light detection is used. The heterojunctions, formed by layering MoS2 monolayer crystals onto organic [12-(benzo[b]benzo[4,5]thieno[2,3-d]thiophen-2-yl)dodecyl)]phosphonic acid SAM, are characterized by Raman and photoluminescence spectroscopy as well as Kelvin probe force microscopy. Remarkably, this vdW heterojunction transistor exhibits a superior photoresponsivity of 475 A W−1 and enhanced external quantum efficiency of 1.45 × 105%, as well as an extremely low dark photocurrent in the pA range. This work demonstrates that hybridizing SAM with 2D materials can be a promising strategy for fabricating diversified optoelectronic devices with unique properties.
CRIS-Team Scopus Importer:2021-08-06
Keywords: charge transfer; organic–inorganic hybrid; photodetection; self-assembled monolayer; transition metal dichalcogenides; van der Waals heterojunction

3D-Printed Multifunctional Hydrogels with Phytotherapeutic Properties: Development of Essential Oil-Incorporated ALG-XAN Hydrogels for Wound Healing Applications - Ünalan, Irem; Schrüfer, Stefan; Schubert, Dirk W.; Boccaccini, Aldo R. (ACS Biomaterials Science and Engineering, 2023)
This study aimed to develop three-dimensional (3D)-printed hydrogels containing phytotherapeutic agents as multifunctional wound dressings. In this regard, 3D-printed sodium alginate (ALG)-xanthan gum (XAN) hydrogels incorporated with different clove essential oil (CLV) concentrations were produced by the extrusion-based 3D-printing technology. Rheology measurements, filament fusion, and filament collapse analyses indicated that XAN’s blending overcame the challenges associated with ALG’s printability and shape fidelity. Attenuated total reflection-Fourier-transform infrared (ATR-FTIR) spectra and total phenolic content assay confirmed the presence of CLV in the 3D-printed hydrogels. Additionally, the releasing profile showed that CLV exhibited long-term release for up to 28 days. Furthermore, the incorporation of CLV increased 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging while reducing the S. aureus and E. coli relative bacterial viability; thereby, the CLV incorporation enhanced the 3D-printed ALG-XAN hydrogel antioxidant and antibacterial activity. In addition, anti-inflammatory activity was assessed using Raw 264.7 macrophage-like cells, and the results demonstrated that CLV reduced nitric oxide (NO) concentration in medium, indicating a potential anti-inflammatory effect. Moreover, in vitro cytotoxicity results showed that the incorporation of CLV has no toxic effect on NHDF cells, whereas the proliferation of NHDF cells exhibited a dose-dependent response. In conclusion, the present study shows not only the development of a new ALG-XAN biomaterial ink but also the potential benefit of natural phytotherapeutics incorporated into 3D-printed hydrogels as a multifunctional wound dressing.
CRIS-Team Scopus Importer:2023-07-21
Keywords: 3D printing; essential oils; hydrogels; phytotherapeutic agents; sodium alginate; wound healing; xanthan gum

3D Printing of Mechanically Resistant Poly (Glycerol Sebacate) (PGS)-Zein Scaffolds for Potential Cardiac Tissue Engineering Applications - Ruther, Florian; Roether, Judith; Boccaccini, Aldo R. (Advanced Engineering Materials, 2022)
Due to the limited regenerative capacity of the natural human myocardium, 3D printing of the cyclic polyester poly (glycerol sebacate) (PGS) offers a promising alternative to produce scaffolds (cardiac patches) for cardiac tissue engineering. Since the 3D printability and subsequent thermal crosslinking of pure PGS without any modification or additives are challenging, a PGS-zein-salt-based printing process is developed in this work by mixing PGS pre-polymer with ground and sieved sodium chloride particles and additionally with different amounts of the corn protein zein. The resulting inks show excellent printability and high shape fidelity both during the printing process and after thermal crosslinking. Chemical analysis indicates the successful integration of zein into the PGS backbone. Mechanical characterization shows the anisotropic behavior of the structure in the alternating printing direction. Subsequent biological assessments reveal no cytotoxic effects on C2C12 cells, rendering the developed PGS-zein combination a suitable material for 3D printing of cardiac patches.
CRIS-Team Scopus Importer:2022-04-15
Keywords: 3D printing; cardiac tissue engineering; poly (glycerol sebacate); self-regulating properties; zein

45S5 bioactive glass-based scaffolds coated with cellulose nanowhiskers for bone tissue engineering - Li, Wei; Garmendia, Nere; De Larraya, Uxua Perez; Ding, Yaping; Detsch, Rainer; Gruenewald, Alina; Roether, Judith; Schubert, Dirk W.; Boccaccini, Aldo R. (RSC Advances, 2014)
Highly porous 45S5 bioactive glass-based scaffolds prepared by foam replication method were coated with cellulose nanowhiskers by dip coating method. The obtained cellulose nanowhisker-coated scaffolds retained the high porosity and interconnected pore structure. The cellulose coating improved the mechanical properties of the scaffolds and did not hinder their bioactivity in simulated body fluid. In vitro biocompatibility assessment was carried out by qualitative evaluation of the morphology of osteoblast-like cells (MG-63) seeded onto the scaffolds. The cells were shown to attach and spread on both uncoated scaffolds and cellulose nanowhisker-coated scaffolds, thus cellulose nanowhisker coating seems to have no negative influence on the behavior of MG-63 cells. The obtained bioactive and biocompatible composite scaffolds represent promising candidates for bone tissue engineering applications.

70-cm-Yagis - Schubert, Dirk W. (CQ DL, 2019)
Wer beim Wandern und im Urlaub auf Amateurfunk nicht verzichten möchte, arbeitet vorteilhaft auf UKW, denn dabei sind die Antennen leicht und handlich. Für das 70-cm-Band ausgelegt wurden die hier unterbreiteten einfachen Vorschläge für Yagis.<br
Keywords: YAGIS; UKW; Amateurfunk

Abrasion-Induced Acceleration of Melt Crystallisation of Wet Comminuted Polybutylene Terephthalate (PBT) - Tischer, Florentin; Düsenberg, Björn; Gräser, Timo; Kaschta, Joachim; Schmidt, Jochen; Peukert, Wolfgang (Polymers, 2022)
Within this contribution, the effect of grinding media wear on the melt crystallisation of polybutylene terephthalate (PBT) is addressed. PBT was wet ground in a stirred media mill in ethanol using different grinding media beads (silica, chrome steel, cerium-stabilised and yttrium-stabilised zirconia) at comparable stress energies with the intention to use the obtained particles as feed materials for the production of feedstocks for laser powder bed fusion additive manufacturing (PBF-AM). In PBF‑AM, the feedstock’s optical, rheological and especially thermal properties—including melt crystallisation kinetics—strongly influence the processability and properties of the manufactured parts. The influence of process parameters and used grinding media during wet comminution on the optical properties, crystal structure, molar mass distribution, inorganic content (wear) and thermal properties of the obtained powders is discussed. A grinding media-dependent acceleration of the melt crystallisation could be attributed to wear particles serving as nuclei for heterogeneous crystallisation. Yttrium-stabilised zirconia grinding beads proved to be the most suitable for the production of polymer powders for the PBF process in terms of (fast) comminution kinetics, unchanged optical properties and the least accelerated crystallisation kinetics.<br
Keywords: wet comminution; stirred media mills; abrasion; polymer; additive manufacturing; powder bed fusion; thermal properties; isothermal DSC

A Case Study: Particulate-Filled Polyester Hybrid Laminated Composites, - Munawar, Muhammad; Schubert, Dirk W.; Khan, Shahzad Maqsood; Gull, Nafisa; Islam, Atif; Ur Rehman, Muhammad Atiq; Voigt, Monika (Polyester - Production, Characterization and Innovative Applications, 2018)

AC electrophoretic deposition of organic-inorganic composite coatings - Yoshioka, T.; Chavez-Valdez, Alejandra; Roether, Judith; Schubert, Dirk W.; Boccaccini, Aldo R. (Journal of Colloid and Interface Science, 2013)
Alternating current electrophoretic deposition (AC-EPD) of polyacrylic acid (PAA)-titanium oxide (TiO2) nanoparticle composites on stainless steel electrodes was investigated in basic aqueous solution. AC square wave with duty cycle of 80% was applied at a frequency of 1kHz. FTIR-ATR spectra showed that both AC and direct current (DC) EPD successfully deposited PAA-TiO2 composites. The deposition rate using AC-EPD was lower than that obtained in direct current DC-EPD. However, the microstructure and surface morphology of the deposited composite coatings were different depending on the type of electric field applied. AC-EPD applied for not more than 5min led to smooth films without bubble formation, while DC-EPD for 1min or more showed deposits with microstructural defects possibly as result of water electrolysis. AC-EPD was thus for the first time demonstrated to be a suitable technique to deposit organic-inorganic composite coatings from aqueous suspensions, showing that applying a square wave and frequency of 1kHz leads to uniform PAA-TiO2 composite coatings on conductive materials. © 2012 Elsevier Inc.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.acelec
Keywords: Alternating current (AC); Coatings; Composites; Electrophoretic deposition (EPD); Nanoparticles; Polyacrylic acid (PAA); Titanium oxide (TiO

A comparative study of mechanical properties of table tennis balls - Hiemer, Stefan; Fey, Tobias; Kaschta, Joachim; Schubert, Dirk W. (54th Nordic Polymer Days, 2017)

A comparative study of oxygen diffusion in tissue engineering scaffolds - Fiedler, T.; Belova, I. V.; Murch, G. E.; Poologasundarampillai, G.; Jones, J. R.; Roether, Judith; Boccaccini, Aldo R. (Journal of Materials Science: Materials in Medicine, 2014)
Tissue engineering scaffolds are designed to support tissue self-healing within physiological environments by promoting the attachment, growth and differentiation of relevant cells. Newly formed tissue must be supplied with sufficient levels of oxygen to prevent necrosis. Oxygen diffusion is the major transport mechanism before vascularization is completed and oxygen is predominantly supplied via blood vessels. The present study compares different designs for scaffolds in the context of their oxygen diffusion ability. In all cases, oxygen diffusion is confined to the scaffold pores that are assumed to be completely occupied by newly formed tissue. The solid phase of the scaffolds acts as diffusion barrier that locally inhibits oxygen diffusion, i.e. no oxygen passes through the scaffold material. As a result, the oxygen diffusivity is determined by the scaffold porosity and pore architecture. Lattice Monte Carlo simulations are performed to compare the normalized oxygen diffusivities in scaffolds obtained by the foam replication (FR) method, robocasting and sol-gel foaming. Scaffolds made by the FR method were found to have the highest oxygen diffusivity due to their high porosity and interconnected pores. These structures enable the best oxygen supply for newly formed tissue among the scaffold types considered according to the present numerical predictions.

A comprehensive study on recycled and virgin PET melt-spun fibers modified by PMDA chain extender - Qu, Muchao; Lu, Dong; Deng, Hongyi; Wu, Qiang; Han, Lei; Xie, Zixin; Qin, Yijing; Schubert, Dirk W. (Materials Today Communications, 2021)
The effect of chain extender Pyromellitic dianhydride (PMDA) on the comprehensive properties of the virgin (vPET) and recycled Polyethylene terephthalate (rPET) fibers was investigated. Five different weight fractions of PMDA were melt mixed with PETs to create long-chain branched (LCB) structures. The modified LCB-PET granules were melt spun into fibers using a capillary rheometer at 270 and 280 °C, and then aerodynamically stretched by an aspirator at seven take-up pressures. The different shear viscosity, thermal properties and spinnability of LCB-vPET and LCB-rPET, and the surface morphology, draw ratios, tenacity, elongation at break of PET fibers, as well as the performance-reliability plots using Weibull distribution were well discussed. A semi-empirical mathematical model further confirmed the exponential relationship between the tenacity and elongation at break of the PET fibers. This research depicts a visible window for academic and industrial researchers to produce PMDA modified PET fibers with desirable comprehensive properties.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Chain Extender; Modeling; PET fibers; PMDA; Weibull Distribution

A comprehensive study on the properties of polypropylene fibers and nonwovens in dependence of processing and storing conditions - Lanyi, Franz; Schubert, Dirk W. (Europe Africa Conference 2017 of the Polymer Processing Society, 2017)

Additive manufacturing of functional components - Recent developments and challenges for the future - Rechtenwald, Thomas; Frick, Thomas; von Wilmowsky, Cornelius; Pohle, Dirk; Amend, Philipp; Pscherer, Claudia; Schmidt, Michael (29th International Congress on Applications of Lasers and Electro-Optics, ICALEO 2010 - Congress Proceedings, 2010)
Additive manufacturing techniques are becoming more and more widespread in industry during the last years due to their high flexibility regarding part geometry. But a true breakthrough does not take place due to the limited choice of applicable materials and consequently the restricted functions the generated parts can fulfill especially in case of polymer materials. Certain process limitations like a special melt and crystallization behavior or an exact defined UV-curability restrict the material selection. One strategy beside the qualification of new materials could be the use of different functionalization approaches. These approaches include not only the possibility to improve certain part properties by filling materials or coating parts but also to establish new part functions. Besides filling or coating a further strategy to enhance the functionality of additive manufactured parts can be the embedding of functional components. This paper presents the challenges in manufacturing functional parts by means of additive technologies and discusses results on new materials and techniques in order to achieve this aim. It especially focuses on the industrial relevant additive technologies of laser sintering and stereolithography. In the field of laser sintering functional additives or coatings allow an improvement of the biocompatibility of individual implants made from PEEK but also the integration of electrical functions on the surface of laser sintered PA 12 parts usable as electronic circuit boards in the near future. Further a new technology 'embedded stereolithography' (E SLA) is shown which allows the fabrication of complex mechatronical modules in one manufacturing system. Based on the presented findings an outlook will be given which shows the necessary work for the future.
Created from Fastlane, Scopus look-up

Adhesion and metabolic activity of human corneal cells on PCL based nanofiber matrices - Stafiej, Piotr; Küng, Florian; Thieme, Daniel; Czugala, Marta; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Advances in Materials Science and Engineering, 2017)

Adhesion and metabolic activity of human corneal cells on PCL based nanofiber matrices. - Stafiej, Piotr; Küng, Florian; Thieme, Daniel; Czugala, Marta; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Materials Science and Engineering C, 2017)
In this work, polycaprolactone (PCL) was used as a basic polymer for electrospinning of random and aligned nanofiber matrices. Our aim was to develop a biocompatible substrate for ophthalmological application to improve wound closure in defects of the cornea as replacement for human amniotic membrane. We investigated whether blending the hydrophobic PCL with poly (glycerol sebacate) (PGS) or chitosan (CHI) improves the biocompatibility of the matrices for cell expansion. Human corneal epithelial cells (HCEp) and human corneal keratocytes (HCK) were used for in vitro biocompatibility studies. After optimization of the electrospinning parameters for all blends, scanning electron microscopy (SEM), attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), and water contact angle were used to characterize the different matrices. Fluorescence staining of the F-actin cytoskeleton of the cells was performed to analyze the adherence of the cells to the different matrices. Metabolic activity of the cells was measured by cell counting kit-8 (CCK-8) for 20days to compare the biocompatibility of the materials. Our results show the feasibility of producing uniform nanofiber matrices with and without orientation for the used blends. All materials support adherence and proliferation of human corneal cell lines with oriented growth on aligned matrices. Although hydrophobicity of the materials was lowered by blending PCL, no increase in biocompatibility or proliferation, as was expected, could be measured. All tested matrices supported the expansion of human corneal cells, confirming their potential as substrates for biomedical applications.

Adipose- and bone marrow-derived mesenchymal stem cells display different osteogenic differentiation patterns in 3D bioactive glass-based scaffolds - Rath, Subha N.; Nooeaid, Patcharakamon; Arkudas, Andreas; Beier, Justus; Strobel, Leonie; Brandl, Andreas; Roether, Judith; Horch, Raymund E.; Boccaccini, Aldo R.; Kneser, Ulrich (Journal of Tissue Engineering and Regenerative Medicine, 2013)
Mesenchymal stem cells can be isolated from a variety of different sources, each having their own peculiar merits and drawbacks. Although a number of studies have been conducted comparing these stem cells for their osteo-differentiation ability, these are mostly done in culture plastics. We have selected stem cells from either adipose tissue (ADSCs) or bone marrow (BMSCs) and studied their differentiation ability in highly porous three-dimensional (3D) 45S5 Bioglass®-based scaffolds. Equal numbers of cells were seeded onto 5 × 5 × 4 mm(3) scaffolds and cultured in vitro, with or without osteo-induction medium. After 2 and 4 weeks, the cell-scaffold constructs were analysed for cell number, cell spreading, viability, alkaline phosphatase activity and osteogenic gene expression. The scaffolds with ADSCs displayed osteo-differentiation even without osteo-induction medium; however, with osteo-induction medium osteogenic differentiation was further increased. In contrast, the scaffolds with BMSCs showed no osteo-differentiation without osteo-induction medium; after application of osteo-induction medium, osteo-differentiation was confirmed, although lower than in scaffolds with ADSCs. In general, stem cells in 3D bioactive glass scaffolds differentiated better than cells in culture plastics with respect to their ALP content and osteogenic gene expression. In summary, 45S5 Bioglass-based scaffolds seeded with ADSCs are well-suited for possible bone tissue-engineering applications. Induction of osteogenic differentiation appears unnecessary prior to implantation in this specific setting. Copyright © 2013 John Wiley & Sons, Ltd.
UnivIS-Import:2015-03-09:Pub.2014.tech.IW.LM.adipos

Advancing Processing Technologies for Designed Geopolymers: 3D Printing and Mechanical Machining - Toniolo, Nicoletta; Bednarzig, Vera; Roether, Judith; Rost, Harald; Boccaccini, Aldo R. (Interceram, 2019)
Abstract: Geopolymers continue to attract interest owing to their good mechanical properties in combination with the ecofriendly fabrication process. However, the applications of geopolymers are still restricted to a limited field, mainly as construction materials. Designing and fabricating components of complex, intricate shape for applications beyond building materials may represent a useful approach to broaden geopolymer applications. In this study, unconventional processing and finishing technologies, such as direct ink printing, drilling, and machining are investigated to demonstrate their suitability for geopolymers. Fly ash-based geopolymers incorporating a relevant amount of waste glass demonstrated suitable flow properties to be used in a direct ink printing process. Moreover, the geopolymer specimens showed high machinability: components were drilled and machined in a lathe obtaining superior surface finish, uniform dimensional accuracy, and complex shape parts. The results presented herein indicate opportunities for expanding applications of geopolymers in areas such as mechanical engineering, where components with accurate, specifically designed shapes and surface finish are needed.
CRIS-Team Scopus Importer:2019-08-13

A dyciandiamine-based methacrylate-epoxy dual-cure blend-system for stereolithography - Romeis, Manuel; Drummer, Dietmar (Polymers, 2021)
In this research, an epoxy-based dual-cure system is developed and characterized for SLA additive manufacturing. Dual-cure systems consist of UV-curable acrylates and thermal active components. The second curing step offers an additional degree of freedom to design specific material properties. In this study, a blend of varying concentrations of an epoxy/curing agent mix, respectively, DGEBA, DICY and photocurable methacrylate, was used to create a material that is printable in the SLA process into a UV-cured or green part and subsequently thermally cured to achieve superior thermal and mechanical properties. Calorimetric measurements were performed to determine the reactivity of the thermal reaction at different concentrations of epoxy. The fully cured specimens were tested in mechanical and dynamic mechanical measurements, and the results showed a significant improvement in tensile stress and glass transition temperature with rising epoxy concentrations. Fractured surfaces from tensile testing were investigated to further characterize the failure of tested samples, and thermal degradation was determined in TGA measurements, which showed no significant changes with an increasing epoxy concentration.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Additive manufacturing (AM); Dual-cure; Stereolithography (SLA)

A facile approach to synthesize an oxo-functionalized graphene/polymer composite for low-voltage operating memory devices - Wang, Zhenxing; Eigler, Siegfried; Ishii, Yoshitaka; Hu, Yichen; Papp, Christian; Lytken, Ole; Steinrück, Hans-Peter; Halik, Marcus (Journal of Materials Chemistry C, 2015)
Memory devices are a key technology of our era and one of the constant challenges is the reduction of their power consumption. Herein, we demonstrate that graphene oxide with very few defects, that is, about 1 nm thin oxo-functionalized graphene derivative, can be used in memory devices operating at 3 V. A memory device stores charges in the material of the active channel. Thereby, writing and erasing information can be performed at low voltage, facilitating low power consumption. To enable operation at low voltage, a novel synthetic approach is necessary. We find that the selective non-covalent electrostatic functionalization of mainly organosulfate ions is possible with dodecylammonium. This functionalization allows the non-covalent coating of flakes with a polystyrene-derivative as nm-thin dielectric medium. The resulting polymer-wrapped composite has a height of about 5 nm. We find that the thin coating of a few nm is mandatory to make the memory device work at low voltage. Furthermore, a self-assembled monolayer of an imidazolium derivative further enhances the function of the memory device. The prepared composite materials are characterized by state-of-the-art analysis including solid state nuclear magnetic resonance spectroscopy and thermogravimetric analysis coupled with gas chromatography, mass spectroscopy or infrared spectroscopy. Reference experiments prove the importance of the controlled synthesis to enable the function of the memory device.

A generic interface to reduce the efficiency-stability-cost gap of perovskite solar cells - Hou, Yi; Du, Xiaoyan; Scheiner, Simon; McMeekin, David P.; Wang, Zhiping; Li, Ning; Killian, Manuela; Chen, Haiwei; Richter, Moses; Levchuk, Ievgen; Schrenker, Nadine; Spiecker, Erdmann; et al. (Science, 2017)
A major bottleneck delaying the further commercialization of thin-film solar cells based on hybrid organohalide lead perovskites is the interface losses in state-of-the-art devices. We present a generic interface architecture that combines solution-processed, reliable, and cost-efficient hole-transporting materials, without compromising efficiency, stability or scalability of perovskite solar cells. Tantalum doped tungsten oxide (Ta-WOx)/conjugated polymer multilayers offer a surprisingly small interface barrier and form quasi-ohmic contacts universally with various scalable conjugated polymers. Using a simple regular planar architecture device, Ta-WOx doped interface-based perovskite solar cells achieve maximum efficiencies of 21.2% and combined with over 1000 hours of light stability based on a self-assembled monolayer. By eliminating additional ionic dopants, these findings open up the whole class of organics as scalable hole-transporting materials for perovskite solar cell

Alginate-based hydrogels with improved adhesive properties for cell encapsulation - Sarker, Bapi; Rompf, Julia; Silva, Raquel; Lang, Nadine; Detsch, Rainer; Kaschta, Joachim; Fabry, Ben; Boccaccini, Aldo R. (International Journal of Biological Macromolecules, 2015)
Hydrogel-based biomaterials are ideal scaffolding matrices for microencapsulation, but they need to be modified to resemble the mechanical, structural and chemical properties of the native extracellular matrix. Here, we compare the mechanical properties and the degradation behavior of unmodified and modified alginate hydrogels in which cell adhesive functionality is conferred either by blending or covalently cross-linking with gelatin. Furthermore, we measure the spreading and proliferation of encapsulated osteoblast-like MG-63 cells. Alginate hydrogels covalently crosslinked with gelatin show the highest degree of cell adhesion, spreading, migration, and proliferation, as well as a faster degradation rate, and are therefore a particularly suitable material for microencapsulation.
Keywords: Alginate; Cell encapsulation; Hydrogel

Alginate/Bioglass® composite coatings on stainless steel deposited by direct current and alternating current electrophoretic deposition - Chen, Qiang; Cordero Arias, Luis Eduardo; Roether, Judith; Cabanas Polo, Sandra; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Surface & Coatings Technology, 2013)
Direct current (DC) and alternating current (AC) electrophoretic deposition (EPD) approaches involving different number of EPD cycles were developed for the fabrication of alginate/Bioglass® composite coatings from water-based suspensions. The high stability of the colloidal suspension was confirmed by zeta-potential assessment and the properties of coatings deposited from both DC-EPD and AC-EPD were quantitatively compared by using a range of characterization methods. The deposition yield and coating composition were determined by mass and thermogravimetric analysis. Coatings with different microstructure and thickness were observed by scanning electron microscopy. Significant differences in surface roughness and hydrophilicity (determined by water contact angle measurement) of coatings obtained by DC-EPD and AC-EPD were identified and discussed. The coating adhesion strength and corrosion resistance were evaluated by standard tape test and electrochemical method, respectively, and the experimental data showed the superior adhesion and corrosion resistance of AC-EPD coatings compared to DC-EPD coatings. In order to investigate the in vitro bioactivity, all coatings were immersed in simulated body fluid for 7. days. Results from Fourier transform infrared spectroscopy (FTIR) analysis showed the typical characteristic peaks of hydroxyapatite formed on both DC- and AC-EPD coatings. Based on the results of this study, bioactive alginate/Bioglass® coatings are proposed as suitable candidates for applications in dental and orthopedic metallic implants and for bone tissue scaffolds. © 2013 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.algina
Keywords: Alginate; Bioactive glass; Bioactivity; Biomedical coatings; Electrophoretic deposition

Aligned PCL/Collagen electrospun nanofibers for skeletal muscle tissue engineering using benign solvents - Dippold, Dirk; Schubert, Dirk W.; Beier, Justus; Boccaccini, Aldo R. (14th Bayreuth Polymer Symposium, 2015)

Ambient Intelligence – Key Technologies in the Information Age - Weber, W.; Brederlow, R.; Briole, S.; Glaser, R.; Gsottberger, Y.; Halik, Marcus; Jung, S.; Klauk, Hagen; Lauterbach, C.; Schmid, Günter; Sturm, T.; Stromberg, Guido; et al. (Technical Digest - International Electron Devices Meeting, 2003)

Ambipolar, low-voltage and low-hysteresis PbSe nanowire field-effect transistors by electrolyte gating - Lokteva, Irina; Thiemann, Stefan; Gannott, Florentina; Zaumseil, Jana (Nanoscale, 2013)
Semiconductor nanowire field-effect transistors (FETs) are interesting for fundamental studies of charge transport as well as possible applications in electronics. Here, we report low-voltage, low-hysteresis and ambipolar PbSe nanowire FETs using electrolyte-gating with ionic liquids and ion gels. We obtain balanced hole and electron mobilities at gate voltages below 1 V. Due to the large effective capacitance of the ionic liquids and thus high charge carrier densities electrolyte-gated nanowire FETs are much less affected by external doping and traps than nanowire FETs with traditional dielectrics such as SiO2. The observed current–voltage characteristics and on/off ratios indicate almost completely transparent Schottky barriers and efficient ambipolar charge injection into a low band gap one-dimensional semiconductor. Finally, we explore the possibility of applying these ambipolar nanowire FETs in complementary inverters for printed electronics.
EAM Import::2019-03-13

A method to reveal bulk and surface crystallinity of Polypropylene by FTIR spectroscopy - Suitable for fibers and nonwovens - Lanyi, Franz; Wenzke, Nicolai; Kaschta, Joachim; Schubert, Dirk W. (Polymer Testing, 2018)
Keywords: X-ray diffraction; Isotactic Polypropylene; Processing; Crystallinity; Fourier-transform infrared spectroscopy; Fiber spinning

An 8V Organic Complementary Logic Process for Flexible Polymeric Substrates - Klauk, Hagen; Halik, Marcus; Zschieschang, Ute; Eder, F.; Schmid, Günter; Dehm, C. (SID Conference Record of the International Display Research Conference, 2004)

Analog Signal Processing with Organic FETs - Gay, N.; Fischer, W. J.; Halik, Marcus; Klauk, Hagen; Zschieschang, Ute; Schmid, Günter (Digest of Technical Papers - IEEE International Solid-State Circuits Conference, 2006)

An Alternating Skin–Core Structure in Melt Multi-Injection-Molded Polyethylene - Liu, Xianhu; Lian, Meng; Pan, Yamin; Wang, Xin; Zheng, Guoqiang; Liu, Chuntai; Schubert, Dirk W.; Shen, Changyu (Macromolecular Materials and Engineering, 2017)
Shish‐kebab, which is endowed with superior strength and modulus, provides the potential to fabricate self‐reinforced polymer products. However, the injection‐molded product usually exhibits a typical skin–core structure, and the shish‐kebab is only located in an extremely thin shear layer. Therefore, the controlling and tailoring of crystal structures in complex flow field to improve the mechanical properties of the injection‐molded sample are still a great challenge. Herein, for the first time, high‐density polyethylene sample with a novel macroscopic alternating skin–core structure is achieved using a melt multi‐injection molding technique. Results show that, with increasing the amount of melt injection, the layers of skin–core structure increase in the form of arithmetic progression, and therefore the tensile strength of the samples progressively increases due to an increase of shish‐kebab content. This study demonstrates a new approach to achieve multilayer homogeneous materials with excellent tensile strength via macroscopic structural design during the practical molding proces
Keywords: shish-kebab; skin–core structure; injection molding; polyethylene

Analysis and Modeling of the Influence of the Size and Fraction of Bonding Points onto the Mechanical Behaviour of Polypropylene Spunbond Nonwovens - Leucker, Karsten; Schubert, Dirk W. (Advanced Engineering Materials, 2019)
While the influence of fiber strength and calendering parameters on the mechanical strength of polypropylene spunbond nonwovens are investigated extensively, only a few nonsystematic studies are available on the influence of bonding point size and bonding point fraction. Therefore, systematic investigations of the influence of bonding point fraction, bonding point size, and spacing on the tensile properties of nonwovens are conducted. In addition, the influence of fiber orientation and cloudiness on the strength is evaluated. It is demonstrated that an increase in the bonding fraction leads to an increase in stiffness and strength, although this effect is weakened due to fiber damage at the edges of bonding points, when many small bonding points are used. An increase in bonding point size and distance between the points with a constant bonding fraction initially leads to an increase in strength. Only when the distance between the points exceeds, the size of the local nonuniformities the strength decreases again, whereas the stiffness decreases continuously with increasing distance between the bonding points. In addition, it is shown that the stress-strain behavior of nonwovens can be described using a Maxwell model and that the strengths can be modeled using statistical modeling with optically accessible parameters.
CRIS-Team WoS Importer:2019-11-12

Analysis of gel from silicone breast implants made by Poly Implant Prothese and other manufactures - Schubert, Dirk W.; Horch, Raymund E.; Kaschta, Joachim (13th Bayreuth Polymer Symposium, 2013)

Analysis of Strain and Defects in Tellurium-WSe2 Moiré Heterostructures Using Scanning Nanodiffraction - Sari, Bengisu; Zeltmann, Steven E.; Zhao, Chunsong; Pelz, Philipp; Javey, Ali; Minor, Andrew M.; Ophus, Colin; Scott, Mary C. (ACS nano, 2023)
In recent years, there has been an increasing focus on 2D nongraphene materials that range from insulators to semiconductors to metals. As a single-elemental van der Waals semiconductor, tellurium (Te) has captivating anisotropic physical properties. Recent work demonstrated growth of ultrathin Te on WSe2 with the atomic chains of Te aligned with the armchair directions of the substrate using physical vapor deposition (PVD). In this system, a moiré superlattice is formed where micrometer-scale Te flakes sit on top of the continuous WSe2 film. Here, we determined the precise orientation of the Te flakes with respect to the substrate and detailed structure of the resulting moiré lattice by combining electron microscopy with image simulations. We directly visualized the moiré lattice using center of mass-differential phase contrast (CoM-DPC). We also investigated the local strain within the Te/WSe2 layered materials using scanning nanodiffraction techniques. There is a significant tensile strain at the edges of flakes along the direction perpendicular to the Te chain direction, which is an indication of the preferred orientation for the growth of Te on WSe2. In addition, we observed local strain relaxation regions within the Te film, specifically attributed to misfit dislocations, which we characterize as having a screw-like nature. The detailed structural analysis gives insight into the growth mechanisms and strain relaxation in this moiré heterostructure.
CRIS-Team Scopus Importer:2023-12-08
Keywords: defects; moiré superlattices; scanning nanodiffraction; strain; tellurium; WSe

Analysis Of The Diffusion Properties Of Cyclic Siloxanes Through Silicone Elastomers - Influence Of Crosslinking And Penetrant Size - Daenicke, Jonas; Schubert, Dirk W.; Gedde, Ulf; Hedenqvist, Mikael; Linde, Erik; Sigl, Thomas; Horch, Raymund E. (Book of Abstracts, 2016)

Analysis of the spinning process and batch-to-batch consistency of aligned PCL/Collagen nanofibers for skeletal muscle - Dippold, Dirk; Schubert, Dirk W. (Europe Africa Conference 2017 of the Polymer Processing Society, 2017)

Analytical and Empirical Consequences from the Correlation of the Cox/Merz-Relation with the Carreau Function - Schubert, Dirk W.; Ziegmann, Andreas (Polychar 21st, 2013)

Analytical and empirical consequences from the correlation of the Cox/Merz-relation with the Carreau function - Ziegmann, Andreas; Schubert, Dirk W. (13th Bayreuth Polymer Symposium, 2013)

Analytical and Empirical Consequences of the Postulated Agreement Between the Cox/Merz-Relation and the Carreau Function - Ziegmann, Andreas; Schubert, Dirk W. (WILEY-V C H VERLAG GMBH, 2016)
We postulate that the Cox/Merz relation and the Carreau function both describe identically the shear-rate-dependent viscosity of a polymer melt. We find that an exponentially decreasing relaxation time distribution and an exponentially increasing relaxation strength distribution can describe the experimental rheological data with respect to storage G' and loss modulus G '' in the literature. We have therefore applied such exponential distributions as well as trial functions to calculate G', G '' and the corresponding shear-rate-dependent viscosity utilizing the Cox/Merz relation. The expansion of the viscosity in a Taylor series, utilizing the Cox/Merz relation and the Carreau function, makes it possible to compare the frequency and shear-rate coefficients, and this results in a system of coupled transcendental equations. We justify the empirical value of m = 1/3 mostly utilized for the Carreau function and prove the square (n = 2) in the denominator of the Carreau function to be a fundamental fact, independent of the above-mentioned formulation of the relaxation time and relaxation strength distributions. Moreover, the empirical relation (gamma) over dot(c) . eta(0) approximate to 10(4) Pa is confirmed by our pure mathematical approach.
Keywords: Carreau function; Cox/Merz-relation; relaxation spectrum; rheology; viscosity

Analyzing the transmission of visible light through electrospun nanofibrous PCL scaffolds - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Nordic Polymer Days, Helsinki (Finland), 2021, 2021)

An anionic organic mixed-valence system with a remarkably well-resolved vibrational structure in its intervalence band - Risko, C.; Barlow, S.; Coropceanu, V.; Halik, Marcus; Bredas, J. L.; Marder, S. R. (Chemical Communications, 2003)

A new printable alginate / hyaluronic acid / gelatin hydrogel suitable for biofabrication of in vitro and in vivo metastatic melanoma models - Schmid, Rafael; Schmidt, Sonja; Detsch, Rainer; Horder, Hannes; Blunk, Torsten; Schrüfer, Stefan; Schubert, Dirk W.; Fischer, Lena; Thievessen, Ingo; Heltmann-Meyer, Stefanie; Steiner, Dominik; Schneidereit, Dominik; et al. (Advanced Functional Materials, 2021)
Two-dimensional (2D) cancer models have been the standard for drug development over the past few years, but they frequently do not resemble in vivo properties adequately. 3D models are superior in many aspects and are, therefore, more similar to human pathophysiology. Over the past years, the emerging field of biofabrication has made significant advances, resulting in even more sophisticated 3D models. With this study, a hydrogel is created for biofabrication that is suitable for mimicking the tumor microenvironment in vitro and is further tested as a new vascularized melanoma model in vivo. The alginate/hyaluronic acid/gelatin bioink shows good shape-fidelity, high cell survival rates, and enables successful cultivation of melanoma cells and adipose-derived stem cells as well as cell differentiation in vitro. In vivo, in the arteriovenous loop model, it proves to be a unique method to study melanoma progression, tumor vascularization, and ultimately and reliably metastases in an isolated and controlled environment. These results show that this 3D model is very application-oriented for molecular research and therapy developmen

A New Printable Alginate/Hyaluronic Acid/Gelatin Hydrogel Suitable for Biofabrication of In Vitro and In Vivo Metastatic Melanoma Models - Schmid, Rafael; Schmidt, Sonja; Detsch, Rainer; Horder, Hannes; Blunk, Torsten; Schrüfer, Stefan; Schubert, Dirk W.; Fischer, Lena; Thievessen, Ingo; Heltmann-Meyer, Stefanie; Steiner, Dominik; Schneidereit, Dominik; et al. (Advanced Functional Materials, 2021)
Two-dimensional (2D) cancer models have been the standard for drug development over the past few years, but they frequently do not resemble in vivo properties adequately. 3D models are superior in many aspects and are, therefore, more similar to human pathophysiology. Over the past years, the emerging field of biofabrication has made significant advances, resulting in even more sophisticated 3D models. With this study, a hydrogel is created for biofabrication that is suitable for mimicking the tumor microenvironment in vitro and is further tested as a new vascularized melanoma model in vivo. The alginate/hyaluronic acid/gelatin bioink shows good shape-fidelity, high cell survival rates, and enables successful cultivation of melanoma cells and adipose-derived stem cells as well as cell differentiation in vitro. In vivo, in the arteriovenous loop model, it proves to be a unique method to study melanoma progression, tumor vascularization, and ultimately and reliably metastases in an isolated and controlled environment. These results show that this 3D model is very application-oriented for molecular research and therapy development.
CRIS-Team Scopus Importer:2021-10-22
Keywords: bioinks; metastasis; stem cells; tissue engineering; tumors

A new printable alginate / hyaluronic acid / gelatin hydrogel suitable for biofabrication of in vitro and in vivo metastatic melanoma models - Schmid, Rafael; Schmidt, Sonja; Detsch, Rainer; Horder, Hannes; Blunk, Torsten; Schrüfer, Stefan; Schubert, Dirk W.; Fischer, Lena; Thievessen, Ingo; Heltmann-Meyer, Stefanie; Steiner, Dominik; Schneidereit, Dominik; et al. (Advanced Functional Materials, 2022)

An experimental investigation of the draw resonance in film casting of polypropylene melts - Grieß, Hans Jürgen; Münstedt, Helmut; Burghelea, Teodor; Schubert, Dirk W. (Book of Abstracts, 2012)

Angiogenic potential of bioactive glasses - Gorustovich, Alejandro A.; Durand, Luis A.Haro; Roether, Judith; Boccaccini, Aldo R. (Imperial College Press, 2013)
CRIS-Team Scopus Importer:2022-08-05

An Innovative Anode Interface Combination for Perovskite Solar Cells with Improved Efficiency, Stability, and Reproducibility - Meng, Wei; Xu, Junyi; Dong, Lirong; Zhang, Jiyun; Xie, Zhiqiang; Luo, Junsheng; Zhao, Baolin; Zhang, Kaicheng; Osvet, Andres; Heumüller, Thomas; Forberich, Karen; Halik, Marcus; et al. (Solar RRL, 2022)
Rational design and engineering of top interface layers with combined properties of effective passivation, high thermal- and photo-stability are effective methods to advance the commercialization of perovskite photovoltaics. Here, an innovative anode interface combination is developed based on alcohol-dispersed poly (3-hexylthiophene-2,5-diyl) (P3HT) nanoparticles as the hole transport material and chlorobenzene-dissolved trioctylphosphine oxide (TO PO) as the passivation agent. It is shown that instead of the commonly used 2D passivation ligands, TOPO-passivated perovskite films exhibit greatly improved thermal stability. Furthermore, the passivation contributes to an enhanced carrier lifetime and reduced surface trap density, yielding an improvement in the quasi-fermi-level splitting of 57 meV. To maintain surface passivation during solution processing of further layers, it is necessary to develop a hole transport layer that can be processed from orthogonal solvents. P3HT nanoparticles formulated in alcoholic media fully meet this requirement, clearly benefitting from their high vertical conductivity and extremely low contact resistance with carbon electrodes. Based on this configuration, device efficiency of up to 18.4% is demonstrated for perovskite solar cells with fully solution-processed carbon electrodes, along with significantly improved device stability and reproducibility.
CRIS-Team WoS Importer:2022-06-17

An in situ investigation of the draw resonance phenomenon in film casting of a polypropylene melt - Burghelea, Teodor I.; Grieß, Hans Jürgen; Münstedt, Helmut (Journal of Non-Newtonian Fluid Mechanics, 2012)
An experimental investigation of the stability of the casting process of a polypropylene film is presented. By combined in situ measurements of the width of the cast film and Digital Particle Image Velocimetry (DPIV) measurements of the velocity distributions within the polymer film, several flow regimes are identified: stable, oscillatory and chaotic. Measurements of the velocity distribution along and across the extruded film corresponding to each drawing regime are presented. The intermittent physical rupture of the film's edges observed within the chaotic drawing regime is explained by the emergence of a " V-shaped" region of high axial gradients of the axial velocity component which indicates a highly inhomogeneous distribution of tensile stresses.By measurements of the statistics of the fluctuations of both the film's width and velocity a continuous (second order) imperfect bifurcation towards oscillatory states is found. The fluctuation data acquired before the chaotic regime is reached can be fitted by the stationary Landau-Ginsburg equation. The observation of a stable limit cycle at the onset of the bifurcation identifies it as a supercritical Hopf bifurcation. The experimentally found scaling of the onset and amplitude of the bifurcation with the Weissenberg number indicates that elasticity destabilizes the drawing process. This can be explained by the thinning behavior of the material in both shear and extension.The spectral analysis of the fluctuations of both film's width and point-wise velocity provides a quantitative description of the harmonics excited beyond the bifurcation point. The transition to chaotic states is accompanied by a major reorganization of the power spectra consistent with a period doubling bifurcation of a stable limit cycle. © 2012 Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Chaos; Coat hanger die; Draw resonance; Film casting; Imperfect bifurcation

Annealing Induced Mechanical Reinforcement of Injection Molded iPP Parts. - Pan, Yamin; Liu, Xian Hu; Shi, Suyu; Liu, Chuntai; Dai, Kun; Yin, Rui; Schubert, Dirk W.; Zheng, Guoqiang; Shen, Changyu (Macromolecular Materials and Engineering, 2016)
The mechanical properties and microstructure of injection molded isotactic polypropylene parts with high orientation before and after annealing are analyzed. The mechanical properties of the annealed samples are improved effectively. Through thorough analysis of various structural characterizations, a microstructural model based on the fact that the total length of long period kept constant to analyze the variation of mechanical properties is proposed. It is suggested that the increase of overall crystallinity, the recombination of crystalline phase, and the increase of amorphous phase, respectively, are beneficial for the improvements of the strength, stiffness, and toughness of annealed samples.

Annealing Induced Mechanical Reinforcement of Injection Molded iPP Parts - Pan, Yamin; Liu, Xian Hu; Shi, Suyu; Liu, Chuntai; Dai, Kun; Yin, Rui; Schubert, Dirk W.; Zheng, Guoqiang; Shen, Changyu (Macromolecular Materials and Engineering, 2016)
The mechanical properties and microstructure of injection molded isotactic polypropylene parts with high orientation before and after annealing are analyzed. The mechanical properties of the annealed samples are improved effectively. Through thorough analysis of various structural characterizations, a microstructural model based on the fact that the total length of long period kept constant to analyze the variation of mechanical properties is proposed. It is suggested that the increase of overall crystallinity, the recombination of crystalline phase, and the increase of amorphous phase, respectively, are beneficial for the improvements of the strength, stiffness, and toughness of annealed samples.
Keywords: Injection molding; Mechanical properties; Microstructure; Orientation

Annealing induced rheological and electrical conductivity variations in carbon black filled polymer composites - Liu, Xian Hu; Pan, Yamin; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Annual Meeting of the German Society for Biomaterials (DGBM), Denkendorf October 2021 - Munawar, Muhammad (Annual Meeting of the German Society for Biomaterials (DBGM), Denkendorf October 2021, 2021)

An organic-inorganic hybrid scaffold with honeycomb-like structures enabled by one-step self-assembly-driven electrospinning - Ding, Yaping; Li, Wei; Schubert, Dirk W.; Boccaccini, Aldo R.; Roether, Judith; Santos, Hélder A. (Materials Science and Engineering C, 2021)
Electrospun organic/inorganic hybrid scaffolds have been appealing in tissue regeneration owing to the integrated physicochemical and biological performances. However, the conventional electrospun scaffolds with non-woven structures usually failed to enable deep cell infiltration due to the densely stacked layers among the fibers. Herein, through self-assembly-driven electrospinning, a polyhydroxybutyrate/poly(ε-caprolactone)/58S sol-gel bioactive glass (PHB/PCL/58S) hybrid scaffold with honeycomb-like structures was prepared by manipulating the solution composition and concentration during a one-step electrospinning process. The mechanisms enabling the formation of self-assembled honeycomb-like structures were investigated through comparative studies using Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) between PHB/PCL/58S and PHB/PCL/sol-gel silica systems. The obtained honeycomb-like structure was built up from nanofibers with an average diameter of 370 nm and showed a bimodal distribution of pores: large polygonal pores up to hundreds of micrometers within the honeycomb-cells and irregular pores among the nanofibers ranging around few micrometers. The cell-materials interactions were further studied by culturing MG-63 osteoblast-like cells for 7 days. Cell viability, cell morphology and cell infiltration were comparatively investigated as well. While cells merely proliferated on the surface of non-woven structures, MG-63 cells showed extensive proliferation and deep infiltration up to 100–200 μm into the honeycomb-like structure. Moreover, the cellular spatial organization was readily regulated by the honeycomb-like pattern as well. Overall, the newly obtained hybrid scaffold may integrate the enhanced osteogenicity originating from the bioactive components, and the improved cell-material interactions brought by the honeycomb-like structure, making the new scaffold a promising candidate for tissue regeneration.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Electrospinning; Honeycomb-like architecture; Organic-inorganic hybrid scaffolds; Self-assembly

An outstanding antichlorine and antibacterial membrane with quaternary ammonium salts of alkenes via in situ polymerization for textile wastewater treatment - Liu, Chao; Guo, Yongqiang; Wei, Xinjing; Wang, Chao; Qu, Muchao; Schubert, Dirk W.; Zhang, Chunhua (Chemical Engineering Journal, 2019)
Developing an efficient and stable separation membrane material for textile water treatment is of considerable significance but challenging due to the limitation of chlorination degradation and bacterial fouling. To solve this problem, in this work, the amides groups in the polyamide structure were converted to imides by targeted grafted from diallyl dimethyl ammonium chloride (DADMAC) molecules. Consequently, chlorination degradation and bacterial fouling was markedly improved due to the reduction or elimination of N-H bonds and the increase of DADMAC grafting chains. Chlorine exposure experiment results showed that the salt rejection and water flux of modified membranes change less than that of the pristine membrane, and the surface morphology and chemical structure and basically remained unchanged. Meanwhile, the introduction of quaternary ammonium salt generated a hydrophilic and smooth membrane surface, thus improving the anti-fouling performance. In addition, with the advantage of an excellent antimicrobial activity, hardly any bacterial growth was observed even after 24 h culture, the membrane exhibits satisfactory stability in long-term textile water separation, which is considerable potential in the advanced wastewater treatment. The presented strategy on membrane preparation is believed to be a simple and effective method, which can also be widely used in other industrial wastewater treatment, such as medical wastewater, oilfield wastewater, etc.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Anti-biofouling; Anti-chlorine; Membrane fouling; Reverse osmosis membrane; Wastewater treatment

A Novel Approach for Spreading Dynamics of Polymer Fluids - Schubert, Dirk W.; Härth, Michael (9th Annual European Rheology Conference, 2014)

A novel simple approach to material parameters from commonly accessible rheometer data - Schrüfer, Stefan; Sonnleitner, D.; Lang, G.; Schubert, Dirk W. (Polymers, 2020)
When characterizing the viscoelastic properties of polymers, shear rheological measurements are commonly the method of choice. These properties are known to affect extrusion and nozzle-based processes such as fiber melt spinning, cast film extrusion and 3D-printing. However, an adequate characterization of shear thinning polymers can be challenging and still insufficient to not only describe but predict process relevant influences. Furthermore, the evaluation of rheological model systems in literature is mostly based on stress-relaxation experiments, which are rarely available for various polymeric materials. Therefore, a simple approach is presented, that can be used to evaluate and benchmark a wide range of rheological model systems based on commonly accessible frequency sweep data. The approach is validated by analyzing alginate PH176 solutions of various concentrations, a thermoplastic poly-urethane (TPU) Elastollan 1180A melt, the liquid silicon rubber Elastosil 7670 and a polycaprolactone (PCL) fiber-alginate composite system. The used rheological model systems, consisting of simple springs and dashpots, are suitable for the description of complex, viscoelastic material properties that can be observed for polymer solutions and gel-like systems. After revealing a suitable model system for describing those material properties, the determination and evaluation of relevant model parameters can take place. We present a detailed guideline for the systematic parameter revelation using alginate solutions of different concentrations as example. Furthermore, a starting point for future correlations of strut spreading in 3D-bioprinting and model parameters is revealed. This work establishes the basis for a better understanding and potential predictability of key parameters for various fabrication techniques.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Parameter determination; Rheological model systems; Rheology

A novel suture retention test for scaffold strength characterization in ophthalmology. - Küng, Florian; Schubert, Dirk W.; Stafiej, Piotr; Kruse, Friedrich; Fuchsluger, Thomas (Materials Science and Engineering C, 2016)
Sutures are a common way to attach scaffolds in patients. For tubular cardiac scaffolds, the 'suture retention strength' is commonly used to evaluate the resistance of a scaffold against the pull-out of a suture. In order to make this quantity accessible for ophthalmological scaffolds the test procedure has been modified in a novel way. Polycaprolactone (PCL) films of different thicknesses and an amniotic membrane (AM) were used for the experiments. Circular samples with a radius of 7mm were taken and a suture was passed through each sample and tied to a loop. The sample was clamped in a tensile tester and a bolt was passed through the loop. The suture was then pulled with a constant deformation rate until pull-out occurred. The suture retention strength, the deformation at the suture retention strength, and the deformation at rupture were determined for each sample. The presented modified suture retention test allows to measure the relevant parameters of samples on the scale of ophthalmological scaffolds in a reproducible way. A comparison between the first data on PCL and AM has been made.

Anthracene-Pentacene Dyads: Synthesis and OFET Characterization - Hauschild, Miriam; Chen, Lan; Etschel, Sebastian; Ferguson, Michael J.; Hampel, Frank; Halik, Marcus; Tykwinski, Rik R. (ChemPlusChem, 2020)
The synthesis of a series of unsymmetrical derivatives of pentacene appended with functionalized anthracene moieties is reported. These anthracene-pentacene dyads have been characterized by UV-vis spectroscopy and cyclic voltammetry to examine their electronic properties. X-ray crystallographic analysis was used to examine the solid-state features of anthracene-pentacene dyads 1 a-d with H-, F-, Cl-, and Br- substituents on the 9-position of anthracene, and shows that the packing arrangement of anthracene-pentacene derivatives 1 b,d,e are remarkably similar irrespective of the presence of fluoride, bromide or methyl substituents. The pentacene-anthracene dyads have been incorporated into OTFTs to evaluate their semiconducting properties. The pentacene derivative 1 b shows ambipolar behavior using AlOx C14 PA as the gate dielectric (electron and hole mobilities of 7.6 ⋅ 10-3 and 1.6 ⋅ 10-1 cm2 V-1 s-1 ), while performance of all derivatives was poor using p-doped Silicon as the substrate. These studies highlight the importance of thin-film formation over molecular structure.
CRIS-Team Scopus Importer:2020-05-22
Keywords: acenes; anthracenes; organic field-effect transistor; organic semiconductor; pentacenes

Antibacterial 45S5 Bioglass®-based scaffolds reinforced with genipin cross-linked gelatin for bone tissue engineering - Li, Wei; Wang, Hui; Ding, Yaping; Scheithauer, Ellen Corinna; Goudouri, Ourania Menti; Grünewald, Alina; Detsch, Rainer; Agarwal, Seema; Boccaccini, Aldo R. (Journal of Materials Chemistry B, 2015)
45S5 Bioglass® (BG) scaffolds with high porosity (>90%) were coated with genipin cross-linked gelatin (GCG) and further incorporated with poly(p-xylyleneguanidine) hydrochloride (PPXG). The obtained GCG coated scaffolds maintained the high porosity and well interconnected pore structure. A 26-fold higher compressive strength was provided to 45S5 BG scaffolds by GCG coating, which slightly retarded but did not inhibit the in vitro bioactivity of 45S5 BG scaffolds in SBF. Moreover, the scaffolds were made antibacterial against both Gram-positive and Gram-negative bacteria by using polyguanidine, i.e. PPXG, in this study. Osteoblast-like cells (MG-63) were seeded onto PPXG and GCG coated scaffolds. PPXG was biocompatible with MG-63 cells at a low concentration (10 μg mL-1). MG-63 cells were shown to attach and spread on both uncoated and GCG coated scaffolds, and the mitochondrial activity measurement indicated that GCG coating had no negative influence on the cell proliferation behavior of MG-63 cells. The developed novel antibacterial bioactive 45S5 BG-based composite scaffolds with improved mechanical properties are promising candidates for bone tissue engineerin

Antibacterial activity and biocompatibility of zein scaffolds containing silver-doped bioactive glass - El-Rashidy, Aiah A.; Waly, Gihan; Gad, Ahmed; Roether, Judith; Hum, Jasmin; Yang, Yuyun; Detsch, Rainer; Hashem, Azza A.; Sami, Inas; Goldmann, Wolfgang; Boccaccini, Aldo R. (Biomedical Materials, 2018)
Keywords: zein scaffolds; silver; in vitro biocompatibility; bioactive glass; antibacterial

An unsymmetrical pentacene derivative with ambipolar behavior in organic thin-film transistors - Tykwinski, Rik; Etschel, Sebastian; Halik, Marcus; Jäger, Christof; Clark, Timothy; Margraf, Johannes; Waterloo, Andreas; Hampel, Frank; Yousefi Amin, Atefeh (Chemical Communications, 2013)
Three new unsymmetrical anthracenyl-pentacene derivatives have been synthesized, characterized using X-ray crystallography, and used as semiconductors in OTFTs. For one derivative, ambipolar charge carrier transport was observed with a hole mobility of 0.2 cm V s and an electron mobility of 0.03 cm V s. © 2013 The Royal Society of Chemistry.

Application-Oriented Modeling of Draw Resonance in Polymer Melt Spinning - Schubert, Dirk W.; Bechert, Mathias (Polychar 21st, 2013)

Approaching efficient models for stability analysis in polymer melt spinning process - Bechert, Mathias; Kunzelmann, Peter; Schubert, Dirk W. (13th Bayreuth Polymer Symposium, Bayreuth, 2013)

Area-Selective Growth of HfS(2)Thin Films via Atomic Layer Deposition at Low Temperature - Cao, Yuanyuan; Wähler, Tobias; Park, Hyoungwon; Will, Johannes; Prihoda, Annemarie; Moses Badlyan, Narine; Fromm, Lukas; Yokosawa, Tadahiro; Wang, Bingzhe; Guldi, Dirk Michael; Görling, Andreas; Maultzsch, Janina; et al. (Advanced Materials Interfaces, 2020)
The transition-metal dichalcogenide HfS(2)is a promising alternative semiconductor with adequate band gap and high carrier mobility. However, a controllable growth of continuous HfS(2)films with selectivity for specific surfaces at a low temperature on a large scale has not been demonstrated yet. Herein, HfS(2)films are grown at 100 degrees C by atomic layer deposition (ALD) based on the precursors tetrakis(dimethylamido)hafnium and H2S. In situ vibrational spectroscopy allows for the definition of the temperature range over which (Me2N)(4)Hf chemisorbs as one monolayer. In that range, sequential exposures of the solid surface with (Me2N)(4)Hf and H2S result in self-limiting reactions that yield alternating surface termination with dimethylamide and thiol. Repeating the cycle grows smooth, continuous, stoichiometric films of thicknesses adjustable from angstroms to >100 nm, as demonstrated by spectroscopic ellipsometry, XRR, AFM, UV-vis and Raman spectroscopy, XPS, and TEM. The well-defined surface chemistry enables one to deposit HfS(2)selectively using, for example, patterns generated in molecular self-assembled monolayers. This novel ALD reaction combines several attractive features necessary for integrating HfS(2)into devices.
CRIS-Team Scopus Importer:2020-10-23
Keywords: 2D materials; atomic layer deposition; dichalcogenides; hafnium disulfide; thin films

Area-Selective Growth of HfS(2)Thin Films via Atomic Layer Deposition at Low Temperature - Cao, Yuanyuan; Wähler, Tobias; Park, Hyoungwon; Will, Johannes; Prihoda, Annemarie; Moses Badlyan, Narine; Fromm, Lukas; Yokosawa, Tadahiro; Wang, Bingzhe; Guldi, Dirk Michael; Görling, Andreas; Maultzsch, Janina; et al. (Advanced Materials Interfaces, 2020)
The transition-metal dichalcogenide HfS(2)is a promising alternative semiconductor with adequate band gap and high carrier mobility. However, a controllable growth of continuous HfS(2)films with selectivity for specific surfaces at a low temperature on a large scale has not been demonstrated yet. Herein, HfS(2)films are grown at 100 degrees C by atomic layer deposition (ALD) based on the precursors tetrakis(dimethylamido)hafnium and H2S. In situ vibrational spectroscopy allows for the definition of the temperature range over which (Me2N)(4)Hf chemisorbs as one monolayer. In that range, sequential exposures of the solid surface with (Me2N)(4)Hf and H2S result in self-limiting reactions that yield alternating surface termination with dimethylamide and thiol. Repeating the cycle grows smooth, continuous, stoichiometric films of thicknesses adjustable from angstroms to >100 nm, as demonstrated by spectroscopic ellipsometry, XRR, AFM, UV-vis and Raman spectroscopy, XPS, and TEM. The well-defined surface chemistry enables one to deposit HfS(2)selectively using, for example, patterns generated in molecular self-assembled monolayers. This novel ALD reaction combines several attractive features necessary for integrating HfS(2)into devices.
Keywords: 2D materials; atomic layer deposition; dichalcogenides; hafnium disulfide; thin films

A review on natural fiber-reinforced geopolymer and cement-based composites - Molano Camargo, Marfa Carolina; Taye, Eyerusalem; Roether, Judith; Redda, Daniel Tilahun; Boccaccini, Aldo R. (Materials, 2020)
The use of ecological materials for building and industrial applications contributes to minimizing the environmental impact of new technologies. In this context, the cement and geopolymer sectors are considering natural fibers as sustainable reinforcement for developing composites. Natural fibers are renewable, biodegradable, and non-toxic, and they exhibit attractive mechanical properties in comparison with their synthetic fiber counterparts. However, their hydrophilic character makes them vulnerable to high volumes of moisture absorption, thus conferring poor wetting with the matrix and weakening the fiber–matrix interface. Therefore, modification and functionalization strategies for natural fibers to tailor interface properties and to improve the durability and mechanical behavior of cement and geopolymer-based composites become highly important. This paper presents a review of the physical, chemical and biological pre-treatments that have been performed on natural fibers, their results and effects on the fiber–matrix interface of cement and geopolymer composites. In addition, the degradation mechanisms of natural fibers used in such composites are discussed. This review finalizes with concluding remarks and recommendations to be addressed through further in-depth studies in the field.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Composites; Fibers; Geopolymers; Interphases; Surface treatments

Artefacts of the storage modulus due to bubbles in polymeric fluids - Wolff, Friedrich; Münstedt, Helmut (Rheologica Acta, 2013)
The occurrence of bubbles in samples to be characterised by rotational rheometry may lead to artefacts which can easily be misinterpreted. Exemplarily, a silicone resin is discussed which shows the formation of small bubbles near the interphase between the sample and the rheometer plate if the samples are not carefully dried before being installed in the rheometer. These small bubbles which can easily be overlooked lead to a bending of G′ at low frequencies which was erroneously attributed to the molecular structure in the past. Therefore, even for hydrophobic polymers like the silicone resin, great care concerning bubbles has to be taken since water might be adsorbed on the surface and lead to artefacts which result in wrong conclusions. © 2013 Springer-Verlag Berlin Heidelberg.
Created from Fastlane, Scopus look-up
Keywords: Bubbles; Frequency dependence; Humidity; Silicone resin; Storage modulus

A simple Approach to describe the electrical resistance of conductive polymer composites under oscillatory shear - Krückel, Johannes; Stary, Zdenek; Schubert, Dirk W. (Nordic Polymer Days, 2013)

A Simple Approach to Describe the Electrical Restiance of Conductive Polymer Composites Under Oscillatory Shear - Krückel, Johannes; Stary, Zdenek; Schubert, Dirk W. (Polychar 21st, 2013)

A simple model to describe the electrical resistance of conductive polymer composites under oscillatory shear - Krückel, Johannes; Stary, Zdenek; Schubert, Dirk W. (8th Annual European Rheology Conference, 2013)

Aspergillus fumigatus Spores Are Not Able to Penetrate Silicone Breast Implant Shells - Horch, Raymund E.; Krappmann, Sven; Duemig, Michaela; Schmitz, Marweh; Kengelbach-Weigand, Annika; Schubert, Dirk W.; Kremser, Thomas; Bogdan, Christian; Ludolph, Ingo (Annals of Plastic Surgery, 2019)
Bacterial contamination is hypothesized to be one reason for the development of capsular contracture after alloplastic breast reconstruction using silicone breast implants. The role of fungal colonization or infection in this context as well as the question if microorganisms can penetrate the shell of silicone breast implants remains an unresolved question to date. Therefore, the aim of this study was to assess whether fungal spores are able to penetrate the shell of silicone implants. In an experimental in vitro setup with different arrangements of growth compartments, silicone chambers were placed in culture dishes filled with Aspergillus minimal medium or liquid culture medium. Inoculation was performed with conidia of Aspergillus fumigatus and incubated for seven days. On a daily basis, plates were inspected for conidial germination and hyphal growth. In none of the different experimental settings nutrients or hyphae of Aspergillus fumigatus were able to penetrate the silicone material.ConclusionsFungal spores and hyphae do not permeate through an intact silicone shell used in breast implants; thus, the silicone material serves as an impenetrable barrie
Keywords: Aspergillus fumigatus; penetration; silicone implants; breast

Assigning Electronic States in Carbon Nanodots - Strauß, Volker; Kahnt, Axel; Zolnhofer, Eva; Meyer, Karsten; Maid, Harald; Placht, Christian; Bauer, Walter; Nacken, Thomas; Peukert, Wolfgang; Etschel, Sebastian; Halik, Marcus; Guldi, Dirk Michael (Advanced Functional Materials, 2016)
Luminescent carbon nanodots exhibit enormous potential to be used as functional building blocks in energy conversion devices. Their intrinsic heterogeneity, however, hinders a thorough characterization and subsequently their applicability. In this work, the spectroscopic and electrochemical properties of prototype carbon nanodots were thoroughly studied in solution. Spectro-electrochemical experiments revealed information on the spectral features of several oxidized and reduced species of our carbon nanodots. Therefore, these experiments were complemented with pulse radiolysis where the spectral signature of the one-electron oxidized and reduced forms were identified. Both, electrochemically and radiolytically reduced and oxidized products show high reactivity in solution which correlates with an open-shell character, detected by paramagnetic resonance spectroscopy. The herein presented studies help to understand the complex nature of carbon nanodots and serve to overcome difficulties in device fabrication.

A Study of a Novel Synergy Definition for Ternary CB/CNT Composites Suggesting a Representative Model for CB and CNT - Yang, Guanda; Schubert, Dirk W.; Nilsson, Fritjof; Qu, Muchao; Redel, Michael (Macromolecular Theory and Simulations, 2020)
For polymer composites containing two types of conductive fillers, the electrical conductivity can be predicted with a ternary mixing equation. However, a slight deviation from the foreseen trend is recently observed for ternary polymethyl methacrylate (PMMA) nanocomposites containing carbon nanotubes (CNT) and carbon black (CB). In this study, the reason for the deviation is examined. Representative composite geometries are generated with Monte-Carlo technique and the composite conductivity is calculated with Finite Element Modeling (FEM) Traditional FEM strategies would give results resembling the ternary mixing equation, but when the CB particles are modeled as solid spheres whereas the CNT are modeled as solid cylinders surrounded by soft, conductive shells, the composite conductivity gained the same shape as observed experimentally. One possible interpretation is that a small geometrical rearrangement of the CNT fibers has a larger impact on the composite conductivity than a corresponding movement of the spherical CB particles. As a consequence, the CNT/CB/PMMA nanocomposite exhibits a special kind of synergy (“synergism”), caused by the grape-shaped morphology. These findings can be utilized in the future development and optimization of conductive polymer nanocomposites.
CRIS-Team Scopus Importer:2020-07-31
Keywords: conductivity; CPCs; simulation; ternary systems

A Study of Finite Size Effects and Periodic Boundary Conditions to Simulations of a Novel Theoretical Self-Consistent Mean-Field Approach - Yang, Guanda; Nilsson, Fritjof; Schubert, Dirk W. (Macromolecular Theory and Simulations, 2019)
In a previous work, a very promising mathematical model for predicting the electrical conductivity below the electrical percolation threshold, for both isotropic and anisotropic composites, was published by Schubert. In this work, periodic boundary condition of the simulation is utilized. The results are also compared to the previous work and other theoretical models. The truncated fibers due to finite size of the simulation volume are considered as two individual pieces so that the real aspect ratios will also be taken into consideration. A comparison is made between two groups, in which the length and the radius of the carbon fibers are changed, respectively, under certain aspect ratios. With three different sizes of the simulation volumes, the influence on the results due to the finite size effect is calculated.
CRIS-Team Scopus Importer:2019-08-06
Keywords: conductivity; finite size effect; simulation

A Sustainable Method for Removal of the Full Range of Liquid and Solid Hydrocarbons from Water Including Up- and Recycling - Gaß, Henrik; Sarcletti, Marco; Müller, Lukas; Hübner, Sabine; Yokosawa, Tadahiro; Park, Hyoungwon; Przybilla, Thomas; Spiecker, Erdmann; Halik, Marcus (Advanced Science, 2023)
Beyond their CO2 emittance when burned as fuels, hydrocarbons (HCs) serve as omnipresent raw materials and commodities. No matter if as liquid oil spills or the endless amounts of plastic roaming the oceans, HCs behave as persistent pollutants with water as main carrier to distribute. Even if their general chemical structure [-(CH2)n-] is quite simple, the endless range of n leads to contaminations of different appearances and properties. A water remediation method based on superparamagnetic iron oxide nanoparticles (SPIONs) modified with self-assembled monolayers of alkyl phosphonic acid derivatives is presented. These molecules enable the SPIONs to non-covalently bind HCs, independently from the molecular weight, size and morphology. The attractive interaction is mainly based on hydrophobic and Coulomb interaction, which allows recycling of the SPIONs. The superparamagnetic core allows a simple magnetic collection and separation from the water phase which makes it a promising addition to wastewater treatment. Agglomerates of collected plastic “waste” even exhibit superior adsorption properties for crude oil, another hydrocarbon waste which gives these collected wastes a second life. This upcycling approach combined with presented recycling methods enables a complete recycling loop.<br

Asymmetry Matters: Structure Elucidation and Application Potential of Solution-Processed Monoalkylated BTBT Thin Films - Hawly, Tim; Johnson, Manuel; Zhao, Baolin; Wu, Mingjian; Späth, Andreas; Streller, Fabian; Nickles Jäkel, Hannah; Halik, Marcus; Spiecker, Erdmann; Watts, Benjamin; Nefedov, Alexei; Fink, Rainer (ACS Applied Electronic Materials, 2022)
Two-dimensionally (2D) extended thin films of p-type organic semiconductor C13-BTBT (BTBT = [1]benzothieno[3,2-b]-[1]benzothiophene) were fabricated via self-controlled growth at the liquid-liquid interface. Depicting a compound class originally developed for further functionalization and subsequent realization of self-assembled monolayers (SAMs), the potent BTBT core unit commonly excels in high-quality structure formation as well as charge-transport characteristics. Utilizing a manifold spectromicroscopic toolbox, we observe extraordinarily crystalline C13-BTBT films with an upright standing configuration of the backbone unit accounting for superior intermolecular orbital overlap. The well-defined morphology and internal structure of the film are being underpinned by charge-transport parameters that are in the range of comparable organic electronic devices based on bisubstituted BTBT films from the same processing technique. The inherently favorable membrane-like bilayer molecular arrangement is confirmed by unambiguous representation of the unit cell as derived from electron tomography.
CRIS-Team WoS Importer:2023-01-27

A universal concept for area-selective assembly of metal oxide core-shell nanoparticles, nanorods, and organic molecules via amide coupling reactions - Zubets, Uladzislau; Zhao, Baolin; Park, Hyoungwon; Halik, Marcus (Nano Select, 2022)

Avoiding waviness of relaxation spectra - Kaschta, Joachim; Stadler, Florian (Rheologica Acta, 2009)
Spectra are material functions, whose different integral transforms yield the measurable rheological quantities in the linear viscoelastic regime. Therefore, their knowledge is of high fundamental interest. However, the calculation of spectra from experimental data is an ill-posed problem. Thus, it is hampered by the problem that a too low density of relaxation modes does not lead to a good description of the input data, while a higher one usually causes a wavy spectrum which cannot be interpreted. To overcome this problem, an additional criterion assuming only gradual changes in the spectrum is introduced allowing for an increase in mode density without an enhanced waviness of the spectrum. This is novel in comparison to previously published spectra algorithms and commercial software packages.
Keywords: Relaxation spectrum; Error minimization; Spectrum shape

Basal-Plane Functionalization of Chemically Exfoliated Molybdenum Disulfide by Diazonium Salts - Knirsch, Kathrin; Nerl, Hannah C.; Cucinotta, Clotilde S.; Berner, Nina; Gholamvand, Zahra; McEvoy, Niall; Wang, Zhenxing; Abramovic, Irena; Vecera, Philipp; Halik, Marcus; Sanvito, Stefano; Duesberg, Georg S.; et al. (ACS nano, 2015)
Although transition metal dichalcogenides such as MoS2 have been recognized as highly potent two-dimensional nanomaterials, general methods to chemically functionalize them are scarce. Herein, we demonstrate a functionalization route that results in organic groups bonded to the MoS2 surface via covalent C-S bonds. This is based on lithium intercalation, chemical exfoliation and subsequent quenching of the negative charges residing on the MoS2 by electrophiles such as diazonium salts. Typical degrees of functionalization are 10-20 atom % and are potentially tunable by the choice of intercalation conditions. Significantly, no further defects are introduced, and annealing at 350 °C restores the pristine 2H-MoS2. We show that, unlike both chemically exfoliated and pristine MoS2, the functionalized MoS2 is very well dispersible in anisole, confirming a significant modification of the surface properties by functionalization. DFT calculations show that the grafting of the functional group to the sulfur atoms of (charged) MoS2 is energetically favorable and that S-C bonds are formed.
Keywords: 1T-polytype; basal-plane; chemical exfoliation; covalent functionalization; layered materials; molybdenum disulfide; transition metal dichalcogenides

Behaviour of conductive particle networks in polymer melts under deformation - Stary, Zdenek; Krückel, Johannes; Schubert, Dirk W.; Münstedt, Helmut (AIP Conference Proceedings, 2011)
The electrical properties of the composites containing conductive fillers are given by the structure of the particle network. Therefore, the behavior of these networks under deformation in the molten state is of great interest in order to obtain materials with desirable electrical properties. In this work the composites containing carbon black or carbon fibers were exposed to a shear deformation in two different experimental modes—oscillation and creep and the electrical conductivity of the materials was measured simultaneousl
Keywords: Polymer composites; Conductivity; Rheology

Behaviour of conductive particle networks in polymer melts under deformation - Stary, Zdenek; Krückel, Johannes; Schubert, Dirk W.; Münstedt, Helmut (Novel Trends In Rheology IV, 2011)
Keywords: Polymer composites; Conductivity; Rheology

Biaxial Elongation Behavior in Partially Molted State of Two-Layer Sheets Containing Postconsumer Material - Wittmann, Lisa-Maria; Kaschta, Joachim; Drummer, Dietmar (Polymers, 2022)
Due to the lack of raw material and forced by political demand, an increasing percentage of postconsumer materials (PCR) shall be used in all processing methods in polymer technology. Thermoforming, as one of the oldest polymer-processing methods, has special requirements regarding the melt stability at high temperatures. Low melt stability affects the thermoforming in a negative manner, as the low stiffness leads the sheet to sag during the heating phase. In this study, two-layer sheets are used in order to improve melt stability of PCR material. The focus is placed on the influence of rheological properties on the biaxial stretching behavior of mono- and two-layer sheets in partially molted state. In order to create a stabilizing layer, two different thermoformable virgin materials with a melt flow rate (MFR) of 3 g/10 min and 6 g/10 min were chosen. The second layer consists of instable PCR materials with a MFR of 16 g/10min and 50 g/10 min. Rheological investigations, molecular characterization and biaxia tretching tests are used to show the benefit of two-layer sheets for processing PCR material under elongational stress. The results show that the use of two-layer sheets can improve the biaxial stretching properties, so that two-layer sheets can offer a significant potential in the processing of PCR materials in thermoforming.<br

Bi-layered porous constructs of PCL-coated 45S5 bioactive glass and electrospun collagen-PCL fibers - Balasubramanian, Preethi; Roether, Judith; Schubert, Dirk W.; Beier, Justus; Boccaccini, Aldo R. (Journal of Porous Materials, 2015)
A simple yet promising approach to construct bi-layered scaffolds using bioactive ceramics and biodegradable polymers is presented. This method involves two versatile fabrication techniques used in the field of TE: foam replication process and electrospinning. By the foam replication method, three-dimensional 45S5 bioactive glass (BG)-based scaffolds with high porosity, in the range of 95.8 ± 0.9 %, were produced. To improve the mechanical properties of the BG scaffolds, dip-coating using polycaprolactone (PCL) was performed, which led to a significant increase in the compressive strength of the scaffolds. In order to develop a bi-layered construct, bead-less submicrometric fibers of collagen-PCL were electrospun over the PCL-coated BG scaffolds. Surface morphology, surface properties and mechanical strength of the bi-layered construct were evaluated using scanning electron microscopy analysis, contact angle measurements and compressive strength testing, respectively. In vitro degradation of the collagen-PCL fibers in phosphate buffered saline and in vitro bioactivity of the bi-layered constructs in simulated body fluid were investigated. Formation of hydroxyapatite on the PCL-coated BG and along the morphology of the collagen-PCL fibers was ascertained using different characterization techniques. The bi-layered construct is intended for interface tissue engineering applications where the PCL-coated BG scaffold, which is highly bioactive, can serve as a support for the bone side and the composite collagen-PCL submicrometric fibers are intended for the cartilage side.
Keywords: Bioactivity; Electrospinning; In vitro degradation; Osteochondral region; Scaffold

Binary and Ternary Blends of Polypropylene Types-Influence on the Homogeneity of Biaxial Oriented Films - Schubert, Dirk W.; Kaschta, Joachim; Seidl, Stephan; Kunzelmann, Peter (Polychar 23rd, 2015)

Binary and Ternary Blends of Polypropylene Types – Influence on the Homogeneity of Biaxial-Oriented Films - Schubert, Dirk W.; Kaschta, Joachim; Seidl, Stephan; Kunzelmann, Peter (Macromolecular Symposia, 2016)
Biaxial-oriented polypropylene (BOPP) is one of the most used materials for industrial films and food packaging. In terms of environmental and economic issues, the reduction of the film thickness, increasing the homogeneity, enhancing the process efficiency and stability are in the focus of this work. A systematic investigation on the biaxial stretching process is presented in this study. Therefore, two commercial linear polypropylenes with different molar masses and a commercial long-chain-branched polypropylene were used to obtain binary and ternary blends to adjust the elongation behavior on the molecular level. The blending was carried out using a cast film process on a twin-screw extruder. The cast films obtained, were investigated before and after biaxial stretching. The thickness distribution of the films, were used as a measure of the film homogeneity, before and after the film stretching process. It turns out that casting and biaxial stretching are competing steps with respect to the film homogeneity. The casting step is dominated by the extrusion behavior of the blends. With increasing amount of the long-chain branched material extrusion flow instabilities appear leading to an irregular surface and to a poor film homogeneity. Contrarily, long-chain branches promote a more homogeneous deformation during the biaxial stretching inducing strain hardening which leads to a self-healing effect and thus to an improved film homogeneity. The homogeneity of the final stretched film depends on both, casting and stretching. Therefore, a desirable polymer blend recipe with a medium amount of long-chain branches is revealed for the stretched film.
Keywords: blends; BOPP films; film homogeneity; film stretching; linear and branched molecules

Bioactive Electrospun Fibers of Poly(glycerol sebacate) and Poly(ε-caprolactone) for Cardiac Patch Application - Rai, Ranjana; Tallawi, Marwa; Frati, Caterina; Falco, Angela; Gervasi, Andrea; Quaini, Federico; Roether, Judith; Hochburger, Tobias; Schubert, Dirk W.; Seik, Lothar; Barbani, Niccoletta; Lazzeri, Luigi; et al. (Advanced Healthcare Materials, 2015)
Scaffolds for cardiac patch application must meet stringent requirements such as biocompatibility, biodegradability, and facilitate vascularization in the engineered tissue. Here, a bioactive, biocompatible, and biodegradable electrospun scaffold of poly(glycerol sebacate)–poly(ε-caprolactone) (PGS–PCL) is proposed as a potential scaffold for cardiac patch application. The fibers are smooth bead free with average diameter = 0.8 ± 0.3 μm, mean pore size = 2.2 ± 1.2 μm, porosity = 62 ± 4%, and permeability higher than that of control biological tissue. For the first time, bioactive PGS–PCL fibers functionalized with vascular endothelial growth factor (VEGF) are developed, the approach used being chemical modification of the PGS–PCL fibers followed by subsequent binding of VEGF via amide bonding. The approach results in uniform immobilization of VEGF on the fibers; the concentrations are 1.0 μg cm−2 for the PGS–PCL (H) and 0.60 μg cm−2 for the PGS–PCL (L) samples. The bioactive scaffold supports the attachment and growth of seeded myogenic and vasculogenic cell lines. In fact, rat aortic endothelial cells also display angiogenic features indicating potential for the formation of vascular tree in the scaffold. These results therefore demonstrate the prospects of VEGF-functionalized PGS–PCL fibrous scaffold as promising matrix for cardiac patch application.

Bioactive Glass Applications: A Literature Review of Human Clinical Trials - Cannio, Maria; Bellucci, Devis; Roether, Judith; Boccaccini, Dino N.; Cannillo, Valeria (Materials, 2021)
The use of bioactive glasses in dentistry, reconstructive surgery, and in the treatment of infections can be considered broadly beneficial based on the emerging literature about the potential bioactivity and biocompatibility of these materials, particularly with reference to Bioglass (R) 45S5, BonAlive (R) and 19-93B3 bioactive glasses. Several investigations have been performed (i) to obtain bioactive glasses in different forms, such as bulk materials, powders, composites, and porous scaffolds and (ii) to investigate their possible applications in the biomedical field. Although in vivo studies in animals provide us with an initial insight into the biological performance of these systems and represent an unavoidable phase to be performed before clinical trials, only clinical studies can demonstrate the behavior of these materials in the complex physiological human environment. This paper aims to carefully review the main published investigations dealing with clinical trials in order to better understand the performance of bioactive glasses, evaluate challenges, and provide an essential source of information for the tailoring of their design in future applications. Finally, the paper highlights the need for further research and for specific studies intended to assess the effect of some specific dissolution products from bioactive glasses, focusing on their osteogenic and angiogenic potential.
CRIS-Team WoS Importer:2021-10-08

Bioactive glass based scaffolds coated with gelatin for the sustained release of icariin. - Reiter, Theresa; Panick, Tanja; Schuhladen, Katharina; Roether, Judith; Hum, Jasmin; Boccaccini, Aldo R. (Bioactive Materials, 2019)
Gelatin-coated, 3D sponge-like scaffolds based on 45S5 bioactive glass were produced using the foam replication technique. Compressive strength tests of gelatin-coated samples compared to uncoated scaffolds showed significant strengthening and toughening effects of the gelatin coating with compressive strength values in the range of cortical bone. Additionally, the crosslinked gelatin network (using either caffeic acid or N-(3-Dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC)/N-hxdroxysuccinimide (NHS) as crosslinking agent) was shown to be a suitable candidate for the sustained release of the bioactive molecule icariin. Concerning bioactivity of the produced scaffolds, characterization by FTIR and SEM indicated the formation of hydroxyapatite (HA) in all samples after immersion in simulated body fluid (SBF) for 14 days, highlighting the favorable combination of mechanical robustness, bioactivity and drug delivery capability of this new type of scaffolds.

Bioactive glass based scaffolds incorporating gelatin/manganese doped mesoporous bioactive glass nanoparticle coating - Nawaz, Qaisar; Ur Rehman, Muhammad Atiq; Roether, Judith; Yufei, Liu; Grünewald, Alina; Detsch, Rainer; Boccaccini, Aldo R. (Ceramics International, 2019)
We investigated the bioactivity and cytocompatibility of 45S5 bioactive glass (BG) based scaffolds coated with a composite layer formed by gelatin and manganese doped mesoporous bioactive glass nanoparticles (Mn-MBGNs). The scaffolds were prepared using the foam replica method, and they were further coated with Mn-MBGNs/gelatin via dip coating. The synthesized scaffolds were characterized in relation to morphology, porosity, mechanical stability, bioactivity and cell biology behavior using osteoblast-like (MG-63) cells. The scaffolds were highly porous with interconnected porosity, and a suitable pore structure was maintained even after the Mn-MBGNs/gelatin coating. Energy-dispersive X-ray spectroscopy (EDX) confirmed the presence of Mn-MBGNs in the coatings. Moreover, the presence of gelatin was confirmed by Fourier transform infrared spectroscopy (FTIR). The coated scaffolds exhibited in-vitro bioactivity in simulated body fluid comparable to that of uncoated BG scaffolds. Finally, Mn-MBGNs/gelatin coated scaffolds were shown to be non-cytotoxic to MG-63 cells. Hence, the results presented here confirm that the novel Mn containing scaffolds can be considered in the field of biologically active ion releasing scaffolds for bone tissue engineering applications.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Bioactive glasses; Bone tissue engineering; Gelatin; Manganese; Mesoporous bioactive glass nanoparticles; Scaffolds

Bioactive glass-biopolymer composites for applications in tissue engineering - Ding, Yaping; Souza, M. T.; Li, Wei; Schubert, Dirk W.; Boccaccini, Aldo R.; Roether, Judith (Springer International Publishing, 2016)
Tissue engineering (TE) is a biomedical field in continuous expansion. However, there are still many challenges to be tackled. The further development of TE approaches requires interdisciplinary interaction and collaboration among various research areas with a notable contribution expected from biomaterials science. In the last couple of decades, significant advances in the development of biomaterial-based scaffolds for hard and soft tissue regeneration have been accomplished, including the manufacture of biocomposites that combine natural or synthetic polymers with bioactive glasses or glass-ceramics. These novel biomaterials present the possibility of tailoring a variety of parameters and properties such as degradation kinetics, mechanical properties, and chemical composition according to the aimed application. This chapter presents a concise update of the field of biopolymer–bioactive glass composite scaffold development for TE covering several popular processing techniques for biocomposite fabrication, namely, microsphere processing, solvent casting-particulate leaching method, electrospinning, freeze-drying, and rapid prototyping techniques, which lead to scaffolds exhibiting a variety of 3D morphologies and different pore structure
Keywords: Degradation; Fabrication techniques; Cell biocompatibility; Composite materials; Soft tissue engineering; Porosity; Scaffolds; Bioactive glass; Bone tissue engineering; Biodegradable polymers

Bioactive glass-biopolymer multilayer coatings fabricated by electrophoretic deposition combined with layer-by-layer assembly - Chen, Qiang; Cabanas Polo, Sandra; Ding, Yaping; Boccaccini, Aldo R. (Key Engineering Materials, 2015)
45S5 bioactive glass (BG) based multilayer coatings on stainless steel were produced by a combination of electrophoretic deposition (EPD) and layer-by-layer (LbL) deposition. The properties of the multilayer coating were tested with different characterization methods including SEM, FTIR, XRD, laser profilometer and water contact angle measurements. Degradation and in-vitro bioactivity behaviors were tested in simulated body fluid (SBF) over different time periods. The decomposition of the coating was inhibited and the hydroxyapatite (HA) formation after short immersion period (0.5d) was confirmed. At the same time, levofloxacin, used as a model antibiotic, was incorporated into the multilayer structure for antibacterial purpose.
Keywords: Bioactive glass; Bioactivity; EPD; Layer-by-layer; Multilayer coating

Bioactive Glasses for Soft Tissue Engineering Applications - Miguez-Pacheco, Valentina; Gorustovich, Alejandro A.; Boccaccini, Aldo R.; Roether, Judith (Bioactive Glasses: Fundamentals, Technology and Applications, 2017)
In the last few years the usage of bioactive glasses as scaffolds for soft tissue engineering has been investigated more thoroughly. The reason for the boost in interest is the attractive properties bioactive glasses offer, including bioactivity as well as antibacterial, angiogenic and hemostatic properties. So far, most research efforts have focused on applications for repairing skin and nerve tissue although there have been interesting developments in other fields including lung and intestine, which could potentially benefit a large group of patients. Three review articles on this topic have been published, so this chapter will mainly focus on the latest relevant findings. A great number of patents have been registered for the use of bioactive glass for hard tissue engineering. Recently, however, patents have been filed detailing the use of bioactive glass for soft tissue engineering applications which open the way to marketing bioactive glasses for soft tissue repair. The angiogenic effect of bioactive glasses and their dissolution products is of great interest for tissue engineering applications in general and in particular for soft tissue regeneration and repair. The third part of this chapter will detail the latest research on these angiogenic properties of bioactive glasses.
CRIS-Team Scopus Importer:2022-08-05

Bioactive glasses meet phytotherapeutics: The potential of natural herbal medicines to extend the functionality of bioactive glasses - Schuhladen, Katharina; Roether, Judith; Boccaccini, Aldo R. (Biomaterials, 2019)
Herbal medicine, the use of plants or plant extracts with known beneficial biological effects to treat and/or prevent diverse health disorders, has been known for thousands of years. After their replacement by synthetic drugs in the beginning of the 20th century, plant derived therapeutic agents have been recently attaining more attention again. Phytotherapeutics, which can be extracted from a wide range of different herbal plants, are believed to have a broad spectrum of therapeutic effects and less negative side effects than synthetic drugs. On the other hand, it is often difficult to prove the therapeutic effect of herbal drugs due to their chemical complexity. In the last decade, research has focused increasingly on the relatively new concept of the combination of herbal drugs with modern engineered biomaterials in order to achieve synergy of their therapeutic effects. Even if several studies based on this concept have been published, no systematic overview of the performed investigations and their results is available. In this context, this review focuses on the combination of phytotherapeutics with bioactive glasses (BGs), which are bioactive and biodegradable materials capable of releasing biologically active ions being suitable for several applications as bone substituting and replacing materials as well as in the regeneration of soft and hard tissue. The literature search was carried out using the WEB OF SCIENCE® and SCOPUS® databases using a combination of relevant keywords. Besides giving an overview of the research done in the last years and summarizing the results obtained in those studies, the possible synergistic effects of herbal drugs in combination with BGs are critically discussed, and potential health risks are overviewed. Of all plant-derived drugs investigated so far, the coumarin family appears to be the one that has been most widely combined with BGs showing beneficial outcomes. Overall, the analysis of the literature has revealed the great potential of this organic-inorganic multi-functional system approach as an advantageous alternative to conventional medicine in several applications, but also highlights the need for more systematic in vivo studies to evaluate the effective time and dose dependent combined effects of BGs and phytotherapeutic agents.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Bioactive glass; Composite; Drug delivery; Phytotherapeutics; Synergistic effect

Biocompatible, Flexible Strain Sensor Fabricated with Polydopamine-Coated Nanocomposites of Nitrile Rubber and Carbon Black - Qu, Muchao; Qin, Yijing; SUN, YANYAN; Xu, Huagen; Schubert, Dirk W.; Zheng, Kai; Xu, Wei; Nilsson, Fritjof (ACS Applied Materials and Interfaces, 2020)
A flexible, biocompatible, nitrile butadiene rubber (NBR)-based strain sensor with high stretchability, good sensitivity, and excellent repeatability is presented for the first time. Carbon black (CB) particles were embedded into an NBR matrix via a dissolving-coating technique, and the obtained NBR/CB composite was coated with polydopamine (PDA) to preserve the CB layer. The mechanical properties of the NBR films were found to be significantly improved with the addition of CB and PDA, and the produced composite films were noncytotoxic and highly biocompatible. Strain-sensing tests showed that the uncoated CB/NBR films possess a high sensing range (strain of similar to 550%) and good sensitivity (gauge factor of 52.2), whereas the PDA/NBR/CB films show a somewhat reduced sensing range (strain of similar to 180%) but significantly improved sensitivity (gauge factor of 346). The hysteresis curves obtained from cyclic strain-sensing tests demonstrate the prominent robustness of the sensor material. Three novel equations were developed to accurately describe the uniaxial and cyclic strain-sensing behavior observed for the investigated strain sensors. Gloves and knee/elbow covers were produced from the films, revealing that the signals generated by different finger, elbow, and knee movements are easily distinguishable, thus confirming that the PDA/NBR/CB composite films can be used in a wide range of wearable strain sensor applications.
CRIS-Team WoS Importer:2020-10-16

Biodegradable poly(glycerol sebacate)/poly(3-hydroxybutyrate)-TiO2 nanocomposites: fabrication and characterisation - Roether, Judith; Rai, Ranjana; Wolf, R.; Tallawi, Marwa; Boccaccini, Aldo R. (Materials Science and Technology, 2014)
Novel Nanocomposite films containing TiO2 nanoparticles incorporated in blend matrices of biocompatible and bioresorbable polymers, namely poly(glycerol sebacate) (PGS) and poly(3-hydroxybutyrate) P(3HB), were developed. The samples were fabricated via a sequential step of solvent casting followed by cross-linking. PGS/P(3HB) blends (controls) were fabricated in two different ratios, i.e. 7 : 1 and 8 : 1. Varying amounts of TiO2 nanoparticles (1 and 2 vol.-%) were incorporated into the matrices. SEM studies revealed that the TiO2 particles were distributed both within the matrix and on the surface of the films thus imparting surface nanotopography and increasing the surface roughness. These microstructural features combined with the cumulative effect of blending of the two polymeric systems influenced the wettability, chemical and mechanical properties of the films. In vitro degradation of the fabricated matrices in PBS medium over a 30 day period confirmed that the composites undergo weight loss and mechanical, chemical and surface topography changes. The nanocomposites constitute model biodegradable organic-inorganic systems suitable for tissue engineering applications.
Keywords: Nanocomposite; TiO2; Nanoparticles; Poly(glycerol sebacate); Poly(3-hydroxybutyrate)

Biofabrication and Characterization of Alginate Dialdehyde-Gelatin Microcapsules Incorporating Bioactive Glass for Cell Delivery Application - Reakasame, Supachai; Jin, Anbang; Zheng, Kai; Qu, Muchao; Boccaccini, Aldo R. (Macromolecular Bioscience, 2020)
The effect of the incorporation of 45S5 bioactive glass (BG) microparticles (mean particle size ≈ 2 µm) on the fabrication and physicochemical properties of alginate dialdehyde-gelatin hydrogel capsules is investigated. The addition of BG particles decreases the hydrogel gelation time by ≈79% and 91% for the samples containing 0.1% w/v and 0.5% w/v BG, respectively. Moreover, it results in increasing average diameter of hydrogel capsules produced via a pressure-driven extrusion technique from about 1000 µm for the samples without BG to about 1700 and 1900 µm for the samples containing BG at concentrations of 0.1% w/v and 0.5% w/v, respectively. The presence of BG particles in the capsules decreases the degradation rate and improves the bioactivity of the materials. The viability of MG-63 cells encapsulated in all samples increases during the first 7 d of cultivation and maintains the same level during 21 d of cultivation. The early cell viability in samples containing BG is lower than that in samples without BG. The results show that 45S5 BG can positively regulate the osteogenic activity of cells incorporated in hydrogel capsules. The fabricated composite capsules exhibit promising potential for cell delivery in bone regeneration applications.
CRIS-Team Scopus Importer:2020-09-11
Keywords: bioactive glass; bone cells; cell encapsulation; microcapsules; oxidized alginate

Bioglass®-based scaffolds incorporating polycaprolactone and chitosan coatings for controlled vancomycin delivery - Yao, Qingqing; Nooeaid, Patcharakamon; Roether, Judith; Dong, Yanining; Zhang, Qiqing; Boccaccini, Aldo R. (Ceramics International, 2013)
Highly porous scaffolds have been fabricated by the replication technique using 45S5 Bioglass® (BG) powder. For the purpose of imparting a local drug release capability, the scaffolds were coated with polycaprolactone and vancomycin-loaded chitosan by a two-step procedure. Bare BG scaffolds loaded with vancomycin via a direct immersion method were used as control. The chemical composition and microstructure of bare and coated scaffolds were characterized through Fourier-transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM), respectively. The mechanical properties of the coated scaffolds were significantly improved compared with uncoated scaffolds; the compressive strength values of the coated scaffolds were about 3 times and the area under the stress-strain curve was about 7 times higher than those of the uncoated scaffolds. The scaffolds degradation behavior and the drug release profiles were studied in a phosphate buffered saline (PBS) solution. There was a sharp release of the drug in the first few hours (8 h) for both bare and coated scaffolds. For the bare scaffolds the drug was released completely in 24 h. However, the coated scaffolds showed a sustained release in a period of 11 days, suggesting the potential of the present polymer coated BG scaffolds to be used as bone tissue scaffolds with drug carrier and delivery ability. © 2013 Elsevier Ltd and Techna Group S.r.l.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.biogla
Keywords: Bioactive glass; Drug delivery; Scaffolds; Tissue engineering

Bioglass®/chitosan-polycaprolactone bilayered composite scaffolds intended for osteochondral tissue engineering - Yao, Qingqing; Nooeaid, Patcharakamon; Detsch, Rainer; Roether, Judith; Dong, Yanming; Goudouri, Ourania Menti; Schubert, Dirk W.; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part A, 2014)
Polymer-coated 45S5 Bioglass® (BG)/chitosan-polycaprolactone (BG/CS-PCL) bilayered composite scaffolds were prepared via foam replication and freeze-drying techniques for application in osteochondral tissue engineering. The CSPCL coated and uncoated BG scaffolds were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The mechanical properties of the coated scaffolds were significantly improved in comparison to uncoated scaffolds. The bioactivity and biodegradation behavior of scaffolds were studied in simulated body fluid (SBF) for up to 28 days. The interface between the BG scaffold and the polymer coating layer was observed by SEM and a suitable interpenetration of the polymer into the scaffold struts was found. The effects of coated and uncoated BG scaffolds on MG-63 osteoblastlike cells were evaluated by cell viability, adhesion and proliferation.
Keywords: Bilayered scaffolds; Bioglass®; Chitosan; Osteochondral tissue engineering; Polycaprolactone

Biomaterial engineering in ophthalmology - Thieme, Daniel; Schubert, Dirk W. (European Association of Vision and Eye Research (EVER), 2018)
Keywords: Biomaterial; engineering; eye

Biomaterial engineering in ophthalmology - from vision to insight - Thieme, Daniel; Schubert, Dirk W. (4th Annual Vision for 3D Cell Culture, 2018)
Keywords: Biomaterials; engineering; phthalmology

Biomaterialien als DMEK-& Amnionmembranersatz - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas (2. Baltic Sea Eye Conference, Rostock (Deutschland), 2020, 2020)

Biomimetic poly(glycerol sebacate) (PGS) membranes for cardiac patch application - Rai, Ranjana; Tallawi, Marwa; Barbani, Niccoletta; Frati, Caterina; Madeddu, Denise; Cavali, Stefano; Graiani, Gallia; Quaini, Frederico; Schubert, Dirk W.; Roether, Judith; Rosellini, Elisabetta; Boccaccini, Aldo R. (Materials Science and Engineering C, 2013)
In this study biomimetic poly(glycerol sebacate) PGS matrix was developed for cardiac patch application. The rationale was that such matrices would provide conducive environment for the seeded cells at the interphase with PGS. From the microstructural standpoint, PGS was fabricated into dense films and porous PGS scaffolds. From the biological aspect, biomimetic PGS membranes were developed via covalently binding peptides Tyr-Ile-Gly-Ser-Arg (YIGSR) and Gly-Arg-Gly-Asp-Ser-Pro (GRGDSP), corresponding to the epitope sequences of laminin and fibronectin, respectively onto the surface. To improve and enhance homogenous binding of peptides onto the PGS surface, chemical modification of its surface was carried out. A sequential regime of alkaline hydrolysis with 0.01 M NaOH for 5 min and acidification with 0.01 M HCl for 25 s was optimal. More COOH chemical group was exposed without causing deleterious effect on the bulk properties of the polymer as revealed by the physicochemical analysis carried out. HPLC analysis, chemical imaging and ToF-SIMS were able to establish the successful homogenous functionalization of PGS membranes with the peptides. Finally, the developed biomimetic membranes supported the adhesion and growth of rat and human cardiac progenitor cells.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.biomim
Keywords: Poly(glycerol sebacate); Cardiac patch; Biomimetic; Surface modification; Laminin; Fibronectin

Biosilicate®–gelatine bone scaffolds by the foam replica technique: development and characterization - Desimone, Deborah; Li, Wei; Roether, Judith; Schubert, Dirk W.; Crovace, Murilo; Rodrigues, Ana; Zanotto, Edgar; Boccaccini, Aldo R. (Science and Technology of Advanced Materials, 2013)
The development of bioactive glass-ceramic materials has been a topic of great interest aiming at enhancing the mechanical strength of traditional bioactive scaffolds. In the present study, we test and demonstrate the use of Biosilicate® glass-ceramic powder to fabricate bone scaffolds by the foam replica method. Scaffolds possessing the main requirements for use in bone tissue engineering (95% porosity, 200–500 μm pore size) were successfully produced. Gelatine coating was investigated as a simple approach to increase the mechanical competence of the scaffolds. The gelatine coating did not affect the interconnectivity of the pores and did not significantly affect the bioactivity of the Biosilicate® scaffold. The gelatine coating significantly improved the compressive strength (i.e. 0.80 ± 0.05 MPa of coated versus 0.06 ± 0.01 MPa of uncoated scaffolds) of the Biosilicate® scaffold. The combination of Biosilicate® glass-ceramic and gelatine is attractive for producing novel scaffolds for bone tissue engineering.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.biosil
Keywords: bioactivity; bone tissue engineering; glass-ceramics; scaffolds

Biosilicate®-gelatine bone scaffolds by the foam replica technique: Development and characterization - Desimone e Silva, Deborah; Li, Wei; Roether, Judith; Schubert, Dirk W.; Crovace, Murilo; Rodrigues, Ana; Zanotto, Edgar; Boccaccini, Aldo R. (Science and Technology of Advanced Materials, 2013)
The development of bioactive glass-ceramic materials has been a topic of great interest aiming at enhancing the mechanical strength of traditional bioactive scaffolds. In the present study, we test and demonstrate the use of Biosilicate® glass-ceramic powder to fabricate bone scaffolds by the foam replica method. Scaffolds possessing the main requirements for use in bone tissue engineering (95% porosity, 200–500 μm pore size) were successfully produced. Gelatine coating was investigated as a simple approach to increase the mechanical competence of the scaffolds. The gelatine coating did not affect the interconnectivity of the pores and did not significantly affect the bioactivity of the Biosilicate® scaffold. The gelatine coating significantly improved the compressive strength (i.e. 0.80 ± 0.05 MPa of coated versus 0.06 ± 0.01 MPa of uncoated scaffolds) of the Biosilicate® scaffold. The combination of Biosilicate® glass-ceramic and gelatine is attractive for producing novel scaffolds for bone tissue engineerin
Keywords: bioactivity; glass-ceramics; bone tissue engineering; scaffolds

Bio-templated bioactive glass particles with hierarchical macro-nano porous structure and drug delivery capability - Zheng, Kai; Bortuzzo, Judith Agnes; Liu, Yufang; Li, Wei; Pischetsrieder, Monika; Roether, Judith; Lu, Miao; Boccaccini, Aldo R. (Colloids and Surfaces B: Biointerfaces, 2014)
Hierarchically porous bioactive glass particles (BGPs) were synthesized by a facile sol-gel process using pollen grains as the templates. The synthesized pollen-templated bioactive glass particles (PBGPs) exhibited dual macro-nano porous structure. The macro pores ( 1μm) were inherited from the template of pollen grains while the nano pores ( 9.5nm) were induced by the intrinsic mechanism of the sol-gel process. PBGPs possessed a high specific surface area (111.4m/g) and pore volume (0.35cm/g). Hydroxyapatite (HA) formation on PBGPs was detected within 3 days after immersion in simulated body fluid (SBF). Due to their larger specific surface area and pore volume, PBGPs could be loaded with more tetracycline hydrochloride (TCH) than non-templated BGPs and conventional melt-derived 45S5 BGPs. In addition, PBGPs exhibited a low initial burst release (within 10% of the loaded amount) within 18h and a sustained release with a two-stage release pattern for up to 6 days in phosphate buffered saline (PBS). The antibacterial assay confirmed that the TCH-loaded PBGPs could release TCH within 5 days, and the released TCH could reach the minimum inhibitory concentration (MIC) against Escherichia coli. MTT assay indicated that PBGPs showed non-cytotoxic effects toward human hepatocellular carcinoma (Hep G2) cells after co-culture for up to 72h in vitro. These results showed that the biocompatible hierarchically macro-nano porous PBGPs are potential for bone regeneration and local drug delivery applications.
Keywords: Bio-template; Bioactive glass; Drug delivery; Hierarchical pores

Bis(dioxaborine) compounds with large two-photon cross section and their use in the photodeposition of silver - Halik, Marcus; Wenseleers, W.; Grasso, C.; Stellacci, F.; Zojer, E.; Barlow, S.; Bredas, J. L.; Perry, J. W.; Marder, S. R. (Chemical Communications, 2003)

Bovine serum albumin-modified 3D printed alginate dialdehyde-gelatin scaffolds incorporating polydopamine/SiO2-CaO nanoparticles for bone regeneration - Kim, Myong-Ho; Schöbel, Lisa; Geske, Michael; Boccaccini, Aldo R.; Ghorbani, Farnaz (International Journal of Biological Macromolecules, 2024)
Three-dimensional (3D) printing allows precise manufacturing of bone scaffolds for patient-specific applications and is one of the most recently developed and implemented technologies. In this study, bilayer and multimaterial alginate dialdehyde-gelatin (ADA-GEL) scaffolds incorporating polydopamine (PDA)/SiO2-CaO nanoparticle complexes were 3D printed using a pneumatic extrusion-based 3D printing technology and further modified on the surface with bovine serum albumin (BSA) for application in bone regeneration. The morphology, chemistry, and in vitro bioactivity of PDA/SiO2-CaO nanoparticle complexes were characterized (n = 3) and compared with those of mesoporous SiO2-CaO nanoparticles. Successful deposition of the PDA layer on the surface of the SiO2-CaO nanoparticles allowed better dispersion in a liquid medium and showed enhanced bioactivity. Rheological studies (n = 3) of ADA-GEL inks consisting of PDA/SiO2-CaO nanoparticle complexes showed results that may indicate better injectability and printability behavior compared to ADA-GEL inks incorporating unmodified nanoparticles. Microscopic observations of 3D printed scaffolds revealed that PDA/SiO2-CaO nanoparticle complexes introduced additional topography onto the surface of 3D printed scaffolds. Additionally, the modified scaffolds were mechanically stable and elastic, closely mimicking the properties of natural bone. Furthermore, protein-coated bilayer scaffolds displayed controllable absorption and biodegradation, enhanced bioactivity, MC3T3-E1 cell adhesion, proliferation, and higher alkaline phosphatase (ALP) activity (n = 3) compared to unmodified scaffolds. Consequently, the present results confirm that ADA-GEL scaffolds incorporating PDA/SiO2-CaO nanoparticle complexes modified with BSA offer a promising approach for bone regeneration applications.
CRIS-Team Scopus Importer:2024-03-22
Keywords: 3D printing; Alginate dialdehyde-gelatin; Bovine serum albumin; Polydopamine; Silica-calcia; Tissue engineering

Breakdown of Far-Field Raman Selection Rules by Light-Plasmon Coupling Demonstrated by Tip-Enhanced Raman Scattering - Poliani, Emanuele; Wagner, Markus R.; Vierck, Asmus; Herziger, Felix; Nenstiel, Christian; Gannott, Florentina; Schweiger, Manuel; Fritze, Stephanie; Dadgar, Armin; Zaumsei, Jana; Krost, Alois; Hoffmann, Axel; et al. (Journal of Physical Chemistry Letters, 2017)
We present an experimental study on the near-field light-matter interaction by tip-enhanced Raman scattering (TERS) with polarized light in three different materials: germanium-doped gallium nitride (GaN), graphene, and carbon nanotubes. We investigate the dependence of the TERS signal on the incoming light polarization and on the sample carrier concentration, as well as the Raman selection rules in the near-field. We explain the experimental data with a tentative quantum mechanical interpretation, which takes into account the role of plasmon polaritons, and the associated evanescent field. The driving force for the breakdown of the classical Raman selection rules in TERS is caused by photon tunneling through the perturbation of the evanescent field, with the consequent polariton annihilation. Predictions based on this quantum mechanical approach are in good agreement with the experimental data, which are shown to be independent of incoming light polarization, leading to new Raman selection rules for TERS.
CRIS-Team Scopus Importer:2022-04-14

Building and testing a simple set up to investigate the conductivity of polymer /carbon black composites - Liu, Xian Hu; Krückel, Johannes; Schubert, Dirk W. (1st International Conference on Computational and Experimental Methods for Composite Materials and Structures, 2014)

Building and testing a simple setup to investigate the electrical properties of polymer/carbon black composites - Liu, Xian Hu; Krückel, Johannes; Schubert, Dirk W. (Composite Structures, 2015)
In this work, a simple experimental setup was built to investigate the electrical properties of polymer/carbon black composites. It was found that the measured experimental data from our setup can be well described by the percolation theory and tunneling conduction. Those results indicate that our device is applicable for electrical resistance measurements. Additionally, based on this device, a method was proposed to investigate the electrical properties of disk-shape samples as a function of the radial position in order to study samples with different shear deformation history. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Electrical properties; Experiment method; Polymer composite; Shear

Buried Microphase Separation by Dynamic Interplay of Crystallization and Microphase Separation in Semicrystalline PEO-Rich PS-b-PEO Block Copolymer Thin Films - Rejek, Tobias; Schweizer, Peter; Joch, Daniel; Portilla, Luis; Spiecker, Erdmann; Halik, Marcus (Macromolecules, 2020)
The interplay between microphase separation and crystallization in the semicrystalline PS-b-PEO system is investigated in the context of solution-based thin film formation. For this end, the film morphology is studied depending on the PEO volume fraction in a broad f(vol)(PEO) range from 0.17 to 0.8. Topographical two-dimensional AFM measurements are extended to the third dimension to gain information about the vertical film structure by successive removal of the surface layer by controlled O-2 plasma etching. The depth profiling reveals a dynamic film formation process where competing microphase separation and crystallization forces create a two-layered BCP film composed of a buried microphase-separated layer featuring cylinder morphology under a fine-structured crystalline lamellae surface layer. An explanation is presented considering the thermal properties and solvent interactions. Phase-selective TiO2 nanoparticles addressing the PEO block are further used to demonstrate the accessibility of the buried microphase-separated layer and thus that we were able to extend the usable range of the phase diagram of PS-b-PEO thin films to the PEO-rich regime. Lastly, the impact of a second film-air interface is shown, which is formed in free-standing BCP membranes.
CRIS-Team WoS Importer:2020-08-07

Cell-laden alginate dialdehyde–gelatin hydrogels formed in 3D printed sacrificial gel - Dranseikiene, Dalia; Schrüfer, Stefan; Schubert, Dirk W.; Reakasame, Supachai; Boccaccini, Aldo R. (Journal of Materials Science: Materials in Medicine, 2020)
Alginate dialdehyde–gelatin (ADA–GEL) hydrogels have been reported to be suitable matrices for cell encapsulation. In general, application of ADA–GEL as bioink has been limited to planar structures due to its low viscosity. In this work, ring shaped constructs of ADA–GEL hydrogel were fabricated by casting the hydrogel into sacrificial molds which were 3D printed from 9% methylcellulose and 5% gelatin. Dissolution of the supporting structure was observed during the 1st week of sample incubation. In addition, the effect of different crosslinkers (Ba2+ and Ca2+) on the physicochemical properties of ADA–GEL and on the behavior of encapsulated MG-63 cells was investigated. It was found that Ba2+ crosslinked network had more than twice higher storage modulus, and mass decrease to 70% during incubation compared to 42% in case of hydrogels crosslinked with Ca2+. In addition, faster increase in cell viability during incubation and earlier cell network formation were observed after Ba2+ crosslinking. No negative effects on cell activity due to the use of sacrificial materials were observed. The approach presented here could be further developed for cell-laden ADA–GEL bioink printing into complex 3D structures. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2020-03-27

Cellular polyethylene-naphthalate films for ferroelectret applications: foaming, inflation and stretching, assessment of electromechanically relevant structural features - Fang, Peng; Wirges, Werner; Wegener, Michael; Zirkel, Larissa; Gerhard, Reimund (e-polymers, 2008)
Cellular polymer films are frequently employed for packaging, insulation, and printing. They can also be used as ferroelectrets in transducer applications. Here, we propose a preparation process for cellular polyethylene-naphthalate (PEN) films with the following steps: (1) foaming by means of supercritical carbon dioxide (CO2), (2) controlled inflation through gas diffusion and expansion, and (3) biaxial stretching. We describe and assess the cellular structure that is formed under suitable processing conditions. For foaming, the PEN films are saturated with supercritical CO2 at room temperature for a few hours, at a pressure as high as 100 bar. The subsequent temperature treatment is very critical for controlling the sample density. Additional inflation can improve the cellular geometry, and higher stabilization temperatures during the inflation process cause stronger inflation and thus lower densities. Stretching may be employed in order to achieve a regular cellular structure with lens-like voids. High electromechanical responses, i.e. large piezoelectric thickness coefficients are found only on samples within the proper density range and with optimal cellular structures.
EAM Import::2019-03-13

Cellulose-Based Ionogels for Paper Electronics - Thiemann, Stefan; Sachnov, Swetlana; Pettersson, Fredrik; Bollström, Roger; Österbacka, Ronald; Wasserscheid, Peter; Zaumseil, Jana (Advanced Functional Materials, 2014)
A new class of biofriendly ionogels produced by gelation of microcellulose thin films with tailored 1-ethyl-3-methylimidazolium methylphosphonate ionic liquids are demonstrated. The cellulose ionogels show promising properties for application in flexible electronics, such as transparency, flexibility, transferability, and high specific capacitances of 5 to 15 extgreekmF cm-2. They can be laminated onto any substrate such as multilayer-coated paper and act as high capacitance dielectrics for inorganic (spray-coated ZnO and colloidal ZnO nanorods) and organic (poly[3-hexylthiophene], P3HT) electrolyte-gated field-effect transistors (FETs), that operate at very low voltages (<2 V). Field-effect mobilities in ionogel-gated spray-coated ZnO FETs reach 75 cm2 V-1 s-1 and a typical increase of mobility with decreasing specific capacitance of the ionogel is observed. Solution-processed, colloidal ZnO nanorods and laminated cellulose ionogels enable the fabrication of the first electrolyte-gated, flexible circuits on paper, which operate at bending radii down to 1.1 mm.

Changes in the Conductive Structure of Polymethylmethacrylate Carbon Black Composites Induced by Oscillatory Shear - Krückel, Johannes; Stary, Zdenek; Schubert, Dirk W. (Book of Abstracts, 2013)

Chapter “Fullerene-Based FETs” in“Encyclopedia of Polymeric Nanomaterials” edited by S. Kobayashi, K. Müllen - Schmaltz, Thomas; Halik, Marcus (Springer, 2014)

Chapter "Gate Dielectrics" in "Organic Electronics – Materials, Manufacturing and Applications” edited by Hagen Klauk - Halik, Marcus (Wiley-VCH, 2006)

Characterisation of Magneto-Sensitive Elastomers; Material Model meets Experimental Results - Walter, Bastian; Saxena, Prashant; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (13th Bayreuth Polymer Symposium, Bayreuth, 2013)

Characterisation of porcine dermis scaffolds decellularised using a novel non-enzymatic method for biomedical applications - Greco, K. V.; Francis, L.; Somasundaram, M.; Greco, G.; English, Nicholas R.; Roether, Judith; Boccaccini, Aldo R.; Sibbons, P.; Ansari, T. (Journal of Biomaterials Applications, 2015)
Off-the-shelf availability of tissue-engineered skin constructs, tailored by different combinations of reagents to produce a highly preserved biological matrix is often the only means to help patients suffering skin damage. This study assessed the effect of five different decellularisation methods on porcine dermal scaffolds with regard to matrix composition, biomechanical strength, and cytotoxicity using an in vitro biocompatibility assay. Results demonstrated that four out of the five tested decellularisation protocols were efficient in producing acellular scaffolds. Nevertheless, decellularisation method using osmotic shock without enzymatic digestion showed to be efficient not only in removing cellular material and debris from dermal scaffolds but was also beneficial in the preservation of extracellular matrix components (glycosaminoglycans and collagen). Histological assessment revealed that the dermal architecture of coarse collagen bundles was preserved. Examinations by scanning electron microscopy and transmission electron microscopy showed that the arrangement and ultrastructure of collagen fibrils in the scaffolds were retained following non-enzymatic method of decellularisation and also after collagen crosslinking using genipin. Moreover, this decellularised scaffold was not only shown to be biologically compatible when co-cultured with bone marrow-derived mesenchymal stem cells and fibroblasts, but also stimulated the cells to release trophic factors essential for tissue regeneration.
Keywords: dermis; fibroblast; genipin; in vitro biocompatibility; mesenchymal stem cell; Scaffold

Characterization of branched ultrahigh molar mass polymers by asymmetrical flow field-flow fractionation and size exclusion chromatography - Otte, Tino; Stadler, Florian; Kaschta, Joachim; Becker, Florian; Buback, Michael; et al. (Journal of Chromatography A, 2011)
The molar mass distribution (MMD) of synthetic polymers is frequently analyzed by size exclusion chromatography (SEC) coupled to multi angle light scattering (MALS) detection. For ultrahigh molar mass (UHM) or branched polymers this method is not sufficient, because shear degradation and abnormal elution effects falsify the calculated molar mass distribution and information on branching. High temperatures above 130 degrees C have to be applied for dissolution and separation of semi-crystalline materials like polyolefins which requires special hardware setups. Asymmetrical flow field-flow fractionation (AF4) offers the possibility to overcome some of the main problems of SEC due to the absence of an obstructing porous stationary phase. The SEC-separation mainly depends on the pore size distribution of the used column set. The analyte molecules can enter the pores of the stationary phase in dependence on their hydrodynamic volume. The archived separation is a result of the retention time of the analyte species inside SEC-column which depends on the accessibility of the pores, the residence time inside the pores and the diffusion ability of the analyte molecules. The elution order in SEC is typically from low to high hydrodynamic volume. On the contrary AF4 separates according to the diffusion coefficient of the analyte molecules as long as the chosen conditions support the normal FFF-separation mechanism. The separation takes place in an empty channel and is caused by a cross-flow field perpendicular to the solvent flow. The analyte molecules will arrange in different channel heights depending on the diffusion coefficients. The parabolic-shaped flow profile inside the channel leads to different elution velocities. The species with low hydrodynamic volume will elute first while the species with high hydrodynamic volume elute later. The AF4 can be performed at ambient or high temperature (AT-/HT-AF4). We have analyzed one low molar mass polyethylene sample and a number of narrow distributed polystyrene standards as reference materials with known structure by AT/HT-SEC and AT/HT-AF4. Low density polyethylenes as well as polypropylene and polybutadiene, containing high degrees of branching and high molar masses, have been analyzed with both methods. As in SEC the relationship between the radius of gyration (R(g)) or the molar mass and the elution volume is curved up towards high elution volumes, a correct calculation of the MMD and the molar mass average or branching ratio is not possible using the data from the SEC measurements. In contrast to SEC. AF4 allows the precise determination of the MMD, the molar mass averages as well as the degree of branching because the molar mass vs. elution volume curve and the conformation plot is not falsified in this technique. In addition, higher molar masses can be detected using HT-AF4 due to the absence of significant shear degradation in the channel. As a result the average molar masses obtained from AF4 are higher compared to SEC. The analysis time in AF4 is comparable to that of SEC but the adjustable cross-flow program allows the user to influence the separation efficiency which is not possible in SEC without a costly change of the whole column combination. (C) 2011 Elsevier B.V. All rights reserve
Keywords: Polyethylene; Polybutadiene; Polypropylene; Polystyrene; Field-flow fractionation; Light scattering; Size exclusion chromatography; Ultrahigh molar masses; Branching; Shear degradation

Characterization of False Banana Fiber as a Potential Reinforcement Material for Geopolymer Composites - Addis, Lulseged Belay; Sendekie, Zenamarkos Bantie; Habtu, Nigus Gabbiye; Schubert, Dirk W.; Roether, Judith; Boccaccini, Aldo R. (Green Energy and Technology, 2023)
There is renewed interest in the use of plant-derived fibers as reinforcement material in the manufacture of composites. Replacing synthetic fiber with natural fiber has several benefits. Availability, biodegradability, lightweight, reduction of carbon footprint, and less abrasiveness in tool wear during processing are among the common benefits over synthetic fiber counterparts. The objective of this study is to investigate the physical, mechanical, thermal, and chemical properties of false banana fiber, obtained from false banana plants. The results show that the fiber has a relatively low moisture content, demonstrating that the false banana fiber has good physical properties as the moisture content of the fiber determines the dimensional stability of the produced composites. The mean diameter and true density of the fiber were found to be 173 μm and 1.483 g/cm3, respectively. A single fiber tensile test was carried out to determine the mechanical strength of the fiber. Its strength varied between 125 and 784 MPa. Based on the thermal stability test, the initial degradation of the fiber starts at 263 °C while its maximum degradation is observed at 364 °C. From the results of the chemical analysis, the fiber contains about 58.16% cellulose, 23.64% hemicellulose, and 11.12% lignin as the main components, and a small amount of extractives and ash, 4.04%, and 3.03%, respectively. Based on the overall analysis of the test results, the false banana fiber can be confirmed as one of the potential reinforcement source materials that can be used for the production of polymer composites for various applications.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Chemical analysis; False banana fiber; Mechanical properties; Physical properties; Thermal properties

Characterization of polyethylene of raised temperature resistance (PE-RT) materials - a mini review and insights - Schneider, Nicolai; Kaschta, Joachim; Heiduk, Ines; Schubert, Dirk W. (Nordic Polymer Days 2023, 2023)
Since the development of the first pipe sys- tems over 5500 years ago, various materials in- cluding terracotta, metals and polymers, were used in this field of application. High-density polyethylens (HDPE) display good processabil- ity and chemical resistance at low costs since their first pipe application in 1954 [1, 2]. Polyethylenes in long-term high temperature implementations tend to failure mechanisms such as slowcrack-growth (SCG) and environmental-stress-cracking (ESC). In both failure mechanisms, long-term stresses lead to the formation of so-called craze-structures, where crystals rotate in stress direction with an alternating pattern of crystalline and amor- phous segments (fibrills) between accruing voids, promoted by raised temperatures. The cohesion of crystallites within the craze is main- ly assured by tiemolecules, amorphous chains that are incorporated in several crystallites, forming intercrystalline bridges [3]. Therefore, creep resistant materials such as cross-linked polyethylene (PE-X) and polyethylene of raised temperature resistance (PE-RT) were invented to impede the failure in the amorphous regions. In the case of PE-RTs, the macromolecules in the high molecular mass fractions are short- chain branched by multistep polymerisation with α-olefins. Consequently, their crystalli- zation is hindered. The crystalline matrix is formed by the almost linear low molar mass fractions, whereas the highbranched high molecular mass fractions are incorporated in multiple crystals and so form tie-molecules. This work reviews several methods to char- acterize those polyethylenes with respect to their comonomer distribution and tie mole- cule density. Due to the necessity to locate the comonomer solely on the long chains, polymers will be separated by means of their molar mass by chemical precipitation frac- tionation or by successive self-nucleation and annealing treatment (SSA). The precipitates molar mass distributions are subsequently analysed by high temperature gel permeation chromatography (HT-GPC) measurements. The comonomer content and is determined by Fourier-transform infrared spectroscopy (FTIR), whereas the SSA spectrum provides informa- tion about the intra-fractional distribution of the comonomer. The long-term performance of such materials can be estimated by the measurement of their strain hardening modu- lus (SH-Modulus) at elevated temperature [

Characterization of the temperature and frequency dependency of the complex Poisson’s ratio using a novel combined torsional-axial rheometer - Rodríguez Agudo, José Alberto; Haeberle, Jan; Müller-Pabel, Michael; Troiss, Alexander; Shetty, Abhishek; Kaschta, Joachim; Giehl, Christopher (Journal of Rheology, 2023)
This study discusses the feasibility of using a combined torsional-axial rheometer to indirectly measure the complex Poisson’s ratio based on shear and Young’s modulus. For this purpose, isothermal frequency sweeps in torsion and extension are performed sequentially on the same cylindrical specimen and under the same environmental conditions. The method is tested on two amorphous polymers, a semicrystalline polymer, a polymer blend, and a copolymer. The article includes an extensive literature review and an uncertainty assessment of the method to provide a basis for subsequent data comparison with existing research. The experimental data show a monotonic increase in the complex Poisson’s ratio up to 0.5 as the temperature approaches α-relaxation for all samples, except for the amorphous polymer. The latter shows a local minimum in the complex Poisson’s ratio observed near α-relaxation, which disappears after thermal annealing of the sample above the α-relaxation temperature. The real and imaginary parts of the complex Poisson’s ratio are additionally determined by evaluating both phase shift angles from torsional and extensional measurements. All polymers show a certain offset between the torsional and extensional phase shift angles in the glassy state, which gradually decreases as the temperature approaches α-relaxation. The complex Poisson’s ratio results are in good agreement with the literature data obtained by existing methods. This confirms that the method is applicable to polymers up to α-relaxation temperatures with significant time savings due to the nondestructive approach. This is of particular interest, given the limited availability of data in the literature.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Acrylonitrile butadiene styrene; Dynamic mechanical analysis; Glass transition temperature; Poisson’s ratio; Polycarbonate; Polymer testing; Polymethylmethacrylate; Polypropylene; Rheology; Thermal annealing; Thermoplastic Polyurethane; Viscoelasticity

Charge transport in nanoparticular thin films of zinc oxide and aluminum-doped zinc oxide - Lenz, Thomas; Richter, Moses; Matt, Gebhard; Luechinger, N.A.; Halim, S.C.; Heiß, Wolfgang; Brabec, Christoph (Journal of Materials Chemistry C, 2015)
In this work, we report on the electrical characterization of nanoparticular thin films of zinc oxide (ZnO) and aluminum-doped ZnO (AZO). Temperature-dependent current-voltage measurements revealed that charge transport for both, ZnO and AZO, is well described by the Poole-Frenkel model and excellent agreement between the experimental data and the theoretical predictions is demonstrated. For the first time it is shown that the nature of the charge-transport is not affected by the doping of the nanoparticles and it is proposed that the Poole-Frenkel effect is an intrinsic and universally limiting mechanism for the charge transport in nanoparticular thin films with defect states within the bandgap. © The Royal Society of Chemistry 2015.
Keywords: Engineering controlled terms: Aluminum; Carrier transport; Optical films; Semiconductor doping; Thin films; Zinc; Zinc oxide Aluminum-doped zinc oxide; Aluminum-doped ZnO; Current voltage measurement; Electrical characterization; Poole-Frenkel effect; Poole-Frenkel model; Temperature dependent; Zinc oxide (ZnO) Engineering main heading: Oxide films

Chemical-recognition-driven selectivity of SnO2-nanowire-based gas sensors - Park, Hyoungwon; Kim, Jae-Hun; Vivod, Dustin; Kim, Sungil; Mirzaei, Ali; Zahn, Dirk; Park, Changkyoo; Halik, Marcus; Kim, Sang Sub (Nano Today, 2021)
The sensing capabilities of semiconducting metal oxide (SMO)-based gas sensors, which are a promising type of sensors, were improved in the present study using a novel method that enhanced gas selectivity toward various gas molecules. A simple and effective post-modification with functional self-assembled monolayer (SAM) molecules enhanced the selective sensing properties. The chemical-affinity-driven interaction between SAM and gas molecules enabled selective gas sensing, and the small size of SnO2 nanowires (NWs; diameter = 50 nm) provided a large sensing area. Moreover, simple alteration of the chemical moiety in SAM molecules facilitated the tuning of SAM-induced selectivity over a broad range of collections. The binding of SAMs on the NWs was analyzed by infrared spectroscopy, thermogravimetric analysis, and X-ray photoelectron spectroscopy, with the selective gas sensing being investigated under various sensing conditions. The results from the molecular dynamics simulations supported the proposed selective sensing mechanism. The combination of passivation and selective gas sensing resulted in a simple method for the selective gas sensing of SnO2 NWs, and the concept could be generally expanded to other types of SMO-based sensing platform
Keywords: Self-assembled monolayer; SnO2 nanowire; Gas sensor; Selectivity; Surface chemistry; MD simulation

CHIR99021 Promotes hiPSC-Derived Cardiomyocyte Proliferation in Engineered 3D Microtissues - Hesselbarth, Ramona; Esser, Tilman; Roshanbinfar, Kaveh; Schrüfer, Stefan; Schubert, Dirk W.; Engel, Felix (Advanced Healthcare Materials, 2021)
Cardiac tissue engineering is a promising strategy to generate human cardiac tissues for modeling cardiac diseases, screening for therapeutic drugs, and repairing the injured heart. Yet, several issues remain to be resolved including the generation of tissues with high cardiomyocyte density. Here, it is shown that the integration of the glycogen synthase kinase-3β inhibitor CHIR99021 in collagen I hydrogels promotes proliferation of human-induced pluripotent stem cell-derived (hiPSC) cardiomyocytes post-fabrication improving contractility of and calcium flow in engineered 3D cardiac microtissues. CHIR99021 has no effect on the gelation kinetics or the mechanical properties of collagen I hydrogels. Analysis of cell density and proliferation based on Ki-67 staining indicates that integration of CHIR99021 together with external CHIR99021 stimulation increases hiPSC-cardiomyocyte number by ≈2-fold within 7 d post-fabrication. Analysis of the contractility of engineered cardiac tissues after another 3 d in the absence of external CHIR99021 shows that CHIR99021-induced hiPSC-cardiomyocyte proliferation results in synchronized calcium flow, rhythmic beating, increased speed of contraction and contraction amplitude, and reduced peak-to-peak time. The CHIR99021-stimulated engineered cardiac microtissues exhibit spontaneous rhythmic contractions for at least 35 d. Collectively, the data demonstrate the potential of induced cardiomyocyte proliferation to enhance engineered cardiac microtissues by increasing cardiomyocyte density.
CRIS-Team Scopus Importer:2021-09-17
Keywords: cardiomyocytes; CHIR99021; heart; hiPSC; proliferation; tissue engineering

Chondrogenesis of human bone marrow mesenchymal stromal cells in highly porous alginate-foams supplemented with chondroitin sulfate - Huang, Zhao; Nooeaid, Patcharakamon; Kohl, Benjamin; Roether, Judith; Schubert, Dirk W.; Meier, Carola; Boccaccini, Aldo R.; Godkin, Owen; Ertel, Wolfgang; Arens, Stephan; Schulze-Tanzil, Gundula (Materials Science and Engineering C, 2015)
To overcome the limited intrinsic cartilage repair, autologous chondrocyte or bone-marrow-derived mesenchymal stromal cell (BM-MSC) was implanted into cartilage defects. For this purpose suitable biocompatible scaffolds are needed to provide cell retention, chondrogenesis and initial mechanical stability. The present study should indicate whether a recently developed highly porous alginate (Alg) foam scaffold supplemented with chondroitin sulfate (CS) allows the attachment, survival and chondrogenesis of BM-MSCs and articular chondrocytes. The foams were prepared using a freeze-drying method; some of them were supplemented with CS and subsequently characterized for porosity, biodegradation and mechanical profile. BM-MSCs were cultured for 1-2 weeks on the scaffold either under chondrogenic or maintenance conditions. Cell vitality assays, histology, glycosaminoglycan (sGAG) assay, and type II and I collagen immunolabelings were performed to monitor cell growth and extracellular matrix (ECM) synthesis in the scaffolds. Scaffolds had a high porosity similar to 93-95% with a mean pore sizes of 237 +/- 48 mu m (Alg) and 197 +/- 61 mu m (Alg/CS). Incorporation of CS increased mechanical strength of the foams providing gradually CS release over 7 days. Most of the cells survived in the scaffolds. BM-MSCs and articular chondrocytes formed rounded clusters within the scaffold pores. The BM-MSCs, irrespective of whether cultured under non/chondrogenic conditions and chondrocytes produced an ECM containing sGAGs, and types II and I collagen. Total collagen and sGAG contents were higher in differentiated BM-MSC cultures supplemented with CS than in CS-free foams after 14 days. The cell cluster formation induced by the scaffolds might stimulate chondrogenesis via initial intense cell-cell contacts. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Chondrogenesis; Alginate-foam scaffolds; Chondrocytes; Mesenchymal stromal cells; Chondroitin sulfate

CO2-laser treatment of indium tin oxide nanoparticle coatings on flexible polyethyleneterephthalate substrates - Königer, Tobias; Rechtenwald, Thomas; Al-Naimi, Ihab; Frick, Thomas; Schmidt, Michael; Münstedt, Helmut (Journal of Coatings Technology and Research, 2010)
A CO2-laser treatment was used to improve the electrical conductivity of coatings of indium tin oxide (ITO) nanoparticles on flexible polyethyleneterephthalate (PET) substrates. The electrical conductivity and the transparency of CO2-laser-treated ITO nanoparticle coatings were characterized with regard to the application as transparent electrodes. Furthermore, the stability of the electrical conductivity under oscillatory bending was investigated. A specific resistance of 0.12 Ω cm is obtained by CO2-laser treatment without thermally damaging the PET film. The improvement of the electrical conductivity can be explained by a slight sinter neck formation. For a film thickness of 3 μm, a sheet resistance of 400 Ω/□ and a transmission in the visible range of 80%were achieved. The stability of the electrical conductivity of CO2-laser-treated ITO nanoparticle coatings under bending was investigated using a specially constructed device for the application of various oscillatory bending loads. For a bending radius of 10 mm, the sheet resistance does not exceed 1000 Ω/h after 300 bending cycles. Compared to commercial sputtered ITO coatings, CO 2-laser-treated ITO nanoparticle coatings show a significant higher stability under oscillatory bending. © FSCT and OCCA 2009.
Created from Fastlane, Scopus look-up
Keywords: Indium tin oxide (ITO); Laser treatment; Nanoparticles; Oscillatory bending tests

Collagen Hydrogel Containing Polyethylenimine-Gold Nanoparticles for Drug Release and Enhanced Beating Properties of Engineered Cardiac Tissues - Roshanbinfar, Kaveh; Kolesnik-Gray, Maria; Angeloni, Miriam; Schrüfer, Stefan; Fiedler, Maren; Schubert, Dirk W.; Ferrazzi, Fulvia; Krstic, Vojislav; Engel, Felix (Advanced Healthcare Materials, 2023)
Cardiac tissue engineering is a promising strategy to prevent heart failure. However, several issues remain unsolved, including efficient electrical coupling and incorporating factors to enhance tissue maturation and vascularization. Herein, a biohybrid hydrogel that enhances beating properties of engineered cardiac tissues and allows drug release concurrently is developed. Gold nanoparticles (AuNPs) with different sizes (18–241 nm) and surface charges (33.9–55.4 mV) are synthesized by reducing gold (III) chloride trihydrate using branched polyethyleneimine (bPEI). These nanoparticles increase gel stiffness from ≈91 to ≈146 kPa, enhance electrical conductivity of collagen hydrogels from ≈40 to 49–68 mS cm−1, and allow slow and steady release of loaded drugs. Engineered cardiac tissues based on bPEI-AuNP-collagen hydrogels and either primary or human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes show enhanced beating properties. hiPSC-derived cardiomyocytes exhibit more aligned and wider sarcomeres in bPEI-AuNP-collagen hydrogels compared to collagen hydrogels. Furthermore, the presence of bPEI-AuNPs result in advanced electrical coupling evidenced by synchronous and homogenous calcium flux throughout the tissue. RNA-seq analyses are in agreement with these observations. Collectively, this data demonstrate the potential of bPEI-AuNP-collagen hydrogels to improve tissue engineering approaches to prevent heart failure and possibly treat diseases of other electrically sensitive tissues.
CRIS-Team Scopus Importer:2023-04-21
Keywords: collagen; gold nanoparticles; heart; tissue engineering

Comparative Rheological Studies of Autoclave and Tubular Low-Density Polyethylene - Wang, Hao; Kaschta, Joachim; Schubert, Dirk W. (29th International Conference of the Polymer Processing Society, 2013)

Comparing recycled and virgin poly (ethylene terephthalate) melt-spun fibres - Qin, Yijing; Qu, Muchao; Kaschta, Joachim; Schubert, Dirk W. (Polymer Testing, 2018)
Keywords: Virgin PET; Mechanical properties; Recycled PET; Melt spinning

Comparing recycled and virgin poly(ethyleneterephthalate) melt-spun fibres - Qin, Yijing; Qu, Muchao; Kaschta, Joachim; Schubert, Dirk W. (Annual European Rheology Conference (AERC2019), 2019)

Comparison of hydrogels for the development of well-defined 3d cancer models of breast cancer and melanoma - Schmid, Rafael; Schmidt, Sonja; Hazur, Jonas; Detsch, Rainer; Maurer, Evelyn; Boccaccini, Aldo R.; Hauptstein, Julia; Teßmar, Jörg; Blunk, Torsten; Schrüfer, Stefan; Schubert, Dirk W.; Horch, Raymund E.; et al. (Cancers, 2020)
Bioprinting offers the opportunity to fabricate precise 3D tumor models to study tumor pathophysiology and progression. However, the choice of the bioink used is important. In this study, cell behavior was studied in three mechanically and biologically different hydrogels (alginate, alginate dialdehyde crosslinked with gelatin (ADA–GEL), and thiol-modified hyaluronan (HA-SH crosslinked with PEGDA)) with cells from breast cancer (MDA-MB-231 and MCF-7) and melanoma (Mel Im and MV3), by analyzing survival, growth, and the amount of metabolically active, living cells via WST-8 labeling. Material characteristics were analyzed by dynamic mechanical analysis. Cell lines revealed significantly increased cell numbers in low-percentage alginate and HA-SH from day 1 to 14, while only Mel Im also revealed an increase in ADA–GEL. MCF-7 showed a preference for 1% alginate. Melanoma cells tended to proliferate better in ADA– GEL and HA-SH than mammary carcinoma cells. In 1% alginate, breast cancer cells showed equally good proliferation compared to melanoma cell lines. A smaller area was colonized in high-percentage alginate-based hydrogels. Moreover, 3% alginate was the stiffest material, and 2.5% ADA–GEL was the softest material. The other hydrogels were in the same range in between. Therefore, cellular responses were not only stiffness-dependent. With 1% alginate and HA-SH, we identified matrices that enable proliferation of all tested tumor cell lines while maintaining expected tumor heterogeneity. By adapting hydrogels, differences could be accentuated. This opens up the possibility of understanding and analyzing tumor heterogeneity by biofabrication.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Biofabrication; Breast cancer; Hydrogel; Melanoma; Tumor heterogeneity

Comparison of rheological and electrical properties of polymethylmethacrylate filled with carbon black or carbon fibres - Krückel, Johannes; Stary, Zdenek; Schubert, Dirk W.; Münstedt, Helmut (Final Program and Book of Abstracts, 2011)

Comparison of the Behavior of 3D-Printed Endothelial Cells in Different Bioinks - Schulik, Jana; Salehi, Sahar; Boccaccini, Aldo R.; Schrüfer, Stefan; Schubert, Dirk W.; Arkudas, Andreas; Kengelbach-Weigand, Annika; Horch, Raymund E.; Schmid, Rafael (Bioengineering, 2023)
Biomaterials with characteristics similar to extracellular matrix and with suitable bioprinting properties are essential for vascular tissue engineering. In search for suitable biomaterials, this study investigated the three hydrogels alginate/hyaluronic acid/gelatin (Alg/HA/Gel), pre-crosslinked alginate di-aldehyde with gelatin (ADA-GEL), and gelatin methacryloyl (GelMA) with respect to their mechanical properties and to the survival, migration, and proliferation of human umbilical vein endothelial cells (HUVECs). In addition, the behavior of HUVECs was compared with their behavior in Matrigel. For this purpose, HUVECs were mixed with the inks both as single cells and as cell spheroids and printed using extrusion-based bioprinting. Good printability with shape fidelity was determined for all inks. The rheological measurements demonstrated the gelling consistency of the inks and shear-thinning behavior. Different Young’s moduli of the hydrogels were determined. However, all measured values where within the range defined in the literature, leading to migration and sprouting, as well as reconciling migration with adhesion. Cell survival and proliferation in ADA-GEL and GelMA hydrogels were demonstrated for 14 days. In the Alg/HA/Gel bioink, cell death occurred within 7 days for single cells. Sprouting and migration of the HUVEC spheroids were observed in ADA-GEL and GelMA. Similar behavior of the spheroids was seen in Matrigel. In contrast, the spheroids in the Alg/HA/Gel ink died over the time studied. It has been shown that Alg/HA/Gel does not provide a good environment for long-term survival of HUVECs. In conclusion, ADA-GEL and GelMA are promising inks for vascular tissue engineering.
CRIS-Team Scopus Importer:2023-08-11
Keywords: biofabrication; bioprinting; endothelial cells; hydrogels; tissue engineering; vascularization

Comparison of viscous and elastic properties of polyolefin melts in shear and elongation - Wolff, Friederich; Resch, Julia; Kaschta, Joachim; Münstedt, Helmut (Rheologica Acta, 2010)
Viscous and elastic properties of a linear polypropylene (PP) and a long-chain branched low-density polyethylene (LDPE) have been investigated by creep and creep-recovery experiments in shear and elongation. The data obtained verify the ratios between the linear values of the viscosities and the steady-state elastic compliances in shear and elongation predicted by the theory of linear viscoelasticity. In the nonlinear range, no simple correlation between the viscous behaviour in shear and elongation exists. The elongational viscosity of the PP decreases with increasing stress analogously to the shear thinning observed; the linear range extends to higher stresses in elongation than in shear, however. The LDPE shows thinning in shear and strain hardening in elongational flow. For the LDPE, a linear steady-state elastic tensile compliance corresponding to one third of the linear steady-state elastic compliance in shear was determined. For the PP, this theoretically predicted value is approximately reached. Analogous to the viscous behaviour, the linear range extends to higher stresses in elongation than in shear. For both materials, the steady-state elastic compliances in the nonlinear range decrease with increasing stress in shear as well as in elongation. However, the decrease in elongation is more pronounced.
Keywords: Polypropylene; Polyethylene; Viscosity; Elasticity; Shear; Elongation

Composite polymer-bioceramic scaffolds with drug delivery capability for bone tissue engineering - Mourino, Viviana; Cattalini, Juan P.; Roether, Judith; Dubey, Prachi; Roy, Ipsita; Boccaccini, Aldo R. (Expert Opinion on Drug Delivery, 2013)
Introduction: Next-generation scaffolds for bone tissue engineering (BTE) should exhibit the appropriate combination of mechanical support and morphological guidance for cell proliferation and attachment while at the same time serving as matrices for sustained delivery of therapeutic drugs and/or biomolecular signals, such as growth factors. Drug delivery from BTE scaffolds to induce the formation of functional tissues, which may need to vary temporally and spatially, represents a versatile approach to manipulating the local environment for directing cell function and/or to treat common bone diseases or local infection. In addition, drug delivery from BTE is proposed to either increase the expression of tissue inductive factors or to block the expression of others factors that could inhibit bone tissue formation. Composite scaffolds which combine biopolymers and bioactive ceramics in mechanically competent 3D structures, including also organic-inorganic hybrids, are being widely developed for BTE, where the affinity and interaction between biomaterials and therapeutic drugs or biomolecular signals play a decisive role in controlling the release rate. Areas covered: This review covers current developments and applications of 3D composite scaffolds for BTE which exhibit the added capability of controlled delivery of therapeutic drugs or growth factors. A summary of drugs and biomolecules incorporated in composite scaffolds and approaches developed to combine biopolymers and bioceramics in composites for drug delivery systems for BTE is presented. Special attention is given to identify the main challenges and unmet needs of current designs and technologies for developing such multifunctional 3D composite scaffolds for BTE. Expert opinion: One of the major challenges for developing composite scaffolds for BTE is the incorporation of a drug delivery function of sufficient complexity to be able to induce the release patterns that may be necessary for effective osseointegration, vascularization and bone regeneration. Loading 3D scaffolds with different biomolecular agents should produce a codelivery system with different, predetermined release profiles. It is also envisaged that the number of relevant bioactive agents that can be loaded onto scaffolds will be increased, whilst the composite scaffold design should exploit synergistically the different degradation profiles of the organic and inorganic components. © 2013 Informa UK, Ltd.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.compos
Keywords: Bone tissue engineering; Composite scaffolds; Drug delivery

Compression moduli of foamed films of fluorinated ethylene propylene copolymers determined by nanoindentation - Zirkel, Larissa; Maier, Verena; Durst, Karsten; Münstedt, Helmut (Polymer Testing, 2011)
Nanoindentation was applied to determine the elastic moduli in the compression mode of films of fluorinated ethylene propylene copolymers (FEP) foamed by means of supercritical carbon dioxide. For this purpose, a flat punch indenter with a diameter larger than the average cell size of the foams was found to be appropriate. The dependence of the mechanical properties of the films on their cellular structure was investigated by varying material and process parameters: molar mass of the FEP, the magnitude of the pressure drop and the temperature during the foaming process. The elastic modulus showed a strong influence of the cellular structure of the films. A decrease of the molar mass of FEP as well as an increase of pressure drop and foaming temperature considerably reduced the elastic modulus of the foams generated. This lowering of the stiffness correlated with the decrease of foam density. In addition, a significant contribution of the cellular morphology and the thickness of the compact skin layers of the foams could be noted. A further reduction of the foam stiffness was achieved by a biaxial stretching of the foams, which deformed the cells into a lens shape.
WW1::864

Compressive and cyclic loading of silicone breast implants and their effect on shape resilience and reliability of the shell material - Schubert, Dirk W.; von Hanstein, Harald; Daenicke, Jonas; Werner, Siegfried; Horch, Raymund E. (Polymer International, 2018)
The mechanical behavior of gel-filled silicone breast implants has been examined as well as the mechanical properties of the implant shell itself. For the first time the implants were tested under compression in two different ways. Subsequently the implant shell material was analyzed by tensile test on dumbbell-shaped specimens. The results are presented in contour plots which provide a detailed view of the measured values of the samples. Finally a statistical failure analysis was carried out by means of a Weibull fit to provide further data on the mechanical behavio
Keywords: Compression test; cyclic loading; mechanical properties; silicone breast implant; tensile test

Concept of a Molecular Charge Storage Dielectric Layer For Organic Thin-Film Memory Transistors - Burkhardt, Martin; Jedaa, Abdesselam; Novak, Michael; Ebel, Alexander; Voitchovsky, Kislon; Stellacci, Francesco; Hirsch, Andreas; Halik, Marcus (Advanced Materials, 2010)
(Figure Presented) A mixed self-assembled monolayer containing aliphatic and electron-accepting (C ) components is employed as an ultrathin molecular gate dielectric to facilitate reversible, nonvolatile electronic memory functionality in organic transistors at low supply voltages. By adjusting the stoichiometry of the monolayer components, the transistor and memory characteristics can be tuned. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Concept of a thin film memory transistor based on ZnO nanoparticles insulated by a ligand shell - Hirschmann, Johannes; Faber, Hendrik; Halik, Marcus (Nanoscale, 2012)

Conductance Enhancement of Nano-Particulate Indium Tin Oxide Layers Fabricated by Printing Technique - Groß, Michael; Maksimenko, Ilja; Faber, Hendrik; Linse, N.; Wellmann, Peter (Nanotech 2008, Vol. 1-3, 2008)
To understand the mechanisms behind the conductance improvement and to fathom the limits we did some investigations: long-term resistance measurements gave an insight in oxygen vacancy balance concentration. From infrared absorption measurements we inferred the free charge carrier density and at present we carry out XPS measurements which yield information about the alteration of oxygen vacancy concentration. Considering these data we discuss two conductance improving mechanisms: The increase of the free charge carrier density by a rise of oxygen vacancy concentration as well as a release of trapped charge carriers from the aggregate surface
Keywords: ITO; nanoparticles; transmittance; conductance

Conductivity and adhesion enhancement in low-temperature processed indium tin oxide/polymer nanocomposites - Maksimenko, Ilja; Groß, Michael; Königer, Tobias; Münstedt, Helmut; Wellmann, Peter (Thin Solid Films, 2010)
We report on the conductivity and adhesion enhancement of indium tin oxide (In(2)O(3):Sn; ITO) nanoparticle films by the application of polymers as matrix material. We fabricated ITO layers at a maximum process temperature of 130 degrees C by modifying and spin-coating nanoparticulate ITO dispersions. Dispersions containing the organic film-forming agent polyvinylpyrrolidone (PVP) and the organofunctional coupling agent 3-methacryloxypropyltrimethoxysilane (MPTS) have been developed to obtain transparent and conducting coatings on substrates which do not withstand high process temperatures like polymers or already processed glasses. The layers were cured by UV-irradiation as well as by low-temperature heat treatment (T = 130 degrees C) in air and under forming gas atmosphere (N(2)/H(2)). The influence of the additives on the electrical, optical, morphological and mechanical layer properties is reported. Compared to best pure ITO layers (3.1 Omega(-1)cm(-1)), the ITO-MPTS-PVP nanocomposite coatings exhibit a conductance of 9.8 Omega(-1)cm(-1). Stable sheet resistances of 750 Omega/square at a coexistent transmittance of 86% at 550 nm for a layer thickness of about 1.3 mu m were achieved. The conductance enhancement is a consequence of the consolidation of the ITO nanoparticle network due to the acting shrinkage forces caused either by drying in the case of PVP or UV-irradiation induced condensation and polymerization reactions in the case of MPTS. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Indium tin oxide (ITO); Nanoparticles; Polyvinylpyrrolidone (PVP); 3-Methacryloxypropyltrimethoxysilane (MPTS); Nanocomposite; Adhesion

Conductivity and phase morphology of carbon black-filled immiscible polymer blends under creep: an experimental and theoretical study. - Pan, Yamin; Liu, Xian Hu; Hao, Xiaoqiong; Schubert, Dirk W. (Physical Chemistry Chemical Physics, 2016)
Blends of carbon black (CB)-filled co-continuous immiscible polystyrene/poly(methyl-methacrylate) (PS/PMMA) with a PS/PMMA ratio of 50/50 and CB selectively located in the PS phase have been prepared by melt blending. The simultaneous evolution of conductivity and phase morphology of blend composites was investigated under shear and in the quiescent state at 200 °C. It was found that shear deformation had a significant influence on the conductivity of the unfilled PS/PMMA blend and its composites, which was attributed to the change of phase morphology during shear. After the shear stress of 10 kPa, the conductivity of PS/PMMA blends filled with 2 vol% of CB decreased by about two orders of magnitude and the phase morphology transformed from a fine co-continuous structure into a highly elongated lamellar structure. The deformation of phase morphology and the decrease of conductivity were weakened upon decreasing the shear stress or increasing the CB concentration. During subsequent recovery, pronounced phase structure coarsening was observed in the mixture and the conductivity increased as well. A simple model describing the behavior of conductivity under shear deformation was derived and utilized for the description of the experimental data. For the first time, the Burgers model was used to describe the conductivity, and the viscoelastic and viscoplastic parameters were deduced by fitting the conductivity under shear. The results obtained in this study provide a deeper insight into the evolution of phase structure in the conductive polymer blend composite induced by shear deformation.

Conductivity and phase morphology of carbon black filled immiscible polymer blends under shear in the molten state - Pan, Yamin; Liu, Xian Hu; Schubert, Dirk W. (Book of Abstracts, 2016)

Conductivity of carbon black-based polymer composites under creep in the molten state - Stary, Zdenek; Krückel, Johannes; Schubert, Dirk W. (Polymer, 2014)
The mechanical deformation of conductive polymer composites during melt processing affects their final electrical properties considerably. To get an insight in this relationship, simultaneous electrical-rheological measurements can be used to follow the changes in composite phase structure induced by defined deformation. In this work, the evolution of electrical conductivity was investigated during and after shear deformation at constant stress. From the experiments performed it can be concluded, that the flow-induced build-up mechanism leads to the formation of conductive pathways with enhanced stability compared to the structures build-up under quiescent conditions. This finding can be explained by the orientation of particle structures in the shear direction. Therefore, materials with different deformation history but the same electrical conductivity can display markedly different electrical behaviour under deformation. © 2014 Elsevier Ltd. All rights reserved.
Keywords: Electrical conductivity; Polymer composites; Rheology

Conductivity of melt spun PMMA composites with aligned carbon fibers - Qu, Muchao; Schubert, Dirk W. (Composites Science and Technology, 2016)
The conductivity and morphology of melt-spun PMMA/carbon fiber (CF) composites have been investigated and analyzed. Using a two-step melt mixing procedure, CF aspect ratios of 6.3, 9.2 and 12.0 were achieved. Fiber composites with different CFs concentrations were melt spun using a capillary rheometer, to induce CF orientation, and the morphologies of both the surface and the cross-section were observed and discussed. The conductivity of composite fibers at room temperature was compared with the McLachlan GEM equation and Balberg excluded volume theory. The percolation threshold as well as the relationship between the percolation behavior and the aspect ratio were also determined. Taking into consideration the filler orientation, the slope K = 3.4 in excluded volume theory was estimated for the first time.
Keywords: Carbon fibers; Electrical properties; Melt-spinning

Conductivity of melt spun PMMA composites with aligned carbon fibers - Qu, Muchao; Schubert, Dirk W. (Composites Science and Technology, 2016)
The conductivity and morphology of melt-spun PMMA/carbon fiber (CF) composites have been investigated and analyzed. Using a two-step melt mixing procedure, CF aspect ratios of 6.3, 9.2 and 12.0 were achieved. Fiber composites with different CFs concentrations were melt spun using a capillary rheometer, to induce CF orientation, and the morphologies of both the surface and the cross-section were observed and discussed. The conductivity of composite fibers at room temperature was compared with the McLachlan GEM equation and Balberg excluded volume theory. The percolation threshold as well as the relationship between the percolation behavior and the aspect ratio were also determined. Taking into consideration the filler orientation, the slope K = 3.4 in excluded volume theory was estimated for the first tim

Conductivity of Melt-Spun PMMA Composites with Aligned Carbon Fibers - Qu, Muchao; Schubert, Dirk W. (Programme and Books of Abstracts, 2016)

Conductivity of Melt-Spun PMMA Composites with Aligned Carbon Fibers - Qu, Muchao; Schubert, Dirk W. (Book of Abstracs, 2016)

Conductivity of Melt Spun PMMA Composites with Aligned Carbon Fibers - Qu, Muchao; Schubert, Dirk W. (Polychar, 2017)

Conductivity of Melt Spun PMMA Composites with Aligned Carbon Fibers. - Qu, Muchao; Schubert, Dirk W. (The 29th International Conference on Diamond and Carbon like Materials, 2018)

Conductivity of Melt Spun PMMA Composites with Aligned Carbon Fibers revealing a master curve - Qu, Muchao; Schubert, Dirk W. (15th Bayreuth Polymer Symposium, 2017)

Conductivity of melt spun PMMA composites with aligned carbon fibers – revealing a master curve - Schubert, Dirk W.; Qu, Muchao (Workshop on Italian-Nordic Polymer Future, 2017)

Conductivity of PMMA composite casting films filled with ultra-high aspect ratio of carbon fibers - Xu, Huagen; Qu, Muchao; Schubert, Dirk W. (2019)

Conductivity of poly(methyl methacrylate) composite films filled with ultra-high aspect ratio carbon fibers - Xu, Huagen; Qu, Muchao; Schubert, Dirk W. (Composites Science and Technology, 2019)
In this study, the poly(methyl methacrylate) (PMMA)/carbon fibers (CFs) composite films with different CFs concentrations have been prepared using the solution casting technique. CFs were modified using aqua regia to reduce aggregations. The residual aspect ratios (ARs) of CFs in the composite films are 49, 105, 227, 312, 417, 527 and 616, respectively. Light microscopy and SEM were applied to investigate the morphology of the composite films. The resistance of the film with different ARs of CFs was measured (1) perpendicularly and (2) along the in-plane direction. Both percolation thresholds ϕc,⊥ and ϕc,∥ were determined by fitting the Mclachlan GEM equation. The conductivity in both directions was presented in contour plot versus ARs of CFs and concentration of CFs. A huge amount of experimental data was obtained in this study, seven aspect ratio (AR) of CFs multiply 12 vol fraction of CFs with two measuring directions. Based on Balberg's excluded volume theory, for the first time the pre-factors K⊥ and K∥ were revealed, considering different measuring direction on the film.
CRIS-Team Scopus Importer:2019-07-02
Keywords: onductive composite films; Percolation threshold; carbon fiber; aspect ratio; orientation; confined geometry

Conductivity of polymethylmethacrylate filled with carbon black or carbon fibres under oscillatory shear - Krückel, Johannes; Stary, Zdenek; Triebel, Christian; Schubert, Dirk W.; Münstedt, Helmut (Polymer, 2012)
The electrical conductivity of polymer composites containing conductive fillers is strongly influenced by the structure of the particle network. Therefore, the change of this network under deformation in the molten state is of great interest, in order to obtain materials with desirable electrical properties. In this work polymethylmethacrylate containing carbon black or carbon fibres was exposed to oscillatory shear deformations and the electrical conductivity of the materials was measured simultaneously. It was found that the particle networks in the composites filled with carbon fibres were more sensitive to deformation than those of the carbon black composites. The stability of the networks increased with growing amount of fillers. Furthermore, it could be shown that conductive and rheological networks behave completely different under shear deformations.
Keywords: Polymer composites; Rheology; Conductivity

Conductivity of poly(methyl methacrylate)/polystyrene/carbon black and poly(ethyl methacrylate)/polystyrene/carbon black ternary composite films - Xu, Huagen; Qu, Muchao; Pan, Yamin; Schubert, Dirk W. (Chinese Journal of Polymer Science, 2019)
Both poly(methyl methacrylate) (PMMA)/polystyrene (PS)/carbon black (CB) and poly(ethyl methacrylate) (PEMA)/PS/CB ternary composite films were obtained using solution casting technique to investigate double percolation effect. In both PMMA/PS/CB, PEMA/PS/CB ternary composite films, the CB particles prefer to locate into PS phase based on the results of calculating wetting coefficient, which is also confirmed by SEM images. The conductivity of the films were investigated, the percolation threshold (c) of both ternary composite films with different polymer blend ratio were determined by fitting the McLachlan GEM equation. Conductivity of PMMA/PS/CB ternary composite films shows a typical double percolation effect. However, due to the double emulsion structure of PEMA/PS polymer blends, even the CB only located in PS phase, the PEMA/PS/CB ternary composite films (PEMA/PS = 50/50) shows a higher c, which conflicts with double percolation effect. A schematic diagram combined with SEM images was proposed to explain this phenomeno
Keywords: Double percolation effect; Conductivity; Ternary composite films; Compatibility

Continuous direct melt foaming of a preceramic polymer using carbon dioxide: extrusion device and first results - Wolff, Friedrich; Münstedt, Helmut (Journal of Materials Science, 2011)
EAM Import::2019-03-13

Controlled In Situ PbSe Quantum Dot Growth around Single-Walled Carbon Nanotubes: A Noncovalent PbSe-SWNT Hybrid Structure - Schornbaum, Julia; Winter, Benjamin; Schießl, Stefan; Butz, Benjamin; Spiecker, Erdmann; Zaumseil, Jana (Chemistry of Materials, 2013)
We developed a simple method of synthesizing noncovalently linked hybrids of PbSe quantum dots (QDs) and single-walled carbon nanotubes (SWNTs). The PbSe QDs grow around the SWNTs without any linker molecule or chemical modification of the SWNTs. We are able to control the size and shape of the QDs attached to the SWNTs by varying the synthesis conditions and elucidate the three-dimensional (3D) morphology and atomic structure of the half-ring-shaped PbSe QDs bonded to the SWNTs using scanning transmission electron microscopy (STEM) tomography and high-resolution transmission electron microscopy (HRTEM). The PbSe QDs not only assemble on the SWNT bundles, but they actually grow around them. The growth of the PbSe QDs around SWNT sidewalls is favored over the growth of spherical particles in solution, probably due to dipole stabilization by the large pi-electron system of the SWNTs.
Keywords: hybrid material; PbSe quantum dots; single-walled carbon nanotubes; electron tomography

Controlled manufacturing of the surface texture of gel-filled silicone breast implants and the correlation to mechanical behavior - Werner, Siegfried; Schubert, Dirk W. (Abstracts, 2016)

Controlled Self-Assembly of Gold Nanotetrahedra into Quasicrystals and Complex Periodic Supracrystals - Wang, Yi; Chen, Jun; Li, Ruipeng; Götz, Alexander; Drobek, Dominik; Przybilla, Thomas; Hübner, Sabine; Pelz, Philipp; Yang, Lin; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Engel, Michael; et al. (Journal of the American Chemical Society, 2023)
The self-assembly of shape-anisotropic nanocrystals into large-scale structures is a versatile and scalable approach to creating multifunctional materials. The tetrahedral geometry is ubiquitous in natural and manmade materials, yet regular tetrahedra present a formidable challenge in understanding their self-assembly behavior as they do not tile space. Here, we report diverse supracrystals from gold nanotetrahedra including the quasicrystal (QC) and the dimer packing predicted more than a decade ago and hitherto unknown phases. We solve the complex three-dimensional (3D) structure of the QC by a combination of electron microscopy, tomography, and synchrotron X-ray scattering. Nanotetrahedron vertex sharpness, surface ligands, and assembly conditions work in concert to regulate supracrystal structure. We also discover that the surface curvature of supracrystals can induce structural changes of the QC tiling and eventually, for small supracrystals with high curvature, stabilize a hexagonal approximant. Our findings bridge the gap between computational design and experimental realization of soft matter assemblies and demonstrate the importance of accurate control over nanocrystal attributes and the assembly conditions to realize increasingly complex nanopolyhedron supracrystals.
CRIS-Team Scopus Importer:2023-09-29

Controlling the diameter of aligned single-walled carbon nanotubes on quartz via catalyst reduction time - Schweiger, Manuel; Schaudig, Maximilian; Gannott, Florentina; Killian, Manuela; Bitzek, Erik; Schmuki, Patrik; Zaumseil, Jana (Carbon, 2015)
One of the main objectives of chemical vapor deposition (CVD) growth of single-walled carbon nanotubes (SWCNT) is control over their diameter and type (metallic or semiconducting). Here, we investigate the evolution of iron catalyst particles on quartz substrates depending on the duration of the reduction step with hydrogen and its effect on the growth of horizontally aligned SWCNT. We find a strong dependence of catalyst particle size and size distribution on the initial iron film thickness and the reduction time at 630 °C. Initial decrease of the particle size is followed by an unexpected increase. Statistical analysis of the Raman radial breathing modes of the SWCNT over large areas gave reliable and reproducible diameter distributions that correlated directly with the catalyst particle size distributions. By changing the reduction time it was possible to reproducibly shift the average SWCNT diameter from 1.5 (±0.3) nm to 1.2 (±0.2) nm while maintaining a nanotube density of 5–6 SWCNT/ extgreekmm. In order to describe the evolution of the particle size during the reduction process at this particular temperature, we propose a model that includes the diffusion of iron into the quartz and its re-emergence.
WW1::1053
Keywords: Simulation and Modeling

Conventional non-woven vs. novel nano FFP2 masks - a competetive study on the filtration performance after various types of conditions - Halamicek, Robin; Wiesmann, Carolin; Kröner, Richard; Bogdan, Christian; Schubert, Dirk W. (Nordic Polymer Days, 2023)
Filtering face piece (FFP) masks, categorized by different filtration efficiency standards, are mandatory to achieve an efficient protection against viruses like the severe acute respirato- ry syndrome coronavirus type 2 (SARS-CoV-2) [1]. They conventionally comprise an electro- statically treated melt blown non-woven layer as the main filtering medium if the standard is FFP2. However, novel nanofibrous masks with the same standard are arising on the market, promising a higher safety alongside a high- er better wearing comfort – but for a higher unit price. This study compared different mask models from both mask types regard- ing their filtration performance after various types of conditions (change of temperature and air humidity, exposure to isopropyl al- cohol (IPA) and an autoclave sterilization) to evaluate the superior FFP2 mask type. Due to the absence of prior electrostatic treatment, the nanofibrous masks did not show a signi- ficant change in filtration efficiency when exposed to IPA, unlike to the melt blown non-woven masks. However, most melt blown type masks maintained a sufficient filtration efficiency after all other treatments and also at the untreated condition – with even better results than the nanofibrous competitors. This applied particulary for the capacity to filter smallest particles/droplets with a size of around 0.1 μm, which is below the range of typical filtering standards but important for the retention of virally contaminated nano- aerosols or unattached viruses [2-4]. Based on their better filtration performance, lower price and potential reusability, it can be concluded that conventional melt blown non-woven masks with an electrostatic treatment are the preferable FFP2 mask type for a protective purpo

Copper releasing boron containing bioactive glass-based scaffolds coated with alginate for bone tissue engineering - Erol, M. M.; Mournio, V.; Newby, P.; Chatzistavrou, Xanthippi; Roether, Judith; Hupa, L.; Boccaccini, Aldo R. (Acta Biomaterialia, 2012)
The aim of this study was to synthesize and characterize new boron-containing bioactive glass-based scaffolds coated with alginate cross-linked with copper ions. A recently developed bioactive glass powder with nominal composition (wt.%) 65 SiO 2, 15 CaO, 18.4 Na 2O, 0.1 MgO and 1.5 B 2O 3 was fabricated as porous scaffolds by the foam replica method. Scaffolds were alginate coated by dipping them in alginate solution. Scanning electron microscopy investigations indicated that the alginate effectively attached on the surface of the three-dimensional scaffolds leading to a homogeneous coating. It was confirmed that the scaffold structure remained amorphous after the sintering process and that the alginate coating improved the scaffold bioactivity and mechanical properties. Copper release studies showed that the alginate-coated scaffolds allowed controlled release of copper ions. The novel copper-releasing composite scaffolds represent promising candidates for bone regeneration. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.copper
Keywords: Alginate; Antibacterial; Bioactive glass; Cu ion release; Scaffolds

Corneal endothelium can be protected against cell by anti-Bax siRNA - Fuchsluger, Thomas; Thieme, Daniel; Kruse, Friedrich; Mahajan, Siddharth; Schubert, Dirk W. (The Association for Research in Vision and Ophthalmology (ARVO), 2018)
Keywords: corneal; ani-Bak

Correction: Patient-tailored silicone plug for HeartMate 3™ left ventricular assist device explantation (Journal of Artificial Organs, (2023), 10.1007/s10047-023-01397-w) - Elbayomi, Mohamed; Tandler, Rene; Ebel, Nina; Schubert, Dirk W.; Werner, Siegfried; Kondruweit, Markus; Weyand, Michael; Heim, Christian (Journal of Artificial Organs, 2023)
In this article the author’s name Dirk W. Schubert was incorrectly written as Shubert Dirk. Also, the given and family names of the authors were incorrectly structured. The correct name should read as “Mohamed Elbayomi, Rene Tandler, Nina Ebel, Dirk W. Schubert, Siegfried Werner, Markus Kondruweit, Micheal Weyand, Christian Heim". The original article has been corrected.
CRIS-Team Scopus Importer:2023-12-08

Correction to: Ni Flower/MXene-Melamine Foam Derived 3D Magnetic/Conductive Networks for Ultra-Efficient Microwave Absorption and Infrared Stealth (Nano-Micro Letters, (2022), 14, 1, (63), 10.1007/s40820-022-00812-w) - Cheng, Haoran; Pan, Yamin; Wang, Xin; Liu, Chuntai; Shen, Changyu; Schubert, Dirk W.; Guo, Zhanhu; Liu, Xianhu (Nano-Micro Letters, 2022)
The original version of this article unfortunately contained some mistakes. The corrections are updated as follows:
CRIS-Team Scopus Importer:2022-06-03

Correlating rheology and printing performance of fiber-reinforced bioinks to assess predictive modelling for biofabrication - Sonnleitner, David; Schrüfer, Stefan; Berglund, Linn; Schubert, Dirk W.; Lang, Gregor (Journal of Materials Research, 2021)
A crucial property for the evaluation of bioinks, besides biocompatibility, is printability, which is determined by resolution and shape fidelity. Recently, fiber reinforcement was used to overcome rheological limitations and introduce biomimetic structuring. This study provides a systematic approach to evaluate the printability of fiber reinforced hydrogels. Alginate and Pluronic hydrogels were blended with cellulose nanofibers (CeNF) and polycaprolactone (PCL) microfibers. SEM imaging revealed fiber-induced structural changes. Oscillatory rheological experiments showed that the addition of fiber fragments significantly altered the complex viscosity. A customized setup was utilized to determine strut spreading behavior in a real extrusion printing process. Strikingly, the data displayed excellent correlation with viscoelastic model-based predictions. CeNF increased the shape fidelity of both hydrogels, while PCL microfibers increased the viscosity but resulted in a time dependent loss of structural integrity in Pluronic. The results emphasize the need to complement shear-rheological analysis of bioinks by print-related customized analytical tools.<br
CRIS-Team Scopus Importer:2021-07-16
Keywords: 3D printing; Composite; Extrusion; Fiber; Modeling; Viscoelasticity

Correlation between dispersion, rheological and electrical characteristics of barium titanate filled liquid silicone rubber - Ziegmann, Andreas; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Correlation of the Cox/Merz-relation with the Carreau function – Analytical and empirical consequences - Ziegmann, Andreas; Schubert, Dirk W. (8th Annual European Rheology Conference, 2013)

Coupled Electrical and Rheological Experiments as a Tool to Study the Aggregation Kinetics of Carbon Black in Polymer Melts - Krückel, Johannes; Schubert, Dirk W. (9th Annual European Rheology Conference, 2014)

Covalent 2D Patterning, Local Electronic Structure and Polarization Switching of Graphene at the Nanometer Level - Bao, Lipiao; Zhao, Baolin; Assebban, M'hamed; Halik, Marcus; Hauke, Frank; Hirsch, Andreas (Chemistry - A European Journal, 2021)
A very facile and efficient protocol for the covalent patterning and properties tuning of graphene is reported. Highly reactive fluorine radicals were added to confined regions of graphene directed by laser writing on graphene coated with 1-fluoro-3,3-dimethylbenziodoxole. This process allows for the realization of exquisite patterns on graphene with resolutions down to 200 nm. The degree of functionalization, ranging from the unfunctionalized graphene to extremely high functionalized graphene, can be precisely tuned by controlling the laser irradiation time. Subsequent substitution of the initially patterned fluorine atoms afforded an unprecedented graphene nanostructure bearing thiophene groups. This substitution led to a complete switch of both the electronic structure and the polarization within the patterned graphene regions. This approach paves the way towards the precise modulation of the structure and properties of nanostructured graphene.
CRIS-Team Scopus Importer:2021-05-07
Keywords: covalent patterning; fluorination; graphene; polarization switch; substitution

Creep and recovery behavior of injection-molded isotactic polypropylene with controllable skin-core structure - Wang, Xin; Pan, Yamin; Qin, Yijing; Voigt, Monika; Liu, Xianhu; Zheng, Guoqiang; Chen, Qiang; Schubert, Dirk W.; Liu, Chuntai; Shen, Changyu (Polymer Testing, 2018)
The creep behavior is one of the most important properties and should be characterized to evaluate long-term durability and reliability of polymeric materials. An alteration of the crystalline structure and morphology in the semicrystalline polymer leads to a change in the creep behavior as well. In this work, in order to understand the creep behavior of different morphologies, a modified injection molding technology with twice melt filling (M2) was used to prepare isotactic polypropylene (iPP) samples with controllable skin-core structure. The different shear layer thicknesses were obtained by adjusting the time intervals of the twice melt filling. Compared with the conventional injection-molded samples (M1), M2 samples present better efficiencies in reducing the creep and recovery response, and the response was strongly influenced by the shear layer thicknesses. For example, the thickness of skin layer of M2 sample with a time interval of 9 s increased approximately 42% and its creep deformation reduced to 52% at 80 °C. It was also found that the creep and recovery strain reduced with decreased temperature or with applied stress. In addition, several theoretical models were used to describe the creep and recovery behavior of M2 samples for a better understanding of the mechanism
Keywords: Creep; Injection molding; PP; Polypropylene; Skin-core structure

Crystalline structure of injection molded β-isotactic polypropylene: Analysis of the oriented shear zone - Liu, Xianhu; Dai, Kun; Hao, Xiaoqiong; Zheng, Guoqiang; Liu, Chuntai; Schubert, Dirk W.; Shen, Changyu (Industrial & Engineering Chemistry Research, 2013)
Although both shear flow and β-nucleating agent (β-NA) could separately induce β-crystal in isotactic polypropylene (iPP), their combination, particularly in the typical industrial processes, in fact has received comparatively little attention. In the current study, two-dimensional wide-angle X-ray diffraction and small-angle X-ray scattering (2D-WAXD/SAXS) measurements were performed to investigate the effect of β-NA on the crystalline structure of the oriented shear zone in injection molded iPP. It is observed that, regardless of the β-NA concentration, parent–daughter structure of α-crystal can be formed in iPP. Furthermore, the fraction of daughter lamellae elevates with the increasing concentration of β-NA. Interestingly, unexpected scattering patterns of (300) reflection for β-crystal, which is similar with that for parent–daughter lamellar branching of α-crystal, is exclusively found in iPP with higher concentration of β-NA (1.0 wt %). The most possible explanation is that the addition of high content of β-NA lowers the free energy barrier. Additionally, the same change tendency of long period, crystal lamellar thickness and lateral dimension, d-spacing and crystallite size is found, viz., they first increase and then decrease with the increasing β-NA content. The results demonstrate that the concentrations of β-NA have a significant effect on the crystal grain structure under the practical molding proces
Keywords: injection molding process; polypropylene; x-ray; β-isotactic polypropylene; shear zone

Crystallization and Melting Behavior of Poly(Butylene Succinate) Nanocomposites Containing Silica-Nanotubes and Strontium Hydroxyapatite Nanorods - Papageorgiou, George Z.; Papageorgiou, Dimitrios G.; Chrissafis, Konstantinos; Bikiaris, Dimitrios; Will, Julia; Hoppe, Alexander; Roether, Judith; Boccaccini, Aldo R. (Industrial & Engineering Chemistry Research, 2014)
The multiple melting behavior of poly(butylene succinate) (PBSu) nanocomposites containing silica nanotubes (SiNTs) and strontium hydroxyapatite nanorods (SrHNRs) was studied with Step Scan DSC. In the reversing signal curves, recrystallization proved to be significant for samples crystallized at low temperature, which lead to large supercooling, favoring fast crystallization and formation of poor crystals that suffer recrystallization on subsequent heating scans. The crystallization study, under both isothermal and nonisothermal conditions, evidenced that only SiNTs act effectively as nucleating agents. Consequently, crystallization of the nanocomposite samples filled with 5 and mainly with 20 wt % SiNTs occurred faster than that of the neat polymeric matrix. The insertion of SrHNRs slightly lowered the crystallization rate of PBSu due to the formation of larger aggregates inside the PBSu matrix, which may inhibit crystallization. The size of crystals was smaller for PBSu/SiNTs samples, as it was proved by wide angle X-ray diffracrion (WAXD), whereas the addition of SrHNRs did not significantly affect the crystalline size of nanocomposites. © 2013 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2014.tech.IW.LM.crysta

Cultivation and characterisation of primary retinal pigment epithelium cells on nanofibre scaffolds - Heiduschka, Peter; Zimmermann, Julian Alexander; Plagemann, Tanja; Stafiej, Piotr; Himmler, Marcus; Fuchsluger, Thomas Armin; Eter, Nicole (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Curcumin-Containing Orthopedic Implant Coatings Deposited on Poly-Ether-Ether-Ketone/Bioactive Glass/Hexagonal Boron Nitride Layers by Electrophoretic Deposition - Virk, Ranjot; Ur Rehman, Muhammad Atiq; Munawar, Muhammad; Schubert, Dirk W.; Goldmann, Wolfgang; Dusza, Ján; Boccaccini, Aldo R. (Coatings, 2019)
Electrophoretic deposition (EPD) was used to produce a multilayer coatings system based on chitosan/curcumin coatings on poly-ether-ether-ketone (PEEK)/bioactive glass (BG)/hexagonal boron nitride (h-BN) layers (previously deposited by EPD on 316L stainless steel) to yield bioactive and antibacterial coatings intended for orthopedic implants. Initially, PEEK/BG/h-BN coatings developed on 316L stainless steel (SS) substrates were analyzed for wear studies. Then, the EPD of chitosan/curcumin was optimized on 316L SS for suspension stability, thickness, and homogeneity of the coatings. Subsequently, the optimized EPD parameters were applied to produce chitosan/curcumin coatings on the PEEK/BG/h-BN layers. The multilayered coatings produced by EPD were characterized in terms of composition, microstructure, drug release kinetics, antibacterial activity, and in vitro bioactivity. Scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) confirmed the deposition of chitosan/curcumin on the multilayer coating system. The release of curcumin upon immersion of multilayer coatings in phosphate-buffered saline (PBS) was confirmed by ultraviolet/visible (UV/VIS) spectroscopic analysis. The antibacterial effect of chitosan/curcumin as the top coating was determined by turbidity tests (optical density measurements). Moreover, the multilayer coating system formed an apatite-like layer upon immersion in simulated body fluid (SBF), which is similar in composition to the hydroxyapatite component of bone, confirming the possibility of achieving close bonding between bone and the coating surface.
Keywords: curcumin; chitosan; bioactive coatings; electrophoretic deposition; antibacterial coatings

Cu-releasing bioactive glass/polycaprolactone coating on Mg with antibacterial and anticorrosive properties for bone tissue engineering - Yang, Yuyun; Zheng, Kai; Liang, Ruifang; Mainka, Astrid; Taccardi, Nicola; Roether, Judith; Detsch, Rainer; Goldmann, Wolfgang; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Biomedical Materials, 2017)
Copper (Cu)-containing bioactive glass nanoparticles (Cu-BGNs) were introduced in polycaprolactone (PCL) coating systems to improve the bioactivity, antibacterial property, and corrosion resistance of vulnerable magnesium matrices under physiological conditions. The influence of different amounts of Cu-BGNs in PCL coatings was thoroughly investigated determining the wettability, electrochemical properties, and antibacterial effects against Staphylococcus carnosus and Escherichia coli, as well as their cyto-compatibility. Cu-BGNs were observed randomly scattered in PCL coatings. Increasing concentration of Cu-BGNs resulted in slightly decreasing water contact angle, and reducing anti-corrosion properties of the Cu-BGNs composite coatings. Yet higher Cu-BGNs content in coatings led to more calcium phosphate formation on the surface after 7 days of immersion in DMEM, which was confirmed by FTIR and XPS. The growth of S. carnosus and E. coli was inhibited by Cu2+ ion released from Cu-BGN coatings. In addition, both direct and indirect cyto-compatibility experiments showed that the viability and proliferation of MG-63 cells on Cu-BGN coatings were highly increased compared to pure magnesium; however, an additional increase of Cu-BGNs concentration showed a slight decrease of cell proliferation and cell activity. In summary, Cu-BGN/PCL composite coatings impart magnesium-based biomaterials antibacterial and anticorrosive properties for clinical applications.
EVALuna2:13499

Cyclic loading of model silicone elastomer samples with regard to the failure of silicone breast implants - Lämmlein, Michael; Schubert, Dirk W. (Nordic Polymer Days, 2015)

Cyclic loading of model silicone elastomer samples with regard to the failure of silicone breast implants - Schubert, Dirk W.; Lämmlein, Michael (14th Bayreuth Polymer Symposium, 2015)

Cyclic loading of model silicone elastomer samples with regard to the failure of silicone breast implants - Schubert, Dirk W.; Lämmlein, Michael; von Hanstein, Harald (Polymer Testing, 2018)
It is estimated that 15.000 to 20.000 breast augmentations are performed annually in Germany and several million worldwide. To obtain better knowledge of the reason for and the time of a possible failure of the implant shell, it is important to acquire information regarding the stability and durability of the material used and the associated failure criteria. The mechanical properties of silicone elastomers have therefore been investigated with regard to breast implants. Sample strips of the elastomer of various thicknesses were prepared and exposed to a cyclic bending load for a number of load cycles. Tensile specimens were punched out according to a defined pattern from the preloaded sample strips and tested with regard to their tensile properties, particularly the influence of cyclic loading on the stress at break. However, hence quality of a silicone implant depends not only on the strength of the material, but also on the spatial variation in the mechanical properties, and the quality of the silicone samples was also assessed in terms of the characteristic stress at break and the Weibull modulus, applying Weibull statistics to the tensile test results. The study revealed that the characteristic stress at break remained constant with increasing number of load cycles, but that the Weibull modulus decreased during the first 10.000 cycles exponentially to a critical leve
Keywords: Failure; mapping; mechanical properties; silicone breast implants

Cyclic Loading Of Silicone Breast Implatns Influence On The Failure Statistics - A Model Study - Schubert, Dirk W.; Lämmlein, Michael; Horch, Raymund E. (Book of Abstracts, 2016)

Cyclic voltammetry on n-alkylphosphonic acid self-assembled monolayer modified large area indium tin oxide electrodes - Habich, Dana; Halik, Marcus; Schmid, Guenter (Thin Solid Films, 2011)

Decyl-end-capped thiophene-phenylene oligomers as organic semiconducting materials with improved oxidation stability - Ponomarenko, S. A.; Kirchmeyer, S.; Elschner, A.; Alpatova, N. M.; Halik, Marcus; Klauk, Hagen; Zschieschang, Ute; Schmid, Günter (Chemistry of Materials, 2006)

Defects caused by degradation - A stumbling block for nanocomposites in thin film capacitors - Werner, Siegfried; Kaschta, Joachim; Schubert, Dirk W. (ICD 2022 - IEEE 2022 4th International Conference on Dielectrics, Proceedings, 2022)
The aim of this study is to shed light on why the often-praised beneficial effects of nanoparticles on dielectric breakdown strength are not observed in biaxially oriented PP-based films. Therefore, thin films of capacitor grade PP and nanocompounds containing one of two SiO2 based nanoparticles (pyrogenic and colloidal) at 2wt.% and 4wt.% were produced at a pilot scale thin film production line. Additionally, neat PP was deliberately degraded to a similar extent using cyclic extrusion on a twin-screw extruder. After cast film extrusion and biaxial stretching using a Karo IV lab stretcher, all films were tested for their dielectric strength, surface roughness, molar mass and particle dispersion using a diamond tip profilometer, HT-GPC and SEM. All films showed a reduction in molar mass of up to 50 % in mathrmM_mathrmw followed by a linear decrease in breakdown strength. It is known that the degradation mechanisms in PP lead to the inclusion of radicals, double bonds and carbonyl groups in the polymer chain, decreasing the width of the bandgap and thereby reducing dielectric strength in a stronger way than nanoparticles could enhance it. This study shows that the negative effect of degradation during processing is probably stronger than the superimposed and potentially beneficial effect of adding nanoparticles.
CRIS-Team Scopus Importer:2022-09-30

Degradation of polystyrene during processing – Utilization of molecular labels - Schubert, Dirk W.; Wenzke, Nicolai (Nordic Polymer Days, 2015)

Degradation of polystyrene during processing – Utilization of molecular labels - Schubert, Dirk W.; Wenzke, Nicolai (14th Bayreuth Polymer Symposium, 2015)

Degradation studies of a commercial radiation-resistant polypropylene sterilized by gamma and electron beam technology before and after subsequent accelerated aging cycles - Kremser, Thomas; Susoff, Markus; Roth, Stefan; Kaschta, Joachim; Schubert, Dirk W. (Journal of Applied Polymer Science, 2019)
Irradiation is one of the most widely used technologies for sterilization of medical products. Unfortunately, some polymers in the medical field are susceptible to high-energy radiation. In the case of polypropylene, this leads to yellowing and embrittlement due to degradation mechanisms. This study compares the impact of gamma and eBeam sterilizations at a dose of 45 kGy on a commercially available, radiation-resistant polypropylene in combination with accelerated aging studies. Mechanical behavior as well as yellowing, accompanied by structural investigations like molar mass characterization and crystallinity analysis, have been investigated. It is shown that eBeam has less damaging effects compared with gamma irradiation. This is shown by an initial drop in elongation at break by 46% for gamma irradiated samples in contrast to 24% decrease using eBeam irradiation. Also, an initial drop in molar mass by 43% was found for gamma irradiated samples and by 27% for eBeam. Change in color was observed by an initial increase in the yellowness index of 42% at samples after gamma irradiation, respectively, of 22% for eBeam irradiated samples. Interestingly, molar mass remained constant during aging, whereas yellowing and Embrittlement further change. Additionally, empirical equations were found, which describe the experimental data. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 48436.
CRIS-Team Scopus Importer:2019-09-17
Keywords: accelerated aging; degradation; polypropylene; radiation sterilization

Dem Rätsel des Knickens auf der Spur - Kremser, Thomas; Roth, Stefan; Schubert, Dirk W. (Kunststoffe, 2017)

Dependence of the extensional properties of polypropylene blends on the concentration of long-chain branches - Kunzelmann, Peter; Dörnhöfer, Andrea; Schubert, Dirk W. (Book of Abstracts, 2013)

Der bakterielle Biofilm auf Brustprothesen - eine aktuelle Übersicht - Horch, Raymund E.; Schultz, Gregory; Schubert, Dirk W. (Plastische Chirurgie, 2012)

Designing novel scaffolds for ocular surface reconstruction based on aligned nanofibers - Küng, Florian; Fuchsluger, Thomas; Schubert, Dirk W. (Polychar, 2017)

Determination of method-invariant activation energies of long-chain branched low-density polyethylenes - Keßner, Ute; Kaschta, Joachim; Münstedt, Helmut (Journal of Rheology, 2009)
The idea to use the temperature dependence of rheological properties, especially the flow activation energy, as a tool to investigate branching structures is well-known from literature. However, there is no common method to obtain activation energies, which are independent of the measuring quantity chosen, particularly, in the case of slightly thermorheologically complex polymers like low-density polyethylene (LDPE). Hence, differing activation energies result, which cannot unequivocally be correlated with the branching structure. This paper describes a method for the determination of method-independent activation energies for thermorheologically complex polymers like LDPE. From a generalized approach to the time-temperature superposition principle, a vertical shift factor is introduced, which is related to the temperature dependence of the linear steady-state compliance. In the case of the complex LDPE, a decrease in the linear steady-state compliance with temperature is found. Taking this experimentally determined shift factor into account leads to activation energies independent of the rheological quantity chosen. These values can be taken to analyze differences of the branching architecture.
Keywords: polymer melts; rheology; viscoelasticity

Determining the coating speed limitations for organic photovoltaic inks - Jakubka, Florian; Heyder, Madeleine; Kaschta, Joachim; Machui, Florian; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2013)
To determine the output capability of present organic photovoltaic (OPV) materials, it is important to know the theoretical maximum coating speeds of the used semiconductor formulations. Here, we present a comprehensive investigation of the coating stability window of several prototype organic semiconductor inks relevant for organic solar cells. The coating stability window was first determined experimentally by a sheet to sheet coater at velocities of up to 10 m/min. A numerical simulation model based on the "Coating Window Suite 2010" software was established to give insight into the coating stability limitations at higher coating velocities. An analysis of PEDOT:PSS [poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate)] in a water/isopropyl alcohol mixture as well as P3HT:PCBM [poly(3-hexylthiophene-2,5-diyl):Phenyl-C61-butyric acid methyl ester] in chlorobenzene, o-xylene and tetrahydronaphthalene showed the possibility of coating speeds up to 60 m/min. The simulation further revealed the maximum coating head distances for a given wet film thickness. Finally, we show a solar-cell with slot-die coated PEDOT:PSS and P3HT:PCBM-layer based on the parameters obtained by the simulated data, which exhibits reasonable performance. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: OPV solar cell; Slot-die coating; Coating speed

Development and characterization of glass-ceramics from combinations of slag, fly ash, and glass cullet without adding nucleating agents - Valderrama, Diana M.Ayala; Cuaspud, Jairo A.Gómez; Roether, Judith; Boccaccini, Aldo R. (Materials, 2019)
Developments in the field of materials science are contributing to providing solutions for the recycling of industrial residues to develop new materials. Such approaches generate new products and provide optimal alternatives to the final disposal of different types of industrial wastes. This research focused on identifying and characterizing slag, fly ash, and glass cullet from the Boyacá region in Colombia as raw materials for producing glass-ceramics, with the innovative aspect of the use of these three residues without the addition of nucleating agents to produce the glass-ceramics. To characterize the starting materials, X-ray diffraction (XRD), X-ray fluorescence (XRF), and Scanning Electron Microscopy (SEM) techniques were used. The results were used to evaluate the best conditions to produce mixtures of the three waste components and to determine the specific compositions of glass-ceramics to achieve products with attractive technical properties for potential industrial applications. The proposed mixtures were based on three compositions: Mixture 1, 2, and 3. The materials were obtained through thermal treatment at 1200 °C in a tubular furnace in accordance with the results of a comprehensive characterization using thermal analysis. The microstructure, thermal stability, and structural characteristics of the samples were examined through SEM, differential thermal analysis (DTA), and XRD analyses, which showed that the main crystalline phases were diopside and anorthite, with a small amount of enstatite and gehlenite. The obtained glass-ceramics showed properties of technical significance for structural applications.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Fly ash; Glass cullet; Glass-ceramics; Slag

Development and characterization of magnetic iron oxide nanoparticles with a cisplatin-bearing polymer coating for targeted drug delivery - Unterweger, Harald; Tietze, Rainer; Janko, Christina; Zaloga, Jan; Lyer, Stefan; Dürr, Stephan; Taccardi, Nicola; Goudouri, Ourania Menti; Hoppe, Alexander; Eberbeck, Dietmar; Schubert, Dirk W.; Boccaccini, Aldo R.; et al. (International Journal of Nanomedicine, 2014)
A highly selective and efficient cancer therapy can be achieved using magnetically directed superparamagnetic iron oxide nanoparticles (SPIONs) bearing a sufficient amount of the therapeutic agent. In this project, SPIONs with a dextran and cisplatin-bearing hyaluronic acid coating were successfully synthesized as a novel cisplatin drug delivery system. Transmission electron microscopy images as well as X-ray diffraction analysis showed that the individual magnetite particles were around 4.5 nm in size and monocrystalline. The small crystallite sizes led to the superparamagnetic behavior of the particles, which was exemplified in their magnetization curves, acquired using superconducting quantum interference device measurements. Hyaluronic acid was bound to the initially dextran-coated SPIONs by esterification. The resulting amide bond linkage was verified using Fourier transform infrared spectroscopy. The additional polymer layer increased the vehicle size from 22 nm to 56 nm, with a hyaluronic acid to dextran to magnetite weight ratio of 51:29:20. A maximum payload of 330 μg cisplatin/mL nanoparticle suspension was achieved, thus the particle size was further increased to around 77 nm with a zeta potential of -45 mV. No signs of particle precipitation were observed over a period of at least 8 weeks. Analysis of drug-release kinetics using the dialysis tube method revealed that these were driven by inverse ligand substitution and diffusion through the polymer shell as well as enzymatic degradation of hyaluronic acid. The biological activity of the particles was investigated in a nonadherent Jurkat cell line using flow cytometry. Further, cell viability and proliferation was examined in an adherent PC-3 cell line using xCELLigence analysis. Both tests demonstrated that particles without cisplatin were biocompatible with these cells, whereas particles with the drug induced apoptosis in a dose-dependent manner, with secondary necrosis after prolonged incubation. In conclusion, combination of dextran-coated SPIONs with hyaluronic acid and cisplatin represents a promising approach for magnetic drug targeting in the treatment of cancer.

Development and characterization of novel electrically conductive PANI-PGS composites for cardiac tissue engineering applications - Qazi, Taimoor H.; Rai, Ranjana; Dippold, Dirk; Roether, Judith; Schubert, Dirk W.; Rosellini, Elisabetta; Barbani, Niccoletta; Boccaccini, Aldo R. (Acta Biomaterialia, 2014)
Cardiovascular diseases, especially myocardial infarction, are the leading cause of morbidity and mortality in the world, also resulting in huge economic burdens on national economies. A cardiac patch strategy aims at regenerating an infarcted heart by providing healthy functional cells to the injured region via a carrier substrate, and providing mechanical support, thereby preventing deleterious ventricular remodeling. In the present work, polyaniline (PANI) was doped with camphorsulfonic acid and blended with poly(glycerol-sebacate) at ratios of 10, 20 and 30 vol.% PANI content to produce electrically conductive composite cardiac patches via the solvent casting method. The composites were characterized in terms of their electrical, mechanical and physicochemical properties. The in vitro biodegradability of the composites was also evaluated. Electrical conductivity increased from 0 S cm for pure PGS to 0.018 S cm for 30 vol.% PANI-PGS samples. Moreover, the conductivities were preserved for at least 100 h post fabrication. Tensile tests revealed an improvement in the elastic modulus, tensile strength and elasticity with increasing PANI content. The degradation products caused a local drop in pH, which was higher in all composite samples compared with pure PGS, hinting at a buffering effect due to the presence of PANI. Finally, the cytocompatibility of the composites was confirmed when C2C12 cells attached and proliferated on samples with varying PANI content. Furthermore, leaching of acid dopants from the developed composites did not have any deleterious effect on the viability of C2C12 cells. Taken together, these results confirm the potential of PANI-PGS composites for use as substrates to modulate cellular behavior via electrical stimulation, and as biocompatible scaffolds for cardiac tissue engineering applications. © 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Biocompatibility; Cardiac patch; Conductive composite; Poly(glycerol-sebacate); Polyaniline

Development of alginate dialdehyde-gelatin based bioink with methylcellulose for improving printability - Reakasame, Supachai; Dranseikiene, Dalia; Schrüfer, Stefan; Zheng, Kai; Schubert, Dirk W.; Boccaccini, Aldo R. (Materials Science and Engineering C, 2021)
This study used methylcellulose (MC) to improve the printability of the alginate dialdehyde-gelatin (ADA-GEL) based bioink. The printability as well as the capability to maintain shape fidelity of ADA-GEL could be enhanced by the addition of 9% (w/v) MC. Moreover, the properties of the ink crosslinked with Ca2+ and Ba2+ were investigated. The samples crosslinked with Ba2+ were more stable and stiffer than the Ca2+ crosslinked samples. However, both Ca2+ and Ba2+ crosslinked samples exhibited a similar trend of MC release during incubation under cell culture conditions. The toxicity test indicated that both samples (crosslinked with Ca2+ and Ba2+) exhibited no toxic potential. The fabrication of cell-laden constructs using the developed bioinks was evaluated. The viability of ST2 cells in Ba2+ crosslinked samples increased while for Ca2+ crosslinked samples, a decreased viability was observed over the incubation time. After 21 days, cell spreading in the hydrogels crosslinked with Ba2+ occurred. However, a certain degree of cell damage was observed after incorporating the cells in the high viscosity bioink.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Alginate; Alginate dialdehyde; Biofabrication; Bioinks; Methylcellulose

Development of a model for the mechanical behavior of polypropylene nonwovens for different test directions and strain rates - Leucker, Karsten; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Development of a model for the mechanical behaviour of polypropylene nonwovens for different test directions and strain rates - Leucker, Karsten; Schubert, Dirk W. (Book of Abstracts, 2016)

Development of a model for the mechanical behaviour of polypropylene nonwovens for different test directions and strain rates - Leucker, Karsten; Schubert, Dirk W. (Europe Africa Conference 2017 of the Polymer Processing Society, 2017)

Development of a model for the mechanical behavour of Polypropylene nonwovens for different test directions and strain rates - Leucker, Karsten; Schubert, Dirk W. (Abstracts, 2016)

Development of an embossing process for micro-scale patterns of polypropylene films using statistical design of experiments (DoE) – A strategy to reduce the number of freedom in process settings to find the optimum - Wölfel, Bastian; Schubert, Dirk W.; Lanyi, Franz (Polymer Testing, 2018)
An imprinting process with a brass stamp is used to generate a step on polypropylene plates.Process parameters are systematically varied, temperature, pressing-time, -pressure and the resulting step-heights are determined. Combining the direct correlation of step-height with its variation as a function of process parameters reveals most desirable process parameters. The approach described can be applied to a wide range of processing challenges.
Keywords: Imprinting; Embossing; Polypropylene; Microscale pattern; Optimization strategy

Development of a novel hybrid bioactive hydrogel for future clinical applications. - Francis, Lydia; Greco, Karin V.; Boccaccini, Aldo R.; Roether, Judith; English, Nicholas R.; Huang, Honglei; Ploeg, R.; Ansari, Tahera (Journal of Biomaterials Applications, 2018)
Three-dimensional hydrogels are ideal for tissue engineering applications due to their structural integrity and similarity to native soft tissues; however, they can lack mechanical stability. Our objective was to develop a bioactive and mechanically stable hydrogel for clinical application. Auricular cartilage was decellularised using a combination of hypertonic and hypotonic solutions with and without enzymes to produce acellular tissue. Methacryloyl groups were crosslinked with alginate and PVA main chains via 2-aminoethylmathacrylate and the entire macromonomer further crosslinked with the acellular tissue. The resultant hydrogels were characterised for its physicochemical properties (using NMR), in vitro degradation (via GPC analysis), mechanical stability (compression tests) and in vitro biocompatibility (co-culture with bone marrow-derived mesenchymal stem cells). Following decellularisation, the cartilage tissue showed to be acellular at a significant level (DNA content 25.33 ng/mg vs. 351.46 ng/mg control tissue), with good structural and molecular integrity of the retained extra cellular matrix (s-GAG= 0.19 μg/mg vs. 0.65 μg/mg ±0.001 control tissue). Proteomic analysis showed that collagen subtypes and proteoglycans were retained, and SEM and TEM showed preserved matrix ultra-structure. The hybrid hydrogel was successfully cross-linked with biological and polymer components, and it was stable for 30 days in simulated body fluid (poly dispersal index for alginate with tissue was stable at 1.08 and for PVA with tissue was stable at 1.16). It was also mechanically stable (Young's modulus of 0.46 ± 0.31 KPa) and biocompatible, as it was able to support the development of a multi-cellular feature with active cellular proliferation in vitro. We have shown that it is possible to successfully combine biological tissue with both a synthetic and natural polymer and create a hybrid bioactive hydrogel for clinical application.

Development of bioactive glass based scaffolds for controlled antibiotic release in bone tissue engineering via biodegradable polymer layered coating - Nooeaid, Patcharakamon; Li, Wei; Roether, Judith; Mourino, Viviana; Goudouri, Ourania Menti; Schubert, Dirk W.; Boccaccini, Aldo R. (Biointerphases, 2014)
Highly porous 45S5 Bioglass(®)-based scaffolds coated with two polymer layers were fabricated to serve as a multifunctional device with controlled drug release capability for bone regeneration applications. An interior poly(d,l-lactide)/poly(ethylene glycol)-(polypropylene glycol)-poly(ethylene glycol) triblock copolymer (Pluronic P123) coating improved the mechanical stability of Bioglass-based scaffolds, while an exterior natural polymer (alginate or gelatin) coating served as an antibiotic drug carrier. The results showed improved mechanical properties of Bioglass-based scaffolds by the bilayer polymer coating. In addition, hydrochloride tetracycline loaded in either alginate or gelatin coatings was released rapidly at the initial stage (∼1 h), while the released rate subsequently decreased and was sustained for 14 days in phosphate buffered saline. Therefore, these layered polymer coated scaffolds exhibit attractive characteristics in terms of improved mechanical properties and controlled drug release, simultaneously with the added advantage that the drug release rate is decoupled from the intrinsic scaffold Bioglass degradation mechanism. The layered polymer coated scaffolds are of interest for drug-delivery enhanced bone regeneration applications.

Development of poly(L-lactide) (PLLA) microspheres precipitated from triacetin for application in powder bed fusion of polymers - Dechet, Maximilian; Demina, Anna; Römling, Lea; Gomez Bonilla, Juan Sebastian; Lanyi, Franz; Schubert, Dirk W.; Bück, Andreas; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2020)
In this work, the development and processing behavior of poly(L-lactide) (PLLA) particles for powder bed fusion (PBF) of polymers obtained via a green and sustainable process route are thoroughly studied. Liquid-liquid phase separation and precipitation from triacetin, a non-toxic solvent, are applied for the production of highly spherical PLLA particles of excellent flowability. Starting from the measured cloud-point diagram of the PLLA-triacetin system, appropriate temperature profiles for the precipitation process are derived. The effect of process parameters on the product properties is addressed in detail; the PLLA particles are characterized regarding their size distribution and morphology. Furthermore, material properties including thermal behavior (c.f. processing window for powder bed fusion (PBF)) and powder flowability are assessed. The spherical PLLA particles of narrow size distribution display a wide sintering window of 59 K and an excellent flowability due to the intrinsic surface roughness of the particles. Thus, tensile test bars and complex porous gyroid specimens were successfully manufactured via PBF without the need for any additional surface functionalization of the particles with flow agents. The high potential of the newly developed PLLA powders produced via an environmentally friendly approach omitting the use of halogenated or toxic solvents, as well as flowing aids, is demonstrated by mechanical testing of the printed specimen

Dewetted Au Nanoparticles on TiO2 Surfaces: Evidence of a Size-Independent Plasmonic Photoelectrochemical Response - Licklederer, Markus; Mohammadi, Reza; Nguyen, Nhat Truong; Park, Hyoungwon; Hejazi, Seyedsina; Halik, Marcus; Vogel, Nicolas; Altomare, Marco; Schmuki, Patrik (Journal of Physical Chemistry C, 2019)
We induce solid-state dewetting of thin Au films (nominal thickness of 0.5-10 nm) on flat TiO2 surfaces to produce Au nanoparticles with an average size tunable in the 3-200 nm range. Such Au-decorated TiO2 surfaces enable plasmonic photoelectrochemical water splitting under visible light illumination (450-750 nm), with a photon-to-current conversion efficiency that reaches a maximum for TiO2 surfaces decorated with similar to 30 nm sized Au particles. Optical measurements show, as expected, a red shift of the plasmon resonance with the increasing Au nanoparticle size. More interestingly, the photocurrent is found to peak for every photoanode at similar to 600 nm regardless of the Au nanoparticle size, i.e., the wavelength of maximum photocurrent is size-independent. Such a remarkable observation can be ascribed to a hot electron injection cutoff effect, i.e., can be explained in terms of the interband versus intraband transition scenario.
CRIS-Team WoS Importer:2019-07-30

Diastereoselective Epoxidation and Bishydroxylation of Cyclic tert-Butyl Allyl Peroxides - Schulz, M.; Kluge, R.; Liebsch, S.; Halik, Marcus; Gadissa, F. (Tetrahedron, 1996)

Differentiating gel compositions of silicone breast implants from Poly Implant Prothèse and other Manufactures - Schubert, Dirk W.; Horch, Raymund E.; Kaschta, Joachim (Book of Abstracts, 2013)

Direct 3D‐Bioprinting of hiPSC‐derived Cardiomyocytes to Generate Functional Cardiac Tissues - Esser, Tilman; Anspach, Annalise; Muenzebrock, Katrin; Kah, Delf-Thorge Eric; Schrüfer, Stefan; Schenk, Joachim; Heinze, Katrin G.; Schubert, Dirk W.; Fabry, Ben; Engel, Felix (Advanced Materials, 2023)
3D-bioprinting is a promising technology to produce human tissues as drug screening tool or for organ repair. However, direct printing of living cells has proven difficult. Here, we present a method to directly 3D-bioprint human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes embedded in a collagen-hyaluronic acid ink generating centimeter-sized functional ring- and ventricle-shaped cardiac tissues in an accurate and reproducible manner. The printed tissues contained hiPSC-derived cardiomyocytes with well-organized sarcomeres and exhibited spontaneous and regular contractions, which persisted for several months and were able to contract against passive resistance. Importantly, beating frequencies of the printed cardiac tissues could be modulated by pharmacological stimulation. This approach opens up new possibilities for generating complex functional cardiac tissues as models for advanced drug screening or as tissue grafts for organ repair or replacement.<br

Direct-Patterning ZnO Deposition by Atomic-Layer Additive Manufacturing Using a Safe and Economical Precursor - Stefanovic, Sonja; Gheshlaghi, Negar; Zanders, David; Kundrata, Ivan; Zhao, Baolin; Barr, Maissa; Halik, Marcus; Devi, Anjana; Bachmann, Julien (Small, 2023)
Area-selective atomic layer deposition (AS-ALD) is a bottom-up nanofabrication method delivering single atoms from a molecular precursor. AS-ALD enables self-aligned fabrication and outperforms lithography in terms of cost, resistance, and equipment prerequisites, but it requires pre-patterned substrates and is limited by insufficient selectivity and finite choice of substrates. These challenges are circumvented by direct patterning with atomic-layer additive manufacturing (ALAM) — a transfer of 3D-printing principles to atomic-layer manufacturing where a precursor supply nozzle enables direct patterning instead of blanket coating. The reduced precursor vapor consumption in ALAM as compared with ALD calls for the use of less volatile precursors by replacing diethylzinc used traditionally in ALD with bis(dimethylaminopropyl)zinc, Zn(DMP)2. The behavior of this novel ZnO ALAM process follows that of the corresponding ALD in terms of deposit quality and growth characteristics. The temperature window for self-limiting growth of stoichiometric, crystalline material is 200–250 °C. The growth rates are 0.9 Å per cycle in ALD (determined by spectroscopic ellipsometry) and 1.1 Å per pass in ALAM (imaging ellipsometry). The preferential crystal orientation increases with temperature, while energy-dispersive X-ray spectroscopic and XPS show that only intermediate temperatures deliver stoichiometric ZnO. A functional thin-film transistor is created from an ALAM-deposited ZnO line and characterized.
CRIS-Team Scopus Importer:2023-05-19
Keywords: additive manufacturing; atomic layer deposition; nanofabrication; sensors; zinc oxide

Discrepancies between linear viscoelastic measurements and double-reptation predictions for commercial polystyrene samples - Guzmán, Job D.; Mangnus, Marc; Aerts, Peter; Mes, Edwin; Kaschta, Joachim; Pierini, Pete (Rheologica Acta, 2008)
We have found discrepancies between the predictions of two double-reptation models and the corresponding linear viscoelasticity measurements for commercial, polydisperse polystyrene samples with weight-average molecular weights ranging from 140 to 300kg/mol. The accuracy of the experimental data has been confirmed by conducting viscoelasticity measurements in different laboratories using different types of rheometers and by verifying that small distortions in chromatographic measurements cannot account for the discrepancies seen in the viscoelastic response. In addition, we show that the discrepancies between predictions and measurements are systematic, suggesting that gaps in the theory are responsible for the mismatch. Is it concluded that commercial polystyrene resins may pose additional challenges for rheological modeling because of their relatively high polydispersity and low degree of entanglement. The experimental data given here can be used to validate future modeling effort
Keywords: molecular weight distribution; linear viscoelasticity; double reptation

Dispersibility of nanoparticels with different surface functionalization at various processing parameters in the internal mixer - Peltner, David; Werner, Siegfried; Schubert, Dirk W. (Nordic Polymer days 2023, 2023)
The present study investigates the dispers- ibility of silica nanoparticles with different types of hydrophobic surface functionaliza- tion in polypropylene. Therefore, the particles and the PP were compounded in an internal mixer at various processing parameters. The obtained compounds were hot pressed into square shaped plugs and biaxially stretched into films. The latter was done to increase the size of the agglomerates, so they could be de- tected by light microscopy. The agglomerates were analysed using a contrast-based parti- cle detection and a 12-spot pattern over the stretched film. Parameters such as number, size, and area fraction of agglomerates were used to characterize the dispersion and corre- lated with rotation speed and mixing time. A reduction of number, size and agglomerate area fraction with higher rotation speed and mixing time was found. The latter could be described with an exponential decay function with three adjustable parameters. These pa- rameters correlated with the hydrophobicity of the surface functionalization indicating a faster reduction to lower levels with increas- ing hydrophobicity. The area fraction of agglomerates was identified as the most meaningful dispersion parameter as it com- bines information about size and number of the particles. This study shows a new method of analysing the dispersion of silica nano- particles in PP and that their dispersibility in dependence of the surface functionalization can be characterized by the mixing kinetics of an internal mixe

Double percolation effect on conductivity of PMMA/PS/CB and PEMA/PS/CB ternary composite films - Xu, Huagen; Qu, Muchao; Schubert, Dirk W. (2019)

Draw Resonance Behavior of Polypropylene – A Critical Reflection of the Rheotens Test - Kunzelmann, Peter; Danzer, Stefan; Schubert, Dirk W. (29th International Conference of the Polymer Processing Society, 2013)

Driving forces for the self-assembly of graphene oxide on organic monolayers - Kirschner, Johannes; Wang, Zhenxing; Eigler, Siegfried; Steinrück, Hans-Peter; Jäger, Christof; Clark, Timothy; Hirsch, Andreas; Halik, Marcus (Nanoscale, 2014)

Durch Biofilm bakteriell besiedelte Implantate bedingen Wundheilungsstörungen - Beier, Justus; Bogdan, Christian; Schmitz, Markus; Schubert, Dirk W.; Schultz, Gregory; Horch, Raymund E. (Chirurgische Allgemeine - Zeitung für Klinik und Praxis, 2013)

Effect of Filler Content, Particle Size and Size Distribution on the Permeability of Soft Magnetic Liquid Silicone Rubber - Schubert, Dirk W.; Werner, Siegfried; Heitbrink, Alexander (International Workshop on Silicone based Poylmers, 2017)

Effect of filler orientation on the electrical conductivity of carbon Fiber/PMMA composites - Qu, Muchao; Nilsson, Fritjof; Schubert, Dirk W. (Composites Science and Technology, 2018)
Keywords: Conductivity; Carbon fibers; Orientation; Extrusion

Effect of Ligand Treatment on the Tuning of Infrared Plasmonic Indium Tin Oxide Nanocrystal Electrochromic Devices - Mashkov, Oleksandr; Körfer, Julien; Eigen, Andreas; Yousefi Amin, Amir-Abbas; Killilea, Niall Andrew; Barabash, Anastasiia; Sytnyk, Mykhailo; Khansur, Neamul Hayet; Halik, Marcus; Webber, Kyle Grant; Heiß, Wolfgang (Advanced Engineering Materials, 2020)
Electrochromic devices operating in the near infrared are being developed as a part of smart windows that can dynamically modulate visible light and heat transmittance of solar irradiation, dependent on weather conditions and personal preferences. Here, doped metal oxide nanocrystals are used to obtain the desired effect in the infrared spectral region. Specifically, the infrared transmittance is electrochemically modulated by control of the carrier concentration in the nanocrystals. While indium tin oxide nanocrystals are already known to provide this effect, the consequence of ligand treatment during preparation of the nanocrystal electrode on the electrochromic properties is studied. The type of ligand treatment is shown to affect the surface morphology, as well as the localized plasmon resonance energy of the nanocrystal films. A short and convenient treatment by ethanedithiol cross-linking ligands is shown to provide superior results as compared with the formic acid treatment used in the previous work. Future work combining windows based on optimized electrochromic effects in the near infrared combined with those in the visible spectral range will simultaneously improve building energy efficiency and indoor human comfort.
CRIS-Team Scopus Importer:2020-05-02
Keywords: electrochromic windows; ligand exchange; localized surface plasmon resonances; metal oxide nanocrystals

Effect of paint removal with kilowatt level nanosecond pulsed laser on microstructure and mechanical properties of stainless steel - Yoo, Hyun Jong; Park, Hyoungwon; Kim, Jeoung Han; Park, Changkyoo (Optics and Laser Technology, 2023)
In this study, a kilowatt level nanosecond pulsed laser is used to remove the paint layer on the 304L stainless steel (SS304L) surface. Different number of repetitions of laser paint removal (LPR) processes were applied, and their corresponding influences to SS304L were analyzed with various analytic methods. An electron probe X-ray microanalyzer (EPMA) confirmed complete removal of the paint layer for the number of LPR process repetitions of nine (LPR 9) and twelve (LPR 12) times. Also, an LPR-induced microstructural modification was investigated using electron backscatter diffraction (EBSD), revealing the smaller grain size and larger strain rate for the larger number of LPR process. Moreover, the surface properties including the surface profile and residual stress, and mechanical properties were characterized before and after the LPR processes. For the LPR 9 and LPR 12, a decrease in the elongation and an increase in the surface microhardness were observed, originated from the grain refinement and high strain rate.
CRIS-Team Scopus Importer:2023-04-14
Keywords: 304L stainless steel; Laser cleaning; Mechanical properties; Microstructure; Paint removal

Effect of particle rounding on the processability of polypropylene powder and the mechanical properties of selective laser sintering produced parts - Gomez Bonilla, Juan Sebastian; Kletcher, Robin; Lanyi, Franz; Schubert, Dirk W.; Bück, Andreas; Schmidt, Jochen; Peukert, Wolfgang (30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019, 2019)
Common techniques for the production of polymer powders for selective laser sintering (SLS) involve the comminution of polymers. Comminution of polymers often results in powders made of irregular shaped particles with a low bulk density and a bad flow behavior. With the aim to improve the flowability of grinded powders and, thus, the SLS processability, a thermal process for particle shape modification was developed. This has been applied successfully for a broad variety of thermoplasts. In this contribution, a modified design of a rounding reactor with direct heating and optimized geometry is presented. The performance of the new design is assessed by the rounding of commercially available polypropylene powders. The influence of the rounding process on the packing density, flowability and particle size and shape distributions of the powders is investigated. Test specimens produced by SLS were tested to assess the effect of the rounding process on the mechanical properties of the produced parts. © Solid Freeform Fabrication 2019: Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019. All rights reserve
Keywords: Additives; Comminution; Compressive strength; Laser heating; Particle size; Polypropylenes; Powders; Sintering; Modified designs; Optimized geometries; Packing density; Particle size and shape; Polymer powders; Selective laser sintering (SLS); Shaped particles; Thermal process

Effect of particle size and size distribution on the permeability of softmagnetic liquid silicone rubber - Schubert, Dirk W.; Werner, Siegfried (54th Nordic Polymer Days, 2017)

Effect of particle size and size distribution on the permeability of soft magnetic liquid silicone rubber composites - Schubert, Dirk W.; Werner, Siegfried; Hahn, Ingo; Solovieva, Veronika (Composites Science and Technology, 2019)
Magnetic composites made of LSR (Liquid Silicone Rubber) and a magnetic filler have been investigated with respect to magnetic field guidance for transcutaneous energy transport. Effects of particle size and size distribution on the effective initial magnetic permeability are analyzed. A simple model is presented to describe the permeability as a function of the degree of filling, particle size and size distribution. From this, a calculus for the relevant size average of the filler was developed at 20 vol% of magnetic filler. The calculus showed self-consistency and can be used to tailor optimized powders for better field guidance.
Keywords: polymer matrix composite; magnetic properties; modelling; powder processing

Effect of polymer molecular weight and solution parameters on selective dispersion of single-walled carbon nanotubes - Jakubka, Florian; Schießl, Stefan; Martin, Sebastian; Englert, Jan; Hauke, Frank; Hirsch, Andreas; Zaumseil, Jana (ACS Macro Letters, 2012)
The selective dispersion of single-walled carbon nanotube species (n,m) with conjugated polymers such as poly(9,9-dioctylfluorene) (PFO) and poly(9,9-dioctylfluorene-cobenzothiadiazole) (F8BT) in organic solvents depends not only on the type of solvent but also on the molecular weight of the polymer. We find an increasing amount of nanotubes and altered selectivities for dispersions with higher molecular weight polymers. Including the effects of different aromatic solvents, we propose that solution viscosity is one of the factors influencing the apparent selectivity by changing the reaggregation rate of the single-walled carbon nanotubes (SWNT). The type of solvent, polymer molecular weight, concentration, and viscosity should thus be taken into account when screening for new polymers for selective SWNT dispersion. © 2012 American Chemical Society.

Effect of Structure and Disorder on the Charge Transport in Defined Self-Assembled Monolayers of Organic Semiconductors - Schmaltz, Thomas; Gothe, Bastian; Krause, Andreas; Leitherer, Susanne; Steinrück, Hans-Georg; Thoss, Michael; Clark, Timothy; Halik, Marcus (Acs Nano, 2017)
Self-assembled monolayer field-effect transistors (SAMFETs) are not only a promising type of organic electronic device but also allow detailed analyses of structure-property correlations. The influence of the morphology on the charge transport is particularly pronounced, due to the confined monolayer of 2D- extgreekp-stacked organic semiconductor molecules. The morphology, in turn, is governed by relatively weak van-der-Waals interactions and is thus prone to dynamic structural fluctuations. Accordingly, combining electronic and physical characterization and time-averaged X-ray analyses with the dynamic information available at atomic resolution from simulations allows us to characterize self-assembled monolayer (SAM) based devices in great detail. For this purpose, we have constructed transistors based on SAMs of two molecules that consist of the organic p-type semiconductor benzothieno[3,2-b][1]benzothiophene (BTBT), linked to a C11 or C12 alkylphosphonic acid. Both molecules form ordered SAMs; however, our experiments show that the size of the crystalline domains and the charge-transport properties vary considerably in the two systems. These findings were confirmed by molecular dynamics (MD) simulations and semiempirical molecular-orbital electronic-structure calculations, performed on snapshots from the MD simulations at different times, revealing, in atomistic detail, how the charge transport in organic semiconductors is influenced and limited by dynamic disorder.

Effects of Bioglass and ß-TCP containing three-dimensional laser sintered polyetheretherketone composites on osteoblasts in vitro - von Wilmowsky, Cornelius; Vairaktaris, Eleftherios; Pohle, Dirk; Rechtenwald, Thomas; Lutz, Rainer; Münstedt, Helmut; Koller, Garrit; Schmidt, Michael; Neukam, Friedrich Wilhelm; Schlegel, Andreas; Nkenke, Emeka (Journal of Biomedical Materials Research Part A, 2007)
LFT Import::2019-07-16 (1422)

Eine Geschichte des Versagens - der PIP Skandal - Schubert, Dirk W.; Kaschta, Joachim; Horch, Raymund E.; Walter, Bastian; Daenicke, Jonas; Wichert, Franziska (Würzburger Tage 2014, 2014)

Eine Geschichte des Versagens - der PIP Skandal - Schubert, Dirk W.; Kaschta, Joachim; Horch, Raymund E.; Walter, Bastian; Daenicke, Jonas; Wichert, Franziska (Würzbuger Tage 2014, 2014)

Elasticity of polystyrene melts filled with silica nanoparticles: Influence of matrix polydispersity - Triebel, Christian; Kunzelmann, Peter; Schubert, Dirk W.; Münstedt, Helmut (Final Program and Book of Abstracts, 2011)

Electrical and mechanical characterization of medical grade silicones as dielectric layers in aerosol jet printed dielectric elastomers - Martin, Sina; Himmler, Marcus; Bruns, Arne; Reitelshöfer, Sebastian; Pham, Duc Huy Hoang; Schubert, Dirk W.; Franke, Jörg (Proceedings Volume 11587, Electroactive Polymer Actuators and Devices (EAPAD) XXIII, 2021)
The name artificial muscles has given dielectric elastomer actuators much attention in the field of medical technology. In healthcare applications, these compliant materials are particularly suitable for soft and lightweight actuators and in addition, they show many advantageous properties such as great extensibility for on-body sensors. However, the lack of industrial scaled production capabilities is still a limiting factor in the transfer of these promising materials into a broad application. To address this issue, we have modified an aerosol jet printer for automated stacking of electrodes and dielectric layers in one process device, which is described in earlier publications. As the performance is mainly dependent on the electrical and mechanical characteristics of the dielectric, a broad material variety is required to face different tasks in healthcare technology. Therefore, different medical grade silicones are investigated in this paper regarding the suitability for aerosol jet printing. In a first step, the printing parameters are derived from rheological testing of the uncured components that are used pure and in mixture with silicone oils to vary the specific Young’s module. Through heat application and dilution, the range for printable materials increases to silicones with initial viscosities up to 8200 mPas. Subsequently aerosol jet printing is used to manufacture stacked silicone dielectrics that are then investigated regarding their mechanical and electrical characteristics for dielectric elastomers. Finally, the collected parameters are compared and an overview of the feasible property combinations is given which can be used as a material guideline for different applications.<br
Keywords: dielectric elastomers; medical grade silicones; mechanical characterization; electrical testing; additive manufacturing; rheological measurement; aerosol jet printing

Electrical conductivities of melt spun PMMA/aligned carbon fibers/carbon black fiber composites - Qu, Muchao; Schubert, Dirk W. (Europe Africa Conference 2017 of the Polymer Processing Society, 2017)

Electrical conductivity and fiber orientation of poly(methyl methacrylate)/carbon fiber composite sheets with various thickness - Luo, Xiaoling; Qu, Muchao; Schubert, Dirk W. (Polymer Composites, 2020)
Poly(methyl methacrylate) (PMMA) composites containing carbon fibers (CFs) with the controlled aspect ratio (AR) at various concentrations were produced and hot pressed into rectangular sheets with a variety of thickness. The orientation of CFs on the surface and inside the specimen was obtained, and the conductivity σ in three different directions (X-length, Y-width, Z-thickness) were investigated. A preferential orientation of CFs in XY plane was found inside the samples, resulting in higher σX and σY. The orientation of CFs in Z direction increases with the sample thickness increasing, leading to an increasing σZ. Thus the anisotropic conductivity between σX (or σY) and σZ reduces from three orders of magnitude to one order of magnitude. The percolation thresholds (Φc) in three directions of the samples were revealed by fitting with McLachlan GEM equation, which lead to Φc,X ≈ Φc,Y ≈ Φc,Z, independent of the thickness and the measuring direction. The values of exponent t in GEM equation were found to be tX > tY > tZ, while tZ increases with the sample thickness. For the first time, the relationship between the exponent t and the sample thickness was revealed and discussed.
CRIS-Team Scopus Importer:2020-10-30
Keywords: anisotropic; carbon fibers; electrical conductivity; orientation; thickness

Electrical conductivity and mechanical properties of melt-spun ternary composites comprising PMMA, carbon fibers and carbon black - Qu, Muchao; Nilsson, Fritjof; Qin, Yijing; Yang, Guanda; Pan, Yamin; Liu, Xian Hu; Hernández Rodríguez, Gabriel; Chen, Jianfan; Zhang, Chunhua; Schubert, Dirk W. (Composites Science and Technology, 2017)
Keywords: Carbon black; Melt-spinning; Carbon fibers; Electrical properties

Electrical conductivity behaviour of sheared poly(methyl methacrylate)/carbon black composites - Liu, Xian Hu; Krückel, Johannes; Zheng, Guoqiang; Schubert, Dirk W. (Composites Science and Technology, 2014)
The electrical conductivity behaviour of unsheared (static) and sheared poly(methyl methacrylate)/carbon black (CB) composite disc-shaped samples with various CB concentrations as a function of the radial position were investigated and analysed. It was found that the angular averaged electrical conductivity of the static samples is independent of the radius and CB concentration. In comparison to that, the angular averaged electrical conductivity of the samples with a shear history is decreasing as a function of the radius due to the linear increase of the deformation from the centre to the rim of the samples. It is shown, that this effect is less pronounced increasing the composite concentration. A simple model is proposed to explain this behaviour. The results obtained in this study are in a very good agreement with the investigations performed via coupled electrical and rheological measurements and provide a deeper insight into structural changes in conductive polymer composites induced by shear deformations. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Nanocomposites; Electrical properties; Deformation; Rheology

Electrical conductivity of anisotropic pmma composite filaments with aligned carbon fibers-predicting the influence of measurement direction - Qu, Muchao; Nilsson, Fritjof; Qin, Yijing; Yang, Guanda; Gao, Qun; Xu, Wei; Liu, Xianhu; Schubert, Dirk W. (RSC Advances, 2020)
In order to study the electrical conductivity of anisotropic PMMA/carbon fiber (CF) composites, cylindrical PMMA/CF filaments were extruded through a capillary rheometer, resulting in an induced CF orientation along the extrusion direction. The aspect ratios of the CFS in the filaments were accurately regulated using a two-step melt mixing process. By measuring the vertical and horizontal resistances of filaments where the outermost layer was successively peeled off, the anisotropic conductivities could be calculated. This was done using a novel analytical model where each cylindrical composite filament was defined as a structure consisting of three concentric cylinders with potentially different conductivities and CF orientations. The electrical conductivity increased with the degree of fiber orientation along the voltage direction and the effects of anisotropy and measurement direction were incorporated into the (isotropic) McLachlan equation. The required distance for electrical contact between the CFS was calculated to be 16 nm. Finite element (FEM) simulations were successfully utilized to confirm the data.
CRIS-Team Scopus Importer:2020-02-07

Electrical conductivity of melt spun PMMA/aligned carbon fibers/carbon black fiber composites - Qu, Muchao; Nilsson, Fritjof; Schubert, Dirk W. (The 29th International Conference on Diamond and Carbon like Materials, 2018)

Electrical conductivity of polystyrene/poly(n-alkyl methacrylate)s / carbon nanotube ternary composite casting films - Xu, Huagen; Schubert, Dirk W. (Journal of Polymer Research, 2020)
In this work, poly(n-alkyl methacrylate)s (P-alkyl-MA)/Polystyrene (PS)/Carbon nanotube (CNT) composite films with different CNT concentration and polymer blend ratio were prepared utilizing solution casting method. Light microscope and scanning electron microscope were used to investigate the CNT location in polymer blends and morphology of ternary composite films. The electrical conductivity of the films were investigated, all the percolation thresholds (ϕc) of PS/P-alkyl-MA/CNT composite films were determined and the experimental data are fitted utilizing McLachlan’s equation. The fitting data indicate both PS/PMMA/CNT and PS/PEMA/CNT composite films show an obviously double percolation effect with polymer blend ratio at 50/50. Compared with pure PMMA and PEMA, the ϕc of composite films when polymer blend ratio at PS /PMMA =50/50 and PS/PEMA =50/50 were decreased by 69.0% and 73.1%, respectively. A contour plot based on all PS/PMMA/CNT and PS/PEMA/CNT experimental data were presented to show the electrical conductivity as a function of CNT concentration and polymer blend ratio. With PS content increasing in P-alkyl-MA/PS blends, the conductivity of both PS/PMMA/ CNT and PS/PEMA/ CNT composite films shows a similar tendency. The morphology with different polymer blend ratio at a certain CNT concentration and different CNT concentration at a certain polymer blend ratio was presented to explain the conductivity and ϕc of ternary composite films changing tendenc
CRIS-Team Scopus Importer:2020-05-29
Keywords: Carbon nanotube; Composite films; Double percolation structure; Electrical conductivity; Polymer blend

Electrically conductive NBR/CB flexible composite film for ultrastretchable strain sensors: fabrication and modeling - Qu, Muchao; Qin, Yijing; Xu, Wei; Zheng, Zhenxing; Xu, Huagen; Schubert, Dirk W.; Gao, Qun (Applied Nanosciene, 2021)
In this study, a flexible strain sensor with ultrahigh stretchability, outstanding sensitivity, and excellent repeatability based on conductive carbon black (CB) and nitrile butadiene rubber (NBR) was presented. Two organic solvents with three different coating time during the dissolve-coating process were investigated. The morphology and the degradation temperature of all the NBR/CB composite films were studied, and the tensile strength, elongation at break, as well as the young’s modulus and the dissipated energy for all the specimen were revealed. The strain-sensing tests indicated that the NBR/CB film possess a good sensitivity (max. gauge factor = 24.9) and an ultrahigh sensing range (max. 681% strain). The mathematic model from Simmons for predicting the sensing behavior based on the tunneling theory was further simplified, and a novel equation was proposed for predicting the relative change of resistance as a function of time during the cyclic test, which showed great agreement with the cyclic strain-sensing data in experiments. Overall, this study introduces a simple low-cost fabrication method for preparing the polymeric flexible strain sensors with great strain-sensing performance. The development of the two mathematical modellings makes several noteworthy contributions to the existing knowledge of strain-sensing behavior.
CRIS-Team Scopus Importer:2021-01-08
Keywords: Carbon black; Modeling; Nitrile butadiene rubber; Strain sensor; Ultrastrechable

Electrically conductive polymer composite containing hybrid graphene nanoplatelets and carbon nanotubes: synergistic effect and tunable conductivity anisotropy - Luo, Xiaoling; Yang, Guanda; Schubert, Dirk W. (Advanced Composites and Hybrid Materials, 2021)
Pristine carbon nanotubes (CNTs) and functionalized carbon nanotubes (f-CNTs) were introduced into conductive poly(methyl methacrylate)/graphene nanoplatelet (PMMA/GNP) composites to achieve a synergistic effect in the enhancement of the conductivity and the reduction in the percolation threshold by forming a 3-Dimensional(3-D) hybrid structure. Both the in-plane and perpendicular electrical properties were investigated. The synergies of hybrid fillers in the in-plane direction were more dependent on the total filler loading, while those in the perpendicular direction were significantly influenced by the GNP/CNT or GNP/f-CNT ratios. Typically, a schematic diagram of the evolution of the 3-D conductive pathways of PMMA/GNP/f-CNT composite at different GNP/f-CNT ratios was presented to explain this phenomenon. Moreover, tunable conductivity anisotropy (defined as the ratio of in-plane conductivity to perpendicular conductivity) ranging from 0.01 to 1000 was achieved, simply by constructing different conductive structures at various filler loadings or ratios in composites.
CRIS-Team WoS Importer:2021-10-08

Electron-Transport Properties and Use in Organic Light-Emitting Diodes of a Bis(dioxaborine)fluorene Derivative - Domercq, B.; Grasso, C.; Maldonado, J.-L.; Halik, Marcus; Barlow, S.; Marder, S. R.; Kippelen, B. (Journal of Physical Chemistry B, 2004)

Electrophoretic co-deposition of chitosan and graphene oxide results in antibacterial coatings for medical applications - Metze, Anke-Lisa; Pishbin, Fatemehsadat; Ryan, Mary P.; Seuß, Sigrid; Diba, Mani; Shaffer, Milo S P; Boccaccini, Aldo R. (Key Engineering Materials, 2015)
Chitosan - graphene oxide (GO) composite coatings intended for antibacterial applications were obtained by cathodic electrophoretic deposition (EPD) on stainless steel. The coatings were characterized using SEM, FTIR, contact angle and roughness measurements and by antibacterial studies against E.coli. The coating was observed to consist of a polymer matrix with embedded, agglomerated graphene oxide sheets. A decrease in bacteria cell viability of at least 50 % was measured on the chitosan - GO surface in comparison to uncoated stainless steel.
Keywords: Antibacterial; Chitosan; Electrophoretic deposition; Graphene oxide

Electrophoretic deposition of antibiotic loaded PHBV microsphere-alginate composite coating with controlled delivery potential - Chen, Qiang; Li, Wei; Goudouri, Ourania Menti; Ding, Yaping; Cabanas Polo, Sandra; Boccaccini, Aldo R. (Colloids and Surfaces B: Biointerfaces, 2015)
Electrophoretic deposition (EPD) technique has been developed for the fabrication of antibiotic-loaded PHBV microsphere (MS)-alginate antibacterial coatings. The composite coatings deposited from suspensions with different MS concentrations were produced in order to demonstrate the versatility of the proposed method for achieving functional coatings with tailored drug loading and release profiles. Linearly increased deposit mass with increasing MS concentrations was obtained, and MS were found to be homogeneously stabilized in the alginate matrix. Chemical composition, surface roughness and wettability of the deposited coatings were measured by Fourier transform infrared (FTIR) spectroscopy, laser profilometer and water contact angle instruments, respectively. The co-deposition mechanism was described by two separate processes according to the results of relevant measurements: (i) the deposition of alginate-adsorbed MS and (ii) the non-adsorbed alginate. Qualitative antibacterial tests indicated that MS containing coatings exhibit excellent inhibition effects against E. coli (gram-negative bacteria) after 1. h of incubation. The proposed coating system combined with the simplicity of the EPD technique can be considered a promising surface modification approach for the controlled in situ delivery of drug or other biomolecules.
Keywords: Alginate; Antibacterial coatings; Drug delivery; Electrophoretic deposition; Microspheres

Electrophoretic deposition of chitosan/gelatin/bioactive glass composite coatings on 316L stainless steel: A design of experiment study - Ur Rehman, Muhammad Atiq; Munawar, Muhammad; Schubert, Dirk W.; Boccaccini, Aldo R. (Surface & Coatings Technology, 2019)
Keywords: Bioactive glass; Chitosan; Gelatin; Design of experiment; Electrophoretic deposition

Electrophoretic deposition of chitosan/h-BN and chitosan/h-BN/TiO2 composite coatings on stainless steel (316L) substrates - Raddaha, Namir S.; Cordero Arias, Luis Eduardo; Cabanas Polo, Sandra; Virtanen, Sannakaisa; Roether, Judith; Boccaccini, Aldo R. (Materials, 2014)

Electrophoretic deposition of nanostructured-TiO2/chitosan composite coatings on stainless steel - Cordero Arias, Luis Eduardo; Cabanas Polo, Sandra; Gao, Haoxiang; Gilabert, J.; Sanchez, E.; Roether, Judith; Schubert, Dirk W.; Virtanen, Sannakaisa; Boccaccini, Aldo R. (RSC Advances, 2013)
Novel chitosan composite coatings containing titania nanoparticles (n-TiO2) for biomedical applications were developed by electrophoretic deposition (EPD) from ethanol–water suspensions. The optimal ethanol–water ratio was studied in order to avoid bubble formation during the EPD process and to ensure homogeneous coatings. Different n-TiO2 contents (0.5–10 g L−1) were studied for a fixed chitosan concentration (0.5 g L−1) and the properties of the electrophoretic coatings obtained were characterized. Coating composition was analyzed by thermogravimetric analysis (TG), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analysis. Scanning electron microscopy (SEM) was employed to study both the surface and the cross section morphology of the coatings, and the thicknesses (2–6 μm) of the obtained coatings were correlated with the initial ceramic content. Contact angle measurements, as a preliminary study to predict hypothetic protein attachment on the coatings, were performed for different samples and the influence of a second chitosan layer on top of the coatings was also tested. Finally, the electrochemical behavior of the coatings, evaluated by polarization curves in DMEM at 37 °C, was studied in order to assess the corrosion resistance provided by the n-TiO2/chitosan coating
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.electr

Electrophoretic deposition of tetracycline hydrochloride loaded halloysite nanotubes chitosan/bioactive glass composite coatings for orthopedic implants - Radda'A, Namir S.; Goldmann, Wolfgang H.; Detsch, Rainer; Roether, Judith; Cordero-Arias, Luis; Virtanen, Sannakaisa; Moskalewicz, Tomasz; Boccaccini, Aldo R. (Surface & Coatings Technology, 2017)
Keywords: Antibacterial; Bioactive glass; Chitosan; Electrophoretic deposition; Halloysite nanotubes; Stainless steel; Tetracycline hydrochloride

Electrospinning of aligned polymeric nanofibers for biomedical applications; Synthesis - Dörgens, Anna; Roether, Judith; Dippold, Dirk; Boccaccini, Aldo R.; Schubert, Dirk W. (13th Bayreuth Polymer Symposium, Bayreuth, 2013)

Electrospun nanofiber membranes as substitutes for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas A. (16th Biennial - Bayreuther Polymer Symposium, 2019)

Electrospun nanofiber membranes as substitutes for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (16th Bayreuther Polymer Symposium, Bayreuth (Deutschland), 2019., 2019)

Electrospun nanofiber membranes as substitutes for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (30th Annual Conference of the European Society for Biomaterials, Dresden (Deutschland), 2019, 2019)

Electrospun PCL-Collagen nanofiber membranes as substitute for posterior lamellar keratoplasty - Himmler, Marcus (6th International Symposium on Interface Biology of Implants, 2019)

Electrospun PCL-Collagen nanofiber membranes as substitute for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (The Association for Research in Vision and Ophthalmology (ARVO), 2019)

Electrospun PCL-Collagen nanofiber membranes as substitute for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Nordic Polymer Days, Trondheim (Norwegen),, 2019)

Electrospun PCL Scaffolds as Drug Carrier for Corneal Wound Dressing Using Layer-by-Layer Coating of Hyaluronic Acid and Heparin - Himmler, Marcus; Schubert, Dirk W.; Daehne, Lars; Egri, Gabriella; Fuchsluger, Thomas A. (International Journal of Molecular Sciences, 2022)
Due to its ability to reduce scarring and inflammation, human amniotic membrane is a widely used graft for wound dressings after corneal surgery. To overcome donor dependency and biological variances in the donor tissue, artificial nanofibrous grafts acting as drug carrier systems are promising substitutes. Electrospun nanofibrous scaffolds seem to be an appropriate approach as they offer the properties of permeable scaffolds with a high specific surface, the latter one depending on the fiber diameter. Electrospun scaffolds with fiber diameter of 35 nm, 113 nm, 167 nm and 549 nm were manufactured and coated by the layer-by-layer (LbL) technology with either hyaluronic acid or heparin for enhanced regeneration of corneal tissue after surgery. Studies on drug loading capacity and release kinetics defined a lower limit for nanofibrous scaffolds for effective drug loading. Additionally, scaffold characteristics and resulting mechanical properties from the application-oriented characterization of suture pullout from suture retention tests were examined. Finally, scaffolds consisting of nanofibers with a mean fiber diameter of 113 nm were identified as the best-performing scaffolds, concerning drug loading efficiency and resistance against suture pullout.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Cornea; Drug delivery; Electrospinning; Heparin; Hyaluronic acid; Layer-by-layer coating; Polycaprolactone; Suture retention test; Wound dressing

Electrospun PHB/PCL/FUMED Silica Fibrous Structure for Bone Tissue Engineering - Ding, Yaping; Li, Wei; Roether, Judith; Boccaccini, Aldo R.; Schubert, Dirk W. (Polychar 23rd, 2015)

Electrospun Polyhydroxybutyrate/Poly(ϵ-caprolactone)/58S Sol-Gel Bioactive Glass Hybrid Scaffolds with Highly Improved Osteogenic Potential for Bone Tissue Engineering - Ding, Yaping; Li, Wei; Mueller, Teresa; Schubert, Dirk W.; Boccaccini, Aldo R.; Yao, Qingqing; Roether, Judith (ACS Applied Materials and Interfaces, 2016)
Electrospinning of biopolymer and inorganic substances is one of the efficient ways to combine various advantageous properties in one single fibrous structure with potential for tissue engineering applications. In the present study, to integrate the high stiffness of polyhydroxybutyrate (PHB), the flexibility of poly(ε-caprolactone) (PCL) and the bioactivity of 58S bioactive glass, PHB/PCL/58S sol-gel bioactive glass hybrid scaffolds were fabricated using combined electrospinning and sol-gel method. Physical features such as fiber diameter distribution, mechanical strength and Young's modulus were characterized thoroughly. FTIR analysis demonstrated the successful incorporation of 58S bioactive glass into the blend polymers, which greatly improved the hydrophilicity of PHB/PCL fibermats. The primary biological response of MG-63 osteoblast-like cells on the prepared fibrous scaffolds was evaluated, proving that the 58S glass sol containing hybrid scaffold were not only favorable to MG-63 cell adhesion but also slightly enhanced cell viability and significantly increased alkaline phosphate activity
Keywords: sol-gel method; tissue engineering; poly(ϵ-caprolactone); polyhydroxybutyrate; hybrid scaffolds; electrospinning

Electrospun Polyhydroxybutyrate/Poly(ϵ-caprolactone)/58S Sol-Gel Bioactive Glass Hybrid Scaffolds with Highly Improved Osteogenic Potential for Bone Tissue Engineering - Ding, Yaping; Li, Wei; Mueller, Teresa; Schubert, Dirk W.; Boccaccini, Aldo R.; Yao, Qingqing; Roether, Judith (ACS Applied Materials and Interfaces, 2016)
Keywords: electrospinning; hybrid scaffolds; poly(ϵ-caprolactone); polyhydroxybutyrate; sol-gel method; tissue engineering

Electrospun Polyhydroxybutyrate/Poly(ε-caprolactone)/Sol-Gel-Derived Silica Hybrid Scaffolds with Drug Releasing Function for Bone Tissue Engineering Applications. - Ding, Yaping; Li, Wei; Correia, Alexandra; Yang, Yuyun; Zheng, Kai; Liu, Dongfei; Schubert, Dirk W.; Boccaccini, Aldo R.; Santos, Helder A.; Roether, Judith (ACS Applied Materials and Interfaces, 2018)
Electrospun hybrid scaffolds are an effective platform to deliver drugs site specifically for the prevention and treatment of diseases in addition to promote tissue regeneration because of the flexibility to load drugs therein. In the present study, electrospun hybrid scaffolds containing antibiotics were developed to support cellular activities and eliminate potential postoperative inflammation and infection. As a model drug, levofloxacin (LFX) was successfully incorporated into pure polyhydroxybutyrate/poly(ε-caprolactone) (PHB/PCL) scaffolds and PHB/PCL/sol-gel-derived silica (SGS) scaffolds. The influence of LFX on the morphology, mechanical performance, chemical structure, drug release profile, and antibacterial effect of the scaffolds was thoroughly and comparatively investigated. MG-63 osteoblast-like cell cultivation on both scaffolds certified that LFX inclusion did not impair the biocompatibility. In addition to the favorable cellular proliferation and differentiation, scaffolds containing both LFX and SGS displayed highly increased mineralization content. Therefore, the present multifunctional hybrid scaffolds are promising in tissue engineering applications.

Electrospun Polyhydroxybutyrate/Poly(ϵ-caprolactone)/Sol-Gel-Derived Silica Hybrid Scaffolds with Drug Releasing Function for Bone Tissue Engineering Applications - Ding, Yaping; Li, Wei; Correia, Alexandra; Yang, Yuyun; Zheng, Kai; Liu, Dongfei; Schubert, Dirk W.; Boccaccini, Aldo R.; Santos, Helder A.; Roether, Judith (ACS Applied Materials and Interfaces, 2018)
Electrospun hybrid scaffolds are an effective platform to deliver drugs site specifically for the prevention and treatment of diseases in addition to promote tissue regeneration because of the flexibility to load drugs therein. In the present study, electrospun hybrid scaffolds containing antibiotics were developed to support cellular activities and eliminate potential postoperative inflammation and infection. As a model drug, levofloxacin (LFX) was successfully incorporated into pure polyhydroxybutyrate/poly(ε-caprolactone) (PHB/PCL) scaffolds and PHB/PCL/sol-gel-derived silica (SGS) scaffolds. The influence of LFX on the morphology, mechanical performance, chemical structure, drug release profile, and antibacterial effect of the scaffolds was thoroughly and comparatively investigated. MG-63 osteoblast-like cell cultivation on both scaffolds certified that LFX inclusion did not impair the biocompatibility. In addition to the favorable cellular proliferation and differentiation, scaffolds containing both LFX and SGS displayed highly increased mineralization content. Therefore, the present multifunctional hybrid scaffolds are promising in tissue engineering application
Keywords: hybrid scaffolds; poly(ϵ-caprolactone); antibacterial; polyhydroxybutyrate; sol.gel silica

Electrospun Zein Fibers Incorporating Poly(glycerol sebacate) for Soft Tissue Engineering. - Vogt, Lena; Liverani, Liliana; Roether, Judith; Boccaccini, Aldo R. (Nanomaterials, 2018)
For biomedical applications such as soft tissue engineering, plant proteins are becoming increasingly attractive. Zein, a class of prolamine proteins found in corn, offers excellent properties for application in the human body, but has inferior mechanical properties and lacks aqueous stability. In this study, electrospun scaffolds from neat zein and zein blended with prepolymer and mildly cross-linked poly(glycerol sebacate) (PGS) were fabricated. Less toxic solvents like acetic acid and ethanol were used. The morphological, physiochemical and degradation properties of the as-spun fiber mats were determined. Neat zein and zein-PGS fiber mats with high zein concentration (24 wt % and 27 wt %) showed defect-free microstructures. The average fiber diameter decreased with increasing PGS amount from 0.7 ± 0.2 µm to 0.09 ± 0.03 µm. The addition of PGS to zein resulted in a seven-fold increase in ultimate tensile strength and a four-fold increase in failure strain, whereas the Young’s Modulus did not change significantly. Degradation tests in phosphate buffered saline revealed the morphological instability of zein containing fiber mats in contact with aqueous media. Therefore, the fibers were in situ cross-linked with N-(3-Dimethylaminopropyl)-N′-ethylcarbodiimide (EDC)/N-Hydroxysuccinimide (NHS), which led to improved morphological stability in aqueous environment. The novel fibers have suitable properties for application in soft tissue engineering.
Keywords: zein; poly(glycerol sebacate); electrospinning; nano-fibers; soft tissue engineering

Elongational Flow Properties of Long-Chain Branched Poly(Ethylene Terephthalate) - Härth, Michael; Kaschta, Joachim; Schubert, Dirk W. (Polychar 22nd, 2014)

Elongational Flow Properties Of Long-Chain Branched Poly(Ethylene Terephthalate) - Härth, Michael; Kaschta, Joachim; Schubert, Dirk W. (9th Annual European Rheology Conference, 2014)

Elongational Rheology of Carbon Black Filled Polymethylmethacrylate - Weck, Constantin; Stary, Zdenek; Krückel, Johannes; Schubert, Dirk W. (9th Annual European Rheology Conference, 2014)

Endurance of gel-filled silicone breast implants as a function of maximum load in cyclic compression tests - von Hanstein, Harald; Horch, Raymund E.; Schubert, Dirk W. (Polymer International, 2019)
The mechanical behaviour of gel‐filled silicone breast implants is examined under compressive load. First the implants are tested by applying various loads in a repetitive fashion until shell rupture occurs. Subsequently the results are presented allowing an assessment of the correlation between the number of loading cycles and the maximum compressive load. Finally it is possible to estimate the endurance of the silicone breast implants. Using a power law, a correlation between endurance and maximum load is revealed
CRIS-Team WoS Importer:2019-04-04
Keywords: Silicone breast implant; mechanical behavior; compression test; mechanical loading; endurance

Engineering Stable Perovskite Film for High Color Purity Display Application - Hu, Huiying; Levchuk, Ievgen; Kalkowski, Felix; Elia, Jack; Osvet, Andres; Brabec, Christoph (ACS Energy Letters, 2023)
Lead halide perovskite nanocrystals (NCs) are the most promising candidates for displays satisfying the Rec. 2020 UHDTV color standard. However, moisture sensitivity currently limits light-emitting applications requiring color stability and purity. In this study, we propose a large-area FAPbBr3-based quantum dot brightness enhancing film (QDEF) strategy developed in our group five years ago. The combination of a polymeric binder tailored to the ligands optimized perovskite NCs for light conversion and demonstrates QDEF applications with 91% coverage of Rec. 2020 standard in tablet displays, using polyhedral oligomeric silsesquioxane-capped FAPbBr3 as the green emitter and K2SiF6: Mn4+ (KSF) as a red emitter. Remarkably, our films operating in displays showed 4 year stability without lead leakage. Even without barrier protection, the unpackaged QDEF maintained 55% of its initial performance. This highlights the importance of a dual stabilization strategy for extending operational and shelf lifetimes of advanced functional perovskite composites.<br

Engineering Stable Perovskite Quantum Dot Films for High Color Purity Display Applications - Hu, Huiying; Levchuk, Ievgen; Kalkowski, Felix; Elia, Jack; Osvet, Andres; Brabec, Christoph (ACS Energy Letters, 2023)

Enhanced Ambipolar Charge Injection with Semiconducting Polymer/Carbon Nanotube Thin Films for Light-Emitting Transistors - Gwinner, Michael C.; Jakubka, Florian; Gannott, Florentina; Sirringhaus, Henning; Zaumseil, Jana (ACS nano, 2012)
We investigate the influence of small amounts of semiconducting single-walled carbon nanotubes (SWNTs) dispersed in polyfluorenes such as poly(9,9-di-n-octylfluorene-alt-benzothiadiazole (F8BT) and poly(9,9-dioctylfluorene) (F8) on device characteristics of bottom contact/top gate ambipolar light-emitting field-effect transistors (LEFETs) based on these conjugated polymers. We find that the presence of SWNTs within the semiconducting layer at concentrations below the percolation limit significantly increases both hole and electron injection, even for a large band gap semiconductor like F8, without leading to significant luminescence quenching of the conjugated polymer. As a result of the reduced contact resistance and lower threshold voltages, larger ambipolar currents and thus brighter light emission are observed. We examine possible mechanisms of this effect such as energy level alignment, reduced bulk resistance above the contacts, and field-enhanced injection at the nanotube tips. The observed ambipolar injection improvement is applicable to most conjugated polymers in staggered transistor configurations or similar organic electronic devices where injection barriers are an issue.
EAM Import::2019-03-14

Enhanced In Vitro Biocompatibility and Water Dispersibility of Magnetite and Cobalt Ferrite Nanoparticles Employed as ROS Formation Enhancer in Radiation Cancer Therapy - Klein, Stefanie; Kizaloglu, Melek; Portilla Berlanga, Luis; Park, Hyoungwon; Rejek, Tobias; Hümmer, Julian; Meyer, Karsten; Hock, Rainer; Distel, Luitpold; Halik, Marcus; Kryschi, Carola (Small, 2018)

Enhancement of engineered cardiac tissues by promotion of hiPSC-cardiomyocyte proliferation - Hesselbarth, Ramona; Esser, Tilman; Roshanbinfar, Kaveh; Schrüfer, Stefan; Schubert, Dirk W.; Engel, Felix (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Enhancing electrical conductivity of carbon black filled immiscible polymer blends by tuning the morphology - Pan, Yamin; Liu, Xian Hu; Hao, Xiaoqiong; Stary, Zdenek; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Enhancing Photoelectric Powder Deposition of Polymers by Charge Control Substances - Düsenberg, Björn; Kopp, Sebastian-Paul; Tischer, Florentin; Schrüfer, Stefan; Schmidt, Jochen; Schmidt, Michael; Schubert, Dirk W.; Peukert, Wolfgang; Bück, Andreas; Roth, Stephan (Polymers, 2022)
Charge control substances (CCS) as additives for polymer powders are investigated to make polymer powders suitable for the electrophotographic powder deposition in powder-based additive manufacturing. The use of CCS unifies the occurring charge of a powder, which is crucial for this novel deposition method. Therefore, commercially available polymer powder is functionalized via dry coating in a shaker mixer with two different CCS and analyzed afterwards. The flowability and the degree of coverage of additives on the surface are used to evaluate the coating process. The thermal properties are analyzed by use of differential scanning calorimetry. Most important, the influence of the CCS on the powder charge is shown by measurements of the electrostatic surface potential at first and the powder deposition itself is performed and analyzed with selected formulations afterwards to show the potential of this method. Finally, tensile strength specimens are produced with the conventional deposition method in order to show the usability of the CCS for current machines.<br
Keywords: additive manufacturing; charge control substances; photoelectric powder deposition; polypropylene; dry coating

Enhancing the dispersability of TiO2 nanorods and gaining control over region-selective layer formation - Etschel, Sebastian; Tykwinski, Rik; Halik, Marcus (Langmuir, 2016)
We demonstrate that the dispersibility and reactivity of core-shell TiO2 nanorods (NRs) can be controlled significantly through functionalization with a combination of ligands based on phosphonic acid derivatives (PAs). Specifically, a glycol based PA allows dispersion of the NRs in methanol (MeOH). On the other hand, incorporating an alkyne terminated PA in the ligand shell of the NRs allows for a copper-catalyzed alkyne-azide cycloaddition (CuAAC) reaction with an azide-patterned aluminum oxide (AlOx) substrate and forms a region-selectively deposited film of NRs. We clearly demonstrate that the quality of the NR films correlates strongly with the stability of the NR dispersions in the reaction medium. In particular, tuning the concentration of alkyne PA in the ligand shell inhibits aggregation of the NRs on the substrate, while reactivity for the CuAAC reaction is maintained. The surface coverage with NRs fits the Langmuir model. This study illustrates that surface functionalization of AlOx substrates can be effectively and conveniently controlled through enhancing the dispersibility of the NRs using mixed ligand shells.

Enhancing the electrical conductivity of carbon black-filled immiscible polymer blends by tuning the morphology - Pan, Yamin; Liu, Xian Hu; Hao, Xiaoqiong; Stary, Zdenek; Schubert, Dirk W. (European Polymer Journal, 2016)
Blends of carbon black (CB)-filled polystyrene (PS) and poly(methyl methacrylate) (PMMA) with different PS/PMMA ratios have been prepared by melt blending in order to obtain conductive polymer composites with a low electrical percolation threshold according to the concept of double percolation. The dependence of the electrical conductivity on the morphology of the composite was examined before and after annealing in the molten state. The electrical conductivity of the composites was highest when the PS and PMMA phases formed a co-continuous structure and CB particles were selectively located and percolated in the PS phase. PS/PMMA (30/70) blends exhibited the lowest electrical percolation threshold of 1.26 vol% CB. A simple model is suggested to explain this effect. After annealing, the CB clearly affected the stabilization of the co-continuous structure. Moreover, the electrical conductivity increased after annealing and the percolation threshold decreased to below 1 vol% CB regardless of PS content. The largest increase in electrical conductivity after annealing was found with PS/PMMA (70/30) blends filled with 1 vol% CB. With increasing PMMA content, this effect became less pronounced. The different behaviors in the composites can be explained by dynamic percolation and decrease in continuity of the CB-filled PS phase induced by structure coarsening.
Keywords: Annealing; Electrical properties; Interface; Phase morphology; Polymer composites

Enhancing the electronic properties of VLS-grown silicon nanowires by surface charge transfer - Shalabny, Awad; Buonocore, Francesco; Celino, Massimo; Zhang, Lu; Sardashti, Kasra; Härth, Michael; Schubert, Dirk W.; Bashouti, Muhammad Y. (Applied Surface Science, 2022)
The need to develop new energy storage technology has led to deeper investigation into materials science to produce highly efficient batteries, primarily the lithium ion battery. The importance of electrodes in such devices has led to the reemergence of silicon nanowires (Si NWs) at the forefront of materials study—in this context, as an energy storage material (as electrodes). Redox potential and work function play the most important roles in charge transfer, the battery charging/discharging process. Thus, the NWs’ interfacial properties become important in achieving higher stability and efficiency. In this work, a deep study was conducted using equilibrium perturbation to change the surface electronic properties of Si NWs, which can be integrated into various technologies, while simultaneously achieving an interesting interface that is chemically passive and cheap to produce. By using an X-ray photoelectron spectroscope, a Kelvin probe, and contact angle measurement, combined with theoretical analysis, a full picture is achieved regarding the Si NWs’ interface, paving the way for this new technique to develop unique interfaces and to achieve a higher energy capacity and a longer lifetime.<br
Keywords: Non-equilibrium reactions; Silicon nanowire; Surface chemistry; Surface Fermi level; Sub-oxides; DFT; Work function; Charge transfer

Entanglement network formed in miscible PLA/PMMA blends and its role in rheological and thermo-mechanical properties of the blends - Hao, Xiaoqiong; Kaschta, Joachim; Liu, Xian Hu; Pan, Yamin; Schubert, Dirk W. (Polymer, 2015)
The miscible amorphous/semi-crystalline polymer blends with shape memory potential has received increasing interests in recent years. In this work, the shape memory mechanism of the miscible amorphous PMMA/semi-crystalline PLA blends was investigated using thermo-mechanical and rheological approaches. With the incorporation of PMMA into PLA, a broad glass transition and increased glass transition temperature Tg were observed by differential scanning calorimetry (DSC) measurements. The broadening of glass transition is attributed to the local nanoscale heterogeneities in the miscible blend system which is related to the self-concentration of the components. The degree of molecular entanglement of the blends was derived based on the oscillatory rheological measurements, showing that the dissimilar chains are more likely to entangle with each other than the similar ones, and the entanglement density ve is enhanced with increased PMMA content up to 50% where a 100% recovery of the initial shape is yielded. After that, ve is reduced with the addition of PMMA. The mechanism underlying the shape memory property is further validated by performing the shape memory test on the PLA/PMMA blend films at respective Tg. It is evident that for the semi-crystalline blends (PLA rich), PLA crystallites and molecular entanglement provide physical cross-links for shape recording, while a negative effect of crystallinity on the shape recovery ratio is obtained due to the strain-induced crystallization and chain slippage between the crystalline and amorphous chains. In contrast, for the amorphous blends (PMMA rich), the shape recovery ratio shows a strong positive linear dependence on ve, and the entanglement network is regard as the most important factor in the shape memory performanc
Keywords: Rheological property; Shape memory polymer; Molecular entanglement

Entanglement network formed in miscible PLA/PMMA blends and its role in rheological and thermo-mechanical properties of the blends - Hao, Xiaoqiong; Kaschta, Joachim; Liu, Xian Hu; Pan, Yamin; Schubert, Dirk W. (Polymer, 2015)
The miscible amorphous/semi-crystalline polymer blends with shape memory potential has received increasing interests in recent years. In this work, the shape memory mechanism of the miscible amorphous PMMA/semi-crystalline PLA blends was investigated using thermo-mechanical and rheological approaches. With the incorporation of PMMA into PLA, a broad glass transition and increased glass transition temperature Tg were observed by differential scanning calorimetry (DSC) measurements. The broadening of glass transition is attributed to the local nanoscale heterogeneities in the miscible blend system which is related to the self-concentration of the components. The degree of molecular entanglement of the blends was derived based on the oscillatory rheological measurements, showing that the dissimilar chains are more likely to entangle with each other than the similar ones, and the entanglement density ve is enhanced with increased PMMA content up to 50% where a 100% recovery of the initial shape is yielded. After that, ve is reduced with the addition of PMMA. The mechanism underlying the shape memory property is further validated by performing the shape memory test on the PLA/PMMA blend films at respective Tg. It is evident that for the semi-crystalline blends (PLA rich), PLA crystallites and molecular entanglement provide physical cross-links for shape recording, while a negative effect of crystallinity on the shape recovery ratio is obtained due to the strain-induced crystallization and chain slippage between the crystalline and amorphous chains. In contrast, for the amorphous blends (PMMA rich), the shape recovery ratio shows a strong positive linear dependence on ve, and the entanglement network is regard as the most important factor in the shape memory performanc
Keywords: Rheological property; Shape memory polymer; Molecular entanglement

Epitaxial Growth of PbSe Quantum Dots on MoS2 Nanosheets and their Near-Infrared Photoresponse - Schornbaum, Julia; Winter, Benjamin; Schießl, Stefan; Gannott, Florentina; Katsukis, Georgios; Guldi, Dirk Michael; Spiecker, Erdmann; Zaumseil, Jana (Advanced Functional Materials, 2014)
A facile one-pot synthesis of hybrid materials consisting of PbSe quantum dots (QDs) that grow epitaxially on MoS2 nanoflakes resulting in three equivalent orientation variants of the PbSe QDs with respect to the MoS2 lattice is demonstrated. The epitaxial growth and cross-sectional high-resolution transmission electron microscopy (HRTEM) investigations verify a direct and linker-free contact between the quantum dots and the transition metal dichalcogenide (TMD) nanoflakes, while maintaining surface passivation of the PbSe with oleic acid ligands on the outside. Solution-processed photodetectors based on PbSe-MoS2 hybrids exhibit stable photoconduction when illuminated with near-IR light (wavelength > 1200 nm) without any laborious ligand-exchange steps. Flexible devices fabricated on polyethylene terephthalate (PET) substrates show excellent stability upon repeated bending. These hybrid materials are air-stable and solution-processable at low temperatures and thus promising for low-cost flexible near-IR photodetectors.

Erratum: 45S5 bioactive glass-based scaffolds coated with cellulose nanowhiskers for bone tissue engineering (RSC Adv. (2014) 4 (56156-56164) DOI: 10.1039/C4RA07740G) - Li, Wei; Garmendia, Nere; De Larraya, Uxua Perez; Ding, Yaping; Detsch, Rainer; Grünewald, Alina; Roether, Judith; Schubert, Dirk W.; Boccaccini, Aldo R. (RSC Advances, 2023)
The authors regret unattributed data overlap between their RSC Advances article and ref. 1. The Royal Society of Chemistry apologises for these errors and any consequent inconvenience to authors and readers.
CRIS-Team Scopus Importer:2023-05-26

Evaluation and optimisation of the melt-electrospinning process for selected polypropylene additive compounds - Daenicke, Jonas; Schubert, Dirk W.; Lämmlein, Michael; Steinhübl, Felix (Polymertec18, 2018)

Evaluation of fibroblasts adhesion and proliferation on alginate-gelatin crosslinked hydrogel - Sarker, Bapi; Singh, Raminder; Silva, Raquel; Roether, Judith; Kaschta, Joachim; Detsch, Rainer; Schubert, Dirk W.; Cicha, Iwona; Boccaccini, Aldo R. (PLoS ONE, 2014)
Due to the relatively poor cell-material interaction of alginate hydrogel, alginate-gelatin crosslinked (ADA-GEL) hydrogel was synthesized through covalent crosslinking of alginate di-aldehyde (ADA) with gelatin that supported cell attachment, spreading and proliferation. This study highlights the evaluation of the physico-chemical properties of synthesized ADA-GEL hydrogels of different compositions compared to alginate in the form of films. Moreover, in vitro cell-material interaction on ADA-GEL hydrogels of different compositions compared to alginate was investigated by using normal human dermal fibroblasts. Viability, attachment, spreading and proliferation of fibroblasts were significantly increased on ADA-GEL hydrogels compared to alginate. Moreover, in vitro cytocompatibility of ADA-GEL hydrogels was found to be increased with increasing gelatin content. These findings indicate that ADA-GEL hydrogel is a promising material for the biomedical applications in tissue-engineering and regeneration. Copyright:

Evaluation of silica-nanotubes and strontium hydroxyapatite nanorods as appropriate nanoadditives for poly(butylene succinate) biodegradable polyester for biomedical applications - Grigoriadou, I.; Nianias, N.; Hoppe, Alexander; Terzopoulou, Z.; Bikiaris, D.; Will, Julia; Hum, Jasmin; Roether, Judith; Detsch, Rainer; Boccaccini, Aldo R. (Composites Part B-Engineering, 2014)
In the present study two series of poly(butylene succinate) (PBSu) nanocomposites containing 5 and 20 wt% of silica-nanotubes or strontium hydroxyapatite [Sr(PO)OH] nanorods were prepared by melt mixing at 130 C. From SEM images it was found that SiO nanotubes are well dispersed inside the PBSu matrix while Sr (PO)OH nanorods formed some aggregates. In both cases the mechanical properties of nanocomposites were slightly affected by the amount of nanoadditives. Enzymatic hydrolysis of PBSu and its nanocomposites was studied in aqueous solutions containing a mixture of R. delemar and Pseudomonas Cepacia lipases, at 50 C and pH = 7.2. It was found that all nanocomposites have higher hydrolysis rates than neat PBSu indicating that nanoparticles accelerate the hydrolysis degradation process. The hydrophilicity of nanofillers, the presence of hydroxyl groups and the effect of a ''gap" at the interface due to low adhesion of PBSu matrix and inorganic nanofillers, could increase the enzymatic hydrolysis rate of the polyester matrix. All prepared samples were tested in relevant cell culture using osteoblast-like cells (MG-63) to demonstrate their biocompatibility. It was found that SiO nanotubes support cell attachment, while Sr(PO )OH nanorods decrease cell activity. © 2013 Elsevier Ltd. All rights reserved.
Keywords: A. Discontinuous reinforcement; A. Nano-structures; B. Mechanical properties; B. Microstructures; B. Surface properties

Evaluation of the crosslinking density and the mechanical properties of silicone elastomers filled with bariumtitanates of different particle sizes as dielectric elastomers - Ziegmann, Andreas; Schubert, Dirk W. (Europe Africa Conference 2017 of the Polymer Processing Society, 2017)

Evaluation of the diffusion properties of cyclic siloxanes through the silicone breast implant shell - Daenicke, Jonas; Schubert, Dirk W.; Gedde, Ulf; Hedenqvist, Mikael; Linde, Erik; Kaschta, Joachim; Horch, Raymund E. (Nordic Polymer Days, 2015)

Evaluation of the diffusion properties of cyclic siloxanes through the silicone breast implant shell - Daenicke, Jonas; Schubert, Dirk W.; Gedde, Ulf; Hedenqvist, Mikael; Linde, Erik; Kaschta, Joachim; Horch, Raymund E. (14th Bayreuth Polymer Symposium, 2015)

Evaluation of the diffusion properties of silicone elastomers related to the crosslinking density and of the mechanical weakening due to silicone oil up-take - Daenicke, Jonas; Schubert, Dirk W. (International Workshop on Silicone based Poylmers, 2017)

Evaluation of the electromechanical transduction performance of silicone elastomers filled with bariumtitanates of different particle sizes - Ziegmann, Andreas; Schubert, Dirk W. (International Workshop on Silicone based Poylmers, 2017)

Evaluation of the influence of crosslink density and penetrant size on the diffusion properties of silicone oils into silicone elastomers - Daenicke, Jonas; Schubert, Dirk W.; Hedenqvist, Mikael; Linde, Erik; Sigl, Thomas; Horch, Raymund E. (AIP Conference Proceedings, 2019)
Driven by the continuing discussion on safety and quality of silicone breast implants, they have turned into focus of this study with respect to the diffusivity of low molar mass components from the silicone gel filling into the silicone breast implant shell. Therefore, the diffusivity of silicone oils into silicone elastomers were analysed by means of the crosslink density and the penetrant size. The study was focused on the diffusion of the cyclic siloxanes Octamethylcyclotetrasiloxane (D4), Decamethylcyclopentasiloxane (D5) and Dodecamethyl-cyclohexasiloxane (D6) due to their potential occurrence in silicone breast implants. The analysis of the diffusion behavior was carried out with silicone breast implant shells taken from explants and tailor-made silicone elastomer samples varying in crosslink density. Therefore, sorption experiments were performed. The subsequent evaluation of the sorption data yield to the corresponding diffusion properties. Based on the diffusion coefficient related to the crosslink density a model was developed to describe the material behavio
CRIS-Team WoS Importer:2019-05-03
Keywords: polymer; materials analysis

Evaluation of the influence of crosslink density and penetrant size on the diffusion properties of silicone oils into silicone elastomers - Schubert, Dirk W.; Daenicke, Jonas (Europe Africa Conference 2017 of the Polymer Processing Society, 2017)

Evaluation of the Performance Potential of Organic TFT Circuits - Brederlow, R.; Briole, S.; Klauk, Hagen; Halik, Marcus; Zschieschang, Ute; Schmid, Günter; Gorriz-Saez, J. -M.; Pacha, C.; Thewes, R.; Weber, Werner (Digest of Technical Papers - IEEE International Solid-State Circuits Conference, 2003)

Evidence of Tailoring the Interfacial Chemical Composition in Normal Structure Hybrid Organohalide Perovskites by a Self-Assembled Monolayer - Will, Johannes; Hou, Yi; Scheiner, Simon; Pinkert, Ute; Hermes, Ilka M.; Weber, Stefan A.L.; Hirsch, Andreas; Halik, Marcus; Brabec, Christoph; Unruh, Tobias (ACS Applied Materials and Interfaces, 2018)
Current-voltage hysteresis is a major issue for normal architecture organo-halide perovskite solar cells. In this manuscript we reveal a several Å thick Methylammonium Iodide (MAI) rich interface between the perovskite and the metal oxide. Surface functionalization via selfassembled monolayers (SAMs) allowed us to control the composition of the interface monolayer from Pb poor to Pb rich, which in parallel suppresses hysteresis in perovskite solar cells. The bulk of the perovskite films is not affected by the interface engineering and remains highly crystalline in surface normal direction over the whole film thickness. The subnm structural modifications of the buried interface were revealed by x-ray reflectivity (XRR), which is most sensitive to monitor changes in the mass density of only several Å thin interfacial layers as a function of substrate functionalization. From Kelvin probe force microscopy (KPFM) on a solar cell cross section study, we further demonstrate local variations of the potential on different electron transporting layers (ETLs) within a solar cell. Based on these findings we present a unifying model explaining hysteresis in perovskite solar cells, giving for the first time insight into one crucial aspect of hysteresis and paving the way for new strategies in the fields of perovskite based opto-electronic devices.
Keywords: perovskite solar cell; hysteresis; buried interface; x-ray reflectivity; Kelvin probe force microscopy

Examining the contribution of factors affecting the electrical behavior of poly(methyl methacrylate)/graphene nanoplatelets composites - Luo, Xiaoling; Schubert, Dirk W. (Journal of Applied Polymer Science, 2021)
In this study, poly(methyl methacrylate) (PMMA)/graphene nanoplatelets (GNPs) conductive composite films with different morphologies were fabricated from the same constituent materials using four fabrication techniques, solution casting (SC), SC followed by hot pressing (SCP), melt mixing followed by SC (MSC), and melt mixing followed by hot pressing (MP). Morphologies of dispersed GNPs and electrical properties in both in‐plane and perpendicular direction were investigated and compared systematically. The corresponding percolation thresholds (Φc) of the composites varied from 0.42 ± 0.13 vol% to 3.26 ± 0.48 vol%. The conductivities varied up to two orders of magnitude and decreased in the sequence of SC > MSC > SCP > MP. These variations were explained in terms of GNPs size, GNPs orientation, distribution and dispersion state of fillers. The contribution of the above factors in each procedure were discerned individually, the results were discussed and compared with other experimental studies and simulations as well.<br
Keywords: films; morphology; nanostructured polymers; nanotubes; graphene and fullerenes; theory and modeling

Examining the contribution of factors affecting the electrical behavior of poly(methyl methacrylate)/graphene nanoplatelets composites - Luo, Xiaoling; Schubert, Dirk W. (3rd Advanced Materials Science World Congress, 2022)
In this study, poly(methyl methacrylate) (PMMA)/graphene nanoplatelets (GNPs) conductive composite films with different morphologies were fabricated from the same constituent materials using four fabrication techniques, solution casting (SC), SC followed by hot pressing (SCP), melt mixing followed by SC (MSC), and melt mixing followed by hot pressing (MP). Morphologies of dispersed GNPs and electrical properties in both in-plane and perpendicular directions were investigated and compared systematically. The conductivities, which varied up to two orders of magnitude and decreased in the sequence of SC > MSC >SCP >MP, were described as a function of GNPs volume fraction by using a McLachlan equation to reveal the electrical percolation thresholds (Φc). The Φc of the composites varied from 0.42 ± 0.13 vol % (SC, perpendicular) to 3.26 ± 0.48 vol % (MP, in-plane). The difference in the conductivity and Φc between two measuring directions is ascribed to GNPs orientation, while that for different processing methods is explained in terms of GNPs size, GNPs distribution, and dispersion state. The contribution of the above factors in each procedure was discerned individually, the results were discussed and compared with other experimental studies and simulations as well. The comparative study shows that the SC method endows the composite with the optimum electrical properties in both directions due to the large size, good dispersion and exfoliation of GNPs, and bad distribution of segregation structures. <

Examining the transmission of visible light through electrospun nanofibrous pcl scaffolds for corneal tissue engineering - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas A. (Nanomaterials, 2021)
Keywords: Transparency; Cornea; Nanofibers; Electrospinning; Tissue engineering; Polycaprolactone

Experimental and Theoretical Study on Piezoresistive Behavior of Compressible Melamine Sponge Modified by Carbon-based Fillers - Luo, Xi; Schubert, Dirk W. (Chinese Journal of Polymer Science, 2022)
High-performance compression sensors have been playing an increasingly important role in human motion detection, health monitoring and human-machine interfaces over recent years. However, it remains a great challenge to develop theoretical models providing practical guidance to the sensor design. Herein, carbon black (CB), carbon nanotubes (CNTs) and graphene nanoplatelets (GNPs) were respectively incorporated into porous melamine sponges by a facile approach of dip-coating to fabricate compression sensors. Uniaxial compression-resistance tests show that the compressibility, stability and piezoresistive sensitivity of sensors could be tailored by the filler type and concentration. A model considering the number of conductive pathways (NCP) is given to describe the relationship between the resistance change and applied compression, showing extremely good agreement with the experimental data. Also, the correlation between the equivalent filler volume fraction and conductivity is described by the other two models proposed by McLachlan and Kirkpatrick, revealing the electrical percolation thresholds (Φc) for the conductive systems under compression. Among the three fillers, CB particles endowed the composite with the best piezoresistive sensitivity but the largest Φc due to its small size and aspect ratio. A combination of experimental study and theoretical model opens up a way of further understanding the piezoresistive sensing behavior as well as optimizing the electrical property and piezoresistivity of compressive conductive polymer composite.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Compression sensor; Melamine sponge; Model; Piezoresistivity

Exploring the Steric Hindrance of Alkylammonium Cations in the Structural Reconfiguration of Quasi-2D Perovskite Materials Using a High-throughput Experimental Platform - Zhang, Jiyun; Wu, Jianchang; Langner, Stefan; Zhao, Baolin; Xie, Zhiqiang; Hauch, Jens; Afify, Hany A.; Barabash, Anastasiia; Luo, Junsheng; Sytnyk, Mykhailo; Meng, Wei; Zhang, Kaicheng; et al. (Advanced Functional Materials, 2022)
Reduced-dimensional (2D or quasi-2D) perovskites have recently attracted considerable interest due to their superior long-term stability. The nature of the intercalating cations plays a key role in determining the physicochemical properties and stability of the quasi-2D perovskites. Here, the thermal stability of a series of 2D Ruddlesden−Popper (RP) perovskites is studied using seven types of intercalating cations with increasing linear carbon-chain length from ethylammonium (EA) to n-dodecylammonium (DA) through a high-throughput platform. The results show that long-chain cations in quasi-2D perovskite films lead to strong steric hindrance between adjacent perovskite domains, thus suppressing Ostwald ripening during the thermal-aging process. For short-chain cations, increased-dimensional phase redistribution during the aging period is observed, which can benefit a concomitant regeneration of the 3D/3D-like perovskite phases. The impact of steric hindrance on structural reconfiguration and the subsequent phase redistribution in quasi-2D perovskites are systematically characterized by UV–vis absorption spectra, photoluminescence spectra, and X-ray diffraction patterns. Due to the steric hindrance effect, an optimal chain length is found to maximize film stability by balancing the water/oxygen resistance and increased-dimensional phase redistribution. This work provides new insight into the thermal stability of quasi-2D perovskites.
CRIS-Team Scopus Importer:2022-09-02
Keywords: 2D perovskite materials; high-throughput platform; stability performance; steric hindrance; steric structure and reconfiguration

Extensional Properties of Blends Based on Linear and Long-Chain Branched Polypropylene - Kunzelmann, Peter; Dörnhöfer, Andrea; Schubert, Dirk W. (Book of Abstracts, 2013)

Extensive reuse of soda-lime waste glass in fly ash-based geopolymers - Toniolo, Nicoletta; Rincon, Acacio; Roether, Judith; Ercole, P.; Bernardo, E.; Boccaccini, Aldo R. (Construction and Building Materials, 2018)
Keywords: Geopolymers; Waste glass; Fly ash

Extrusion Foaming of a Preceramic Silicone Resin with a Variety of Profiles and Morphologies - Wolff, Friedrich; Ceron Nicolat, Bruno; Fey, Tobias; Greil, Peter; Münstedt, Helmut (Advanced Engineering Materials, 2012)
Preceramic foams with a variety of profiles and morphologies were fabricated by a continuous foam extrusion process based on a single-screw extruder. A methyl silicone resin was used as the preceramic polymer and carbon dioxide as the foaming agent. Variations of the foam morphology were achieved by changing the key process parameters carbon dioxide content, foaming pressure, and foaming temperature. Samples of different porosities, cell densities, pore sizes, and pore size gradients were obtained. From these results, conditions for the fabrication of particular foam structures can be derived. Various foam profiles as rods, tapes, and tubes were extruded and pyrolysed into ceramic foams.

Fabrication and characterization of Ag- and Ga-doped mesoporous glass-coated scaffolds based on natural marine sponges with improved mechanical properties - Ciraldo, Francesca; Arango-Ospina, Marcela; Goldmann, Wolfgang H.; Beltran, Ana M.; Detsch, Rainer; Gruenewald, Alina; Roether, Judith; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part A, 2020)
Natural marine sponges were used as sacrificial template for the fabrication of bioactive glass-based scaffolds. After sintering at 1050°C, the resulting samples were additionally coated with a silicate solution containing biologically active ions (Ag and Ga), well-known for their antibacterial properties. The produced scaffolds were characterized by superior mechanical properties (maximum compressive strength of 4 MPa) and total porosity of 80% in comparison to standard scaffolds made by using PU foam templates. Direct cell culture tests performed on the uncoated and coated samples showed positive results in terms of adhesion, proliferation, and differentiation of MC3T3-E1 cells. Moreover, vascular endothelial growth factor (VEGF) secretion from cells in contact with scaffold dissolution products was measured after 7 and 10 days of incubation, showing promising angiogenic results for bone tissue engineering applications. The antibacterial potential of the produced samples was assessed by performing agar diffusion tests against both Gram-positive and Gram-negative bacteria.
CRIS-Team Scopus Importer:2020-12-04
Keywords: antibacterial; bioactive glass; bone tissue engineering; ion delivery; scaffolds; VEGF

Fabrication and Properties of Injection Moulded Hardmetal Parts by use of a Pressure Die Casting Machine - Raduta, Sorina; Grötzschel, Gerhard; Kaschta, Joachim; Rosiwal, Stefan; Singer, Robert (1998 PM World Congress, 1998)

Fabrication, characterization and modelling of triple hierarchic PET/CB/TPU composite fibres for strain sensing - Qin, Yijing; Qu, Muchao; Pan, Yamin; Zhang, Chunhua; Schubert, Dirk W. (Composites Part A-Applied Science and Manufacturing, 2020)
In this study, a triple-layered coaxial fibre structure was fabricated for strain sensor applications. The core consisted of melt-spun poly (ethylene terephthalate) (PET) where in a subsequent step carbon black (CB) particles were coated onto the surface of the PET fibre to build the conductive pathways by a dissolving-coating method. For the outer protective sheath, a thermoplastic polyurethane (TPU) with a thickness of about 7 μm was generated using a layer-by-layer assembly technique. Compared with other investigated CB-coated fibres, the novel triple hierarchic PET/CB/TPU composite fibres exhibit a high Young's modulus and tensile strength, as well as a doubled sensing range. The fabrication process can be directly used in the textile industry for the production of wearable and flexible sensors due to its efficacy and low cost. Moreover, a model based on tunnelling theory utilizing only two adjustable parameters was modified based on the actual experimental data, which could precisely describe the relative change of resistance upon the applied strain. Meanwhile, an empirical equation was first proposed and this model offers an effective but simple approach towards quantitative analysis of strain sensors.
CRIS-Team Scopus Importer:2019-12-20
Keywords: A. Polymer (textile) fibres; B. Physical properties; C. Analytical modelling; E. Surface treatments

Fabrication, characterization and modelling of triple hierarchic structural PET/CB/TPU composite fibers for strain sensing - Qin, Yijing; Qu, Muchao; Schubert, Dirk W. (8th International Conference on Carbon NanoParticle based Composites (CNPComp2019), 2019)

Fabrication of alginate-gelatin crosslinked hydrogel microcapsules and evaluation of the microstructure and physico-chemical properties - Sarker, Bapi; Papageorgiou, Dimitrios G.; Silva, Raquel; Zehnder, Tobias; Gul-E-Noor, Farhana; Bertmer, Marko; Kaschta, Joachim; Chrissafis, Konstantinos; Detsch, Rainer; Boccaccini, Aldo R. (Journal of Materials Chemistry B, 2014)
Microencapsulation of cells by using biodegradable hydrogels offers numerous attractive features for a variety of biomedical applications including tissue engineering. This study highlights the fabrication of microcapsules from an alginate-gelatin crosslinked hydrogel (ADA-GEL) and presents the evaluation of the physico-chemical properties of the new microcapsules which are relevant for designing suitable microcapsules for tissue engineering. Alginate di-aldehyde (ADA) was synthesized by periodate oxidation of alginate which facilitates crosslinking with gelatin through Schiff's base formation between the free amino groups of gelatin and the available aldehyde groups of ADA. Formation of Schiff's base in ADA-GEL and aldehyde groups in ADA was confirmed by FTIR and NMR spectroscopy, respectively. Thermal degradation behavior of films and microcapsules fabricated from alginate, ADA and ADA-GEL was dependent on the hydrogel composition. The gelation time of ADA-GEL was found to decrease with increasing gelatin content. The swelling ratio of ADA-GEL microcapsules of all compositions was significantly decreased, whereas the degradability was found to increase with the increase of gelatin ratio. The surface morphology of the ADA-GEL microcapsules was totally different from that of alginate and ADA microcapsules, observed by SEM. Two different buffer solutions (with and without calcium salt) have an influence on the stability of microcapsules which had a significant effect on the gelatin release profile of ADA-GEL microcapsules in these two buffer solutions. © 2014 The Royal Society of Chemistry.

Fabrication of electrospun poly (3-hydroxybutyrate)/poly (ε-caprolactone)/silica hybrid fibermats with and without calcium addition - Ding, Yaping; Roether, Judith; Boccaccini, Aldo R.; Schubert, Dirk W. (European Polymer Journal, 2014)
Poly (3-hydroxybutyrate)(PHB)/poly (ε-caprolactone)(PCL)/silica hybrid scaffolds with and without calcium were fabricated through the combination of electrospinning and sol-gel methods. In this paper, the effects of different amounts of silica sol on the morphology, mechanical and thermal properties of hybrid scaffolds were studied. The results indicated that as the silica content increased to 50 wt%, the ultimate tensile strength and modulus were enhanced to 191% and 614%, respectively. In addition, the presence of silica decreased the elongation at break significantly. Calcium addition changed the morphology of the hybrid scaffolds from relatively dense fibermats to highly fluffy porous structures, which may be due to the ionization of Ca in the polymer solution. Chemical interactions between the different components and the thermal properties were also based on FTIR, DSC and TGA measurements. The addition of inorganic components significantly decreased the crystallinity of PHB and PCL, which was also confirmed by XRD analysis. Due to the intrinsic performance of the biopolymer and inorganic components, the scaffolds in the present study have great potential for tissue engineering applications. © 2014 Elsevier Ltd. All rights reserved.
Keywords: Electrospinning; Hybrid scaffolds; Poly (3-hydroxybutyrate); Poly (ε-caprolactone); Sol-gel

Fabrication of TiO2@Cu mesh with impressive hydrophobic surface for electromagnetic interference shielding - Yuan, Yongchao; He, Yangyang; Shi, Shouxin; Wu, Degang; Yang, Guanda (Surface Innovations, 2023)
This study investigates the surface modification of copper mesh using modified TiO2 coatings to enhance its surface hydrophobic properties while preserving electromagnetic interference (EMI) shielding effectiveness. Silicon coupling agent treated TiO2 particles were employed to create micro/nanostructured superhydrophobic coatings. The deposition times was found to influence the coating distribution, pore filling, and surface hydrophobicity. S-TiO2@Cu mesh with single layer of modified TiO2 coating exhibited the highest water contact angle compared with T-TiO2@Cu mesh with triple layer coatings and original O-TiO2@Cu mesh. Superior self-cleaning performance and robust wear resistance of the hydrophobic coatings for S-TiO2@Cu mesh are revealed. In addition, both S -TiO2@Cu mesh and T-TiO2@Cu mesh exhibited satisfactory EMI shielding efficiency without compromising the intrinsic properties of the copper mesh. These findings provide practical insights into surface modification of copper mesh substrate, emphasizing the balance between surface properties and EMI shielding. The hydrophobic coatings hold promise for multifunctional applications, offering enhanced surface properties without compromising EMI shielding performance.
CRIS-Team Scopus Importer:2023-11-10

Facile Fabrication of Superhydrophobic and Eco-Friendly Poly(lactic acid) Foam for Oil-Water Separation via Skin Peeling - Wang, Xiaolong; Pan, Yamin; Liu, Xianhu; Liu, Hu; Li, Ning; Liu, Chuntai; Schubert, Dirk W.; Shen, Changyu (ACS Applied Materials and Interfaces, 2019)
Superhydrophobic polymer foams are a good candidate for oil absorption because of their lightweight and tunable porosity and have promising applications in the long-term application of oil-water separation. However, developing a facile and green strategy to fabricate pure polymer foams with superhydrophobicity and eco-friendliness for large-scale oil-water separation remains a challenge. Here, a facile template-free water-assisted thermally impacted phase separation approach combined with skin peeling for the fabrication of superhydrophobic and eco-friendly pure poly(lactic acid) (PLA) foam for oil-water separation is proposed for the first time. The PLA foam with special micro- and nanostructures possesses a water contact angle of 151°, and the maximum saturated adsorption capacity is 31.5 g/g. More importantly, during the continuous oil-water pumping experiment, the foam has an efficiency of 98% and could maintain for more than 15 h, showing a promising prospect for cleaning large-scale oil pollution.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Eco-friendly; Oil-water separation; Poly(lactic acid); Polymer foam; Recyclability; Superhydrophobicity

Facile preparation of multifunctional superparamagnetic PHBV microspheres containing SPIONs for biomedical applications - Li, Wei; Zaloga, Jan; Ding, Yaping; Liu, Yufang; Janko, Christina; Pischetsrieder, Monika; Alexiou, Christoph; Boccaccini, Aldo R. (Scientific Reports, 2016)
The promising potential of magnetic polymer microspheres in various biomedical applications has been frequently reported. However, the surface hydrophilicity of superparamagnetic iron oxide nanoparticles (SPIONs) usually leads to poor or even failed encapsulation of SPIONs in hydrophobic polymer microspheres using the emulsion method. In this study, the stability of SPIONs in poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) solution was significantly increased after surface modification with lauric acid. As a result, magnetic PHBV microspheres with high encapsulation efficiencies (71.0-87.4%) were prepared using emulsion-solvent extraction/evaporation method. Magnetic resonance imaging (MRI) showed significant contrast for the magnetic PHBV microspheres. The toxicity of these magnetic PHBV microspheres towards human T-lymphoma suspension cells and adherent colon carcinoma HT-29 cells was investigated using flow cytometry, and they were shown to be non-toxic in a broad concentration range. A model drug, tetracycline hydrochloride, was used to demonstrate the drug delivery capability and to investigate the drug release behavior of the magnetic PHBV microspheres. The drug was successfully loaded into the microspheres using lauric acid-coated SPIONs as drug carrier, and was released from the microspheres in a diffusion controlled manner. The developed magnetic PHBV microspheres are promising candidates for biomedical applications such as targeted drug delivery and MRI.

Facile strategy for advanced selectivity and sensitivity of SnO2 nanowire-based gas sensor using chemical affinity and femtosecond laser irradiation - Park, Hyoungwon; Kim, Jae Hun; Shin, Won Sang; Mirzaei, Ali; Kim, Yoon Jun; Kim, Sang Sub; Halik, Marcus; Park, Changkyoo (Sensors and Actuators B-Chemical, 2022)
This study proposes an effective strategy to improve the selectivity and response of SnO2 nanowire (NW)-based gas sensors. Self-assembled monolayer (SAM) functionalization of SnO2 NWs enhances the gas selectivity by tuning the surface chemical states. Different chemical moieties with alkyl and fluoroalkyl of the SAM molecules are adopted for the chemical affinities toward the corresponding target gas molecules. The alkyl and fluoroalkyl moieties show excellent selectivity toward CH4 and C3F8, respectively, owing to the strong chemical affinity between the moieties and gases. Post-treatment femtosecond (FS) laser irradiation with different laser fluences is applied to the SAM-functionalized SnO2 NW-based gas sensor. The FS laser-irradiated SnO2 NWs show an enhanced sensor response with higher resistance values and shorter response and recovery times compared to those of the pristine SnO2 NWs. Transmission electron microscopy analysis reveals that the FS laser irradiation induces the formation of embossing surface on the SnO2 NW, creating additional gas adsorption sites. Moreover, twin structures develop on the SnO2 NWs with increasing laser fluences. Electron energy loss spectroscopy analysis supports that the FS laser irradiation creates non-stoichiometric SnO and SnOx phases, providing O vacancies and improved response.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Femtosecond laser irradiation; Gas sensors; Self-assembled monolayers; SnO; Surface functionalization

Failure of Silicone Breast Implants – New Insights by Mapping the Mechanical Properties of Implant Shells - Schubert, Dirk W.; Horch, Raymund E.; Kaschta, Joachim; Daenicke, Jonas; Walter, Bastian (13th Bayreuth Polymer Symposium, 2013)

Failure of Silicone Breast Implants – New Insights by Mapping the Mechanical Properties of Implant Shells - Schubert, Dirk W.; Kaschta, Joachim; Horch, Raymund E.; Walter, Bastian; Daenicke, Jonas (Book of Abstracts, 2013)

Failure of Silicone Breast Implants – Novel Insights by Mapping the Mechanical Properties of Implant Shells - Schubert, Dirk W.; Horch, Raymund E.; Kaschta, Joachim; Daenicke, Jonas; Walter, Bastian (Nordic Polymer Days, 2013)

Failure of silicone breast implants – Novel insights on the mechanical properties of implant shells - Schubert, Dirk W. (Europe Africa Conference 2017 of the Polymer Processing Society, 2017)

Faserherstellung - Schubert, Dirk W. (Saechtling Kunststoff-Handbuch, 2022)
Organische Fasern lassen sich nach der Art ihrer Herstellung, des Ussprings ihres Materials oder ihres Faserdurchmessers einteilen.<br
Keywords: Faserherstellung; Melt-blown-Verfahren; Vliesstoffherstellung; SMS-Vliesstoffe

Fetal bovine serum (FBS): Past – present – future - Thieme, Daniel; et al. (Alternatives To Animal Experimentation, 2017)

Fibre spinning and non-woven evaluation - Voigt, Monika; Lanyi, Franz; Leucker, Karsten; Schubert, Dirk W. (Book of Abstracts, 2016)
Fibre spinning is a very effective technique that allows the continuous manufacturing of fibers. This technique can be applied for synthetic fibers, biopolymers, polymers with additives etc. Furthermore fibers can be structured during the manufacturing process, single fibers as well as bundles. Here we want to give an overview on the basic principles in a pilot spinning machine. Main parameters are the polymer parameters as viscosity, molecular mass, etc. Secondly, process parameters as the through-put, take-up speed, process temperatures (melt/ quenching) and others needs to be controlled. Finally, ambient conditions (temperature/ humidity) play an important role. For the evaluation of the fibre composition and the degradation, there are thermogravimetric analysis (TGA), gel permeation chromatography (GPC), differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR) the methods of choice. Mechanical properties determined in single fibre tensile tests need to be investigated as well. The investigation on the linting and pilling behaviour of fibres and textiles are necessary, too. Last but not least, surface energy investigations regarding the wetting of the material and optical characterization to investigate the morphology and related fluid structure interaction are highly relevant for application.

Field-induced modification of the electronic structure in BTBT-based organic thin films observed by NEXAFS spectroscopy - Johnson, Manuel; Hawly, Tim; Zhao, Baolin; Halik, Marcus; Nefedov, A.; Fink, Rainer (Applied Physics Letters, 2022)
We present an in operando near-edge x-ray absorption fine structure (NEXAFS) study on p-type [11-(benzo[b]benzo[4,5]thieno[2,3-d]thiophen-2-yl)dodecyl)] BTBT-based self-assembled monolayer (BTBT-SAM) films. As a 2D-model system, the BTBT-SAM offers direct insight into the active organic semiconductor layer without interfering bulk materials. This allows for the observation of polaronic states caused by charged species at the dielectric/organic interface. Linear NEXAFS dichroism is employed to derive the molecular orientation of the BTBT subunit. Field-induced modifications in the unoccupied molecular orbitals are observed in the NEXAFS spectra. The spectral changes in the on- and off-states are discussed in the context of polaron formation due to charge accumulation induced by the applied electric field. Published under an exclusive license by AIP Publishing.
CRIS-Team WoS Importer:2022-12-02

Film blowing of linear and long-chain branched poly(ethylene terephthalate) - Härth, Michael; Dörnhöfer, Andrea (Polymers, 2020)
Film blowing of Poly(ethylene terephthalate) (PET) is challenging due its inherently low melt viscosity and poor melt strength. In this study, it is shown how the rheological properties of a commercial PET can be altered by reactive extrusion using either pyromellitic dianhydride (PMDA) or a multifunctional epoxy (Joncryl® ADR 4368) as chain extender, in order to improve the processing behavior during film blowing. The modified materials were characterized by shear and elongation rheometry and relevant processing characteristics, like melt pressure, bubble stability, and film thickness uniformity, were used to assess the influence of the type of modifier on processing and product performance. It is shown that PMDA is useful to increase the melt strength which leads to an improved bubble stability, while epoxy modified PET shows a reduced drawability that can cause problems at high take-up ratios. On the other hand, the epoxy modifier indicates a pronounced strain hardening during elongational deformation, and therefore leads to a better film thickness uniformity compared to the neat PET and the PET modified with PMDA. The differences with respect to processing performance are discussed and ascribed to the molecular structure of the materials.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Chain extender; Extensional viscosity; Film blowing; Film uniformity; Long-chain branches; Poly(ethylene terephthalate); Rheology

Flexible and thin multifunctional waterborne polyurethane/Ag film for high-efficiency electromagnetic interference shielding, electro-thermal and strain sensing performances - Jia, Yunpeng; Sun, Ruizhou; Pan, Yamin; Wang, Xin; Zhai, Zhanyu; Min, Zhiyu; Zheng, Guoqiang; Liu, Chuntai; Shen, Changyu; Liu, Xianhu (Composites Part B-Engineering, 2021)
With the rapid development of the flexible electronics industry, the range of multifunctional applications of materials has become extensive. But it is still a challenge to apply flexible materials to different fields while ensuring corresponding performance. Herein, a simple and available approach is addressed to fabricate conductive polymer composite films supported on Ag flakes and waterborne polyurethane (WPU) by spraying. The WPU/Ag films with uniform structure show outstanding flexibility and electromagnetic interference shielding effectiveness of 68.9 dB with thickness of only 50 μm, and could sustain a high standard even undergoing excessive mechanical deformations. Besides, the resulted films possess prominent electro-thermal effect, which can achieve a temperature of over 120 °C by applying a low voltage of 2 V, and the heat can be dissipated rapidly along with the connecting Ag network. Moreover, it shows a high gauge factor (229.2), good durability and reproductivity (over 1000 cycles), and rapid response time to strain (50 ms), which can be potentially used in the field of human movement monitoring and wearable electronic devices. These results indicate the multifunction of the WPU/Ag film, which could widen its practical applications after the corresponding treatment.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Conductivity; Electromagnetic interference shielding; Joule heating; Polymer composites; Strain sensor

Flexible, conductive, and anisotropic thermoplastic polyurethane/polydopamine /MXene foam for piezoresistive sensors and motion monitoring - Chen, Qiang; Gao, Qingsen; Wang, Xin; Schubert, Dirk W.; Liu, Xianhu (Composites Part A-Applied Science and Manufacturing, 2022)
It is a challenge to manufacture pressure sensing materials with flexibility, high sensitivity, wide detection range for the development of intelligent electronic products. Herein, a pressure sensor based on thermoplastic polyurethane (TPU)/polydopamine (PDA)/MXene conductive composite foam (TPMF) was prepared by a combination of directional freezing and dip-coating methods. The compressive strength of anisotropic TPU foam (TF) in the vertical direction is increased by 48.1% compared with isotropic foam. Besides, the conductive foam (0.25 S/m) with an MXene content of 3.45 wt% exhibits low density (105.5 mg/cm3), high porosity (91.2%) and good resistance response behavior. The sensor based on TPMF exhibits excellent flexibility, fast response times (∼40 ms), and good durability over 5000 cycles. Furthermore, the composite foam has excellent recognition ability for different compressive strain amplitudes (up to 80%) and a wide stress range (10 Pa-122.5 kPa), as well as a high gauge factor (GF) up to 2.36 in the strain range of 2.5%-20%. The sensor has shown application potential in many fields, including voice recognition, health monitoring, motion monitoring, and artificial electronic skin.
CRIS-Team Scopus Importer:2022-01-28
Keywords: A. Foam; B. Anisotropy; B. Electrical properties; Sensor

Flexible copper-7,7,8,8 tetracyanochinodimethane memory devices - Operation, cross talk and bending - Novak, Michael; Burkhardt, Martin; Jedaa, Abdesselam; Halik, Marcus (Thin Solid Films, 2010)
Keywords: Device bending; Cross talk; Non-volatile memory

Flexible Copper-7,7,8,8 Tetracyanochinodimethane Memory Devices - Operation, Cross Talk and Bending - Novak, Michael; Burkhardt, Martin; Jedaa, Abdesselam; Halik, Marcus (Thin Solid Films, 2010)
Non-volatile memory devices based on the charge transfer complex copper-7,7,8,8 tetracyanochinodimethane were fabricated on ridged and flexible substrates with special emphasis on their general functionality and cross talk behaviour in 4 × 4 passive matrix arrays. Device characteristics have been investigated at elevated temperatures during operation (ranging from room temperature to 120 °C) under ambient conditions without encapsulation. To explore the influence of mechanical stress on device performance, the memory cells on flexible polyethylene terephthalate substrates were bended during operation, up to a convex and concave radius of 4 mm. The detected shift of the switching voltages and the decrease of reliability can be attributed to stress induced cracks in the active layer.

Flexible Organic Circuits with Printed Gate Electrodes - Zschieschang, Ute; Klauk, Hagen; Halik, Marcus; Schmid, Günter; Dehm, C. (Advanced Materials, 2003)

Flexible Organic Complementary Circuits - Klauk, Hagen; Halik, Marcus; Zschieschang, Ute; Eder, F.; Rhode, D.; Schmid, Günter; Dehm, C. (IEEE Transactions on Electron Devices, 2005)

Flow and hydrodynamic shear stress inside a printing needle during biofabrication - Müller, Sebastian J.; Mirzahossein, Elham; Iftekhar, Emil N.; Bächer, Christian; Schrüfer, Stefan; Schubert, Dirk W.; Fabry, Ben; Gekle, Stephan (PLoS ONE, 2020)
We present a simple but accurate algorithm to calculate the flow and shear rate profile of shear thinning fluids, as typically used in biofabrication applications, with an arbitrary viscosity-shear rate relationship in a cylindrical nozzle. By interpolating the viscosity with a set of power-law functions, we obtain a mathematically exact piecewise solution to the incompressible Navier-Stokes equation. The algorithm is validated with known solutions for a simplified Carreau-Yasuda fluid, full numerical simulations for a realistic chitosan hydrogel as well as experimental velocity profiles of alginate and chitosan solutions in a microfluidic channel. We implement the algorithm in an easy-to-use Python tool, included as Supplementary Material, to calculate the velocity and shear rate profile during the printing process, depending on the shear thinning behavior of the bioink and printing parameters such as pressure and nozzle size. We confirm that the shear stress varies in an exactly linear fashion, starting from zero at the nozzle center to the maximum shear stress at the wall, independent of the shear thinning properties of the bioink. Finally, we demonstrate how our method can be inverted to obtain rheological bioink parameters in-situ directly before or even during printing from experimentally measured flow rate versus pressure data.
CRIS-Team Scopus Importer:2020-08-07

Flow behavior of polypropylenes with different molecular structures in a coat-hanger die - Grieß, Hans Jürgen; Münstedt, Helmut (Polymer Engineering and Science, 2012)
An experimental investigation of the flow behavior of three polypropylene melts with different molecular structures during extrusion through a coat-hanger die is presented. Two linear and one long-chain branched material, rheologically characterized in shear and elongation, were investigated. Using laser-Doppler velocimeter measurements of the velocity profiles across the gap height were performed at five various locations along the die. The uniformity of the velocity distribution along the die has been assessed using the maximum velocities v0 of the corresponding velocity profiles across the gap. The velocity distribution along the die changes with throughput and temperature. Regarding the rheological properties, it was found that the power-law index of the viscosity as a function of shear rate has a decisive influence on the uniformity of flow but that the pronounced strain hardening in elongation typical of the long-chain branched polypropylene is not reflected by the velocity distribution along the die. Copyright © 2012 Society of Plastics Engineers.
Created from Fastlane, Scopus look-up

Flow-induced changes in the structure of conductive polymer composites - Stary, Zdenek; Krückel, Johannes; Schubert, Dirk W. (8th Annual European Rheology Conference, 2013)

Fly-ash-based geopolymers: How the addition of recycled glass or red mud waste influences the structural and mechanical properties - Toniolo, Nicoletta; Taveri, Gianmarco; Hurle, Katrin; Roether, Judith; Ercole, P; Dlouhy⁠, Ivo; Boccaccini, Aldo R. (Journal of Ceramic Science and Technology, 2017)
Keywords: Fly ash; Geopolymers; Red mud; Waste glass

Foaming of thin films of a fluorinated ethylene propylene copolymer using supercritical carbon dioxide - Zirkel, Larissa; Jakob, Martin; Münstedt, Helmut (Journal of Supercritical Fluids, 2009)
The foaming of films of a fluorinated ethylene propylene copolymer (FEP) using supercritical carbon dioxide (scCO_2) was investigated. For this purpose, a one-step foaming process was applied to the films inside a pressure vessel at temperatures in excess of 200 °C and pressures up to 30 MPa. The films prepared show a homogeneous cellular structure with thin compact polymer layers on both sides. The foaming behaviour of the FEP films is determined in dependence on the exposure time of the polymer to the scCO_2, the processing temperature and pressure as well as on the pressure drop rate during the foaming process. The resulting density and the foam morphology can be related to the pressure level during the saturation process. The size of the cells generated mainly depends on the foaming temperature, whereas their number per volume is determined by the magnitude of the applied pressure. Furthermore, the pressure drop rate influences the size of the cells in a way that significantly fewer but larger bubbles are found for longer times of depressurizing. This finding can be explained by nucleation rates becoming the smaller the slower the rate of pressure decrease.
EAM Import::2019-03-14

Formation of Perfluoroalkyl Fullerene Alkylphosphonic Acid Self-Assembled Monolayers on Aluminum Oxide - Clikeman, Tyler T.; Schmaltz, Thomas; Halik, Marcus; Hirsch, Andreas; Strauss, Steven H.; Boltalina, Olga V. (ECS Journal of Solid State Science and Technology, 2017)

From Lab to Pilot Scale: Melt Electrospun Nanofibers of Polypropylene with Conductive Additives - König, Kylie; Langensiepen, Fabian; Seide, Gunnar; Daenicke, Jonas; Schubert, Dirk W. (Journal of Nanomaterials & Molecular Nanotechnology, 2019)
In this paper, the feasibility of fabricating polypropylene (PP) nanofibers was investigated using conductive additives such as sodium stearate (NaSt), sodium oleate (NaOl) and Irgastat during melt electro spinning with a single nozzle lab and a 600- nozzle pilot scale device. Varying PP grades of high melt flow indices (MFI=450-1200 g/10 min) were used with different amounts of additives. The effects of the additives on the fiber diameters, thermal properties, electrical conductivity and polymer degradation were investigated. On a lab scale, fiber diameters of less than 500 nm were achieved with the compound of PP HL712FB, 4 wt% NaSt and 2 wt% Irgastat. The lab scale device was extended by a heatable spinning chamber, which affects fiber diameter reduction. The fabrication of nanofibers was in principle attributed to the increase in electrical conductivity with the introduction of the additives. On a pilot scale, the smallest fiber diameter of 6.64 μm could be achieved with PP HL508FB and 2 wt% NaSt. The comparison between the production of the fibers with a single nozzle and the pilot scale plant has revealed that a transfer of results is not possible without further ado. Due to the higher dwell time in the nozzle, a strong thermal degradation of the polymer could be detected with the high temperature size exclusion chromatography, whereby NaOl had the strongest influence on the thermal degradation. The high melt flow PP HL712FB and its compounds could not be processed with the pilot scale device due to its low viscosity, resulting in an insufficient pressure built up within the spinneret. Another reason for the non-spinnability of the material is the higher thermal and mechanical stress caused by the preceding melts preparation in an extrusion step. Further adjustments to the pilot plant are necessary to ensure a constant temperature distribution in the nozzle plate to achieve uniform fiber cross sections. The implementation of an uneven collector has successfully led to an even deposition of the fibers to obtain an isotropic non-woven fabri
Keywords: Melt electrospinning; Nanofiber; Non-woven; Fiber production; Process upscaling; Electrospinning; Melt spinning; Process development

From trash to treasure in additive manufacturing: Recycling of polymer powders by acid catalyzed hydrolysis - Hesse, Nicolas; Jaksch, Andreas; Kaschta, Joachim; Groh, Dominik; Drummer, Dietmar; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2023)
A persistent problem in laser powder bed fusion (PBF) additive manufacturing (AM) of polymers is the accumulation of used feedstock material that cannot be reprocessed due to alterations in the physical and chemical structure upon ageing at elevated temperatures. The chemical ageing of polyamide 12, the most frequently used feedstock in PBF of polymers, occurs due to solid-state post-condensation during the AM process and can be reversed by appropriate processing. This paper investigates the application of acid-catalyzed hydrolytic reconditioning to restore virgin powder properties from used and annealed feedstock material, highlighting a pathway to more sustainability in AM. The proposed method is optimized towards PBF-printing relevant properties and mechanical characteristics of parts build with the recycled feedstock material, which are benchmarked against conventional powder refreshing strategies.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Hydrolysis; Polyamide 12; Polymer ageing; Polymer recycling; Powder bed fusion; Powder characterization

Fullerene Van der Waals Oligomers as Electron Traps - Shubina, Tatyana; Sharapa, Dmitry; Schubert, Christina; Zahn, Dirk; Halik, Marcus; Keller, Paul A.; Pyne, Stephen G.; Jennepalli, Sreenu; Guldi, Dirk Michael; Clark, Timothy (Journal of the American Chemical Society, 2014)
Density functional theory calculations indicate that van der Waals fullerene dimers and larger oligomers can form interstitial electron traps in which the electrons are even more strongly bound than in isolated fullerene radical anions. The fullerenes behave like "super atoms", and the interstitial electron traps represent one-electron intermolecular σ-bonds. Spectroelectrochemical measurements on a bis-fullerene-substituted peptide provide experimental support. The proposed deep electron traps are relevant for all organic electronics applications in which non-covalently linked fullerenes in van der Waals contact with one another serve as n-type semiconductors.

Fully Patterned All-Organic Thin Film Transistors - Halik, Marcus; Klauk, Hagen; Zschieschang, Ute; Kriem, Tarik; Schmid, Günter; Radlik, Wolfgang; Wussow, Klaus (Applied Physics Letters, 2002)

Fully Patterned Low-Voltage Transparent Metal Oxide Transistors Deposited Solely by Chemical Spray Pyrolysis - Faber, Hendrik; Butz, Benjamin; Dieker, Christel; Spiecker, Erdmann; Halik, Marcus (Advanced Functional Materials, 2013)
All-inorganic transparent thin-film transistors deposited solely by the solution processing method of spray pyrolysis are reported. Different precursor materials are employed to create conducting and semiconducting species of ZnO acting as electrodes and active channel material, respectively, as well as zirconium oxide as gate dielectric layer. Additionally, a simple stencil mask system provides sufficient resolution to realize the necessary geometric patterns. As a result, fully functional low-voltage n-type transistors with a mobility of 0.18 cm2 V−1 s−1 can be demonstrated via a technique that bears the potential for upscaling. A detailed microscopic evaluation of the channel region by electron diffraction, high-resolution and analytical TEM confirms the layer stacking and provides detailed information on the chemical composition and nanocrystalline nature of the individual layers.

Fully Printed Infrared Photodetectors from PbS Nanocrystals with Perovskite Ligands - Yousefiamin, Amirabbas; Killilea, Niall Andrew; Sytnyk, Mykhailo; Maisch, Philipp; Tam, Kwok-Kan; Egelhaaf, Hans-Joachim; Langner, Stefan; Stubhan, Tobias; Brabec, Christoph; Rejek, Tobias; Halik, Marcus; Poulsen, Katharina; et al. (ACS nano, 2019)
Colloidal nanocrystals from PbS are successfully applied in highly sensitive infrared photodetectors with various device architectures. Here, we demonstrate all-printed devices with high detectivity (similar to 10(12) cm Hz(1/2) /W) and a cut-off frequency of >3 kHz. The low material consumption (<0.3 mg per detector) and short processing time (14 s per detector) enabled by the automated printing promises extremely low device costs. To enable all-printed devices, an ink formulation was developed based on nanocrystals stabilized by perovskite-like methylammonium iodobismuthate ligands, which are dispersed in a ternary solvent. Fully inkjet printed devices based on this solvent were achieved with printed silver electrodes and a ZnO interlayer. Considerable improvements were obtained by the addition of small amounts of the polymer poly(vinylpyrrolidone) to the ink. The polymer improved the colloidal stability of the ink and its film-formation properties and thus enabled the scalable printing of single detectors and detector arrays. While photoconductors were shown here, the developed ink will certainly find application in a series of further electronic devices based on nanocrystals from a broad range of materials.
Keywords: colloidal nanocrystals; infrared detectors; inkjet printing; PbS; solution processing

Gamma interferon-induced guanylate binding protein 1 is a novel actin cytoskeleton remodeling factor - Ostler, Nicole; Britzen-Laurent, Nathalie; Liebl, Andrea; Naschberger, Elisabeth; Lochnit, Guenter; Ostler, Markus; Forster, Florian; Kunzelmann, Peter; Ince, Semra; Supper, Verena; Praefcke, Gerrit J. K.; Schubert, Dirk W.; et al. (Molecular and Cellular Biology, 2014)
Gamma interferon (IFN-?) regulates immune defenses against viruses, intracellular pathogens, and tumors by modulating cell proliferation, migration, invasion, and vesicle trafficking processes. The large GTPase guanylate binding protein 1 (GBP-1) is among the cellular proteins that is the most abundantly induced by IFN-? and mediates its cell biologic effects. As yet, the molecular mechanisms of action of GBP-1 remain unknown. Applying an interaction proteomics approach, we identified actin as a strong and specific binding partner of GBP-1. Furthermore, GBP-1 colocalized with actin at the subcellular level and was both necessary and sufficient for the extensive remodeling of the fibrous actin structure observed in IFN-?-exposed cells. These effects were dependent on the oligomerization and the GTPase activity of GBP-1. Purified GBP-1 and actin bound to each other, and this interaction was sufficient to impair the formation of actin filaments in vitro, as demonstrated by atomic force microscopy, dynamic light scattering, and fluorescence-monitored polymerization. Cosedimentation and band shift analyses demonstrated that GBP-1 binds robustly to globular actin and slightly to filamentous actin. This indicated that GBP-1 may induce actin remodeling via globular actin sequestering and/or filament capping. These results establish GBP-1 as a novel member within the family of actin-remodeling proteins specifically mediating IFN-?-dependent defense strategies.
EVALuna2:15143

Gelatin coated 45S5 Bioglass®-derived scaffolds for bone tissue engineering - Metze, Anke-Lisa; Grimm, Alexandra; Nooeaid, Patcharakamon; Roether, Judith; Hum, Jasmin; Newby, Phillipa; Schubert, Dirk W.; Boccaccini, Aldo R. (Key Engineering Materials, 2013)
Highly porous 45S5 Bioglass® scaffolds were fabricated by the foam replica method and successfully coated with a well attached gelatin layer by dipping and pipetting methods. Depending on macropore size of the scaffold and gelatin concentration, mechanically enhanced scaffolds with improved compressive strength in comparison to uncoated scaffolds could be obtained while preserving the high and interconnected porosity that is required for bone in-growth. Moreover, the scaffolds bioactivity by immersion in simulated body fluid (SBF) was investigated showing that gelatin coating preserves the intrinsic bioactivity of the Bioglass® scaffold. It was also shown that the gelatin layer can be loaded with tetracycline hydrochloride for developing scaffolds with drug delivery capability.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.gelati
Keywords: 45S5 Bioglass®; Gelatin; Scaffold; Tetracycline Hydrochloride

Gelation of polyvinylbutyral solutions by the addition of tetrabutyl orthotitanate - Wegener, Carsten Moritz; Kaschta, Joachim; Münstedt, Helmut; Roosen, Andreas (Rheologica Acta, 2014)
This paper discusses the gelation of polyvinylbutyral (PVB) solutions by the addition of tetrabutyl orthotitanate. The addition of around 0.10 vol.% tetrabutyl orthotitanate to an ethanol-based PVB solution already causes a pronounced gelation. For the characterization of this gelation reaction, different rheological measurements are used. The characterization is mainly performed in the linear viscoelastic regime. Time sweeps prove the stability of the samples during the measuring time. Frequency sweeps are used to investigate the state of gelation after different reaction times as well as the dependence of the degree of the gelation on the tetrabutyl orthotitanate concentration. Furthermore, the gelation point is determined by measuring the loss factor tan delta as a function of frequency. A strong influence of water on the degree of gelation is shown; by the addition of different amounts of water, the gelation can be controlled or even avoided. Amplitude sweeps reveal the breakdown of certain network structures at high amplitudes which recover after the strain is lowered.
Keywords: Polyvinylbutyral (PVB); Gelation with titanate; Dynamic mechanical analysis (DMA); Network characterization; Gel point

Generalized enhancement of charge injection in bottom contact/top gate polymer field-effect transistors with single-walled carbon nanotubes - Wang, Ming; Jakubka, Florian; Gannott, Florentina; Schweiger, Manuel; Zaumseil, Jana (Organic Electronics, 2014)
We investigate the influence of small amounts of dispersed single-walled carbon nanotubes (SWNTs) on the contact resistance and device characteristics of bottom contact/top gate polymer field-effect transistors (FETs). Five conjugated polymers representing different classes of polymer semiconductors with different HOMO/LUMO levels are employed, namely, polythiophenes (P3HT), polyphenylenevinylenes (MDMO-PPV), polyfluorenes (F8T2), naphthalene-bis(dicarboximide) bithiophene copolymers (P(NDI2OD-T2)), and diketopyrrolo-pyrrole-bithiophene copolymers (DPPT-TT). In all cases the presence of dispersed SWNTs reduces non-ohmic contact resistance and lowers threshold and onset voltages for charge transport. In some cases inherent ambipolar charge transport in conjugated polymers (F8T2 and P(NDI2OD-T2)) is revealed. The concentration of the SWNTs within the semiconducting layer remains below the percolation limit and thus the apparent mobilities and on/off ratios are still determined by the polymer and independent of the specific type of the carbon nanotubes (metallic or semiconducting). The degree of enhancement depends both on the energy level offset between the injecting gold electrode and the HOMO/LUMO level (i.e., Schottky barrier) and the charge carrier mobility of the respective polymer. The simplicity of this injection enhancement method and its broad applicability make it a step toward high performance polymer transistors without injection limitations.
EAM Import::2019-03-13

Gezielte Beeinflussung der einsatzrelevanten Bauteileigenschaften kaltfließgepresster Zahnräder - Rohrmoser, Andreas; Kiener, Christoph; Schubert, Dirk W.; Hagenah, Hinnerk; Drummer, Dietmar; Merklein, Marion (Konstruktion, 2019)
LFT Import::2019-07-29 (2385)

Graded Cellular Ceramics from Continuous Foam Extrusion - Ceron Nicolat, Bruno; Wolff, Friedrich; Dakkouri, Andrea S.; Fey, Tobias; Münstedt, Helmut; Greil, Peter (Advanced Engineering Materials, 2012)
Cylindrical SiOC foam filaments with a radial gradient in pore cell size were processed by continuous extrusion foaming of a methyl polysilsesquioxane. Upon leaving the extrusion nozzle foaming was initiated by pressure release which caused precipitation of supersaturated carbon dioxide from the polymer filament. Rapid cooling of the thin filaments generates a radial gradient of melt viscosity which gives rise for formation of closed cell morphology of isotropic pore cells in the core (diameter?<!–?200?mu m) and non-isotropic pore cells near the sur-face (shell; <20?mu m). After pyrolysis at temperatures ranging from 800 to 1400?degrees C the stabilized polymer gradient foams were converted into closed cell SiOC ceramic gradient foams. XRD reveals the SiOC residue to be amorphous up to 1200?degrees C whereas crystallization of beta-SiC was observed at 1400?degrees C. A superior compressive strength of 9?MPa and a Young's modulus of 7?GPa at a relative density of 0.18 were measured at an optimum pyrolysis temperature of 1000?degrees C.–>
Keywords: carbon dioxide foaming; graded porosity; polymer derived cellular ceramics

Green Processing of Metal Oxide Core-Shell Nanoparticles as Low-Temperature Dielectrics in Organic Thin-Film Transistors - Portilla Berlanga, Luis; Etschel, Sebastian; Tykwinski, Rik; Halik, Marcus (Advanced Materials, 2015)
TiO2, Fe3O4, AlOx, ITO (indium tin oxide), and CeO2 nanoparticles are tailored to exhibit excellent dispersability in deionized water and alcohols. The latter provides an ecofriendly solution for processing metal oxide nanoparticles at a neutral pH. Water‐processed dielectrics from the metal oxide nanoparticles are incorporated into organic thin‐film transistors fabricated on rigid and flexible substrates.
Keywords: water soluble; nanoparticles; organic electronics; metal oxides; ecofriendly

Green Processing of Metal Oxide Core–Shell Nanoparticles as Low-Temperature Dielectrics in Organic Thin-Film Transistors - Portilla Berlanga, Luis; Etschel, Sebastian; Tykwinski, Rik; Halik, Marcus (Advanced Materials, 2015)
TiO2, Fe3O4, AlOx , ITO (indium tin oxide), and CeO2 nanoparticles are tailored to exhibit excellent dispersability in deionized water and alcohols. The latter provides an ecofriendly solution for processing metal oxide nanoparticles at a neutral pH. Water processed dielectrics from the metal oxide nanoparticles are incorporated into organic thin-film transistors fabricated on rigid and flexible substrates.

Hemp Fiber Reinforced Red Mud/Fly Ash Geopolymer Composite Materials: Effect of Fiber Content on Mechanical Strength - Taye, Eyerusalem; Roether, Judith; Schubert, Dirk W.; Redda, Daniel Tilahun; Boccaccini, Aldo R. (Materials, 2021)
Novel hemp fiber reinforced geopolymer composites were fabricated. The matrix was a new geopolymer based on a mixture of red mud and fly ash. Chopped, randomly oriented hemp fibers were used as reinforcement. The mechanical properties of the geopolymer composite, such as diametral tensile (DTS) (or Brazilian tensile) strength and compressive strength (CS), were measured. The geopolymer composites reinforced with 9 vol.% and 3 vol.% hemp fiber yielded average DTS values of 5.5 MPa and average CS values of 40 MPa. Scanning electron microscopy (SEM) studies were carried out to evaluate the microstructure and fracture surfaces of the composites. The results indicated that the addition of hemp fiber is a promising approach to improve the mechanical strength as well as to modify the failure mechanism of the geopolymer, which changed from brittle to “pseudo-ductile.<br
Keywords: hemp fiber; geopolymer composite; mechanical properties; red mud; fly ash; microstructural analysis

Hierarchical Assembly and Sensing Activity of Patterned Graphene-Hamilton Receptor Nanostructures - Bao, Lipiao; Zhao, Baolin; Ali, Muhammad; Assebban, M'hamed; Yang, Bowen; Kohring, Malte; Ryndyk, Dmitry A.; Heine, Thomas; Weber, Heiko B.; Halik, Marcus; Hauke, Frank; Hirsch, Andreas (Advanced Materials Interfaces, 2022)

Hierarchical Slice Patterns Inhibit Crack Propagation in Brittle Sheets - Zaiser, Michael; Hosseini, Seyyed Ahmad; Moretti, Paolo; Mäkinen, Tero; Koivisto, Juha; Pournajar, Mahshid; Himmler, Marcus; Redel, Michael; Schubert, Dirk W.; Alava, Mikko (Physical Review Applied, 2022)
By introducing hierarchical patterns of load-parallel cuts into axially loaded brittle sheets, the resistance to propagation of mode-I cracks is very significantly enhanced. We demonstrate this effect by simulation of two-dimensional beam network models and experimentally by testing paper and polystyrene (PS) sheets that are sliced with a laser cutter to induce load-perpendicular hierarchical cut patterns. Samples endowed with nonhierarchical reference patterns of the same cut density and nonsliced sheets are considered for comparison. We demonstrate that hierarchical slicing can increase failure load, apparent fracture toughness, and work of fracture of notched paper and PS sheets by factors between 2 and 10.<br

Highly Efficient Encapsulation and Phase Separation of Apolar Molecules by Magnetic Shell‐by‐Shell‐Coated Nanocarriers in Water - Luchs, Tobias; Sarcletti, Marco; Zeininger, Lukas; Portilla Berlanga, Luis; Fischer, Christian; Harder, Sjoerd; Halik, Marcus; Hirsch, Andreas (Chemistry - A European Journal, 2018)
We report on the development of a supramolecular nanocarrier concept that allows for the encapsulation and separation of small apolar molecules from water. The nanocarriers consist of shell‐by‐shell‐coated nanoparticles such as TiO2 and ferromagnetic Fe3O4. The first ligand shell is provided by covalently bound hexadecyl phosphonic acid (PAC16) and the second shell by noncovalently assembled amphiphiles rendering the hybrid architecture soluble in water. Agitation of these constructs with water containing the hydrocarbons G1–G4, the fluorescent marker G5, the polychlorinated biphenyl PCB 77, or crude oil leads to a very efficient uptake (up to 411 %) of the apolar contaminant. In case of the hybrids containing a Fe3O4 core, straightforward phase separation by the action of an external magnet is provided. The load can easily be released by a final treatment with an organic solven
Keywords: hydrophobic molecules; nanocarriers; nanoparticles; noncovalent interactions; separation

Highly elastomeric poly(3-hydroxyoctanoate) based natural polymer composite for enhanced keratinocyte regeneration - Rai, Ranjana; Roether, Judith; Knowles, Jonathan C.; Mordan, Nicola; Salih, Vehid; Locke, Ian C.; Gordge, Michael P.; McCormick, Aine; Mohn, Dirk; Stark, Wendelin J.; Keshavarz, Tajalli; Boccaccini, Aldo R.; et al. (International Journal of Polymeric Materials and Polymeric Biomaterials, 2017)
Keywords: Bioactive glass; composites; poly(3-hydroxyoctanoate); skin tissue engineering; wound healing

Highly oriented conductive electro-spun fibers of biodegradable polymers - Revealing the electrical percolation thresholds - Munawar, Muhammad; Schubert, Dirk W. (16th Biennial - Bayreuther Polymer Symposium, 2019)

Highly Oriented Electrospun Conductive Nanofibers of Biodegradable Polymers-Revealing the Electrical Percolation Thresholds - Munawar, Muhammad (Nordic Rheology Conference & Nordic Polymer Days 2021, 2021)

Highly Oriented Electrospun Conductive Nanofibers of Biodegradable Polymers-Revealing the Electrical Percolation Thresholds - Munawar, Muhammad (31st Annual Conference of the European Society for Biomaterials (ESB 2021), together with the 43rd Annual Congress of the Iberian Society of Biomechanics and Biomaterials (SIBB), Porto, 2021)

Highly Oriented Electrospun Conductive Nanofibers of Biodegradable Polymers-Revealing the Electrical Percolation Thresholds - Munawar, Muhammad; Schubert, Dirk W. (ACS Applied Polymer Materials, 2021)
An electrospinning process with a special rotating collector electrode is used to generate highly oriented electrospun conductive fiber composites (ECFCs) of biodegradable polymers. Poly(ethylene oxide) (PEO), polycaprolactone (PCL), and polylactic acid (PLA) are blended with intrinsically conductive polymers (ICPs) fillers of poly(3,4-ethylenedioxythiophene) (PEDOT) and polyaniline (PANi). As the proportion of filler increases, the number of “conductive pathways” grow, and consequently the conductivity of the ECFCs also increases. A procedure is developed for calculating the volume fraction (φ) of filler, density, and conductivity of electrospun nanofibers. The conductivity as a function of filler fraction is shown and described by using a McLachlan equation for the first time to reveal the electrical percolation thresholds (φc) of nanofibers. During the annealing process, a buildup of additional conductive channels within ECFCs is responsible for increasing inter and intrachain conductivities among fillers and matrices. Therefore, annealed ECFCs transport charge more efficiently due to an increase in continuous pathways, which lead to superior electrical conductivity and lowering the percolation threshold. Moreover, a time–temperature effect on percolation thresholds of ECFCs is evident. The compatibility between filler and matrix and the inherent conductivity of filler and molar mass of matrix are among significant factors for determining φc. The fiber diameter and conductivity of ECFCs are both tunable. The comparative study shows that these highly oriented electrospun conductive nanofibers have great potential in various biomedical applications.<br
Keywords: conductive nanofiber; percolation threshold; electrical conductivity; annealing; orientation

Highly Oriented Electrospun Conductive Nanofibers of Biodegradable Polymers-Revealing the Electrical Percolation Thresholds - Munawar, Muhammad; Schubert, Dirk W. (6th European Symposium on Biomaterials and Related Areas BioMAT 2021, 2021)
An electrospinning process with a special rotating collector electrode is used to generate highly oriented electrospun conductive fiber composites (ECFCs) of biodegradable polymers. Poly(ethylene oxide) (PEO), polycaprolactone (PCL), and polylactic acid (PLA) are blended with intrinsically conductive polymers (ICPs) fillers of poly(3,4-ethylenedioxythiophene) (PEDOT) and polyaniline (PANi). As the proportion of filler increases, the number of “conductive pathways” grow, and consequently the conductivity of the ECFCs also increases. A procedure is developed for calculating the volume fraction (φ) of filler, density, and conductivity of electrospun nanofibers. The conductivity as a function of filler fraction is shown and described by using a McLachlan equation for the first time to reveal the electrical percolation thresholds (φc) of nanofibers. During the annealing process, a buildup of additional conductive channels within ECFCs is responsible for increasing inter and intrachain conductivities among fillers and matrices. Therefore, annealed ECFCs transport charge more efficiently due to an increase in continuous pathways, which lead to superior electrical conductivity and lowering the percolation threshold. Moreover, a time–temperature effect on percolation thresholds of ECFCs is evident. The compatibility between filler and matrix and the inherent conductivity of filler and molar mass of matrix are among significant factors for determining φc. The fiber diameter and conductivity of ECFCs are both tunable. The comparative study shows that these highly oriented electrospun conductive nanofibers have great potential in various biomedical application

Highly Sensitive Ultrathin Flexible Thermoplastic Polyurethane/Carbon Black Fibrous Film Strain Sensor with Adjustable Scaffold Networks - Wang, Xin; Liu, Xian Hu; Schubert, Dirk W. (Nano-Micro Letters, 2021)
In recently years, high-performance wearable strain sensors have attracted great attention in academic and industrial. Herein, a conductive polymer composite of electrospun thermoplastic polyurethane (TPU) fibrous film matrix-embedded carbon black (CB) particles with adjustable scaffold network was fabricated for high-sensitive strain sensor. This work indicated the influence of stereoscopic scaffold network structure built under various rotating speeds of collection device in electrospinning process on the electrical response of TPU/CB strain sensor. This structure makes the sensor exhibit combined characters of high sensitivity under stretching strain (gauge factor of 8962.7 at 155% strain), fast response time (60 ms), outstanding stability and durability (> 10,000 cycles) and a widely workable stretching range (0–160%). This high-performance, wearable, flexible strain sensor has a broad vision of application such as intelligent terminals, electrical skins, voice measurement and human motion monitoring. Moreover, a theoretical approach was used to analyze mechanical property and a model based on tunneling theory was modified to describe the relative change of resistance upon the applied strain. Meanwhile, two equations based from this model were first proposed and offered an effective but simple approach to analyze the change of number of conductive paths and distance of adjacent conductive particles.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2021-02-05
Keywords: Electronic skin; Electrospinning; Fitting model; Strain sensor

High-mobility organic thin film transistors based on a,a’-Didecyloligothiophenes - Halik, Marcus; Klauk, Hagen; Zschieschang, Ute; Schmid, Günter; Radlik, Wolfgang; Ponomarenko, S.; Kirchmeyer, S.; Weber, Werner (Journal of Applied Physics, 2003)

High-mobility polymer gate dielectric pentacene thin film transistors - Klauk, Hagen; Halik, Marcus; Zschieschang, Ute; Schmid, Günter; Radlik, Wolfgang; et al. (Journal of Applied Physics, 2002)

High-Mobility ZnO Nanorod Field-Effect Transistors by Self-Alignment and Electrolyte-Gating - Thiemann, Stefan; Gruber, Mathias; Lokteva, Irina; Halik, Marcus; Zaumseil, Jana (ACS Applied Materials and Interfaces, 2013)
High mobility, solution-processed field-effect transistors are important building blocks for flexible electronics. Here we demonstrate the alignment of semiconducting, colloidal ZnO nanorods by a simple solvent evaporation technique and achieve high electron mobilities in field-effect transistors at low operating voltages by electrolyte‐gating with ionic liquids. The degree of alignment varies with nanorod length, concentration and solvent evaporation rate. We find a strong dependence of electron mobility on the degree of alignment but less on the length of the nanorods. Maximum field-effect mobilities reach up to 9 cm2 V−1 s−1 for optimal alignment. Because of the low process temperature (150 °C), ZnO nanorod thin films are suitable for application on flexible polymer substrates.

High precision processing of flexible P3HT/PCBM modules with geometric fill factor over 95% - Kubis, Peter; Lucera, Luca; Machui, Florian; Spyropoulos, Georgios; Cordero, Johann; Frey, Alfred; Kaschta, Joachim; Voigt, Monika; Matt, Gebhard; Zeira, Eitan; Brabec, Christoph (Organic Electronics, 2014)
Flexible OPV modules, based on P3HT:PCBM as absorber layer, were manufactured with a power conversion efficiency over 3% and for a total area of 3500 mm(2) consisting of 14 in series interconnected cells. The modules utilize the excellent mechanical and the outstanding optical properties of sputtered transparent ITO-Metal-ITO (IMI) electrodes deposited on the PET foil on the one hand, and the combination of large area slot-die coating with high resolution ultrafast laser patterning on the other hand. The manufacturing of modules with outstanding performance was found to be reproducible. The right combination of innovative electrodes and smart roll-to-roll compatible processing technologies demonstrates a viable path towards high efficient industrial module technology. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Flexible transparent electrode; Flexible OPV module; Slot-die coating; Ultra-fast laser patterning; High geometric fill factor

High sensitive electrospun thermoplastic polyurethane/carbon nanotubes strain sensor fitting by a novel optimization empirical model - Wang, Xin; Qu, Muchao; Wu, Kuangqi; Schubert, Dirk W.; Liu, Xian Hu (Advanced Composites and Hybrid Materials, 2023)
A variety of high-performance strain sensors for monitoring changes in physical quantities have attracted considerable interest from academia and industry. In this work, a high sensitive flexible strain sensor is fabricated through electrospun thermoplastic polyurethane (TPU) fibrous film with dip-coating ultrasonication treated carbon nanotubes (CNTs). TPU/CNTs strain sensor exhibits an excellent comprehensive performance of high sensitivity (maximum gauge factor of 1571), outstanding tensile strength and toughness (stress > 24 MPa, strain > 400%), brilliant durability (10,000 cycles at 10% strain) and a widely workable stretching range (0–400%). Based on the properties of high sensitivity, wearable and wide workable, TPU/CNTs strain sensor has been prepared as a simple application for intelligent terminals, e-skins and body activity monitoring. More importantly, this work introduces a novel optimization empirical equation to describe and predict the conductive response on the stretching of the sensor. Compared with the general optimization model, the novel optimization empirical model presents a better fitting degree and more similar to the benchmark mathematic model from tunnelling theory. Furthermore, this model provides a good description of the changes in the conductive pathways during the operation of different sensors as well. Graphical Abstract: Fabrication of high-performance electrospun TPU/CNTs strain sensor and fitting by a novel optimization empirical equation to predict the conductive response. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-04-07
Keywords: Electronic skin; Electrospinning technology; High sensitive strain sensor; Novel optimization empirical model

High shunt resistance in polymer solar cells comprising a MoO3 hole extraction layer processed from nanoparticle suspension - Stubhan, Tobias; Ameri, Tayebeh; Salinas Batallas, Michael; Krantz, Johannes; Machui, Florian; Halik, Marcus; Brabec, Christoph (Applied Physics Letters, 2011)
In this report, we present solution processed molybdenum trioxide (MoO3) layers incorporated as hole extraction layer (HEL) in polymer solar cells (PSCs) and demonstrate the replacement of the commonly employed poly(3,4-ethylene dioxythiophene):(polystyrene sulfonic acid) (PEDOT:PSS). MoO3 is known to have excellent electronic properties and to yield more stable devices compared to PEDOT:PSS. We demonstrate fully functional solar cells with up to 65 nm thick MoO3 HEL deposited from a nanoparticle suspension at low temperatures. The PSCs with an active layer comprising a blend of poly(3-hexylthiophene) and [6,6]-phenyl-C61 butyric acid methyl ester and a MoO3 HEL show comparable performance to reference devices with a PEDOT:PSS HEL. The best cells with MoO3 reach a fill factor of 66.7% and power conversion efficiency of 2.92%. Moreover, MoO3 containing solar cells exhibit an excellent shunt behavior with a parallel resistance of above 100 kΩ cm2.

High speed determination of the degree of crosslinking of PEX using a rheological test - Falk, M.; Heiduk, I.; Kaschta, Joachim; Schubert, Dirk W. (10th Annual European Rheology Conference, 2015)

High speed determination of the degree of crosslinking of PEX using a rheological test - Heiduk, I.; Falk, M.; Kaschta, Joachim; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Host-Guest Systems on the Surface of Functionalized Superparamagnetic Iron Oxide Nanoparticles (SPIONs) Utilizing Hamilton Receptors and Cyanurate Derivative Molecules - Ali, Muhammad; Kataev, Evgeny; Müller, Johannes; Park, Hyoungwon; Halik, Marcus; Hirsch, Andreas (Chemistry - A European Journal, 2021)
The study of hydrogen bonding interactions at the level of functionalized nanoparticles remains highly challenging and poorly explored area. In this work, superparamagnetic iron oxide nanoparticles (SPIONs) were orthogonally functionalized using receptors bearing multiple hydrogen bonding motifs. Pristine SPIONs were modified by wet chemical processes with Hamilton receptors (hosts), or cyanurate-guest molecules linked to phosphonic acid moieties for monolayer functionalization. The modified surfaces were fully characterized and the number of attached ligands on the surface were determined. The host-guest interactions on the interface of modified SPIONs were investigated by using UV-Vis spectroscopic titrations. Functionalized SPIONs demonstrated two to three magnitudes stronger binding affinities as compared to the related molecular interactions in solution due to synergistic effects on complex surface environment. Higher supramolecular binding ratios of host-guest interactions on the modified surface were emerged. These studies provide fundamental insights into supramolecular complexations on the surface at solid-liquid interface systems with applications in engineered nanomaterials, nano-sensing devices, and drug delivery systems.
CRIS-Team Scopus Importer:2021-11-05
Keywords: artificial hydrogen bonds; functionalized nanoparticles; hamilton receptors; host-guest chemistry; SPIONs

How femtosecond laser irradiation can affect the gas sensing behavior of SnO2 nanowires toward reducing and oxidizing gases - Kim, Jae Hun; Park, Hyoungwon; Mirzaei, Ali; Hahm, Myung Gwan; Ahn, Sanghoon; Halik, Marcus; Park, Changkyoo; Kim, Sang Sub (Sensors and Actuators B-Chemical, 2021)
Generating oxygen vacancies on the metal oxides is an effective way to control their sensing properties. Furthermore, embossing surfaces are preferred to the flat surfaces for sensing studies due to providing of more adsorption sites, which is another key parameter for improvement of the gas sensing characteristics. In this study, we generated oxygen vacancies on SnO2 nanowires (NWs) by femtosecond (FS) laser irradiation with the different laser pulse energies of 0.025, 0.05, and 0.075 μJ, corresponding to the laser fluences of 138, 276, and 414 mJ/cm2. We investigated the effect of the FS laser irradiation on the response of the fabricated SnO2 NW gas sensors toward NO2 and toluene (C7H8) gases. The created oxygen vacancies and the response of the sensors were linked to the laser pulse energy. By studying the gas sensing characteristics of the sensors at various temperatures, we found that at 300 °C, the sensor irradiated at 0.025 μJ showed the highest response to C7H8, and the FS laser-irradiated sensors showed a lower response to the NO2 gas as compared to that of the non-irradiated sensor. The sensing mechanism of the gas sensors was comprehensively explained in terms of radial modulation of the SnO2 NWs, formation of SnO2 NW homojunctions, formation of embossing surfaces (increase of surface area) as well as formation of oxygen vacancies as a result of laser irradiation.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Femtosecond laser irradiation; Gas sensor; NO; Sensing mechanism; SnO; Toluene

Hybrid hydrogels based on keratin and alginate for tissue engineering - Silva, Raquel; Singh, Raminder; Sarker, Bapi; Papageorgiou, Dimitrios G.; Juhasz, Judith A.; Roether, Judith; Cicha, Iwona; Kaschta, Joachim; Schubert, Dirk W.; Chrissafis, Konstantinos; Detsch, Rainer; Boccaccini, Aldo R. (Journal of Materials Chemistry B, 2014)
Novel hybrid hydrogels based on alginate and keratin were successfully produced for the first time. The self-assembly properties of keratin, and its ability to mimic the extracellular matrix were combined with the excellent chemical and mechanical stability and biocompatibility of alginate to produce 2D and 3D hybrid hydrogels. These hybrid hydrogels were prepared using two different approaches: sonication, to obtain 2D hydrogels, and a pressure-driven extrusion technique to produce 3D hydrogels. All results indicated that the composition of the hydrogels had a significant effect on their physical properties, and that they can easily be tuned to obtain materials suitable for biological applications. The cell-material interaction was assessed through the use of human umbilical vein endothelial cells, and the results demonstrated that the alginate/keratin hybrid biomaterials supported cell attachment, spreading and proliferation. The results proved that such novel hybrid hydrogels might find applications as scaffolds for soft tissue regeneration. © 2014 the Partner Organisations.

Hydrogel matrices based on elastin and alginate for tissue engineering applications - Silva, Raquel; Singh, Raminder; Sarker, Bapi; Papageorgiou, Dimitrios G.; Juhasz-Bortuzzo, Judith A.; Roether, Judith; Cicha, Iwona; Kaschta, Joachim; Schubert, Dirk W.; Chrissafis, Konstantinos; Detsch, Rainer; Boccaccini, Aldo R. (International Journal of Biological Macromolecules, 2018)
Hydrogels from natural polymers are widely used in tissue engineering due to their unique properties, especially when regarding the cell environment and their morphological similarity to the extracellular matrix (ECM) of native tissues. In this study, we describe the production and characterization of novel hybrid hydrogels composed of alginate blended with elastin from bovine neck ligament. The properties of elastin as a component of the native ECM were combined with the excellent chemical and mechanical stability as well as biocompatibility of alginate to produce two hybrid hydrogels geometries, namely 2D films obtained using sonication treatment and 3D microcapsules produced by pressure-driven extrusion. The resulting blend hydrogels were submitted to an extensive physico-chemical characterization. Furthermore, the biological compatibility of these materials was assessed using normal human dermal fibroblasts, indicating the suitability of this blend for soft tissue engineering. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Alginate; Elastin; Hybrid hydrogels; Soft matrices; Tissue engineering

Hypervalent Iodine Compounds as Versatile Reagents for Extremely Efficient and Reversible Patterning of Graphene with Nanoscale Precision - Bao, Lipiao; Zhao, Baolin; Yang, Bowen; Halik, Marcus; Hauke, Frank; Hirsch, Andreas (Advanced Materials, 2021)
Rational patterning and tailoring of graphene relies on the disclosure of suitable reagents for structuring the target functionalities on the 2D-carbon network. Here, a series of hypervalent iodine compounds, namely, 1-chloro-1,2-benziodoxol-3(1H)-one, 1,3-dihydro-1-hydroxy-3,3-dimethyl-1,2-benziodoxole, and 3,3-dimethyl-1-(trifluoromethyl)-1,2-benziodoxole is reported to be extremely efficient for a diversified graphene patterning. The decomposition of these compounds generates highly reactive Cl, OH, and CF3 radicals exclusively in the irradiated areas, which subsequently attach onto the graphene leading to locally controlled chlorination, hydroxylation, and trifluoromethylation, respectively. This is the first realization of a patterned hydroxylation of graphene, and the degrees of functionalization of the patterned chlorination and trifluoromethylation are both unprecedented. The usage of these mild reagents here is reasonably facile compared to the reported methods using hazardous Cl-2 or ICl and allows for sophisticated pattern designs with nanoscale precision, promising for arbitrary nanomanipulation of graphene's properties like hydrophilicity and conductivity by the three distinct functionalities (Cl, OH, and CF3). Moreover, the attachment of functional entities to these highly functionalized graphene nanoarchitectures is fully reversible upon thermal annealing, enabling a full writing/storing/reading/erasing control over the chemical information stored within graphene. This work provides an exciting clue for target 2D functionalization and modulation of graphene by using suitable hypervalent iodine compounds.
CRIS-Team WoS Importer:2021-07-09

Identification of Process Limits for Electro-Spinning of aligned – Nano Fibres of the CPL/PGS 1: 1 blend - Bischoff, S.; Küng, Florian; Stafiej, Piotr; Fuchsluger, Thomas; Boccaccini, Aldo R.; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Identifying Design Principles for the Transmission of Visible Light through Electrospun Nanofibrous PCL Scaffolds for Corneal Tissue Engineering - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas (4. Baltic Sea Eye Conference, Rostock (Deutschland), 2022, 2022)

Identifying key parameters for the transmission of visible light through electrospun nanofibrous PCL scaffolds for ophthalmic applications - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas (31th Annual Conference of the European Society for Biomaterials, Porto (Portugal), 2021, 2021)

Identifying key processing parameters for the electrospinning of aligned polymer nanofibers - Dörgens, Anna; Roether, Judith; Dippold, Dirk; Boccaccini, Aldo R.; Schubert, Dirk W. (Materials Letters, 2015)
Aligned polycaprolactone (PCL) fibers of interest for numerous applications requiring contact guidance and textured topography were fabricated by electrospinning onto a rotating collector using tangential velocities ranging from 0 m/s to 11 m/s. The deposition characteristics of the fibers were investigated by microscopic methods to gather information about fiber diameter, collection angle theta, and number of fibers per reference length. It was shown that the deposition angle ranged from -2.0 degrees to 1.6 degrees and the diameter of the developed fibers averaged 587 nm to 878 nm. Furthermore the deposition angle was found to be independent of die rotation velocity. Homogeneity of the fiber mats was improved with increasing rotation velocity. The number of fibers per reference length, a measure for collection.efficiency, proved to be dependent on the rotation velocity, following a modified Weibull function. Hence the collection efficiency of the process can be improved by increasing the rotation velocity above a critical value. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Electrospinning; Fiber alignment; Polymers; Fiber technology; Porous materials

Impact of oxygen plasma treatment on the device performance of zinc oxide nanoparticle based thin-film transistors - Halik, Marcus; Peukert, Wolfgang; Braunschweig, Björn; Klaumünzer, Martin; Hirschmann, Johannes; Faber, Hendrik (ACS Applied Materials and Interfaces, 2012)
Thin-films of zinc oxide nanoparticles were investigated by photoluminescence spectroscopy and a broad defect-related yellow-green emission was observed. Oxygen plasma treatment was applied in order to reduce the number of defects, and the emission intensity was quenched to 4% of the initial value. Thin-film transistors that incorporate the nanoparticles as active semiconducting layers show an improved device performance after oxygen plasma treatment. The maximum drain current and the charge carrier mobility increased more than 1 order of magnitude up to a nominal value of 23 cm2 V−1 s−1 and the threshold voltage was lowered.
Keywords: nanoparticles; Plasma treatment; thin-film transistors; zinc oxide

Impact of storage and processing on morphology in thermoplasic polyetherurethanes - Redel, Michael; Regelmann, Christian; Wölfel, Bastian; Schubert, Dirk W. (2023)
The presented study evaluates the influence of storage conditions as well as the impact of temperature, residence time, throughput and draw down speed in fibre spinning on the phase separation in commercially availa- ble thermoplastic polyether-urethanes. Many of the properties inherent to thermoplastic polyurethane (TPU) materials and products are due to the block-copolymer chain of soft and hard segments. The incompatibility of these segments causes demixing into so called “soft” and “hard phases” [1]. The degree of separation as well as the segment content are, according to literature, detectable via FTIR measurements [2]. Granules of two TPUs with differing compo- sition were stored for up to 900 days to eval- uate morphological changes and correlate to material shelf life. Samples consisting of varying ratios of MDI/BD hard and PTMG soft segments (Elastollan®) were subsequently processed by injection moulding. The hard segment ratio and the degree of microphase separation (DPS) were studied for all samples by analysing the peaks of ether and ure- thane groups as well as the free- and hydro- gen-bonded carbonyl (C=O) peaks, respec- tively. Hard segments feature a significantly higher density compared to soft segments, wherefore the results of the C-O peaks, cor- relating with the hard segment ratio, were validated. The determined DPS values were further related to the peak ratio of ether and urethane groups showing a linear correlation. In the second part, one TPU material was processed to nonwovens and characterized applying the calibrated FTIR method. The goal is to study the impact of the processing condi- tions during fibre spinning processes and to investigate the analytic capabilities for TPU

Impact properties of polypropylene/styrene-butadiene-styrene nanocomposities - Mubarak, Y. A.; AbuHalimeh, R.; Schubert, Dirk W. (72nd Annual Technical Conference of the Society of Plastics Engineers: The Plastics Conference, ANTEC 2014, 2014)
Keywords: Percentage crystallinity; Impact; Silicon dioxide nanoparticles; Polypropylene; Styrene-butadiene-styrene

Improved 3D Printing and Cell Biology Characterization of Inorganic-Filler Containing Alginate-Based Composites for Bone Regeneration: Particle Shape and Effective Surface Area Are the Dominant Factors for Printing Performance - Bednarzig, Vera; Schrüfer, Stefan; Schneider, Tom; Schubert, Dirk W.; Detsch, Rainer; Boccaccini, Aldo R. (International Journal of Molecular Sciences, 2022)
The use of organic–inorganic 3D printed composites with enhanced properties in biomedical applications continues to increase. The present study focuses on the development of 3D printed alginate-based composites incorporating inorganic fillers with different shapes (angular and round), for bone regeneration. Reactive fillers (bioactive glass 13–93 and hydroxyapatite) and non-reactive fillers (inert soda–lime glass) were investigated. Rheological studies and the characterization of various extrusion-based parameters, including material throughput, printability, shape fidelity and filament fusion, were carried out to identify the parameters dominating the printing process. It was shown that the effective surface area of the filler particle has the highest impact on the printing behavior, while the filler reactivity presents a side aspect. Composites with angular particle morpholo-gies showed the same high resolution during the printing process, almost independent from their reactivity, while composites with comparable amounts of round filler particles lacked stackability after printing. Further, it could be shown that a higher effective surface area of the particles can circumvent the need for a higher filler content for obtaining convincing printing results. In addition, it was proven that, by changing the particle shape, the critical filler content for the obtained adequate printability can be altered. Preliminary in vitro biocompatibility investigations were carried out with the bioactive glass containing ink. The 3D printed ink, forming an interconnected porous scaffold, was analyzed regarding its biocompatibility in direct or indirect contact with the pre-osteoblast cell line MC3T3-E1. Both kinds of cell tests showed increased viability and a high rate of proliferation, with complete coverage of the 3D scaffolds’ surface already after 7 d post cell-seeding.
CRIS-Team Scopus Importer:2022-05-06
Keywords: 3D printing; alginate; bioactive glasses; organic–inorganic composites; rheology

Improvement of polymer properties for powder bed fusion by combining in situ PECVD nanoparticle synthesis and dry coating - Gomez Bonilla, Juan Sebastian; Düsenberg, Björn; Lanyi, Franz; Schmuki, Patrik; Schubert, Dirk W.; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Plasma Processes and Polymers, 2021)
Polypropylene (PP) powders are coated with silica nanoparticles in a fluidized bed to improve the flow behavior of the powders and the processability in powder bed fusion. The nanoparticles are produced in situ via dusty plasma‐enhanced chemical vapor deposition (PECVD) in an atmospheric‐pressure Ar/O2 plasma jet fixed at the distributor plate of the fluidized bed. Hexamethyldisiloxane is used as a precursor of the nanoparticles. The influence of the oxygen concentration in the plasma gas and the number of treatment cycles on the chemical composition of the nanoparticles, the amount of nanoparticles deposited, and the flow properties of the coated PP powders is investigated. The chemical composition of the formed silica particles is determined by X‐ray photon spectroscopy and infrared spectroscopy. The results reveal that the composition of the nanoparticles is SiOxCy, that is, the portion of organic residues introduced by the precursor can be controlled by changing the oxygen concentration in the plasma gas. The mass of nanoparticles deposited on the polymer powder's surface, as determined by inductively coupled optical emission spectroscopy, shows a linear dependence of the number of cycles and the oxygen concentration in the plasma gas. A considerable improvement of the flow behavior of the PP powders is observed after PECVD treatment.<br
Keywords: nanocomposites; particle coating; plasma‐enhanced chemical vapor deposition; powder bed fusion; powder flowability

Improving alginate printability for biofabrication: establishment of a universal and homogeneous pre-crosslinking technique - Hazur, Jonas; Detsch, Rainer; Karakaya, Emine; Kaschta, Joachim; Teßmar, Jörg; Schneidereit, Dominik; Friedrich, Oliver; Schubert, Dirk W.; Boccaccini, Aldo R. (Biofabrication, 2020)
Many different biofabrication approaches as well as a variety of bioinks have been developed by researchers working in the field of tissue engineering. A main challenge for bioinks often remains the difficulty to achieve shape fidelity after printing. In order to overcome this issue, a homogeneous pre-crosslinking technique, which is universally applicable to all alginate-based materials, was developed. In this study, the Young's Modulus after post-crosslinking of selected hydrogels, as well as the chemical characterization of alginate in terms of M/G ratio and molecular weight, were determined. With our technique it was possible to markedly enhance the printability of a 2% (w/v) alginate solution, without using a higher polymer content, fillers or support structures. 3D porous scaffolds with a height of around 5 mm were printed. Furthermore, the rheological behavior of different pre-crosslinking degrees was studied. Shear forces on cells as well as the flow profile of the bioink inside the printing nozzle during the process were estimated. A high cell viability of printed NIH/3T3 cells embedded in the novel bioink of more than 85% over a time period of two weeks could be observed.
CRIS-Team Scopus Importer:2020-07-24
Keywords: alginate; bioink; bioprinting; pre-crosslinking; printability; rheology; shape fidelity

Improving stability of the fibre spinning process using simple non-newtonian models - Bechert, Mathias; Schubert, Dirk W. (8th Annual European Rheology Conference, 2013)

Improving the Charge Transport in Self-Assembled Monolayer Field-Effect Transistors: From Theory to Devices - Jäger, Christof; Schmaltz, Thomas; Novak, Michael; Khassanov, Artöm; Vorobiev, Alexei; Hennemann, Matthias; Krause, Andreas; Dietrich, Hanno; Zahn, Dirk; Hirsch, Andreas; Halik, Marcus; Clark, Timothy (Journal of the American Chemical Society, 2013)
A three-pronged approach has been used to design rational improvements in self-assembled monolayer field-effect transistors: classical molecular dynamics (MD) simulations to investigate atomistic structure, large-scale quantum mechanical (QM) calculations for electronic properties, and device fabrication and characterization as the ultimate goal. The MD simulations reveal the effect of using two-component monolayers to achieve intact dielectric insulating layers and a well-defined semiconductor channel. The QM calculations identify improved conduction paths in the monolayers that consist of an optimum mixing ratio of the components. These results have been used both to confirm the predictions of the calculations and to optimize real devices. Monolayers were characterized with X-ray reflectivity measurements and by electronic characterization of complete devices. © 2013 American Chemical Society.

Improving the coloring of polypropylene materials for powder bed fusion by plasma surface functionalization - Gomez Bonilla, Juan Sebastian; Szymczak, Tim; Zhou, Xuemei; Schrüfer, Stefan; Dechet, Maximilian; Schmuki, Patrik; Schubert, Dirk W.; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Additive Manufacturing, 2020)
Polypropylene (PP) powder is treated in a fluidized bed reactor with an atmospheric Ar/O2 plasma jet to investigate the influence of the plasma treatment on the coloring of the powders. The oxygen concentration in the plasma gas and duration of the treatment was varied. Contact angle and X-ray photoelectron spectroscopy measurements confirmed and quantified the formation of surface functionalities and their dependence on the process parameters. The plasma treatment contributes to a significant improvement of the dispersibility and coloring of PP. Powder bulk properties such as particle size distribution and flowability were not modified by the process. Effects of the plasma treatment on the material bulk properties are also negligible.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Color strength; Dispersibility; Plasma surface functionalization; Powder bed fusion; Powder coloring; Wettability

Improving the Performance of Organic Thin-Film Transistors by Ion Doping of Ethylene-Glycol-Based Self-Assembled Monolayer Hybrid Dielectrics - Dietrich, Hanno; Scheiner, Simon; Portilla Berlanga, Luis; Zahn, Dirk; Halik, Marcus (Advanced Materials, 2015)
Tuning the electrostatics of ethylene-glycol-based self-assembled monolayers (SAMs) by doping with ions is shown. Molecular dynamics simulations unravel binding mechanisms and predict dipole strengths of the doped layers. Additionally, by applying such layers as dielectrics in organic thin-film transistors, the incorporated ions are proven to enhance device performance by lowering the threshold voltage and increasing conductivity.

Incorporation of bioactive glass nanoparticles in electrospun PCL/chitosan fibers by using benign solvents - Liverani, Liliana; Lacina, Jonas; Roether, Judith; Boccardi, Elena; Killian, Manuela; Schmuki, Patrik; Schubert, Dirk W.; Boccaccini, Aldo R. (Bioactive Materials, 2018)

Incorporation of Cu-Containing Bioactive Glass Nanoparticles in Gelatin-Coated Scaffolds Enhances Bioactivity and Osteogenic Activity - Zheng, Kai; Wu, Jingjing; Li, Wei; Dippold, Dirk; Wan, Ying; Boccaccini, Aldo R. (ACS Biomaterials Science and Engineering, 2018)
Keywords: bioactive nanoparticles; bone regeneration; silicate bioactive glasses; copper; porous scaffolds

Increase in VEGF secretion from human fibroblast cells by bioactive glass S53P4 to stimulate angiogenesis in bone - Detsch, Rainer; Stoor, Patricia; Gruenewald, Alina; Roether, Judith; Lindfors, Nina C.; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part A, 2014)
Bioactive glasses (BAGs) are being investigated for the repair and reconstruction of bone defects, as they exhibit osteoconductive and osteostimulatory potential. However, successful bone regeneration requires also the neovascularization of the construct which is, among other factors, guided by vascular endothelial growth factor (VEGF). In this study, BAG S53P4 (53% SiO, 23% NaO, 20% CaO, 4% PO) is investigated in relation to VEGF-release and response of fibroblast cells. Human CD-18CO fibroblasts were cultivated in contact with different granules of different sizes (0.5-0.8 mm, 1.0-2.0 mm, and 2.0-3.15 mm) and at different concentrations (0-1 wt/vol % of BAG) for 72 h. The analysis of morphology revealed no toxic effect for all granule sizes and concentrations. Compared with the reference, lactate dehydrogenase-activity of CCD-18CO cells increased in contact with BAG samples. The VEGF release from CCD-18CO fibroblasts cultured on different granule sizes and at different concentrations after 72 h of incubation was quantified. It was found that particles of 0.5-0.8 mm and 1.0-2.0 mm in size enhanced VEGF release, whereas BAG particle sizes of 2.0- 3.15 mm led to inhibition of VEGF release. The results are relevant to understand the influence of the particle size and concentration of BAG S53P4 on VEGF expression and neovascularization.
Keywords: Bioactive glass; Bone tissue engineering; Fibroblast; Vascularization; VEGF

Increasing the Fill Factor of Inverted P3HT:PCBM Solar Cells Through Surface Modification of Al-Doped ZnO via Phosphonic Acid-Anchored C60 SAMs - Stubhan, Tobias; Salinas Batallas, Michael; Ebel, Alexander; Krebs, Frederick C.; Hirsch, Andreas; Halik, Marcus; Brabec, Christoph (Advanced Energy Materials, 2012)
The influence of aluminum-doped zinc oxide (AZO) electron extraction layers modified with self-assembled monolayers (SAMs) on inverted polymer solar cells is investigated. It is found that AZO modification with phosphonic acid anchored Fullerene–SAMs leads to a reduction of the series resistance, while increasing the parallel resistance. This results in an increased efficiency from 2.9 to 3.3%.
Keywords: Al-doped ZnO; Aluminum-doped zinc oxide; Electron extraction; Fill factor; Inverted polymer solar cells; Parallel resistance; Phosphonic; Series resistances Engineering controlled terms: Electric resistance; Self assembled monolayers; Solar cells; Zinc oxide Engineering main heading: Organic acids

Individualized Wound Closure - Mechanical Properties of Suture Materials - Polykandriotis, Elias; Daenicke, Jonas; Bolat, Anil; Grüner, Jasmin; Schubert, Dirk W.; Horch, Raymund E. (Journal of Personalized Medicine, 2022)
Wound closure is a key element of any procedure, especially aesthetic and reconstructive plastic surgery. Therefore, over the last decades, several devices have been developed in order to assist surgeons in achieving better results while saving valuable time. In this work, we give a concise review of the literature and present a biomechanical study of different suturing materials under mechanical load mimicking handling in the operating theatre. Nine different suture products, all of the same USP size (4-0), were subjected to a standardized crushing load by means of a needle holder. All materials were subjected to 0, 1, 3 and 5 crushing load cycles, respectively. The linear tensile strength was measured by means of a universal testing device. Attenuation of tensile strength was evaluated between materials and between crush cycles. In the pooled analysis, the linear tensile strength of the suture materials deteriorated significantly with every cycle (p < 0.0001). The suture materials displayed different initial tensile strengths (in descending order: polyglecaprone, polyglactin, polydioxanone, polyamid, polypropylene). In comparison, materials performed variably in terms of resistance to crush loading. The findings were statistically significant. The reconstructive surgeon has to be flexible and tailor wound closure techniques and materials to the individual patient, procedure and tissue demands; therefore, profound knowledge of the physical properties of the suture strands used is of paramount importance. The crushing load on suture materials during surgery can be detrimental for initial and long-term wound repair strength. As well as the standard wound closure methods (sutures, staples and adhesive strips), there are promising novel devices.<br
Keywords: suture materials; crush load; mechanical properties; wound closure

Inductive transcutaneous energy transfer for cardiac assist devices – pushing the limits - Kirchner, Jens; Ebel, Nina; Kinner, Sarah; Fischer, Georg; Werner, Siegfried; Schubert, Dirk W.; Weyand, Michael (22. Chirurgische Forschungstage, 2018)
Background / Purpose Power supply is an essential component of active implants. To provide energy across the skin barrier, inductive energy transfer is well established in low-power devices like Cochlea implants. However, current designs are not applicable to high-power implants like cardiac assist devices due to strong tissue heating, caused by local spots of high magnetic field strength associated with large heat dissipation. Here, we propose a system design that overcomes this problem. Methods To avoid the “hot spots”, the magnetic field is guided and thus homogenized by composite coil cores based on liquid silicon rubber (LSM), which permits to design appropriate gradients of permeability. Furthermore, the frequency is kept below 1 MHz to reduce dielectric losses within the body. LSM is a biocompatible material, whose flexibility allows adaption to the body surface to minimize the gap between extracorporeal and implanted coil. For analysis and optimization of coil and coil core design, the FEM software COMSOL Multiphysics® 5.3 was used. Results The simulations showed that with the proposed coil and coil core design the magnetic fields can be homogenized such that 24 W can be transferred with an efficiency of 98.8% and a temperature increase in the tissue of only 0.8°C. Conclusions These findings suggest the possibility to make inductive energy transfer applicable also for high‑power active implants such as ventricular assist devices, reducing the number of complications of VAD-patients.
Keywords: Inductive energy transfer; transcutaneous energy transfer; cardiac assist device

Infectious complications in implant based breast surgery and implications for plastic surgeons - Horch, Raymund E.; Schultz, Gregory; Schubert, Dirk W.; Schmitz, Marweh (GMS German Plastic, Reconstructive and Aesthetic Surgery - Burn and Hand Surgery, 2013)
Implantation of breast prosthesis is still one of the most frequently performed breast reconstructing or contouring procedures. Infectious complications and capsular contracture are inherent problems that may have different causes which are not clearly defined yet in terms of pathophysiology. Recent findings showed bacterial contamination as a major cause of implant failure. Since this has direct implications for the surgical management we report on biofilm development on alloplastic breast prostheses, characteristics and effects after implantation of medical devices in general. This article gives a review of the current literature and discusses possible issues to solve the problem of infection after implantation of breast prosthesis. In conclusion the reinsertion of single-use devices should not be recommended and should be strictly avoided when a device related infection has occured. According to current knowledge contaminated implants should be removed, the infection then be cured and if necessary, a new prosthesis may be implanted after a regeneration period. Alternatively a change in therapy towards autologous tissue reconstruction should be considered if previous attempts with alloplastic prostheses have failed and if radiation therapy has worsened the local tissue situation in the recipient area.

Influence of a compatibilizer on the morphology development in polymer blends under elongation - Stary, Zdenek; Pemsel, Thomas; Baldrian, Josef; Münstedt, Helmut (Polymer, 2012)
Compatibilization is the modification of the interface in immiscible polymer blends in order to refine and stabilize their phase structure. The presence of a compatibilizer at the interface markedly affects the deformation behaviour of the dispersed droplets during and after cessation of flow. In this work the morphology development in blends of polystyrene and linear low-density polyethylene compatibilized with styrene-butadiene-styrene triblock copolymer during and after uniaxial elongation was investigated by means of electron microscopy and small-angle X-ray scattering. The incorporation of only 1 wt.-% of the compatibilizer led to a pronounced increase of the stationary elongational viscosity of the blend. It was found, that at moderate capillary number (Ca ≈ CaCR) the compatibilizer stabilises the droplets against break-ups during the flow. When Ca >> CaCR no differences in the deformation of uncompatibilized and compatibilized droplets were observed. After cessation of the flow, the presence of the compatibilizer prevented the droplet break-up and supported and accelerated the shape recovery of the elongated particles. © 2012 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Blends; Compatibilization; Morphology

Influence of crosslinking and penetrant size on the diffusion properties of cyclic siloxanes through silicone elastomers - Daenicke, Jonas; Schubert, Dirk W.; Gedde, Ulf; Hedenqvist, Mikael; Linde, Erik; Sigl, Thomas; Horch, Raymund E. (Programme and Book of Abstracts, 2016)

Influence of different treatment conditions on the filtration performance of conventional electret melt blown non-woven and novel nano FFP2 masks - Halamicek, Robin; Wiesmann, Carolin; Kröner, Richard; Eber, Matthias; Bogdan, Christian; Schubert, Dirk W. (PLoS ONE, 2023)
To allow an efficient protection against viruses like the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), it is important to avoid their spreading by using filtering face pieces (FFP), which are categorized by different standards according to their filtration efficiency. In this study, we subjected six brands of FFP2 standard masks to three different conditions and subsequently analysed them for their filtration performance to evaluate potentials for reusability. The conditions comprised changes of temperature and air humidity, an exposure to isopropyl alcohol (IPA) and an autoclave sterilization. While four of six masks consisted of electrostatically treated melt blown non-wovens, two masks were fabricated using a nanofibrous multilayer system. Due to the absence of prior electrostatic treatment, the nano-masks did not show a significant change in filtration efficiency when discharged by IPA, unlike the melt blown nonwoven masks showing a significant decrease of filtration efficiency down to around 50% at a particle size of 0.3 μm. However, most melt blown masks maintained a sufficient filtration efficiency after all other treatments with even better results than the nanofibrous masks. This was particularly the case for the capacity to filter smallest particles/droplets with a size of around 0.1 μm, which is below the range of typical filtering standards and important for the retention of virally contaminated nano-aerosols or unattached viruses. After temperature/humidity variation and autoclave sterilization, melt blown masks were able to retain a filtration efficiency up to over 90% at 0.1 μm contrary to nano-masks showing a decrease down to around 70%. Based on their better filtration performance, lower price and potential reusability, we conclude that electret melt blown masks are the preferable type of FFP2 masks.
CRIS-Team Scopus Importer:2023-09-29

Influence of fibre length and concentration on the rheological and electrical properties of conductive polymer composites - Weck, Constantin; Krückel, Johannes; Stary, Zdenek; Schubert, Dirk W. (13th Bayreuth Polymer Symposium, 2013)

Influence of functionalized halloysite clays (HNT) on selected properties of multiblock (e)PBS-EG copolymer obtained by enzymatic catalysis - Gradzik, Boguslawa; Stenzel, Alexander; Boccaccini, Aldo R.; El Fray, Miroslawa (Designed Monomers and Polymers, 2015)
In this paper, we discuss the functionalization of halloysite aluminosilicate clays (HNT) with anionic surfactant - sodium dodecanoate (NaL) and their use in new polymeric nanocomposites preparation via solvent casting. The selected polymer matrix were segmented; copoly(ester-ether)s - poly(butylene succinate-co-ethylene glycol) (PBS-EG) were synthesized for the first time with the use of enzymatic catalyst from Candida antarctica lipase B. The influence of variable concentration of NaL, temperature, and time on functionalization and finally on the chemical structure (IR) and colloidal stability (zeta potential) of functionalized HNT (f-HNT) was examined. Nanocomposites were prepared via solvent casting process, where 1 wt% of HNTs and 1 wt% of f-HNT clays were added to the (e)PBS-EG solution in chloroform. The chemical structure, topography, and hydrophilic/hydrophobic properties of prepared nanocomposites were determined by nuclear magnetic resonance (1H NMR), infrared spectroscopy (IR), scanning electron microscopy, and water contact angle. It was observed that higher concentration of NaL, longer modification time, and higher temperature lead to even distribution of f-HNT into (e)PBS-EG matrix. Halloysite clays in general improved the hydrophilicity of (e)PBS-EG and f-HNT was found to act as nucleating agent during polymer crystallization.
Keywords: aluminosilicates; enzymatic synthesis; halloysite clays; nanocomposites; poly(butylene succinate) (PBS)

Influence of matrix polydispersity on the viscoelastic properties of polystyrene melts filled with nano silica - Triebel, Christian; Kunzelmann, Peter; Schubert, Dirk W.; Münstedt, Helmut (Book of Abstracts, 2012)

Influence of molar mass distribution and long-chain branching on strain hardening of low density polyethylene - Stadler, Florian; Kaschta, Joachim; Münstedt, Helmut; Becker, Florian; Buback, Michael (Rheologica Acta, 2009)
Low-density polyethylenes (LDPE) were synthesized in a laboratory-scale autoclave under high pressure. These samples were found to possess a high molar mass tail, resulting in a distinctly bimodal molar mass distribution and a lower concentration of long-chain branching than typical of commercial LDPEs. Rheological experiments in elongation showed that these samples exhibit a very pronounced strain hardening, which could be favorable for distinct processing operations. Although the samples have a rather high molar mass (M(w) = 2...4 x 10(6) g/mol), their zero shear-rate viscosities eta(0) and their shear thinning behavior are still in a range, where thermoplastic processing is possible. Aqualitative understanding of the experimental results is tried by the model of the Cayley tree.
Keywords: Low-density polyethylene; Autoclave process; Molar mass distribution; Long-chain branching; Elongational rheology; Viscosity functions

Influence of molecular parameters on the stress dependence of viscous and elastic properties of polypropylene melts in shear - Resch, Julia; Kaschta, Joachim; Wolff, Friedrich; Münstedt, Helmut (Rheologica Acta, 2011)
The stress dependencies of the steady-state viscosity eta and, particularly, that of the steady-state elastic compliance J(e) of various linear isotactic polypropylenes (PP) and one long-chain branched PP are investigated using creep-recovery tests. The creep stresses applied range from 2 to 10,000 Pa. In order to discuss the stress-dependent viscosity eta and elastic compliance J(e) with respect to the influence of the weight average molar mass M-w and the polydispersity factor M-w/M-n the PP are characterized by SEC-MALLS. For the linear PP, linear steady-state elastic compliances J(e)(0) in the range of 10(-5)-10(-3) Pa-1 are obtained depending on the molar mass distribution. J(e)(0) of the LCB-PP is distinctly higher and comes to lie at around 10(-2) Pa-1. J(e)(0) is found to be independent of M-w but strongly dependent on polydispersity. eta and J(e) decrease with increasing stress. For the linear PP, J(e) as a function of the stress tau is temperature independent. The higher M-w/M-n the stronger is the shear thinning of eta and the more pronounced is the stress dependence of J(e). For the LCB-PP, the strongest stress dependence of eta and J(e) is observed. Furthermore, for all PP J(e) reacts more sensitively to an increasing stress than eta. A qualitative explanation for the stronger stress dependence of J(e) compared to eta is given by analyzing the contribution of long relaxation times to the viscosity and elasticity.
Keywords: Polypropylene; Viscosity; Steady-state elastic compliance; Stress dependence; Molecular structure

Influence of operating parameters on the suture retention test for scaffolds in ophthalmology - Küng, Florian; Schubert, Dirk W.; Stafiej, Piotr; Kruse, Friedrich; Fuchsluger, Thomas (Materials Science and Engineering C, 2017)
The strength of a suture used to attach a graft to a patient can be quantified using the suture retention test. In order to gain deeper insight on the influence of testing and application conditions testing parameters were varied. Different pull rates, suture and jaw positions, and suture materials were tested to show their influence on the result of the test. The results of the different states were analyzed using statistical tests. Based on the statistic analysis conditions for testing with a maximum of accuracy and as close as possible to in vivo conditions have been revealed.
EVALuna2:21344

Influence of Residence Time and Moisture Content on Molar Mass Dispersity of Polyethylene Terepthalate - Härth, Michael; Lanyi, Franz; Schubert, Dirk W. (Abstracts, 2012)

Influence of self-assembled monolayer dielectrics on the morphology and performance of α,ω-dihexylquaterthiophene in thin film transistors - Novak, Michael; Schmaltz, Thomas; Faber, Hendrik; Halik, Marcus (Applied Physics Letters, 2011)
Three different ultrathin hybrid dielectrics based on self-assembled monolayers (SAMs) from phosphonic acid molecules were investigated on aluminum oxide. The impact of the underlying SAMs on the semiconductor morphology and transistor device performance was studied by reducing the film thickness of the subsequently deposited extgreeka, extgreekw-dihexylquaterthiophene semiconductor to one monolayer and less. The nature of the SAM relates to the molecular orientation of submonolayer films, which is investigated by photoluminescence microscopy and atomic force microscopy. SAMs with high surface energy tend to induce a face-on growing of the semiconductor, whereas for SAMs with low surface energy an edge-on growth is favorable.
EAM Import::2019-03-14

Influence of temperature and stretching speed on the homogeneity of biaxial oriented polypropylene films from binary and ternary blends - Seidl, Stephan; Kaschta, Joachim; Schubert, Dirk W. (13th Bayreuth Polymer Symposium, 2013)

Influence of Temperature and Stretching Speed on the Homogeneity of Biaxial Oriented Polypropylene Films From Binary and Ternary Blends - Seidl, Stephan; Kaschta, Joachim; Schubert, Dirk W. (Book of Abstracts, 2013)

Influence of the Inlet Velocity on the Onset of Draw Resonance in Fiber Spinning - Bechert, Mathias; Schubert, Dirk W.; Scheid, Benoit (9th Annual European Rheology Conference, 2014)

Influence of the molar mass distribution on the suture-ability of nanofiber meshes for tissue engineering - Hehn, Markus; Küng, Florian; Stafiej, Piotr; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (15th Bayreuth Polymer Symposium, 2017)

Influence of the molar mass on the suture retention properties of polycaprolactone - Küng, Florian; Schubert, Dirk W. (Europe Africa Conference 2017 of the Polymer Processing Society, 2017)

Influence of the molecular weight on the suture retention properties of polycaprolactone - Küng, Florian; Schubert, Dirk W.; Stafiej, Piotr; Kruse, Friedrich; Fuchsluger, Thomas (Association for Research in Vision and Ophthalmology, 2017)

Influence of the particle size and the filling degree of barium titanate filled silicone elastomers used as potential dielectric elastomers on the mechanical properties and the crosslinking density - Ziegmann, Andreas; Schubert, Dirk W. (Materials Today, 2018)
Keywords: Silicone elastomer; Mechanical properties; Particle size; Crosslinking density; Barium titanate; Electro active polymer; Dielectric elastomer

Influence of the pressure dependent contact area between electrode and composite surface on the electrical conductivity - Liu, Xian Hu; Schubert, Dirk W. (18th International Conference on Composite Structures, 2015)

Influence of the pressure-dependent contact area between electrode and composite surface on the electrical conductivity - Liu, Xian Hu; Schubert, Dirk W. (Composite Structures, 2016)
In this work, the influence of the pressure-dependent contact area between electrodes and surfaces of the composite samples on the electrical conductivity of polymer/carbon black composites was investigated. It was found that the electrical conductivity depended on the pressure (P) applied by the testing device and the carbon black concentration (ϕ). Meanwhile, the logarithm of electrical conductivity exhibited a linear relationship with ϕ regardless of the pressures. Furthermore, it was found that the electrical conductivity σ showed a specific relationship (logσ(P)=kP+logb) in the pressure range investigated regardless of the concentration. Based on this correlation, the maximum (true) electrical conductivity of the composite samples at a given concentration for infinite pressure can be revealed by extrapolation. Thus, a novel approach is given to eliminate strong variations in electrical conductivity measurements on composites due to imperfect contacts.
Keywords: Carbon black; Electrical conductivity; Polymer composites; Pressure

Influence of various pretreatments on molecular and rheological properties of a linear and a long-chain branched polypropylene - Münstedt, Helmut; Kaschta, Joachim (Rheologica Acta, 2024)
The influence of a mechanical or a thermal pretreatment of a linear (L-PP) and a long-chain branched polypropylene (LCB-PP) in the molten state was studied. The molar mass distributions and the branching structure were determined by high-temperature gel permeation chromatography HT-GPC coupled with laser-light scattering. The samples were extruded through long or short capillaries of various geometries corresponding to a predominant shear or elongational deformation. As a rheological probe, the extrudate swell at low stresses was measured for the differently pretreated samples. For the L-PP, neither molecular nor rheological changes were observed. However, the extrudate swell of the LCB-PP was found to decrease with increasing volume throughput. It was more strongly affected by shear in the capillary than by molecule stretching in the entry region. The smaller extrudate swell was accompanied by a decrease of the high molar mass tail of the LCB-PP, which could be the reason for the decay of swell, in principle. However, a comparable degradation of the high molar mass tail was obtained by a pure thermal treatment that was shown to leave the extrudate swell unchanged. This result and the unaffected branching structures found by high-temperature gel permeation chromatography (HT-GPC) support the hypothesis of a change of the branching topography by the mechanical pretreatment.<br

In Situ Raman Mapping of Charge Carrier Distribution in Electrolyte-Gated Carbon Nanotube Network Field-Effect Transistors - Zaumseil, Jana; Jakubka, Florian; Wang, Ming; Gannott, Florentina (Journal of Physical Chemistry C, 2013)
Solution-processed networks of purely semiconducting single-walled carbon nanotubes (s-SWNTs) can be used to create high-mobility field-effect transistors (FETs) for flexible electronics. In order to optimize network alignment and density, an understanding of carrier distribution within the FET channel is necessary. Here, we used confocal Raman microscopy to investigate charge accumulation and doping in electrolyte-gated FETs with asymmetric layers of only (7,5) nanotubes, that were selected by dispersion in poly(9,9-dioctylfluorene). The nanotube FETs exhibited hole mobilities of up to 7.5 cm2 V–1 s–1 and on/off ratios of 105. All Raman modes decreased in intensity with hole accumulation. The G′-peak and D-peak shifted linearly with negative gate voltages to higher wavenumbers. Using the G′-peak shift, the charge carrier distribution in an operating FET was mapped at different gate and source-drain voltages with high spatial resolution ( 300 nm) and over large areas. With this simple technique, we were able to visualize directly how the assignment of source and drain electrodes determined channel pinch-off and the onset of the saturation regime in FETs with nonuniform carbon nanotube distributions along the channel. In situ Raman mapping could also be applied to other semiconductors that show significant changes in their Raman spectra with doping.
EAM Import::2019-03-13

In situ STXM investigations of pentacene-based OFETs during operation - Hub, Christian; Burkhardt, Martin; Halik, Marcus; Tzvetkov, G.; Fink, Rainer (Journal of Materials Chemistry, 2010)
Ultrathin pentacene-based organic field-effect transistors (OFETs) on commercially available silicon nitride membranes suitable for transmission X-ray experiments are demonstrated. The devices produced by high-vacuum deposition show excellent electronic performance ( = 0.6 cm V s, I = 10). STXM-experiments recorded with the PolLux microspectroscope correlate structural and electronic properties at highest spatial and spectral resolution while the OFET is operated. Local NEXAFS spectra are used to analyze the different orientations of the pentacene nanocrystals. Spectral changes due to modifications in the electronic structure during OFET operation can hardly be detected with the current setup. © The Royal Society of Chemistry 2010.

Intercalating-Organic-Cation-Induced Stability Bowing in Quasi-2D Metal-Halide Perovskites - Zhang, Jiyun; Langner, Stefan; Wu, Jianchang; Kupfer, Christian; Lüer, Larry; Meng, Wei; Zhao, Baolin; Liu, Chao; Daum, Manuel; Osvet, Andres; Li, Ning; Halik, Marcus; et al. (ACS Energy Letters, 2022)
Quasi-2D metal-halide perovskites with Ruddlesden-Popper structures have shown promising stability due to the protective effects of the intercalating organic cations. However, a systematic study of the effect of intercalating organic cations on stability has rarely been reported. Here we use a high-throughput-robot platform to fabricate over 300 perovskite films and study the effect of cations and their concentrations on the thermal stability of perovskite films. We find that approximately 20-25 mol % of intercalating organic cations into MAPbI3 (nominal n = 4/5) can maximize the film stability, while higher/lower concentrations lead to inferior stability, which is termed stability bowing in analogy to band-gap bowing. A model with two competitive effects of the intercalating organic cation (better protection vs more defects) is proposed to rationalize this behavior. We anticipate this work to provide new insights into the stability of quasi-2D perovskites.
CRIS-Team Scopus Importer:2022-02-11

Interface Engineering in High-Performance Low-Voltage Organic Thin-Film Transistors Based on 2,7-Dialkyl-[1]benzothieno[3,2-b][1]benzothiophenes - Amin, Atefeh Y.; Reuter, Knud; Meyer-Friedrichsen, Timo; Halik, Marcus (Langmuir, 2011)
We investigated two different (2,7-dialkyl-[1]benzothieno[3,2-b][1]benzothiophenes; Cn–BTBT–Cn, where n = 12 or 13) semiconductors in low-voltage operating thin-film transistors. By choosing functional molecules in nanoscaled hybrid dielectric layers, we were able to tune the surface energy and improve device characteristics, such as leakage current and hysteresis. The dipolar nature of the self-assembled molecules led to a shift in the threshold voltage. All devices exhibited high charge carrier mobilities of 0.6–7.0 cm2 V–1 s–1. The thin-film morphology of BTBT was studied by means of atomic force microscopy (AFM), presented a dependency upon the surface energy of the self-assembled monolayer (SAM) hybrid dielectrics but not upon the device performance. The use of C13–BTBT–C13 on hybrid dielectrics of AlOx and a F15C18–phosphonic acid monolayer led to devices with a hole mobility of 1.9 cm2 V–1 s–1 at 3 V, on/off ratio of 105, small device–device variation of mobility, and a threshold voltage of only −0.9 V, thus providing excellent characteristics for further integration.

Interface Engineering of Molecular Charge Storage Dielectric Layers for Organic Thin-Film Memory Transistors - Khassanov, Artöm; Schmaltz, Thomas; Steinrück, Hans-Peter; Magerl, Andreas; Hirsch, Andreas; Halik, Marcus (Advanced Materials Interfaces, 2014)
Mixed self-assembled monolayers of C60-functionalized and different long-chained insulating phosphonic acids provide molecular scale non-volatile memory dielectrics for low-voltage organic thin-film transistors. The memory retention depends on the insulation of the C60 moiety and can be improved by embedding into the insulating SAM matrix and covering by corresponding insulating molecules.

Intermolecular cooperativity and entanglement network in a miscible PLA/PMMA blend in the presence of nanosilica - Hao, Xiaoqiong; Kaschta, Joachim; Pan, Yamin; Liu, Xian Hu; Schubert, Dirk W. (Polymer, 2016)
Nanosilica filled polylactide (PLA)/Poly(methyl methacrylate) (PMMA) 50/50 blends with varying silica concentrations were prepared by melt mixing. In this work, the effects of silica concentration and the preferential adsorption between silica and the component on the thermo-mechanical and rheological properties of PLA/PMMA blends were systematically investigated. The results of DSC indicate the miscibility of PLA/PMMA/silica nanocomposites in the solid state, and the incorporation of nanosilica does not only increase the glass transition temperature but also extend the broadness of glass transition. Local nanoscale heterogeneities in the miscible blends are proposed due to the self-concentration of the components, and the presence of nanosilica increased the concentration fluctuation and dynamic heterogeneity of the PLA/PMMA blends. A distinct "crater" structure can be observed in the fractured surfaces of the blend nanocomposites. According to the results of SEM and rheological measurements, it was proposed that PLA molecules were selectively adsorbed on the surface of nanosilica, and the preferential adsorption of PLA changed the blend composition in the "crater" structure and the bulk matrix. The phase separation temperature of the filled PLA/PMMA blends was also improved by the incorporation of nanosilica, implying a potential role of nanosilica in improving the phase stability of PLA/PMMA blends. In addition, nanosilica could increase and entanglement density and decrease the entanglement molar mass of the blends in a concentration-dependent manner. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Miscible blend; Nanocomposite; Preferential adsorption

Investigating the electrical conductivity of PMMA/ carbon black and of PS/PMMA/ carbon black blends prior to and after shear - Voigt, Monika; Pan, Yamin; Liu, Xian Hu; Schubert, Dirk W. (Book of Abstracts, 2016)
The electrical conductivity of disk-like poly(methyl methacrylate)/carbon black (PMMA/CB) composite samples with   various CB concentrations as a function of the position was investigated prior to and after a shear process. Novel   electrical conductivity maps of the samples were obtained. It was found that the electrical conductivity from angular   averaging of static samples is independent of the radius regardless of the CB concentrations but strongly   dependent for sheared samples with varied CB concentrations. 1 Additionally, CB filled polystyrene (PS) and PMMA   blends with different PS/PMMA ratio have been fabricated by melt blending to obtain conductive polymer   composites with a low electrical percolation threshold. The electrical conductivity of the composites was highest   when PS and PMMA phases form a co-continuous structure and CB particles were selectively located and   percolated in the PS phase. Moreover, the simultaneous evolution of electrical conductivity and phase morphology   of CB filled co-continuous PS/PMMA (50v/50v) composites was investigated under shear and quiescent melt.   Under shear stress, the conductivity of these blends decreased by about two orders of magnitude and the phase   morphology changed into a strip structure 2 . Impact of shear on the phase morphology become less significant as   CB concentration increased or shear stress decreased. During subsequent recovery, pronounced phase structure   coarsening and conductivity increase were observed in the systems. The results obtained in this study provide a   deeper insight into phase structural and conductivity changes in conductive polymer composite induced by shear   deformation.   1. X. Liu, J. Krückel, G.Q. Zheng, D.W. Schubert, ACS Appl. Mater. Interfaces 2013, 5, 8857   2. Y. Pan, X. Liu, X. Hao, Z. Starý, D.W. Schubert, Europ. Polym. J. 78 (2016) 106–115

Investigating the electrical percolation threshold of ternary composite films with different compatibility between polymer blends - Xu, Huagen; Qu, Muchao; Yang, Qiancheng; Schubert, Dirk W. (Journal of Polymer Engineering, 2021)
Electrical conductive of polystyrene (PS)/poly(butyl methacrylate) (PBMA)/carbon black (CB) and PS/poly (cyclohexyl methacrylate) (PChMA)/CB ternary composite films with different polymer blend ratios are prepared through solution casting. The percolation thresholds (φc) of all the composite films before and after thermal annealing have been determined through the McLachlan GEM equation. Moreover, the PS/poly (methyl methacrylate) (PMMA)/CB and PS/poly (ethyl methacrylate) (PEMA)/CB films obtained from the same method while only considering conductivity after thermal annealing as well in this work for comparison. Though the CB particles are revealed to be located at only one polymer phase of all four different polymer blends, with compatibility between polymer blends increasing, the ternary composite films show different φc behaviors by changing polymer blend ratios. In PS/PChMA/CB case, the phase separation between PChMA and PS cannot be observed under scanning electron microscope (SEM). After thermal annealing, all the φc of PS/PChMA/CB films with different PS/PChMA ratios almost show a linear behavior instead of the double percolation behavior with PChMA content increasing. Suppose both φc of binary systems (polymer A/filler and polymer B/filler) is determined. In that case, a linear behavior relationship between the φc of the ternary composites (A + B + fillers) with the ratio of two polymers can be revealed when polymer A and B are miscible.
CRIS-Team Scopus Importer:2021-05-21
Keywords: compatibility; electrical conductivity; poly (alkyl methacrylate); polystyrene; ternary composite films

Investigation and characterization of the additive manufacturing of polycaprolactone/bioactive glass hybrid scaffolds for bone tissue engineering via material extrusion processing - Gritsch, Lukas; Askanian, Haroutioun; Bednarzig, Vera; Schrüfer, Stefan; Kaschta, Joachim; Blavignac, Christelle; Peuble, Steve; Gallice, Frederic; Jallot, Edouard; Boccaccini, Aldo R.; Lao, Jonathan (Progress in Additive Manufacturing, 2023)
Thanks to its versatility and effectiveness, additive manufacturing is expected to completely revolutionize the biomedical science field. In bone regenerative medicine, in particular, additive manufacturing has the great potential of opening new avenues of development for patient-specific ad hoc therapies. In theory, a defect could be scanned and precisely replicated, thus offering the best fitting for each patient. The main bottleneck to date is the relatively scarce availability of materials that can be printed reliably and consistently. This is the case for organic/inorganic hybrids, materials produced by sol–gel chemistry that combine the advantages of polymers and bioinorganics at the molecular scale. Due to their complex structure and unique rheological and mechanical properties, the printing of hybrids remains challenging. With this study, we aim to investigate the rheological, thermal and molecular properties of a class I polycaprolactone/bioactive glass hybrid and discover how they correlate with the printability of the material. The molecular weight distribution (gel permeation chromatography), thermal properties (thermal gravimetric analysis, differential scanning calorimetry) and rheological properties of each hybrid material were investigated at all stages of processing. Printing trials via direct material extrusion processing followed by morphological characterization were performed on both polymers and hybrids. Their apatite-forming ability in simulated body fluid was evaluated by scanning electron microscopy and particle-induced X-ray emission. Results confirmed the successful manufacturing of organic/inorganic hybrids using direct material extrusion processing for the first time. Three-dimensional scaffolds were successfully produced without the need for further processing. No additional solvents or convoluted indirect approaches were necessary. Thanks to the thermal analysis, an ideal temperature window for printing was identified. SBF immersion assays confirmed that the material's bioactivity is retained after printing. Considering the presented findings, material extrusion processing might develop into an essential technique for fabricating superior 3D bioactive scaffolds for bone tissue engineering. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-09-29
Keywords: Additive manufacturing; Bioactive glasses; Bioactivity; Fused deposition modeling; Hybrids; Polycaprolactone

Investigation and modeling of the electrical properties of poly (methyl methacrylate)/graphene nanoplatelets composite sheets with various thickness - Luo, Xiaoling; Schubert, Dirk W. (Advanced Nanomaterials Congress, 2021)
Poly(methyl methacrylate) (PMMA) composites containing graphene nanoplatelets (GNPs) at various concentrations were melt mixed and hot pressed into rectangular sheets with a variety of thickness. The conductivity σ in the in-plane and perpendicular directions were investigated and modeled using McLachlan general effective medium (GEM) equation. In the in-plane direction, the values of the parameter t and the resultant percolation thresholds Φc, I of composite sheets were almost constants of 2.90 vol. % and 2.0 (universal value), respectively, regardless of the sample thickness. In the perpendicular direction, the exponent t decreased from 3.5 to 2.8 as the thickness increased from 0.2 mm to 2 mm, while the percolation threshold Φc, P increased from 2.12 vol. % to 2.72 vol. %. The lower Φc, P reveals an easier formation of the percolated network within thinner samples. This is likely due to the large aspect ratio (AR) of GNPs, the lower Φc, P values relative to Φc, I also confirm the dependence of sample geometry. The parameter t could be termed the “shape factor”, a higher value indicates more tunneling effect or/and more tortuous networks. From the point view of tunneling effect, it is considered that more electron tunneling occurred in the perpendicular direction for composite sheets with lower thickness, which was resulted from more thin layers of insulating polymer between the graphene sheets. The finding is opposite to that of the previous study on PMMA/carbon fibers (CF) composites, which might be ascribed to the different shapes of GNPs and CF. Flake-like GNPs were more prone to construct direct conductive pathways in long-distance transport than rod-like CF. <

Investigation and modeling of various influencing factors on the dielectric breakdown strength of silicone elastomers - Ziegmann, Andreas; Berner, Claus; Schubert, Dirk W. (Nordic Polymer Days 2018, 2018)
Dielectric elastomers are utilized as soft electroactive polymers for actuators, sensors or generator applications to transduce mechanical to electrical energy and vice versa. They are characterized by the ability to change shape while an electrical field is applied. Indeed, this effect is most significant for electrical fields near the electrical breakdown strength, therefore it is a limiting factor for application. This work investigates different factors influencing the dielectric breakdown strength of soft silicone elastomers such as the sample thickness, the force and the radius of the upper electrode, the filling degree and the size of air voids. It can be shown that the main influence is the compression of the sample, thus a novel master curve can be created and fitted by a semi empirical model function. Therefore a comparison of all different experimental set-ups is possibl

Investigation and modeling of various influencing factors on the dielectric breakdown strength of silicone elastomers - Ziegmann, Andreas; Berner, Claus; Schubert, Dirk W. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2019)
Dielectric elastomers are utilized as soft electroactive polymers for actuators, sensors or generator applications to transduce mechanical to electrical energy and vice versa. They are characterized by the ability to change shape while an electrical field is applied. Indeed, this effect is most significant for electrical fields near the electrical breakdown strength, therefore it is a limiting factor for application. This work investigates different factors influencing the dielectric breakdown strength of soft silicone elastomers such as the sample thickness, the force and the radius of the upper electrode, the filling degree and the size of air voids. It can be shown that the main influence is the compression of the sample, thus a novel master curve can be created and fitted by a semi empirical model function. Therefore a comparison of all different experimental set-ups is possibl
Keywords: Dielectric breakdown strength; Silicone elastomer; Barium titanate; Electroactive polymer; Dielectric elastomer

Investigation of functional, physical, mechanical and thermal properties of TiO2 embedded polyester hybrid composites: A design of experiment (DoE) study - Munawar, Muhammad; Schubert, Dirk W.; Khan, Shahzad Maqsood; Ur Rehman, Muhammad Atiq; Gull, Nafisa; Islam, Atif; Sabir, Aneela; Shafique, Muhammad; Haider, Bilal; Azam, Mudassar; Khan, Saba Urooge; Voigt, Monika (Progress in Natural Science, 2018)
Keywords: Design of experiment; Titania; Hybrid composites; Polyester

Investigation of processing parameters for electrospun polycaprolactone / chitosan blends for wound treatment - Kümmritz, Leon; Stafiej, Piotr; Schubert, Dirk W. (15th Bayreuth Polymer Symposium, 2017)

Investigation of the batch-to-batch inconsistencies of Collagen in PCL-Collagen nanofibers. - Dippold, Dirk; Hardt, Moritz; Boccaccini, Aldo R.; Horch, Raymund E.; Beier, Justus P.; Schubert, Dirk W.; Cai, Aijia (Materials Science and Engineering C, 2019)
The application of tissue engineered constructs is an approach in regenerative therapies to support regeneration of damaged muscular tissue. Therefore the development of highly aligned electrospun scaffolds based on polycaprolactone (PCL) and collagen enables a versatile development towards tailor made applications. However, the application of natural polymers like collagen brings the risk of batch-to-batch inconsistencies, which influence the reproducibility of the electrospinning process. Aligned PCL-Collagen nanofibers were fabricated via electrospinning using benign solvents. The spinnability of different collagen batches and polymer concentrations in diluted acetic acid as solvent was investigated. Furthermore spinning parameters and fiber morphology were investigated in order to determine the most stable spinning conditions and analyze the batch-to-batch variations. Finally the effect of the solution temperature and the time of pure collagen in solution were investigated, to complete the analysis of the influences on the spinning behavior.

Investigation of the dielectric breakthrough strength of a silicone elastomer - Revealing the dominant factor - Berner, Claus; Ziegmann, Andreas; Schubert, Dirk W. (Workshop on Italian-Nordic Polymer Future, 2017)

Investigation of the thermal stability of the carbon framework of graphene oxide - Eigler, Siegfried; Grimm, Stefan; Hirsch, Andreas (Chemistry - A European Journal, 2014)
In this study, we use our recently prepared graphene oxide (GO) with an almost intact σ-framework of carbon atoms (ai-GO) to probe the thermal stability of the carbon framework for the first time. Ai-GO exhibits few defects because CO formation is prevented during synthesis. Ai-GO was thermally treated before chemical reduction and the resulting defect density in graphene was subsequently determined by statistical Raman microscopy. Surprisingly, the carbon framework of ai-GO is stable in thin films up to 100°C. Furthermore, we find evidence for an increase in the quality of ai-GO upon annealing at 50°C before reduction. The carbon framework of GO prepared according to the popular Hummers' method (GO-c) appears to be less stable and decomposition starts at 50°C, which is qualitatively indicated by CO-trapping experiments in μm-thin films. Information about the stability of GO is important for storing, processing, and using GO in many applications. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Investigation of various influences on the dielectric breakthrough strength of a silicone elastomer - Berner, Claus; Ziegmann, Andreas; Schubert, Dirk W. (International Workshop on Silicone based Poylmers, 2017)

Investigation on the draw resonance behavior of polypropylene blends via Rheotens experiments - Kunzelmann, Peter; Danzer, Stefan; Dörnhöfer, Andrea; Schubert, Dirk W. (Abstracts, 2012)

Investigations on the quality of dispersion of nanofillers in poly(methyl methacrylate) by creep-recovery experiments - Triebel, Christian; Kunzelmann, Peter; Katsikis, Nikolaos; Stara, Hana; Schubert, Dirk W. (Book of Abstracts, 2012)

In vivo evaluation of B-TCP containing 3D laser sintered poly(ether ether ketone) composites in pigs - von Wilmowsky, Cornelius; Lutz, Rainer; Meisel, Ulf; Srour, Safwan; Rupprecht, Stephan; Toyoshima, Takeshi; Nkenke, Emeka; Schlegel, Karl Andreas; Pohle, Dirk; Münstedt, Helmut; Rechtenwald, Thomas; Schmidt, Michael (Journal of Bioactive and Compatible Polymers, 2009)
The aim of this study was to produce an individually shaped medical implant from a 3D database and to evaluate the biological behavior of a laser sintered poly(ether ether ketone) (PEEK) implant with incorporated osteoconductive bone materials in porcine bone defects. Laser sintered PEEK samples containing ß-tricalciumphosphate (ß-TCP) were implanted into critical size defects in the frontal skull of ten pigs. Compression moulded pure PEEK was used as a reference material. The bone-implant interface was histomorphometrically analysed after 6, 12, and 24 weeks. Histomorphometrical evaluations after 24 weeks revealed that the superficially located ß-TCP was in contact with the surrounding bone, whereas the other groups were fibrous encapsulated. Interfacial shear strength was significantly higher for the ß-TCP containing group in comparison to the compression moulded PEEK group (p = 0.004) and the laser sintered PEEK group. The laser sintered PEEK implants seem to be attractive as bone substitutes for reconstructive surgery due to their individually constructed 3D shape and biocompatibility. © 2009 SAGE Publications.
Created from Fastlane, Scopus look-up
Keywords: ß-TCP; 3D shaped implants; Bone reconstruction.; Bone substitution; In vivo; Individually shaped implants; Laser sintering; Poly(ether ether ketone) (PEEK); Sintered PEEK biocompatibility; Tissue engineering

Ionic Liquids for Electrolyte-Gating of ZnO Field-Effect Transistors - Thiemann, Stefan; Sachnov, Swetlana; Porscha, S.; Wasserscheid, Peter; Zaumseil, Jana (Journal of Physical Chemistry A, 2012)
We investigate the influence of the chemical structure of a range of imidazolium-based ionic liquids (IL) on their properties as electrolytes and the device characteristics of electrolyte-gated field-effects transistors (FETs) based on spray-deposited polycrystalline zinc oxide (ZnO). We find a decrease of electron field-effect mobility that correlates with the capacitance of the ionic liquids and not only with the size of the IL-cation. The device stability depends significantly on testing conditions. While they are reasonably stable in nitrogen, ZnO-FETs degrade rapidly in ambient air due to absorption of water by the IL and the resulting ZnO surface reactions. Replacement of the most acidic hydrogen atom of the imidazolium cation and surface passivation of ZnO with hexamethyldisilazane improve environmental stability.

Is short term intraoperative application of disinfectants harmful to breast implants in breast reconstruction? An experimental study and literature survey - Schmitz, Marweh; Schubert, Dirk W.; Kaschta, Joachim; Daenicke, Jonas; Walter, Bastian; Horch, Raymund E. (Journal of the Mechanical Behavior of Biomedical Materials, 2019)
Objectives: Bacterial contamination of breast implants and biofilm formation has been discussed as a major reason for implant loss and capsular contraction. Intra- and perioperative treatment of breast implants with disinfectants to prevent bacterial contamination has been frequently reported. Given the increasing awareness of concerns about product liability the question of whether short-time irrigation of implants with antimicrobial substances during the operative procedure would potentially alter the integrity of the implant shell has attracted legal and medical interest. In this study we therefore investigated whether irrigating breast implants with antimicrobials commonly used in clinical practice with a clinically relevant application time would affect the physical integrity of the implant shell.
CRIS-Team WoS Importer:2019-02-21

ITO-Free and Fully Solution-Processed Semitransparent Organic Solar Cells with High Fill Factors - Guo, Fei; Zhu, Xiangdong; Forberich, Karen; Krantz, Johannes; Stubhan, Tobias; Salinas Batallas, Michael; Halik, Marcus; Spallek, Stefanie; Butz, Benjamin; Spiecker, Erdmann; Ameri, Tayebeh; Li, Ning; et al. (Advanced Energy Materials, 2013)
Organic photovoltaic (OPV) solar cells that can be simply processed from solution are in the focus of the academic and industrial community because of their enormous potential to reduce cost. One big challenge in developing a fully solution-processed OPV technology is the design of a well-performing electrode system, allowing the replacement of ITO. Several solution-processed electrode systems were already discussed, but none of them could match the performance of ITO. Here, we report efficient ITO-free and fully solution-processed semitransparent inverted organic solar cells based on silver nanowire (AgNW) electrodes. To demonstrate the potential of these AgNW electrodes, they were employed as both the bottom and top electrodes. Record devices achieved fill factors as high as 63.0%, which is comparable to ITO based reference devices. These results provide important progress for fully printed organic solar cells and indicate that ITO-free, transparent as well as non-transparent organic solar cells can indeed be fully solution-processed without losses. Indium tin oxide (ITO)-free and fully solution-processed organic solar cells are demonstrated by employing AgNW as both the bottom and top electrodes, in conjunction with Al-ZnO and poly(3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) as charge extraction layers. Devices with electrical fill factor (FF) up to 63.0% and fully retained open circuit voltage (V) are achieved, indicating that superior optoelectronic and film quality properties of the two interlayers are perfectly compatible to AgNW electrodes. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

JoVE Video Dataset - Polykandriotis, Elias; Himmler, Marcus; Mansouri, Shirin; Ruppe, Florian; Grüner, Jasmin; Bräuer, Lars; Schubert, Dirk W.; Horch, Raymund E. (2022)
With the evolution of suture materials, there has been a change in paradigms in primary and secondary tendon repair. Improved mechanical properties allow more aggressive rehabilitation and earlier recovery. However, for the repair to hold against higher mechanical demands, more advanced suturing and knotting techniques must be assessed in combination with those materials. In this protocol, the use of polytetrafluoroethylene (PTFE) as a suture material in combination with different repair techniques was investigated. In the first part of the protocol, both linear tension strength and elongation of knotted against not-knotted strands of three different materials used in flexor tendon repair were evaluated. The three different materials are polypropylene (PPL), ultra-high molecular weight polyethylene with a braided jacket of polyester (UHMWPE), and polytetrafluoroethylene (PTFE). In the next part (ex vivo experiments with cadaveric flexor tendons), the behavior of PTFE using different suture techniques was assessed and compared with PPL and UHMWPE. This experiment is comprised of four steps: harvesting of the flexor tendons from fresh cadaveric hands, transection of the tendons in a standardized manner, tendon repair by four different techniques, mounting, and measurement of the tendon repairs on a standard linear dynamometer. The UHMWPE and PTFE showed comparable mechanical properties and were significantly superior to PPL in terms of linear traction strength. Repairs with four- and six-strand techniques proved stronger than two-strand techniques. Handling and knotting of PTFE are a challenge due to very low surface friction but fastening of the four- or six-strand repair is comparatively easy to achieve. Surgeons routinely use PTFE suture material in cardiovascular surgery and breast surgery. The PTFE strands are suitable for use in tendon surgery, providing a robust tendon repair so that early active motion regimens for rehabilitation can be applie
Keywords: Polytetrafluoroethylene; PTFE; Suture Material; Tendon Surgery; Mechanical Properties; Flexor Tendon Repair; Linear Tension Strength; Cadaveric Upper Limb; Incision; A1 Pulley; Flexor Digitorum Profundus; Tendon Retractor; Traction

Kinetics of molar mass build-up and degradation in a Polyethylene terephthalate melt - Härth, Michael; Schubert, Dirk W. (8th Annual European Rheology Conference, 2013)

Kinetics of Molar Mass Build-Up and Degradation in a Polyethylene Terephthalate Melt - Härth, Michael; Schubert, Dirk W. (29th International Conference of the Polymer Processing Society, 2013)

Kleine Yagis richtig stocken (2) - Schubert, Dirk W. (CQ DL, 2019)
Yagi-Antennen für das 70-cm-Band sind leicht und handlich. Nach der Vorstellung einfacher Selbstbauvorschläge in Teil 1 geht es hier um das Stocken solcher Yagis.<br
Keywords: Yagis; Amateurfunk; Stocken

Kriech- und Kriecherholungsmessungen zur Charakterisierung von Materialien mit langer charakteristischer Zeit - Walter, Bastian; Kaschta, Joachim (Geesthachter Polymertage: Rheologie von Polymeren für Forschung und Anwendung, 2016)

Lamination and sintering behavior of tape cast, transparent Mg-Al-spinel ceramics - Beck, M.; Hattori, K.; Kaschta, Joachim; Kakimoto, K.; Roosen, A. (Ceramics International, 2015)
High purity Mg–Al–spinel powders were processed to form slurries for tape casting. The dried green tapes were cut and laminated via thermo-compression under uniaxial and isostatic pressure conditions. Finally the laminates were sintered pressurelessly in air. The influence of the transformation temperature of the green tape׳s binder–plasticizer system and of lamination parameters on density and microstructure of the sintered laminates was analyzed. UV‐VIS transmission spectroscopy was performed to measure the transparency of the fired laminates. The interrelation between the lamination parameters, sintering behavior and properties of the sintered product is discussed. Isostatic thermal lamination resulted in higher sintered densities than uniaxial lamination. For both techniques an increase in lamination pressure or temperature led to higher relative densities after sintering. The laminates exhibited total forward transmission values of up to 67% at a wavelength of 700
Keywords: A. Tape casting; Laminated ceramics; D. Spinel; Translucent ceramics

LCB formation in PLA by reactive extrusion - Kaschta, Joachim; Schubert, Dirk W. (Europe Africa Conference 2017 of the Polymer Processing Society, 2017)

Ligand Tuning of Localized Surface Plasmon Resonances in Antimony-Doped Tin Oxide Nanocrystals - Balitskii, Olexiy; Mashkov, Oleksandr; Barabash, Anastasiia; Rehm, Viktor; Afify, Hany A.; Li, Ning; Hammer, Maria; Brabec, Christoph; Eigen, Andreas; Halik, Marcus; Yarema, Olesya; Yarema, Maksym; et al. (Nanomaterials, 2022)
Aliovalent-doped metal oxide nanocrystals exhibiting localized surface plasmons (LSPRs) are applied in systems that require reflection/scattering/absorption in infrared and optical transparency in visible. Indium tin oxide (ITO) is currently leading the field, but indium resources are known to be very restricted. Antimony-doped tin oxide (ATO) is a cheap candidate to substitute the ITO, but it exhibits less advantageous electronic properties and limited control of the LSPRs. To date, LSPR tuning in ATO NCs has been achieved electrochemically and by aliovalent doping, with a significant decrease in doping efficiency with an increasing doping level. Here, we synthesize plasmonic ATO nanocrystals (NCs) via a solvothermal route and demonstrate ligand exchange to tune the LSPR energies. Attachment of ligands acting as Lewis acids and bases results in LSPR peak shifts with a doping efficiency overcoming those by aliovalent doping. Thus, this strategy is of potential interest for plasmon implementations, which are of potential interest for infrared upconversion, smart glazing, heat absorbers, or thermal barriers.
CRIS-Team WoS Importer:2022-10-28

Limitations of Essential-State Models for the Description of Two-Photon Absorption Processes: The Example of Bis(dioxaborine)-Substituted Chromophores - Zojer, E.; Wenseleers, W.; Pacher, P.; Barlow, S.; Halik, Marcus; Grasso, C.; Perry, J. W.; Marder, S. R.; Bredas, J. L. (Journal of Physical Chemistry B, 2004)

Long-chain branched PLA for biaxially streched film - Kaschta, Joachim; Lanzl, Lydia; Lemppenau, Simon; Schubert, Dirk W. (Abstracts, 2016)

Long-chain branched polylactide by reactive extrusion using a multi-functional chain extender - Kaschta, Joachim; Lanzl, Lydia; Schubert, Dirk W. (Book of Abstracts, 2016)

Long-Chain Branches in Syndiotactic Polypropene Induced by Vinyl Chloride - Stadler, Florian; Arikan, Burçak; Kaschta, Joachim; Kaminsky, Walter (Macromolecular Chemistry and Physics, 2010)
Syndiotactic polypropene was synthesized using a metallocene catalyst system and traces of VC. The use of VC was found to decrease the molar mass (M) over bar (w) of the samples distinctly and linearly, while retaining the molar mass distribution, the crystallinity, and the syndiotacticity. The VC, however, initiates the formation of long-chain branches, which were detected by GPC-MALLS and rheology. Besides their effect on the viscosity and modulus functions, a thermorheologic complexity can be observed. Also the flow activation energy E(a) was found to be increased. The modified samples did not obey the eta(0)/(M) over bar (w) relation for linear sPP, indicating the presence of LCBs.
Keywords: GPC-MALLS; long-chain branches; metallocene catalysts; rheology; syndiotactic polypropene

Low-temperature and hysteresis-free electron-transporting layers for efficient, regular, and planar structure perovskite solar cells - Hou, Yi; Ramírez Quiroz, César Omar; Scheiner, Simon; Chen, Wei; Stubhan, Tobias; Hirsch, Andreas; Halik, Marcus; Brabec, Christoph (Advanced Energy Materials, 2015)
With the aim of fully utilizing the low processing temperatures of perovskite solar cells, significant progress in replacing high temperature processed TiO by various low-temperature solution processed electron transporting layers (LT-ETLs) was recently reported. Here, recent progress in the development of LT-ETLs for regular planar structure perovskite solar cells, which is essential for achieving high efficiency in parallel to avoiding hysteresis, is reviewed. In addition, the application of a novel hysteresis-free LT-ETLs for regular planar perovskite solar cells in our laboratory is briefly discussed. By incorporating a low temperature processed WOnanoparticular layer in combination with a mixed fullerene functionalized self-assembled monolayers (SAMs), a regular, planar structure, and hysteresis-free perovskite solar cell with a maximum efficiency of almost 15% can be fabricated. Recent progress in the development of low temperature processed electron-transporting layers for regular planar structure perovskite solar cells is reviewed. Moreover, the application of a novel mixed self-assembled monolayers in hysteresis-free perovskite solar cells is briefly discussed. The as-fabricated perovskite solar cells show a maximum efficiency of almost 15%.
Keywords: electron-transporting layers; hysteresis-free solar cells; low-temperature solution processed; perovskite solar cells

Low-temperature solution-processed memory transistors based on zinc oxide nanoparticles - Faber, Hendrik; Burkhardt, Martin; Jedaa, Abdesselam; Kälblein, D.; Klauk, Hagen; Halik, Marcus (Advanced Materials, 2009)
We report on thin!film transistors based on ZnO nanoparticles processed from solution and with a maximum temperature of 100 °C. Electron mobilities up to 2.5 cm²V−1s−1 are obtained, and top-gate TFTs show non-volatile memory properties with a large, stable hysteresis and a memory ratio of 105. Memory TFTs operate in ambient, have good shelf-life (>6 months), and useful endurance properties.

Low temperature, solution processed metal oxide buffer layers fulfilling large area production requirements - Stubhan, Tobias; Litzov, Ivan; Li, Ning; Wang, Hao; Krantz, Johannes; Machui, Florian; Steidl, M.; Oh, H.; Matt, Gebhard; Brabec, Christoph (Proceedings of SPIE, 2012)
This paper is a review of our previous work on the field of low temperature, solution processed metal oxide buffer layers published in various journals. Our work focuses on zinc oxide (ZnO) and aluminum-doped zinc oxide (AZO) as n-type and molybdenum oxide (MoO3) as p-type solution processed buffer layer. In addition to that, we investigate the surface modification of AZO using phosphonic acid-anchored aliphatic and fullerene self assembled monolayers (SAMs
Keywords: Aluminum-doped zinc oxide; Low temperatures; Metal oxides; P-type; Phosphonic; Production requirements; Solution-processed; Zinc oxide (ZnO) Engineering controlled terms: Aluminum; Metallic compounds; Molybdenum oxide; Optical waveguides; Organic acids; Self assembled monolayers; Temperature; Zinc oxide Engineering main heading: Buffer layers

Low-Voltage Flexible Organic Circuits with Molecular Gate Dielectrics - Klauk, Hagen; Halik, Marcus; Eder, F.; Schmid, Günter; Dehm, C.; Zschieschang, Ute; Rhode, D.; Brederlow, R.; Briole, S.; Maisch, S.; Effenberger, F. (Technical Digest - International Electron Devices Meeting, 2004)

Low-Voltage Organic Field Effect Transistors with a 2-Tridecyl[1]benzothieno[3,2- b ][1]benzothiophene Semiconductor Layer - Amin, Atefeh Y.; Khassanov, Artöm; Reuter, Knud; Meyer-Friedrichsen, Timo; Halik, Marcus (Journal of the American Chemical Society, 2012)
An asymmetric n-alkyl substitution pattern was realized in 2-tridecyl[1]benzothieno[3,2-b][1]benzothiophene (C13-BTBT) in order to improve the charge transport properties in organic thin-film transistors. We obtained large hole mobilities up to 17.2 cm2/(V·s) in low-voltage operating devices. The large mobility is related to densely packed layers of the BTBT π-systems at the channel interface dedicated to the substitution motif and confirmed by X-ray reflectivity measurements. The devices exhibit promising stability in continuous operation for several hours in ambient air.

Low-voltage organic thin film transistors and circuits with molecular gate dielectrics - Halik, Marcus (Proceedings of SPIE, 2005)

Low-voltage organic thin-film transistors with large transconductance - Klauk, Hagen; Zschieschang, Ute; Halik, Marcus (Journal of Applied Physics, 2007)
We have developed an organic thin-film transistor (TFT) technology that aims at providing a good balance of static and dynamic performance parameters. An inverted staggered (bottom-gate, top-contact) device structure with patterned metal gates, a room-temperature-deposited gate dielectric providing a capacitance of 0.7μF∕cm2" role="presentation">0.7μF/cm2, and vacuum-deposited pentacene as the semiconductor were employed. The TFTs have a channel length of 10μm" role="presentation">10μm, a carrier mobility of 0.4cm2∕Vs" role="presentation">0.4cm2/Vs, an on/off current ratio of 107" role="presentation">107, a subthreshold swing of 100mV" role="presentation">100mV/decade, and a transconductance per channel width of 40μS∕mm" role="presentation">40μS∕mm. Ring oscillators operate with supply voltages as low as 2V" role="presentation">2V and with signal propagation delays as low as 200μs" role="presentation">200μs per stag

Low-voltage organic thin film transistor with large transconductance - Klauk, Hagen; Zschieschang, Ute; Halik, Marcus (Journal of Applied Physics, 2007)

Low-voltage organic transistors with an amorphous molecular gate dielectric - Halik, Marcus; Klauk, Hagen; Zschieschang, Ute; Schmid, Günter; Dehm, C.; Schütz, M.; Maisch, S.; Effenberger, F.; Brunnbauer, M.; Stellacci, F. (Nature, 2004)

Low-Voltage p- and n-Type Organic Self-Assembled Monolayer Field Effect Transistors - Novak, Michael; Ebel, Alexander; Meyer-Friedrichsen, Timo; Jedaa, Abdesselam; Vieweg, Benito; Yang, Guang; Voitchovsky, Kislon; Stellacci, Francesco; Spiecker, Erdmann; Hirsch, Andreas; Halik, Marcus (Nano Letters, 2011)
We report on p- and n-type organic self-assembled monolayer field effect transistors. On the base of quaterthiophene and fullerene units, multifunctional molecules were synthesized, which have the ability to self-assemble and provide multifunctional monolayers. The self-assembly approach, based on phosphonic acids, is very robust and allows the fabrication of functional devices even on larger areas. The p- and n-type transistor devices with only one molecular active layer were demonstrated for transistor channel lengths up to 10 μm. The monolayer composition is proven by electrical experiments and by high-resolution transmission electron microscopy, electron energy loss spectroscopy, XPS, and AFM experiments. Because of the molecular design and the contribution of isolating alkyl chains to the hybrid dielectric, our devices operate at low supply voltages (-4 V to +4 V), which is a key requirement for practical use and simplifies the integration in standard applications. The monolayer devices operate in ambient air and show hole and electron mobilities of 10 cm/(V s) and 10 cm/(V s) respectively. In particular the n-type operation of self- assembled monolayer transistors has not been reported before. Hereby, structure-property relations of the SAMs have been studied. Furthermore an approach to protect the sensitive C from immediate degradation within the molecular design is provided. © 2011 American Chemical Society.

Low-Voltage Self-Assembled Monolayer Field-Effect Transistors on Flexible Substrates - Schmaltz, Thomas; Amin, Atefeh Y.; Khassanov, Artöm; Meyer-Friedrichsen, Timo; Steinrück, Hans-Georg; Magerl, Andreas; Segura, Juan Jose; Voitchovsky, Kislon; Stellacci, Francesco; Halik, Marcus (Advanced Materials, 2013)
Self-assembled monolayer field-effect transistors (SAMFETs) of BTBT functionalized phosphonic acids are fabricated. The molecular design enables device operation with charge carrier mobilities up to 10 cm V s and for the first time SAMFETs which operate on rough, flexible PEN substrates even under mechanical substrate bending. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Magnetic Liquid Silicone Rubber - Schubert, Dirk W.; Heitbrink, Alexander (Programme and Book of Abtracts, 2016)

Magnetic Liquid Silicone Rubber – Revealing Effects and Process Limitations - Schubert, Dirk W.; Werner, Siegfried; Heitbrink, Alexander (Macromolecular Symposia, 2017)
Keywords: composites; elastomers; magnetic polymers; permeability; process limits

Magnetic Liquid Silicone Rubber - Revealing Effects and Process Limits - Schubert, Dirk W.; Heitbrink, Alexander (Abstracts, 2016)

Magnetic Removal of Micro- and Nanoplastics from Water—from 100 nm to 100 µm Debris Size - Gaß, Henrik; Höfling, Anna; Müller, Lukas; Rockmann, Linda; Schubert, Dirk W.; Halik, Marcus; Kloos, Tonya (Small, 2023)
Clean water is one of the most important resources of the planet but human-made contamination with diverse pollutants increases continuously. Microplastics (<5 mm diameter) which can have severe impacts on the environment, are present worldwide. Degradation processes lead to nanoplastics (<1 µm), which are potentially even more dangerous due to their increased bioavailability. State-of-the-art wastewater treatment plants show a deficit in effectively eliminating micro- and nanoplastics (MNP) from water, particularly in the case of nanoplastics. In this work, the magnetic removal of three different MNP types across three orders of magnitude in size (100 nm–100 µm) is investigated systematically. Superparamagnetic iron oxide nanoparticles (SPIONs) tend to attract oppositely charged MNPs and form aggregates that can be easily collected by a magnet. It shows that especially the smallest fractions (100–300 nm) can be separated in ordinary high numbers (1013 mg−1 SPION) while the highest mass is removed for MNP between 2.5 and 5 µm. The universal trend for all three types of MNP can be fitted with a derived model, which can make predictions for optimizing SPIONs for specific size ranges in the futur

Magnetic water cleaning - Halik, Marcus; Sarcletti, Marco; Zahn, Dirk (Nachrichten aus der Chemie, 2021)

Magnetite nanoparticles as efficient materials for removal of glyphosate from water - Park, Hyoungwon; May, Alexander; Portilla, Luis; Dietrich, Hanno; Münch, Friedrich; Rejek, Tobias; Sarcletti, Marco; Banspach, Leena; Zahn, Dirk; Halik, Marcus (Nature Sustainability, 2019)
Glyphosate is one of the most commonly used herbicides, but, due to its suspected toxicity, it is simultaneously the most disputed one. Its worldwide application in huge quantities may lead to water concentrations that locally exceed statutory contamination levels. Therefore, a simple toolkit is required to remove glyphosate and its major metabolite from water. Here we show a method for the magnetic remediation of glyphosate from artificial and real water samples to below the maximum permissible value or even below the analytical detection limit. The chemical structure of glyphosate enables fast and stable covalent binding on the surface of magnetite (Fe3O4) nanoparticles, which act as catchers and carriers for magnetic removal. The small size of the nanoparticles ( 20 nm diameter) provides a large active area. The glyphosate binding was analysed by infrared spectroscopy, thermogravimetric analysis and dynamic light scattering, while the remediation was investigated by liquid chromatography–mass spectrometry. Results from molecular dynamics simulations support the proposed binding mechanism. The combination of efficient remediation with inexpensive and recyclable magnetite nanoparticles suggests a simple method for the sustainable removal of glyphosate, and the concept may lead to a general approach to eliminate this class of organophosphorus compounds from water.
CRIS-Team Scopus Importer:2019-12-31

Magneto-Rheological fluids and elastomers based on injection moldable liquid silicone - Kaschta, Joachim; Musialek, Matthias; Böse, Holger; Schubert, Dirk W. (Book of Abstracts, 2011)

Magneto-rheological Fluids and Elastomers Based on Injection Moldable Liquid Silicone - Kaschta, Joachim; Musialek, Matthias; Böse, Holger; Schubert, Dirk W. (Final Program and Book of Abstract, 2011)

Magneto-Sensitive Elastomers: An Experimental Point of View - Walter, Bastian; Saxena, Prashant; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (85th Annual Meeting of the International Association of Applied Mathematics and Mechanics, 2014)

Manufacturing Nanoparticles with Orthogonally Adjustable Dispersibility in Hydrocarbons, Fluorocarbons, and Water - Zeininger, Lukas; Stiegler, Lisa; Portilla Berlanga, Luis; Halik, Marcus; Hirsch, Andreas (ChemistryOpen, 2018)

Mapping Charge-Carrier Density across the p-n Junction in Ambipolar Carbon-Nanotube Networks by Raman Microscopy - Grimm, Stefan; Jakubka, Florian; Schießl, Stefan; Gannott, Florentina; Zaumseil, Jana (Advanced Materials, 2014)
In situ confocal Raman microscopy is used to map the recombination zone (induced p-n junction) in an ambipolar carbon-nanotube-network transistor with high spatial resolution. The shift of the 2D mode (G' mode) depending on hole and electron accumulation serves as a measure for the local charge-carrier density and provides complementary information about charge transport and recombination in ambipolar transistors.
EAM Import::2019-03-12

Mapping charge transport by electroluminescence in chirality-selected carbon nanotube networks - Jakubka, Florian; Backes, Claudia; Gannott, Florentina; Mundloch, Udo; Hauke, Frank; Hirsch, Andreas; Zaumseil, Jana (Acs Nano, 2013)
We demonstrate random network single-walled carbon nanotube (SWNT) field-effect transistors (FETs) in bottom contact/top gate geometry with only five different semiconducting nanotube species that were selected by dispersion with poly(9,9-dioctylfluorene) in toluene. These FETs are highly ambipolar with balanced hole and electron mobilities and emit near-infrared light with narrow peak widths (<40 meV) and good efficiency. We spatially resolve the electroluminescence from the channel region during a gate voltage sweep and can thus trace charge transport paths through the SWNT thin film. A shift of emission intensity to large diameter nanotubes and gate-voltage-dependent photoluminescence quenching of the different nanotube species indicates excitation transfer within the network and preferential charge accumulation on small band gap nanotubes. Apart from applications as near-infrared emitters with selectable emission wavelengths and narrow line widths, these devices will help to understand and model charge transport in realistic carbon nanotube networks. © 2013 American Chemical Society.

Mapping, modelling and characterizing multifilament melt-spinning processes in dependence of variable process parameters and the number of dies - Lanyi, Franz; Schrüfer, Stefan; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Mapping of the Electrical Resistance for PMMA/CB Nanocomposite - Liu, Xian Hu; Krückel, Johannes; Schubert, Dirk W. (29th International Conference of the Polymer Processing Society, 2013)

Mapping of the electrospinning parameters for PLGA-Nanofibers - Regelmann, Christian; Küng, Florian; Stafiej, Piotr; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (15th Bayreuth Polymer Symposium, 2017)

Mapping of the Mechanical Properties of Silicone Breast Implants - Daenicke, Jonas; Horch, Raymund E.; Schubert, Dirk W. (Abstracts, 2012)

Mapping the electrical conductivity of carbon black filled composites prior to and after shear - Liu, Xian Hu; Krückel, Johannes; Schubert, Dirk W. (Polychar 22nd, 2014)

Mapping the Electrical Conductivity of Carbon Black filled Composites prior to and after shear - Liu, Xian Hu; Krückel, Johannes; Schubert, Dirk W. (9th Annual European Rheology Conference, 2014)

Mapping the Electrical Conductivity of Poly(methyl methacrylate)/Carbon Black Composites Prior to and after Shear - Liu, Xian Hu; Krückel, Johannes; Zheng, Guoqiang; Schubert, Dirk W. (ACS Applied Materials and Interfaces, 2013)
In this letter, the electrical conductivity of disklike poly(methyl methacrylate)/carbon black composite samples was investigated prior to and after a shear process. Novel electrical conductivity maps of the samples as a function of the position were obtained. It was found that the electrical conductivity after angular averaging of the static (nonsheared) sample is, as expected, independent of the radius. However, for the sheared sample, the electrical conductivity is decreasing from the center to the outer rim of the sample. This is attributed to the interplay of destruction and buildup effects of the applied linear shear stress on the agglomerate network.
Keywords: carbon black; conductivity; mapping; polymer composites; shear stress

Master Curves for Spreading Dynamics of Polymer Fluids, Polymeric Materials - Härth, Michael; Schubert, Dirk W. (Abstracts, 2012)

Master Curves for Spreading Dynamics of Polymeric Fluids - Härth, Michael; Schubert, Dirk W. (Book of Abstracts, 2013)

Material models for stability analysis in fibre spinning - Bechert, Mathias; Schubert, Dirk W. (Book of Abstracts, 2013)

Materialspezifische Vorraussetzung für das Lasersintern von Polyetheretherketonen als Knochenersatz für den Schädelbereich - Pohle, Dirk; Rechtenwald, T.; von Wilmowsky, Cornelius; Neukam, Friedrich Wilhelm; Münstedt, Helmut (BIOmaterialien, 2007)
LFT Import::2019-07-16 (1427)

Measurement of Skeletal Muscle Fiber Contractility with High-Speed Traction Microscopy - Böhringer, David; Rausch, Martin; Steinmann, Martin; Schrüfer, Stefan; Schubert, Dirk W.; Haertl, Annamaria; Mark, Christoph; Fabry, Ben (BIOPHYSICAL JOURNAL, 2020)
CRIS-Team WoS Importer:2020-03-13

Measurement of Skeletal Muscle Fiber Contractility with High-Speed Traction Microscopy - Rausch, Martin; Böhringer, David; Steinmann, Martin; Schubert, Dirk W.; Schrüfer, Stefan; Mark, Christoph; Fabry, Ben (Biophysical Journal, 2020)
We describe a technique for simultaneous quantification of the contractile forces and cytosolic calcium dynamics of muscle fibers embedded in three-dimensional biopolymer gels under auxotonic loading conditions. We derive a scaling law for linear elastic matrices such as basement membrane extract hydrogels (Matrigel) that allows us to measure contractile force from the shape of the relaxed and contracted muscle cell and the Young's modulus of the matrix without further knowledge of the matrix deformations surrounding the cell and without performing computationally intensive inverse force reconstruction algorithms. We apply our method to isolated mouse flexor digitorum brevis (FDB) fibers that are embedded in 10 mg/mL Matrigel. Upon electrical stimulation, individual FDB fibers show twitch forces of 0.37 ± 0.15 μN and tetanic forces (100-Hz stimulation frequency) of 2.38 ± 0.71 μN, corresponding to a tension of 0.44 ± 0.25 kPa and 2.53 ± 1.17 kPa, respectively. Contractile forces of FDB fibers increase in response to caffeine and the troponin-calcium stabilizer tirasemtiv, similar to responses measured in whole muscle. From simultaneous high-speed measurements of cell length changes and cytosolic calcium concentration using confocal line scanning at a frequency of 2048 Hz, we show that twitch and tetanic force responses to electric pulses follow the low-pass filtered calcium signal. In summary, we present a technically simple high-speed method for measuring contractile forces and cytosolic calcium dynamics of single muscle fibers. We expect that our method will help to reduce preparation time, costs, and the number of sacrificed animals needed for experiments such as drug testing.
CRIS-Team Scopus Importer:2020-01-24

Measuring the Dielectric Breakdown Strength Of Silicone Elastomers - Avoiding Experimental Artefacts - Ziegmann, Andreas; Klaußner, Stefan; Schubert, Dirk W. (Book of Abstracts, 2016)

Mechanical force sensors using organic thin-film transistors - Darlinski, G.; Böttger, U.; Waser, R.; Klauk, Hagen; Halik, Marcus; Zschieschang, Ute; Schmid, Günter; Dehm, C. (Applied Physics, 2005)

Mechanical properties of silicone breast implants under compression load and its effect on the implant shape and the shell material - von Hanstein, Harald; Daenicke, Jonas; Schubert, Dirk W. (International Workshop on Silicone Based Polymers, 2017)

Mechanical stress relaxation of medical tubing for infusion therapy: predicting product performance by material modelling - Kremser, Thomas; Schubert, Dirk W. (Europe Africa Conference 2017 of the Polymer Processing Society, 2017)

Memory Effect of Self-Assembled PS-b-PEO Block Copolymer Films with Selectively Embedded Functionalized TiO2 Nanoparticles - Kirschner, Johannes; Will, Johannes; Rejek, Tobias; Portilla Berlanga, Luis; Berlinghof, Marvin; Schweizer, Peter; Spiecker, Erdmann; Steinrück, Hans-Georg; Unruh, Tobias; Halik, Marcus (Advanced Materials Interfaces, 2017)
The memory effect in organic thin film transistors is described with a dielectric hybrid material composed of selectively localized charge trapping titania nanoparticles in a polystyrene-b-polyethyleneoxide (PS-b-PEO) diblock copolymer film. Upon solvent annealing in toluene atmosphere, the films readily form nanophase-separated features of PEO cylinders in a matrix of PS. X-ray reflectivity (XRR) investigations reveal that the TiO2 particles are selectively distributed in the top half of the hybrid layers. Applied in organic thin film transistor devices with 2-tridecyl-[1]benzothieno[3,2-b][1]benzothiophen (mono-C13-BTBT) semiconductor, the hybrid layers induce clockwise drain current hysteresis with promising memory ratio, long-term stability, and endurance. The occurrence of nonvolatile charge trapping directly relates to the hierarchically assembled nanostructure of the nanoparticles in the block copolymer since reference devices with PS homopolymers blended with TiO2 are found to be hysteresis free. Morphological characterization of the hybrid dielectric layers by atomic force microscopy and XRR experiments is presented to shed light on the internal electron density distribution. The layers are subsequently tested in capacitor stacks and transistors.

Mending a broken heart by biomimetic 3D printed natural biomaterial-based cardiac patches: a review - Rosellini, Elisabetta; Cascone, Maria Grazia; Guidi, G. M.; Schubert, Dirk W.; Roether, Judith; Boccaccini, Aldo R. (Frontiers in Bioengineering and Biotechnology, 2023)
Myocardial infarction is one of the major causes of mortality as well as morbidity around the world. Currently available treatment options face a number of drawbacks, hence cardiac tissue engineering, which aims to bioengineer functional cardiac tissue, for application in tissue repair, patient specific drug screening and disease modeling, is being explored as a viable alternative. To achieve this, an appropriate combination of cells, biomimetic scaffolds mimicking the structure and function of the native tissue, and signals, is necessary. Among scaffold fabrication techniques, three-dimensional printing, which is an additive manufacturing technique that enables to translate computer-aided designs into 3D objects, has emerged as a promising technique to develop cardiac patches with a highly defined architecture. As a further step toward the replication of complex tissues, such as cardiac tissue, more recently 3D bioprinting has emerged as a cutting-edge technology to print not only biomaterials, but also multiple cell types simultaneously. In terms of bioinks, biomaterials isolated from natural sources are advantageous, as they can provide exceptional biocompatibility and bioactivity, thus promoting desired cell responses. An ideal biomimetic cardiac patch should incorporate additional functional properties, which can be achieved by means of appropriate functionalization strategies. These are essential to replicate the native tissue, such as the release of biochemical signals, immunomodulatory properties, conductivity, enhanced vascularization and shape memory effects. The aim of the review is to present an overview of the current state of the art regarding the development of biomimetic 3D printed natural biomaterial-based cardiac patches, describing the 3D printing fabrication methods, the natural-biomaterial based bioinks, the functionalization strategies, as well as the in vitro and in vivo application

Mesenchymal stem cells and myoblast differentiation under HGF and IGF-1 stimulation for 3D skeletal muscle tissue engineering - Witt, Ramona; Weigand, Annika; Boos, Anja; Dippold, Dirk; Boccaccini, Aldo R.; Schubert, Dirk W.; Hardt, Moritz; Lange, Claudia; Arkudas, Andreas; Horch, Raymund E.; Beier, Justus; Cai, Aijia (Bmc Cell Biology, 2017)
Keywords: Mesenchymal stem cells; Myogenic differentiation; HGF; IGF-1; PCL-collagen nanofibers; Skeletal muscle tissue engineering

Mesenchymal stem cells and myoblast differentiation under HGF and IGF-1 stimulation for 3D skeletal muscle tissue engineering - Witt, Ramona; Weigand, Annika; Boos, Anja; Dippold, Dirk; Schubert, Dirk W.; Boccaccini, Aldo R.; Arkudas, Andreas; Horch, Raymund E.; Beier, Justus (Bmc Cell Biology, 2017)
Keywords: HGF; IGF-1; Mesenchymal stem cells; Myogenic differentiation; PCL-collagen nanofibers; Skeletal muscle tissue engineering

Microcontact-Printed Self-Assembled Monolayers as Ultrathin Gate Dielectrics in Organic Thin-Film Transistors and Complementary Circuits - Zschieschang, Ute; Halik, Marcus; Klauk, Hagen (Langmuir, 2008)

Mind the Process – How to Boost Reproducibility, Precision and Printing Time of Gelatin-based Bioinks - Scheuring, Ruben; Schrüfer, Stefan; Schubert, Dirk W.; Groll, Jürgen (ISBF 2022 - International conference of biofabrication, 2022)
Keywords: Biofabrikation

Mixed Organic Ligand Shells: Controlling the Nanoparticle Surface Morphology toward Tuning the Optoelectronic Properties - Henkel, Christian; Wittmann, Judith; Träg, Johannes; Will, Johannes; Stiegler, Lisa; Strohriegl, Peter; Hirsch, Andreas; Unruh, Tobias; Zahn, Dirk; Halik, Marcus; Guldi, Dirk Michael (Small, 2020)
Precise control over the ratio of perylene bisimide (PBI) monomers and aggregates, immobilized on alumina nanoparticle (NP) surfaces, is demonstrated. Towards this goal, phosphonic acid functionalized PBI derivatives (PA-PBI) are shown to self-assemble into stoichiometrically mixed monolayers featuring aliphatic, glycolic, or fluorinated phosphonic acid ligands, serving as imbedding matrix (PA-M) to afford core-shell NPs. Different but, nevertheless, defined PBI monomer/aggregate composition is achieved by either the variation in the PA-PBI to PA-M ratios, or the utilization of different PA-Ms. Various steady-state as well as time-resolved spectroscopy techniques are applied to probe the core-shell NPs with respect to changes in their optical properties upon variations in the shell composition. To this end, the ratio between monomer and excimer-like emission assists in deriving information on the self-assembled monolayer composition, local ordering, and corresponding aggregate content. With the help of X-ray reflectivity measurements, accompanied by molecular dynamics simulations, the built-up of the particle shells, in general, and the PBI aggregation behavior, in particular, are explored in depth.
CRIS-Team WoS Importer:2019-12-10

Mixed self-assembled monolayer of molecules with dipolar and acceptor character-Influence on hysteresis and threshold voltage in organic thin-film transistors - Jedaa, Abdesselam; Salinas Batallas, Michael; Jäger, Christof; Clark, Timothy; Ebel, Alexander; Hirsch, Andreas; Halik, Marcus (Applied Physics Letters, 2012)
In this report, we investigate the impact of the molecular dipole moment and redox active head groups (C ) in pure and mixed self-assembled monolayers (SAMs), which serve as an ultra-thin hybrid dielectric layer in low-voltage operating organic thin-film transistors. We show that the dipole of the SAM-forming molecules affects the threshold voltage, while the concentration of redox-active C moieties determines the hysteresis in devices with α,α′-dihexyl-sexithiophene and pentacene as organic semiconductors. © 2012 American Institute of Physics.

Modeling charge transport in C60-based self-assembled monolayers for applications in field-effect transistors - Leitherer, Susanne; Jäger, Christof; Halik, Marcus; Clark, Timothy; Thoss, Michael (Journal of Chemical Physics, 2014)
We have investigated the conductance properties of C60-containing self-assembled monolayers (SAMs), which are used in organic field-effect transistors, employing a combination of molecular-dynamics simulations, semiempirical electronic structure calculations, and Landauer transport theory. The results reveal the close relation between the transport characteristics and the structural and electronic properties of the SAM. Furthermore, both local pathways of charge transport in the SAMs and the influence of structural fluctuations are analyzed.
UnivIS-Import:2015-04-14:Pub.2014.nat.dphy.ITP.ppem.modeli

Modelling and optimization of electro spun biodegradable polymers: Revealing novel power laws regarding fiber diameter - Munawar, Muhammad; Schubert, Dirk W. (Deutsche Gesellschaft für Biomaterialien - Annual Meeting, 2018)
Keywords: electro spun; electrospinning

Modelling of Fibre Spinning Instabilities Under Industrial Process Conditions - Bechert, Mathias; Schubert, Dirk W. (29th International Conference of the Polymer Processing Society, 2013)

Model to Predict Polymer Fibre Diameter during Melt Spinning - Bier, Alexander; Redel, Michael; Schubert, Dirk W. (Advances in Polymer Technology, 2023)
Polymeric materials were evaluated with regard to their spinnability and respective fibre diameters. A modified single fibre spinning device was firstly used to derive a novel generalised model, utilising process parameters (die diameter, throughput, and stretching relevant take-up pressures) and material properties (zero shear viscosity) to predict the diameter of polymeric fibres on the basis of four different polymers. Further evaluation of the resulting power law dependence was conducted on filaments produced via conventional melt spinning and meltblown processes. Fibres produced on the pilot machines showed close agreement with the model equation with only the need to adjust an easily calculable device dependent factor. The outcome of the presented work is a user-friendly model of high practical relevance, which can be used to predict the diameter of amorphous and semicrystalline polymeric fibres, independent of material and machine used with sufficient accuracy for fast estimations.

Molar Mass and Molecular Weight Distribution Determination Of UHMWPE Synthesized Using a Living Homogeneous Catalyst - Saeid, Talebi; Rob, Duchateau; Sanjay, Rastogi; Peters, Gerrit; Kaschta, Joachim; Peters, Gerrit W. M.; Lemstra, Piet J. (Macromolecules, 2010)
Understanding of the physical characteristics of a polymer requires molar mass determination. For the commercially available polymers, having average molar mass below 1000000 g/mol, chromatography is the method that is often applied to determine the molar mass and molar mass distribution. However, the application of conventional chromatography techniques for polymers having molar mass > 1000 000 g/mol becomes very challenging, and often the results are disputed. In this article, melt rheometry based on the "modulus model" is utilized to measure the molar mass and polydispersity of ultra high-molecular-weight polyethylenes (UHMWPEs) having molar mass > 1000 000 g/mol. Results are compared with the chromatography data of the same polymer samples and the boundary conditions where the chromatography technique fails, whereas the rheometry provides the desired information is discussed. The rheological method is based on converting the relaxation spectrum from the time domain to the molecular weight domain and then Using a regularized integral inversion to recover the molecular weight distribution curve. The method is of relevance in determining very high molar masses (exceeding 3000000 g/mol) that cannot be ascertained conclusively with the existing chromatography techniques. For this study, UHMWPEs with various weight-average molar masses, where the number-average molar mass exceeds > 1000000 g/mol, are synthesized. Catalyst used for the synthesis is a living homogeneous catalyst system: MAO-activated bis(phenoxy imine) titanium dichloride. The rheological behavior of the thus synthesized nascent reactor powders confirms the disentangled state of the polymer that tends to entangle with time in mel

Molar mass and temperature dependence of rheological properties of polymethylmethacrylate melt - Lu, Zhili; Pan, Yamin; Liu, Xianhu; Zheng, Guoqiang; Schubert, Dirk W.; Liu, Chuntai (Materials Letters, 2018)
The influence of molar mass and temperature on the rheological properties of polymethylmethacrylate (PMMA) melts was investigated by dynamical mechanical and creep-recovery experiments. The results shown that the steady state viscosities obtained from both experimental modes were in good agreement, and a well linear relationship between the activation energy and molar mass was obtained. The creep compliance of PMMA increased with the molar mass increased or temperature decreased, while the linear steady state recoverable compliance was found to be independent of the molar mass and temperature. Moreover, it was found that the master curves followed the time-temperature superposition principle well in the whole frequency range or time scal
Keywords: Amorphous materials; Creep; Activation energy; Molar mass; Viscosity

Molecular and Rheological Properties of Peroxide Modified LDPE Based Wood Plastic Composites - Kaschta, Joachim; Harnnarongchai, Wanlop; Schubert, Dirk W. (6th International Symposium on the Separation and Characterization of Natural and Synthetic Macromolecules, 2013)

Molecular changes induced in melanoma by cell culturing in 3D alginate hydrogels - Kappelmann-Fenzl, M.; Schmidt, Sonja; Fischer, Stefan; Schmid, Rafael; Lämmerhirt, Lisa; Fischer, Lena; Schrüfer, Stefan; Thievessen, Ingo; Schubert, Dirk W.; Matthies, Alexander Oliver; Detsch, Rainer; Boccaccini, Aldo R.; et al. (Cancers, 2021)
Alginate hydrogels have been used as a biomaterial for 3D culturing for several years. Here, gene expression patterns in melanoma cells cultivated in 3D alginate are compared to 2D cultures. It is well-known that 2D cell culture is not resembling the complex in vivo situation well. However, the use of very intricate 3D models does not allow performing high-throughput screening and analysis is highly complex. 3D cell culture strategies in hydrogels will better mimic the in vivo situation while they maintain feasibility for large-scale analysis. As alginate is an easy-to-use material and due to its favorable properties, it is commonly applied as a bioink component in the growing field of cell encapsulation and biofabrication. Yet, only a little information about the transcriptome in 3D cultures in hydrogels like alginate is available. In this study, changes in the transcriptome based on RNA-Seq data by cultivating melanoma cells in 3D alginate are analyzed and reveal marked changes compared to cells cultured on usual 2D tissue culture plastic. Deregulated genes represent valuable cues to signaling pathways and molecules affected by the culture method. Using this as a model system for tumor cell plasticity and heterogeneity, EGR1 is determined to play an important role in melanoma progression.
CRIS-Team Scopus Importer:2021-08-20
Keywords: 3D cultivation; Biomaterials; EGR1; Melanoma; Whole transcriptome

Molecular Dynamics Simulation of Phosphonic Acid–Aluminum Oxide self-organization and their evolution into ordered monolayers - Dietrich, Hanno; Schmaltz, Thomas; Halik, Marcus; Zahn, Dirk (Physical Chemistry Chemical Physics, 2017)
We outline an unprejudiced molecular dynamics simulation approach to study the mechanisms of self-organization encompassing the evolution of surfactant–surface interactions to the growth of self-assembled monolayers (SAMs). Therein, the time-length scale problem is tackled by combining an efficient docking-type procedure for implementing surfactant-by-surfactant association with detailed molecular simulations to explore structural relaxation. For this, nanosecond-scale molecular dynamics simulations unravel ordering processes during the gradual assembly of the monolayer. Along this line, different packing motifs of octadecyl phosphonic acid (ODPA) on the (0001) surface of extgreeka-alumina and implications for the final density and ordering of the resulting monolayers are elucidated. Moreover, the role of the solvent is discriminated by comparing SAM formation in 2-propanol, hexane and in a vacuum.

Molecular order of mixed self-assembled monolayers studied by surface vibrational spectroscopy - Rumpel, Armin; Novak, Michael; Braunschweig, Björn; Halik, Marcus; Peukert, Wolfgang (Materials Engineering and Sciences Division - Core Programming Topic at the 2011 AIChE Annual Meeting, 2011)

Molecular structure and rheological properties of a poly(ethylene terephthalate) modified by two different chain extenders - Härth, Michael; Dörnhöfer, Andrea; Kaschta, Joachim; Münstedt, Helmut; Schubert, Dirk W. (Journal of Applied Polymer Science, 2020)
This paper compares the molecular structure and rheological properties of a commercial poly(ethylene terephthalate) (PET) after reactive processing with different concentrations of either pyromellitic dianhydride (PMDA) or a multifunctional epoxide (Joncryl®ADR‐4368) as a chain extender. By size exclusion chromatography with triple detection, an increase of molar mass, a broadening of molar mass distribution, and the generation of long‐chain branched molecules were found for both chain extenders. While gel‐free materials were obtained with PMDA, the processing with Joncryl leads to the formation of gels. The effect of branching, indicated by the Mark–Houwink exponent, is more pronounced for materials with Joncryl compared to PMDA and points to a more compact branching structure of the PET/Joncryl molecules. Rheological measurements in shear and elongation support the analysis from SEC and reveal a complex tree‐like branching structure for both chain extenders. In addition, the role of the two modifiers with respect to processing was assessed.<br

Molecular structure influence on bending behavior of polyester filaments examined using a modified cantilever bending test - Höhnemann, Tim; Himmler, Marcus; Schubert, Dirk W. (Journal of Applied Polymer Science, 2019)
An experimental setup used to measure the bending stiffness of polymer filaments based on existing cantilever approaches is presented. Additionally, it is utilized to evaluate the influence of molar mass and long‐chain branching on filaments of poly(butylene terephthalate), modified with a multifunctional chain extender. Using shear rheological analysis process limits for extrusion of the modified material were revealed, indicated by a change of the curve shape of van Gurp–Palmen plots. For the processable modified materials, it was found that increasing molar mass and degree of long‐chain branching, caused by the modification, raise the bending stiffness of filaments. Also the Young's modulus was found to increase with the amount of chain extender used, while no difference could be generated by using different linear molar grades of the polymer
Keywords: bending; crosslinking; fibers; mechanical properties; polyesters; polymer bristles; properties and characterization; rheology; spectroscopy; structure‐property relations

Molecular Thin Film Transistors with a Subthreshold Swing of 100 mV/decade - Klauk, Hagen; Halik, Marcus; Zschieschang, Ute; Brederlow, R.; Briole, S.; Schütz, M.; Maisch, S.; Effenberger, F.; Schmid, Günter; Dehm, C. (Technical Digest - International Electron Devices Meeting, 2003)

Morphological Development of Conductive Nanofillers in Polymer Melts - Krückel, Johannes; Schubert, Dirk W. (Abstracts, 2012)

Morphological impact of zinc oxide layers on the device performance in thin-film transistors - Faber, Hendrik; Klaumünzer, Martin; Voigt, Michael; Galli, Diana; Vieweg, Benito; Peukert, Wolfgang; Spiecker, Erdmann; Halik, Marcus (Nanoscale, 2011)
Zinc oxide thin-films are prepared either by spin coating of an ethanolic dispersion of nanoparticles (NP, diameter 5 nm) or by spray pyrolysis of a zinc acetate dihydrate precursor. High-resolution electron microscopy studies reveal a monolayer of particles for the low temperature spin coating approach and larger crystalline domains of more than 30 nm for the spray pyrolysis technique. Thin-film transistor devices (TFTs) based on spray pyrolysis films exhibit higher electron mobilities of up to 24 cm² V−1 s−1 compared to 0.6 cm² V−1 s−1 for NP based TFTs. These observations were dedicated to a reduced number of grain boundaries within the transistor channel.

Morphology analysis of near IR sensitized polymer/fullerene organic solar cells by implementing low bandgap heteroanalogue C-/Si-PCPDTBT - Ameri, Tayebeh; Khoram, Parisa; Heumüller, Thomas; Baran, Derya; Machui, Florian; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Halik, Marcus; Rathgeber, Silke; Scherf, Ullrich; Brabec, Christoph (Journal of Materials Chemistry A, 2014)
In the current work, we have investigated the morphological aspects of the ternary solar cells based on host matrices of P3HT:PCBM and P3HT:ICBA, using the low bandgap polymer analogues of C- and Si-bridged PCPDTBT as near IR sensitizers, which show noticeably different performance. A direct comparison of these well-functional and poorly functional ternary blend systems provides insights into the bottlenecks of device performance and enables us to set up an initial set of design rules for ternary organic solar cells. Our study reveals the importance of surface energy as a driving force controlling sensitizer location and morphology formation of ternary blends. The interfacial surface energy results indicate that Si-PCPDTBT locates at amorphous interfaces and P3HT crystallites, while C-PCPDTBT tends to accumulate at amorphous interfaces and semi-crystalline (or agglomerated) domains of the fullerene derivatives. GIWAXS and SCLC results support this prediction where adding high content of C-PCPDTBT influences mainly the semi-crystallinity (aggregation) of the fullerene and reduces the electron mobility, but Si-PCPDTBT impacts mainly the P3HT ordering and, in turn, deteriorates the hole mobility. These findings show that the disruption of the fullerene semi-crystalline domains is more detrimental to the device performance than the disruption of the polymer domains.

Morphology-Controlled Organic Solar Cells Improved by a Nanohybrid System of Single Wall Carbon Nanotubes Sensitized by PbS Core/Perovskite Epitaxial Ligand Shell Quantum Dots - Soltani, Rezvan; Katbab, Ali Asghar; Sytnyk, Mykhailo; Amin, Atefeh Y.; Killilea, Niall Andrew; Berlinghof, Marvin; Ahmadloo, Farzaneh; Osvet, Andres; Unruh, Tobias; Heiß, Wolfgang; Ameri, Tayebeh (Solar RRL, 2017)
In the present work, a new solution processed nanohybrid system comprising of single-wall carbon nanotubes (SWCNTs) loaded by PbS quantum dots (QD) capped with an epitaxial ligand shell of methylammonium lead iodide perovskite clusters (MA4PbI6) is designed and fabricated. Attachment of PbS/PbI6 QDs on the surface of SWCNT is followed and evidenced by performing Fourier Transform Infrared Spectroscopy, X-ray photoelectron spectroscopy, and Field Emission Scanning Electron Microscopy. The steady state and dynamic photoluminescence results reveal efficient charge transfer from photo-excited PbS/PbI6 to SWCNTs. Very low amount (0.3 wt.%) of the as-synthesized PbS/PbI6-SWCNT is further incorporated into a polymeric solar cell containing P3HT and PC61BM and exhibits a power conversion efficiency improvement of around 15% compared to the P3HT:PC61BM bulk heterojunction reference solar cell. Significantly, loading perovskite capped PbS QDs on the surface of SWCNT works more efficient rather than incorporating PbS/PbI6 or SWCNT separately onto the composition of the photoactive layer. While PbS/PbI6 broaden the absorption window of photoactive layer and enhance the photon harvesting, their loading on the SWCNT has a significant influence on the faster exciton splitting by efficient electron transfer as well as keeping the desired crystallinity and nanoscale morphology of host matrix upon addition of QDs.

Morphology development, melt linear viscoelastic properties and crystallinity of polylactide/polyethylene/organoclay blend nanocomposites - Abdolrasouli, Medi Haji; Nazockdast, Hossein; Sadeghi, Gity Mir Mohamad; Kaschta, Joachim (Journal of Applied Polymer Science, 2015)
Polylactide/polyethylene blends (PLA/PE) and their nanocomposites were prepared via the melt blending process. The effects of organoclay, compatibilizer (PE‐g‐MA), and PE content on morphology, linear viscoelastic properties of the melt and cold crystallization of the samples have been studied. The Palierne model is applied to predict the rheological behavior of unfilled blends. It implies that there is a quantitative agreement between model and experimental data for low PE content blend. From WAXD and the rheological behavior, it is shown that organoclay exhibits a higher extent of intercalation and dispersion in PLA/PE/organoclay nanocomposite than in PLA/organoclay nanocomposite. The DSC results present that the addition of compatibilizer into blend nanocomposite increases cold crystallization temperature of PLA by about 3°C. This can be explained by the role of compatibilizer in transfer of a part of organoclay from PLA matrix to droplets resulting in increase of PLA chain mobility and, therefore, slightly greater cold crystallization temperature.
Keywords: Clay; Morphology; Crystallization; Rheology

Multifunctional and Tunable Surfaces Based on Pyrene Functionalized Nanoparticles - Wittmann, Judith; Stiegler, Lisa; Henkel, Christian; Träg, Johannes; Götz, Klaus; Unruh, Tobias; Zahn, Dirk; Hirsch, Andreas; Guldi, Dirk Michael; Halik, Marcus (Advanced Materials Interfaces, 2019)
The tuning of the optical properties of pyrene, immobilized on alumina nanoparticle surfaces, is demonstrated. To this end, phosphonic acid functionalized pyrene derivatives are shown to self‐assemble into stoichiometrically mixed monolayers featuring hydrophilic, hydrophobic, or fluorophilic phosphonic acid ligands and to form defined core–shell hybrids depending on the molecular mixing ratio and the nature of the ligand monomer, excimer, or mutual emission of both evolved. The spectroscopic observations are explained by the respective mobility of the dye molecules with respect to their fixed, specific anchor points and the resulting probability to form excimers and are supported by molecular dynamic simulations, X‐ray reflectivity measurements, and temperature‐dependent steady‐state fluorescence assays. In terms of an additional tuning of the emission color change and/or the on‐off switching of the fluorescence, the formation of core–shell–shell system is carried out by applying amphiphiles. The general concept is fully transferable to demobilized films of nanoparticles, thereby enabling a switchable solid‐state surfac

Multifunctional Chitosan-45S5 Bioactive Glass-Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) Microsphere Composite Membranes for Guided Tissue/Bone Regeneration - Li, Wei; Ding, Yaping; Yu, Shanshan; Yao, Qingqing; Boccaccini, Aldo R. (ACS Applied Materials and Interfaces, 2015)
Novel multifunctional chitosan-45S5 bioactive glass-poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) microsphere (CS-BG-MS) composite membranes were developed with applicability in guided tissue/bone regeneration (GTR/GBR). The incorporation of 45S5 BG and PHBV MS into CS membranes not only provided the membranes with favorable surface roughness, hydrophilicity, and flexibility but also slowed down their degradation rate. Moreover, the CS membranes became bioactive after the incorporation of 45S5 BG and capable of releasing drugs of different physicochemical properties in a controlled and sustained manner with the addition of PHBV MS. Cell culture tests showed that osteoblast-like MG-63 human osteosarcoma cells had significantly higher adhesion, cell proliferation, and alkaline phosphatase (ALP) activity on CS-BG and CS-BG-MS membranes than on neat CS membranes. Therefore, the developed bioactive CS-BG-MS membranes with potential multidrug (e.g., antibacterial and antiosteoporosis drugs) delivery capability are promising candidate membranes for GTR/GBR applications.
Keywords: 45S5 bioactive glass; chitosan; drug delivery; guided bone regeneration; membrane; PHBV microsphere

Multi-functional PDMS/MMT Coating on magnesium substrates: Hydrophobicity, durability, and EMI shielding - Duan, Chunmei; Han, Lei; Yang, Guanda; Schubert, Dirk W.; Zhang, Taochuan (Materials Today Communications, 2024)
In this work, a highly efficient surface coating strategy using polydimethylsiloxane (PDMS) modified low-cost montmorillonite (MMT) was revealed, to enhance the surface performance and durability of magnesium substrates. Contact angle, self-cleaning, wear resistance, corrosion resistance and ultrabroadband electromagnetic absorption and EMI shielding evaluations were comprehensively studied. The obtained PDMS/MMT/Mg substrate consistently exhibited an obvious increased contact angle from 76.1 to 141.9 °, signifying strong hydrophobicity and self-cleaning properties compared to the untreated R-Mg substrate. No significant surface wettability changes were detected even after 50 times of tape peeling or 3.0 wt% NaCl solution immersion for 60 h, indicating high durability of the protective PDMS/MMT coatings. Moreover, the PDMS/MMT/Mg substrates can be applied as microwave-absorbing materials, particularly in high-frequency applications, and as excellent EMI shielding with an SE value above 40 dB. This study highlights the effectiveness of the relatively inexpensive PDMS/MMT coating in enhancing the performance of magnesium substrates, providing a new approach to balance cost control and meet performance requirements in industrial or large-scale production.<br
Keywords: Magnesium substrateSurface coatingHydrophobicityCorrosion resistanceElectromagnetic shielding

Myogenic differentiation of human myoblasts and Mesenchymal stromal cells under GDF11 on NPoly-ɛ-caprolactone-collagen I-Polyethylene-nanofibers - Cai, Aijia; Schneider, Paul; Zheng, Zengming; Beier, Justus P.; Himmler, Marcus; Schubert, Dirk W.; Weisbach, Volker Günter; Horch, Raymund E.; Arkudas, Andreas (BMC Molecular and Cell Biology, 2023)
BACKGROUND: For the purpose of skeletal muscle engineering, primary myoblasts (Mb) and adipogenic mesenchymal stem cells (ADSC) can be co-cultured and myogenically differentiated. Electrospun composite nanofiber scaffolds represent suitable matrices for tissue engineering of skeletal muscle, combining both biocompatibility and stability Although growth differentiation factor 11 (GDF11) has been proposed as a rejuvenating circulating factor, restoring skeletal muscle function in aging mice, some studies have also described a harming effect of GDF11. Therefore, the aim of the study was to analyze the effect of GDF11 on co-cultures of Mb and ADSC on poly-ε-caprolactone (PCL)-collagen I-polyethylene oxide (PEO)-nanofibers. RESULTS: Human Mb were co-cultured with ADSC two-dimensionally (2D) as monolayers or three-dimensionally (3D) on aligned PCL-collagen I-PEO-nanofibers. Differentiation media were either serum-free with or without GDF11, or serum containing as in a conventional differentiation medium. Cell viability was higher after conventional myogenic differentiation compared to serum-free and serum-free + GDF11 differentiation as was creatine kinase activity. Immunofluorescence staining showed myosine heavy chain expression in all groups after 28 days of differentiation without any clear evidence of more or less pronounced expression in either group. Gene expression of myosine heavy chain (MYH2) increased after serum-free + GDF11 stimulation compared to serum-free stimulation alone. CONCLUSIONS: This is the first study analyzing the effect of GDF11 on myogenic differentiation of Mb and ADSC co-cultures under serum-free conditions. The results of this study show that PCL-collagen I-PEO-nanofibers represent a suitable matrix for 3D myogenic differentiation of Mb and ADSC. In this context, GDF11 seems to promote myogenic differentiation of Mb and ADSC co-cultures compared to serum-free differentiation without any evidence of a harming effect.
CRIS-Team Scopus Importer:2023-05-26
Keywords: ADSC; Collagen; Electrospun composite nanofibers; GDF11; Myoblasts; Myogenic differentiation; Myostatin; Nanoscaffolds; poly-ε-caprolacton (PCL); Polyethylene oxide (PEO)

Myogenic differentiation of primary myoblasts and mesenchymal stromal cells under serum-free conditions on PCL-collagen I-nanoscaffolds - Arkudas, Andreas; Weigand, Annika; Beier, Justus; Horch, Raymund E.; Hardt, Moritz; Schneider, Paul; Schmid, Rafael; Lange, Claudia; Dippold, Dirk; Schubert, Dirk W.; Boos, Anja; Cai, Aijia (BMC Biotechnology, 2018)
The creation of functional skeletal muscle via tissue engineering holds great promise without sacrificing healthy donor tissue. Different cell types have been investigated regarding their myogenic differentiation potential under the influence of various media supplemented with growth factors. Yet, most cell cultures include the use of animal sera, which raises safety concerns and might lead to variances in results. Electrospun nanoscaffolds represent suitable matrices for tissue engineering of skeletal muscle, combining both biocompatibility and stability. We therefore aimed to develop a serum-free myogenic differentiation medium for the co-culture of primary myoblasts (Mb) and mesenchymal stromal cells derived from the bone marrow (BMSC) and adipose tissue (ADSC) on electrospun poly-ε-caprolacton (PCL)-collagen I-nanofiber
Keywords: Nanoscaffolds; Myogenic differentiation; Myoblasts; Mesenchymal stromal cells; Serum-free media; BMSC; Electrospun PCL-collagen I-nanofibers; ADSC

Myogenic differentiation of primary myoblasts and mesenchymal stromal cells under serum-free conditions on PCLcollagen I-nanoscaffolds - Hardt, Moritz; Schneider, Paul; Schmid, Rafael; Lange, Claudia; Dippold, Dirk; Schubert, Dirk W.; Boos, Anja; Weigand, Annika; Arkudas, Andreas; Horch, Raymund E.; Beier, Justus; Cai, Aijia (BMC Biotechnology, 2018)
Background: The creation of functional skeletal muscle via tissue engineering holds great promise without sacrificing healthy donor tissue. Different cell types have been investigated regarding their myogenic differentiation potential under the influence of various media supplemented with growth factors. Yet, most cell cultures include the use of animal sera, which raises safety concerns and might lead to variances in results. Electrospun nanoscaffolds represent suitable matrices for tissue engineering of skeletal muscle, combining both biocompatibility and stability. We therefore aimed to develop a serum-free myogenic differentiation medium for the co-culture of primary myoblasts (Mb) and mesenchymal stromal cells derived from the bone marrow (BMSC) and adipose tissue (ADSC) on electrospun poly-ε-caprolacton (PCL)-collagen I-nanofibers. Results: Rat Mb were co-cultured with rat BMSC (BMSC/Mb) or ADSC (ADSC/Mb) two-dimensionally (2D) as monolayers or three-dimensionally (3D) on aligned PCL-collagen I-nanofibers. Differentiation media contained either AIM V, AIM V and Ultroser® G, DMEM/Ham’s F12 and Ultroser® G, or donor horse serum (DHS) as a conventional differentiation medium. In 2D co-culture groups, highest upregulation of myogenic markers could be induced by serum-free medium containing DMEM/Ham’s F12 and Ultroser® G (group 3) after 7 days. Alpha actinin skeletal muscle 2 (ACTN2) was upregulated 3.3-fold for ADSC/Mb and 1.7-fold for BMSC/Mb after myogenic induction by group 3 serum-free medium when compared to stimulation with DHS. Myogenin (MYOG) was upregulated 5.2-fold in ADSC/ Mb and 2.1-fold in BMSC/Mb. On PCL-collagen I-nanoscaffolds, ADSC showed a higher cell viability compared to BMSC in co-culture with Mb. Myosin heavy chain 2, ACTN2, and MYOG as late myogenic markers, showed higher gene expression after long term stimulation with DHS compared to serum-free stimulation, especially in BMSC/Mb cocultures. Immunocytochemical staining with myosin heavy chain verified the presence of a contractile apparatus under both serum free and standard differentiation conditions. Conclusions: In this study, we were able to myogenically differentiate mesenchymal stromal cells with myoblasts on PCL-collagen I-nanoscaffolds in a serum-free medium. Our results show that this setting can be used for skeletal muscle tissue engineering, applicable to future clinical applications since no xenogenous substances were used. <br
Keywords: Myogenic differentiation; Nanoscaffolds; Electrospun PCL-collagen I-nanofibers; Mesenchymal stromal cells; ADSC; BMSC; Myoblasts; Serum-free media

Nanocomposites Based on Waterborne Polyurethane Matrix and Fe3O4 Nanoparticles: Synthesis and Characterization - Meiorin, Cintia; Scherzer, Selina L.; Mucci, Veronica; Actis, Daniel G.; Zelis, Pedro Mendoza; Schubert, Dirk W.; Mosiewicki, Mirna A.; Aranguren, Mirta (Advanced Engineering Materials, 2021)
Herein, the feasibility of producing waterborne polyurethane nanocomposites containing magnetic nanoparticles (MNPs) by casting method, to obtain films with potential magnetic properties, is shown. The characterization of the resulting nanocomposites is carried out using infrared spectroscopy, thermal analysis, colorimetry, tensile tests, microscopy and magnetic tests. The films become opaque and dark colored when MNP is incorporated. The mechanical behavior of the nanocomposites is that of tough plastics, with Young's modulus in the range of 106-143 MPa, increasing with the MNP concentration. Aggregation of the MNP takes place at concentrations above 1.5 wt%, as observed in scanning electron microscopy (SEM) images of the fracture surfaces. Magnetization saturation increases with the concentration of MNP. A small coercivity indicates the presence of a fraction of blocked particles whose size exceeds the critical size for superparamagnetism at the temperature of the measurements.
CRIS-Team WoS Importer:2021-08-13

Nanocomposite scaffolds with tunable mechanical and degradation capabilities: Co-delivery of bioactive agents for bone tissue engineering - Cattalini, Juan P.; Roether, Judith; Hoppe, Alexander; Pishbin, Fatemeh; Haro Durand, Luis; Gorustovich, Alejandro; Boccaccini, Aldo R.; Lucangioli, Silvia; Mourino, Viviana (Biomedical Materials, 2016)
Keywords: alendronate delivery; bone tissue engineering; controlled and sustainable release; ions; nanocomposite scaffolds

Nanocrystal V2O5 thin film as hole-extraction layer in normal architecture organic solar cells - Wang, Hao; Li, Ning; Güldal, Nusret Sena; Brabec, Christoph (Organic Electronics, 2012)
Nanocrystal VO dispersion processed thin films are introduced as efficient hole extraction interlayer in normal architecture P3HT:PCBM solar cells. Both thin and rather thick interlayers are studied and demonstrated to work properly in organic photovoltaic. Nanocrystal V OVO layers effectively block electrons and effectively extract holes at the ITO anode. Very constant and high V (above 0.56 V) are easily achieved. Comparable J and PCE are demonstrated for nanocrystal dispersion-processed devices when compared with amorphous sol-gel processed devices. The excellent functionality of nanocrystal VO interlayers in Si-PCPDTBT:PCBM devices further demonstrates the broad application potential of this material class for photovoltaic applications. © 2012 Elsevier B.V. All rights reserved.
Keywords: Electrode buffer layer; Nanocrystals; Organic solar cell; Vanadium oxide

Nanofaserscaffolds als DMEK-& Amnionmembranersatz – Anforderungen und Eigenschaften - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas (iSearch 2021, Münster (Deutschland), 2021, 2021)

Nanofiber composites in bone tissue engineering - Liverani, Liliana; Roether, Judith; Boccaccini, Aldo R. (Elsevier Inc., 2017)
Keywords: Bioactive glass; Bioactivity; Bone tissue engineering; Electrospinning; Hydroxyapatite; In vivo model; Nanocomposites; Nanofibers

Nanofibrous Composite with Tailorable Electrical and Mechanical Properties for Cardiac Tissue Engineering - Roshanbinfar, Kaveh; Vogt, Lena; Ruther, Florian; Roether, Judith; Boccaccini, Aldo R.; Engel, Felix (Advanced Functional Materials, 2019)
Cardiac tissue engineering is a promising strategy to prevent functional deterioration or even to enhance cardiac function upon myocardial infarction. Here, electrospun fiber mats containing different combinations of electrically conductive polyaniline, collagen, and/or hyaluronic acid are assessed regarding material properties and compatibility with cardiomyocyte attachment and function. Microstructure analysis reveals that collagen fiber mats contain a wide range of fiber diameters after crosslinking (from ≈300 nm to ≈5 µm); all other fiber mats contain fibers in the range of ≈120 to ≈300 nm. Fiber mats exhibit comparable electrical conductivity to and greater mechanical properties than the native human myocardium, which is considered beneficial. Cell–matrix interaction analysis utilizing postnatal rat cardiomyocytes reveals that the fiber mats are non-cytotoxic and permit cell attachment and contraction. Fiber mats containing collagen (9.89%), hyaluronic acid (1.1%), and polyaniline (PANi, 1.34%) exhibit the most favorable properties with longer contraction time, higher contractile amplitude, and lower beating rates. Improved contraction is accompanied by increased connexin 43 expression. Importantly, this fiber mat is a suitable material for human-induced pluripotent stem cell–derived cardiomyocytes regarding cytotoxicity, cell attachment, and function. Collectively, these data demonstrate that fiber mats made of collagen, hyaluronic acid, and polyaniline are promising materials for cardiac tissue engineering.
CRIS-Team Scopus Importer:2019-12-31
Keywords: collagen; electroconductive; electrospinning; heart; hyaluronic acid; polyaniline; tissue engineering

Needs of a Reliable and Efficient Nonwoven Manufacturer on Polymers - Schubert, Dirk W. (Book of Abstracts, 2013)

Neuartige Studien zu Silikon-Brustimplantaten - Walter, Bastian; Daenicke, Jonas; Horch, Raymund E.; Kaschta, Joachim; Schubert, Dirk W. (Würzburger Tage 2012, 2014)

Ni Flower/MXene-Melamine Foam Derived 3D Magnetic/Conductive Networks for Ultra-Efficient Microwave Absorption and Infrared Stealth - Cheng, Haoran; Pan, Yamin; Wang, Xin; Liu, Chuntai; Shen, Changyu; Schubert, Dirk W.; Guo, Zhanhu; Liu, Xianhu (Nano-Micro Letters, 2022)
The development of multifunctional and efficient electromagnetic wave absorbing materials is a challenging research hotspot. Here, the magnetized Ni flower/MXene hybrids are successfully assembled on the surface of melamine foam (MF) through electrostatic self-assembly and dip-coating adsorption process, realizing the integration of microwave absorption, infrared stealth, and flame retardant. Remarkably, the Ni/MXene-MF achieves a minimum reflection loss (RLmin) of − 62.7 dB with a corresponding effective absorption bandwidth (EAB) of 6.24 GHz at 2 mm and an EAB of 6.88 GHz at 1.8 mm. Strong electromagnetic wave absorption is attributed to the three-dimensional magnetic/conductive networks, which provided excellent impedance matching, dielectric loss, magnetic loss, interface polarization, and multiple attenuations. In addition, the Ni/MXene-MF endows low density, excellent heat insulation, infrared stealth, and flame-retardant functions. This work provided a new development strategy for the design of multifunctional and efficient electromagnetic wave absorbing materials.[Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-03-11
Keywords: Flame-retardant; Heat insulation; Infrared stealth; Microwave absorption; Ni-MXene/Melamine foam

Non-linear imaging as tool in biomaterials research - Thieme, Daniel; Fuchsluger, Thomas; Schubert, Dirk W. (Deutsche Gesellschaft für Biomaterialien - Annual Meeting, 2018)
Keywords: biomaterial; bioprinting

Nonlinear viscoelastic behavior or measuring artifact? On the wall slip of magnetorheological (MR) elastomers - Walter, Bastian; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (17th International Congress on Rheology, 2016)

Nonlinear viscoelastic behavior or measuring artifact? On the wall slip of magneto-sensitive elastomers - Walter, Bastian; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (10th Annual European Rheology Conference, 2015)

Non-substituted fused bis-tetracene based thin-film transistor with self-assembled monolayer hybrid dielectrics - Zhao, Baolin; Feofanov, Mikhail; Lungerich, Dominik; Park, Hyoungwon; Rejek, Tobias; Wittmann, Judith; Sarcletti, Marco; Amsharov, Konstantin; Halik, Marcus (Frontiers of Materials Science, 2020)
Polycyclic aromatic hydrocarbons with zigzag peripheries are high perspective candidates for organic electronics. However, large fused acenes are still poorly studied due to the tedious synthesis. Herein we report a non-substituted fused bistetracene DBATT (2.3,8.9-dibenzanthanthrene) as the semiconductor on low-voltage-driven organic thin-film transistors. The systematic studies of thin-film growth on various self-assembled monolayer (SAM) modified gate dielectrics and the electrical performances were carried out. The sub-monolayer of the semiconductor film shows larger island domains on the alkyl chain SAM. This device exhibits the hole mobility of 0.011 cm2·V−1·s−1 with a current ratio of IonIIoff above 105.
CRIS-Team Scopus Importer:2020-09-11
Keywords: contact resistance; fused bis-tetracene; organic field-effect transistor; self-assembled monolayer

Novel approach towards aligned PCL-Collagen nanofibrous constructs from a benign solvent system - Dippold, Dirk; Cai, Aijia; Hardt, Moritz; Boccaccini, Aldo R.; Horch, Raymund E.; Beier, Justus; Schubert, Dirk W. (Materials Science and Engineering C, 2017)
Keywords: Aligned nanofibers; Benign solvent; Collagen; Electrospinning; Polycaprolactone

Novel biomaterials for ocular surface surgery - Thieme, Daniel; Fuchsluger, Thomas; Schubert, Dirk W. (Acta Ophthalmologica, 2018)

Novel Chart for Representation of Material Performance and Reliability - Lanyi, Franz; Kunzelmann, Peter; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Novel Chart for Representation of Material Performance and Reliability - Lanyi, Franz; Kunzelmann, Peter; Schubert, Dirk W. (Macromolecular Symposia, 2016)
In modern industrial production lines various process and materialparameters determine the properties of the final product. Thus, a process optimizationprocedure has to take into account a large design space containing several parameters. Asa consequence, the evaluation of the influenceofsingleprocessparametersonthefinalproduct properties can be quite complicated.Usually a certain property of a product, forexample the mechanical strength, has to satisfy a defined specification. In terms ofquality control not only the performance of the material but also the reliability of thespecified values has to be considered. The Weibull statistic gives an interesting approachto evaluate both, material’s performance and reliability. Regarding the mechanicalproperties e.g. in terms of the stress at breaksbthe Weibull analysis leads to acharacteristic failure constantsb,0at which 63.2 % of the samples will break. Additionally,the Weibull modulus m can be regarded as a measure for the width of the distribution ofthe measuring results. High values of m represent a narrow distribution and thus a betterreliability. Moreover, the Weibull modulus m is independent of the absolute value of themeasuring data. Therefore, it is possible to compare samples produced under differentconditions. The standard deviation and the interquartile range are often used to quantifythe scatter of empirical data. It is shown within this work that the Weibull modulus m canbeamoreprecisediscriminatorfortheevaluation of the reliability because it is ratherstable against outlaying values. As an example this study concentrates on the mechanicalproperties of melt spun fibresconsisting of blends from polypropylenes with differentmolar masses produced under various process conditions. This work presents a novelchart which allows one to compare different samples on the basis of the Weibull statisticswhereat the Weibull modulus m is plotted oversb,0. Defining a reference material, them-sb,0-map can be split into quadrants, whereat each quadrant designates animprovement or worsening of material’s performance and reliability with respect to thereference. An evaluation in terms of performance and reliability of great sets of data iseasily applicable. It will be shown that the Weibull statistic can also be applied to Young’sModulus, the elongation at break and the tensile energy absorpti
Keywords: fibers; key performance indicators; mechanical properties; process reliability; Weibull statistics

Novel Chart for Representation of Material Performance and Reliability - Lanyi, Franz; Schubert, Dirk W. (Polychar 23rd, 2015)

Novel definition of the synergistic effect between carbon nanotubes and carbon black for electrical conductivity - Qu, Muchao; Nilsson, Fritjof; Schubert, Dirk W. (2019)

Novel definition of the synergistic effect between carbon nanotubes and carbon black for electrical conductivity - Qu, Muchao; Nilsson, Fritjof; Schubert, Dirk W. (Nanotechnology, 2019)
Anisotropic ternary composites comprising poly(methy-methacrylate) (PMMA), carbon black (CB), and carbon nanotubes (CNTs) were extruded using a capillary rheometer and the electrical conductivities of the composites were measured and presented in a detailed contour plot covering a large range of filler fractions (up to 30 vol% CNTs, 20 vol% CB). A recent generic conductivity model for ternary composites was successfully validated using the conductivity measurements. When analyzing the conductivity measurements using four traditional definitions of 'synergy' between two conductive fillers, no clear synergetic effect was observed between CB and CNT. Also, when all the conductivity data for ternary CNT/CB composites from the existing literature was carefully gathered and analyzed, the number of confirmed occurrences of strong and convincing CNT/CB synergies was surprisingly low. Finally, a novel definition of synergy based on the physical aspect, in particular, its maximum, the 'synergasm', was defined in order to obtain a more precise instrument for revealing regions of potential synergy.
CRIS-Team WoS Importer:2019-04-12

Novel electrospun poly(glycerol sebacate)-zein fiber mats as candidate materials for cardiac tissue engineering - Dippold, Dirk; Tallawi, Marwa; Tansaz, Samira; Roether, Judith; Boccaccini, Aldo R. (European Polymer Journal, 2016)
The application of a cardiac patch made of biodegradable polymer is a novel approach in regenerative therapies for infarcted cardiac tissue and aims to deliver healthy and functional cells on a mechanically supporting matrix to the damaged area of the myocardium. In this study a novel type of tissue engineered cardiac construct based on poly(glycerol sebacate) (PGS) blended with the corn protein zein was developed. Bead free electrospun PGS-zein fibers were fabricated using acetic acid as a benign solvent. In vitro degradation studies in PBS revealed a physicochemically stable system over a 28 day period showing only a slight drop in pH after 28 days. The results indicate that the novel PGS-zein fibrous structures are attractive biomaterials which can be valuable for cardiac patch applications thus warranting their further investigation in vitro and in vivo.
Keywords: Cardiac tissue engineering; Electrospinning; Poly(glycerol sebacate); Zein

Novel High-Speed Elongation Rheometer - Bier, Alexander; Arne, Walter; Schubert, Dirk W. (Macromolecular Materials and Engineering, 2022)
The elongational viscosity of polymers can be determined by utilizing different devices such as extensional rheometer after Sentmanat (SER), oil bath rheometer after Meissner or tensile rheometer after Munstedt (MTR), with strain rates up to 10 s(-1). Although these investigations are already complex, they do not depict real fiber spinning processes where higher elongation strain rates occur. Therefore, a novel method is developed to calculate the elongational viscosity of polymers during the fiber spinning process. To reduce the complexity of the system, two polymethylmethacrylates (PMMAs) with different molar masses are investigated using a capillary rheometer to exclude crystallization effects. The diameter of the polymeric strand is determined via a high-speed camera from the die exit to the aspirator. In addition, simulations are carried out to describe the temperature profile of the polymeric strand along the spinline. It is possible to determine the elongational viscosity of the polymers in dependence of temperature and strain rates up to 100 s(-1), by calibration of the force in an aerodynamic stretching device (aspirator).
CRIS-Team WoS Importer:2022-04-29

Novel high-speed elongation rheometer - Bier, Alexander; Arne, Walter; Schubert, Dirk W. (Nordic Polymer Days 2023, 2023)
In many processes like film blowing, film casting or fiber spinning elongational strain occurs. For these processes, it is very impor- tant to know and understand the occurring elongational viscosities. However, for high elongation rates the elongational viscosity was and still is not accessible with existing methods e.g. the extensional rheometer after Sentmanat (SER), oil bath rheometer after Meissner or tensile rheometer after Münstedt (MTR) [1]. With the limitation of elongation rates to a maximum of 10 s-1, those setups are not suitable in the range up to 100 s-1, which are typical in fiber spinning [2]. With the “Rheotens”, slightly higher elongation rates of up to 40 s-1 can be achieved, but in compar- ison to the aerodynamic fiber stretching via an aspirator, it is still by far insufficient for an industrial relevant range. Therefore, a novel method is developed to cal- culate the elongational viscosity of polymers during the fiber spinning process. To reduce the complexity of the system two PMMAs (to exclude crystallization effects) with different molar masses are investigated using a capil- lary rheometer. The diameter of the polymeric strand is determined via a high-speed camera from the die exit to the aspirator. In addition, simulations are carried out to describe the temperature profile of the polymeric strand along the spinline. A two-way calibration method was applied to calculate the force ap- plied by the aspirator on the polymeric strand. With this information, the temperature and elongation rate dependent elongational viscosity was determined. Furthermore, a Carreau type function was applied to master all measurements (as shown in Figure 1). With strain rates up to 100 s-1 this work paves the way to learn more about the elongational viscosity in the high deformation range never reached before [3].<br /

Novel method to measure surface crystallinity of fibers and nonwovens - Lanyi, Franz; Schubert, Dirk W. (Europe Africa Conference 2017 of the Polymer Processing Society,, 2017)

Novel method to measure surface crystallinity of fibers and nonwovens - Lanyi, Franz; Wenzke, Nicolai; Kaschta, Joachim; Schubert, Dirk W. (54th Nordic Polymer Days, 2017)

Novel model for the description of the mechanical behavior of polypropylene nonwovens for different test directions and strain rates - Leucker, Karsten; Schubert, Dirk W. (Polymertec18, 2018)

Novel nanocomposite biomaterials with controlled copper/calcium release capability for bone tissue engineering multifunctional scaffolds - Cattalini, J. P.; Hoppe, Alexander; Pishbin, F.; Roether, Judith; Boccaccini, Aldo R.; Lucangioli, S.; Mourino, V. (Journal of the Royal Society Interface, 2015)
This work aimed to develop novel composite biomaterials for bone tissue engineering (BTE) made of bioactive glass nanoparticles (Nbg) and alginate cross-linked with Cu2+ or Ca2+ (AlgNbgCu, AlgNbgCa, respectively). Twodimensional scaffolds were prepared and the nanocomposite biomaterials were characterized in terms of morphology, mechanical strength, bioactivity, biodegradability, swelling capacity, release profile of the cross-linking cations and angiogenic properties. It was found that both Cu2+ and Ca2+ are released in a controlled and sustained manner with no burst release observed. Finally, in vitro results indicated that the bioactive ions released from both nanocomposite biomaterials were able to stimulate the differentiation of rat bone marrow-derived mesenchymal stem cells towards the osteogenic lineage. In addition, the typical endothelial cell property of forming tubes in Matrigel was observed for human umbilical vein endothelial cells when in contact with the novel biomaterials, particularly AlgNbgCu, which indicates their angiogenic properties. Hence, novel nanocomposite biomaterials made of Nbg and alginate cross-linked with Cu2+ or Ca2+ were developed with potential applications for preparation of multifunctional scaffolds for BTE.
Keywords: Alginate; Angiogenesis; Bioactive glass; Bone tissue engineering; Metal ion release; Nanocomposites

Novel objective test method for the abrasion and pilling behaviour of low basis weight spunbond polypropylene nonwovens - Leucker, Karsten; Amtmann, Janosch; Schubert, Dirk W. (Polymer Testing, 2018)
Keywords: Polypropylene; Spunbond; Martindale; Abrasion; Pilling; Nonwoven

Novel objective test method for the abrasion behaviour of low basis weight spunbond nonwovens - Leucker, Karsten; Amtmann, Janosch; Schubert, Dirk W. (15th Bayreuth Polymer Symposium, 2017)

Novel opportunities to investigate elongational behaviour of polymer melts and bio inks - Schubert, Dirk W.; Bier, Alexander; Schrüfer, Stefan (Nordic Polymer Days 2023, 2023)
The thermal stability of recycled polypropyl- ene should be increased by using renewa- ble stabilizers known as antioxidants. These chemical compounds delay the degradation and aging of polymers by offering a hydrogen atom to the radical generated during thermal decomposition, so that the radical does not react with the polymer chain [1]. In this work the use of Irganox 1010 (industry standard), lignin and α-tocopherol (vitamin E) in polypropylene is investigated [2-4]. To assess the effectiveness of the stabilizers, the oxidation induction time (OIT) is determined according to standard (EN ISO 11357-6) [5]. The oxidation induction time is the time a polymer can resist at 200 °C until degradation occurs after the change from nitrogen to oxygen atmosphere. The objective is to increase that time to more than 10 minutes. By adding different amounts of antioxidant, a critical concentration c* is cal- culated at which the objective is achieved. A linear relationship between concentration and thermal stability is found for all systems, except for the addition of α-tocopherol. The highest thermal stability is achieved by α-to- copherol and α-tocopherol succinate, whose structures are formed on the basis of BHA (2, 6-di-tert-butyl-4-methoxyphenol) instead of BHT (2, 6-di-tert-butyl-4-methylphenol), as it is the case for the other stabilizers [4]. Compared to the industry standard (Irganox 1010) the efficiency of α-tocopherol is ten times higher in the relevant concentration level, making Vi- tamin E the most suitable antioxidant found in this research. The wood component lignin also shows good stabilization effects, but requires the tenfold concentration c* than Irganox 1010. Furthermore, the stabilized samples are ana- lysed with regard to their rheological proper- ties. At a temperature of 250 °C, that is equal to the processing temperature in the industry, degradation occurs during the measurement, so the unstabilized sample (pure PP) shows a lower viscosity compared to the stabilized sampl

Novel PGS/PCL electrospun fiber mats with patterned topographical features for cardiac patch applications - Tallawi, Marwa; Dippold, Dirk; Rai, Ranjana; D'Atri, D.; Roether, Judith; Schubert, Dirk W.; Rosellini, E.; Engel, Felix; Boccaccini, Aldo R. (Materials Science and Engineering C, 2016)
Nano- and micro-scale topographical features play a critical role in the induction and maintenance of various cellular properties and functions, including morphology, adhesion, gene regulation, and cell-to-cell communication. In addition, recent studies have indicated that the structure and function of heart tissue are also sensitive to mechanical cues at the nano- and micro-scale. Although fabrication methods exist for generating topographical features on polymeric scaffolds for cell culture, current techniques, especially those with nano-scale resolution, are typically complex, prohibitively expensive and not accessible to most biology laboratories. Here, we present a simple and tunable fabrication method for the production of patterned electrospun fibers that simulate the complex anisotropic and multi-scale architecture of cardiac tissue, to promote cardiac cell alignment. This method is based on the combination of electrospinning and soft lithography techniques, in which electrospun fibers, based on a blend of poly(glycerol sebacate) and poly(caprolactone), were collected on a patterned Teflon-coated silicon wafer with imprinted topographical features. Different surface topographies were investigated, such as squares and grooves, with constant or different interspatial distances. In vitro cell culture studies successfully demonstrated the alignment of both C2C12 myoblasts and neonatal rat cardiomyocytes on fabricated electrospun patterned surfaces. C2C12 cells were cultured over a period of 72h to study the effect of topographical cues on cell morphology. Cells attached within the first 8h after seeding and after 24h most of the cells started to align responding to the topographical cues. Similarly, cardiomyocytes responded to the topographical features by aligning themselves and by expressing Connexin 43 along cellular junctions. Summarizing, we have developed a new method with the potential to significantly promote cardiac tissue engineering by fabricating electrospun fibers with defined topographical features to guide and instruct donor and/or host cells.
EVALuna:34665

Novel poly(hydroxyalkanoates)-based composites containing Bioglass® and calcium sulfate for bone tissue engineering - García-García, Jose; Garrido, Leoncio; Quijada-Garrido, Isabel; Kaschta, Joachim; Schubert, Dirk W.; Boccaccini, Aldo R. (Biomedical Materials, 2012)
Three different poly(hydroxyalkanoates) (PHAs), copolymers of poly(3-hydroxybutyrate) (P3HB), have been used to make composites using two different fillers, bioactive glass (type 45S5 Bioglass®) and calcium sulfate dihydrate. The PHAs used were poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [PHBHV] and two copolymers of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) [PHBHHx]. The aim of the study was the fabrication and characterization of the new composites and the assessment of the influence of the particular filler combination on the physical properties and bioactivity of the films. The thermal behaviour was studied using differential scanning calorimetry while mechanical properties were evaluated using dynamic mechanic thermal analysis and tensile strength test. The mechanical and thermal properties were affected by particles addition. The distribution of the particles in the polymer matrix, observed by scanning electron microscopy, was directly related to the mechanical properties. The surface characteristics were investigated by contact angle measurements and Raman spectroscopy. The extent of formation of hydroxyapatite (HA) upon immersion in simulated body fluid (SBF) depended on the polymer used, the amount of fillers employed and the time of immersion in SBF. Bioactivity was enhanced in the composites with a rise of hydrophilicity. The HA formation was controllable with time in the case of PHBHHx composites.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.novelp

Novel poly(hydroxyalkanoates)-based composites containing Bioglass (R) and calcium sulfate for bone tissue engineering - García-García, Jose; Garrido, Leoncio; Quijada-Garrido, Isabel; Kaschta, Joachim; Schubert, Dirk W.; Boccaccini, Aldo R. (Biomedical Materials, 2012)
Three different poly(hydroxyalkanoates) (PHAs), copolymers of poly(3-hydroxybutyrate) (P3HB), have been used to make composites using two different fillers, bioactive glass (type 45S5 Bioglass (R)) and calcium sulfate dihydrate. The PHAs used were poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [PHBHV] and two copolymers of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) [PHBHHx]. The aim of the study was the fabrication and characterization of the new composites and the assessment of the influence of the particular filler combination on the physical properties and bioactivity of the films. The thermal behaviour was studied using differential scanning calorimetry while mechanical properties were evaluated using dynamic mechanic thermal analysis and tensile strength test. The mechanical and thermal properties were affected by particles addition. The distribution of the particles in the polymer matrix, observed by scanning electron microscopy, was directly related to the mechanical properties. The surface characteristics were investigated by contact angle measurements and Raman spectroscopy. The extent of formation of hydroxyapatite (HA) upon immersion in simulated body fluid (SBF) depended on the polymer used, the amount of fillers employed and the time of immersion in SBF. Bioactivity was enhanced in the composites with a rise of hydrophilicity. The HA formation was controllable with time in the case of PHBHHx composites.

Novel results on spreading dynamics from theoretical and practical point of view - Schubert, Dirk W.; Härth, Michael (Book of Abstracts, 2011)

Novel theoretical self-consistent mean-field approach to describe the conductivity of carbon fiber filled thermoplastics - Yang, Guanda; Schubert, Dirk W.; Qu, Muchao; Nilsson, Fritjof (Nordic Polymer Days 2018, 2018)
A very promising mathematical model for predicting the electrical conductivity below the electrical percolation threshold, for both isotropic and anisotropic composites, is recently published by Schubert. The shortcomings of that study are that the model includes so far only one predicted parameter and that it is not sufficiently validated. In the current study, finite element modeling is used to successfully validate the model of Schubert for isotropic fiber composites and to accurately determine the predicted parameter. These theoretical predictions are finally compared with experimental conductivity data for isotropic carbon fiber/poly(methyl methacrylate) (PMMA) composites with fiber filler fractions in the range 0–12 vol% and fiber aspect ratios from 5 to 30. The model forecasts, without any adjustable parameters, are satisfactory close to the experimental dat

Novel Theoretical Self-Consistent Mean-Field Approach to Describe the Conductivity of Carbon Fiber-Filled Thermoplastics: Part III-Application of the Concept to Mechanical Properties of Composites and Polymer Solutions - Schubert, Dirk W. (Advanced Engineering Materials, 2020)
A novel theoretical approach, which yields a nonlinear differential equation for the mechanical properties of fiber-filled composites as a function of the volume fraction of the filler and the fiber orientation, is shown. Furthermore, the transfer to polymer solutions is shown and gives a physical explanation for various well-known empirical relations and numerical values including the Huggins constant and the exponent of power-law molar mass dependence of the polymer melt viscosity.
CRIS-Team Scopus Importer:2020-06-16
Keywords: mechanical properties; polymer composites; polymer solution; viscosity

Novel Theoretical Self-Consistent Mean-Field Approach to Describe the Conductivity of Carbon Fiber–Filled Thermoplastics: PART II. Validation by Computer Simulation - Yang, Guanda; Schubert, Dirk W.; Qu, Muchao; Nilsson, Fritjof (Macromolecular Theory and Simulations, 2018)
The electrical conductivity of polymeric fiber composites is generally strongly dependent on the constituent conductivities, the fiber filler fraction, the fiber aspect ratio, and on the orientation of the fibers. Even though electrically conductive polymer composites are emerging materials of high scientific and commercial interest, accurate mathematical models for describing such materials are rare. A very promising mathematical model for predicting the electrical conductivity below the electrical percolation threshold, for both isotropic and anisotropic composites, is however recently published by Schubert. The shortcomings of that study are that the model includes so far only one predicted parameter and that it is not sufficiently validated. In the current study, finite element modeling is used to successfully validate the model of Schubert for isotropic fiber composites and to accurately determine the predicted parameter. These theoretical predictions are finally compared with experimental conductivity data for isotropic carbon fiber/poly(methyl methacrylate) (PMMA) composites with fiber filler fractions in the range 0-12 vol% and fiber aspect ratios from 5 to 30. The model forecasts, without any adjustable parameters, are satisfactory close to the experimental data.
Keywords: electrical conductivity; finite element modeling; computer simulation; polymeric fiber composites

Novel Theoretical Self-Consistent Mean-Field Approach to Describe the Conductivity of Carbon Fiber Filled Thermoplastics-PART I-Theory - Schubert, Dirk W. (Macromolecular Theory and Simulations, 2018)
A novel theoretical approach is shown which yields a nonlinear differential equation for the resistivity of carbon fiber filled composites below the percolation threshold as a function of the volume fraction of the filler and the fiber orientation. The solution of the equation is given analytically and a particular value for the exponent predicted. The theoretical concept can be transferred to other composite propertie
Keywords: conductivity; elecrical conductivity; polymer composites; carbon fibers

Novel theoretical self-consistent mean-field approach to describe the condutivity of carbon fiber filled thermoplastics - Qu, Muchao; Schubert, Dirk W.; Nilsson, Fritjof (Polychar 26 World Forum on Advanced Materials,, 2018)

Numerische und experimentelle Betrachtung des Molded Underfills - Paetsch, M.; Nguyen, T. D.; Dreissigacker, M.; Bauer, J.; Hoelck, O.; Bader, V.; Braun, T.; Zuehlke, J.; Minkus, M.; Voges, S.; Becker, K. F.; Woehrmann, M.; et al. (MikroSystemTechnik Kongress 2019 - Mikroelektronik MEMS-MOEMS Systemintegration - Saulen der Digitalisierung und kunstlichen Intelligenz, Proceedings, 2019)
To protect flip chips from thermal and mechanical stress caused by several environmental influences, they are encapsulated to ensure a reliable functionality. Usually low-viscosity, epoxy-based polymers are facilitated. For the conventional underfill the material flows under the die, driven by capillary forces. This is especially time consuming and prevents a high throughput. This procedure is followed by the overmould by either using transfer or compression moulding. Vacuum-assisted compression moulding allows the complete and simultaneously under-fill and overmould in only one process step. The implementation of the moulded under-fill (MUF) requires a single production machine, reduces material costs, process time and allows a higher through put. There is no need for new infrastructure and minimal in-vestments necessary for the changeover, which is an extraordinary advantage. For the MUF process an assembled substrate, containing the flip chips is inserted into the cavity, which is subsequently closed. After reaching the desired quality of vacuum the press continues to its final position and presses the EMC in the cavity, over and under the die. After a short pre-cure, the encapsulated substrate can be removed from the cavity. A problem that arrives, also for the conventional underfill, is the development of voids- the inclusions of gas between the active side of the die and substrate. The presence of voids can decrease the reliability. The dependencies on void formation regarding the variation of process and geometry parameters are only described qualitatively in literature, but not quantitatively. With the aid of a numerical model, which incorporates the specific material properties of the EMC, a basic understanding of the flow is generated allowing insight which are not accessible otherwise. The volume which is needed to be filled, is relevant for the form of the flow front. A large number of chip geometries, bump heights and package densities are analysed and evaluated under realistic process parameters and theirs applicability for the MUF. The results of this work, enable first trends and tendencies under which boundary conditions the MUF is successful to reduce efforts and costs.
CRIS-Team Scopus Importer:2021-04-20

Oil–Water Separation Polypropylene Foam with Advanced Solvent-Evaporation Induced Coexistence of Microspheres and Microporous Structure - Wang, Xin; Zhang, Mingtao; Schubert, Dirk W.; Liu, Xianhu (Macromolecular Rapid Communications, 2022)
For decades, crude oil spills and oil wastewater have become the most problematic environmental pollution and damage to public health. Therefore, it is considerable to develop superhydrophobic polymer foam for separating oil from water with high selectivity and sorption capacity. Here, a new type of environmentally friendly pure polypropylene (PP) foam with superhydrophobicity is first time proposed with a particular coexistence of microspheres and microporous structure fabricated via an advanced solvent-evaporation method. The PP foam exhibits exceptional superhydrophobic with a water contact angle of 151° and the maximum saturated adsorption capacity of 26 g g−1. After more than 15 h of cyclic continuous oil–water pumping experiment, it still maintains a high oil absorption efficiency of 98%, providing the basis for practical commercial applications. More importantly, the variation of hydrophobic properties is described by Flory–Huggins polymer solution theory and Huggins interaction parameters, and the optimal solution ratio range is predicted which provides a relevant theoretical basis for actual industrial production.
CRIS-Team Scopus Importer:2022-04-22
Keywords: microporous structures; microspheres; oil–water separation; polypropylene; superhydrophobic materials

Oligothiophene Organic Thin Film Transistors and Circuits - Halik, Marcus; Klauk, Hagen; Zschieschang, Ute; Schmid, Günter; Ponomarenko, S.; Kirchmeyer, S. (Materials Research Society Symposium - Proceedings, 2003)

Oligothiophene Phosphonic Acids for Self-Assembled Monolayer Field-Effect Transistors - Zhao, Baolin; Gothe, Bastian; Groh, Arthur; Schmaltz, Thomas; Will, Johannes; Steinrueck, Hans-Georg; Unruh, Tobias; Mecking, Stefan; Halik, Marcus (ACS Applied Materials and Interfaces, 2021)
Semiconducting self-assembled monolayers (SAMs) represent highly relevant components for the fabrication of organic thin-film electronics because they enable the precise formation of active it-conjugates in terms of orientation and layer thickness. In this work, we demonstrate self-assembled monolayer field-effect transistors (SAMFETs) composed of phosphonic acid oligomers of 3-hexylthiophene (oligothiophenes-OT) with systematic variations of thiophene repeating units (5, 10, and 20). The devices exhibit stable lateral charge transport with increased mobility as a function of thiophene unit counts. Importantly, our work reveals the packing and intermolecular order of varied-chain-length SAMs at the molecular scale via X-ray reflectivity (XRR) and quantitative X-ray photoelectron spectroscopy (XPS). Short oligomers (OT5-PA and OT10-PA) arrange almost perpendicular to the substrate, forming highly ordered SAMs, whereas the long-chain OT20-PA exhibits a folded structure. By tuning the molecular order in the monolayers via the SAM substitution reaction, the OT20-PA devices show a tripling in mobility.
CRIS-Team WoS Importer:2021-07-30

Oligothiophenes in organic thin film transistors – Morphology, stability and temperature operation - Xia, Qi; Burkhardt, Martin; Halik, Marcus (Organic Electronics, 2008)

On-Demand Coupling of Electrically Generated Excitons with Surface Plasmons via Voltage-Controlled Emission Zone Position - Zakharko, Yuriy; Held, Martin; Sadafi, Fabrizio-Zagros; Gannott, Florentina; Mandavi, Ali; Peschel, Ulf; Klupp Taylor, Robin; Zaumseil, Jana (ACS Photonics, 2016)
The ability to confine and manipulate light below the diffraction limit is a major goal of future multifunctional optoelectronic/plasmonic systems. Here, we demonstrate the design and realization of a tunable and localized electrical source of excitons coupled to surface plasmons based on a polymer light emitting field-effect transistor (LEFET). Gold nanorods that are integrated into the channel support localized surface plasmons and serve as nanoantennas for enhanced electroluminescence. By precise spatial control of the near-infrared emission zone in the LEFET via the applied voltages the near-field coupling between electrically generated excitons and the nanorods can be turned on or off as visualized by a change of electroluminescence intensity. Numerical calculations and spectroscopic measurements corroborate significant local electroluminescence enhancement due to the high local density of photonic states in the vicinity of the gold nanorods. Importantly, the integration of plasmonic nanostructures hardly influences the electrical performance of the LEFETs, thus, highlighting their mutual compatibility in novel active plasmonic devices.
Keywords: surface plasmon polariton; organic semiconductor; field-effect transistor; electroluminescence; Purcell effect; active plasmonics

One-Dimensional Relaxation and Compression Behaviour Hydrogels as Inhomogeneous Bulk Material - Küng, Florian; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

One-Dimensional Relaxation Behaviour and Compression of Superabsorbent Polymers as Inhomogeneous Bulk Material - a Novel Approach to reveal corresponding consecutive Differential equation - Küng, Florian; Schubert, Dirk W. (European Polymer Federation, 2015)

One-Dimensional Relaxation Behaviour and Compression of Superabsorbent Polymers as Inhomogeneous Bulk Material - a Novel Approach to reveal corresponding consecutive Differential equation - Schubert, Dirk W.; Küng, Florian (10th Annual European Rheology Conference, 2015)

On the Determination of the Enthalpy of Fusion of α-Crystalline Isotactic Polypropylene Using Differential Scanning Calorimetry, X-Ray Diffraction, and Fourier-Transform Infrared Spectroscopy: An Old Story Revisited - Lanyi, Franz; Wenzke, Nicolai; Kaschta, Joachim; Schubert, Dirk W. (Advanced Engineering Materials, 2019)
The crystallinity determination of polymers using differential scanning calorimetry (DSC) is a standard procedure in industrial and university research. Its value strongly depends on the enthalpy of fusion, which cannot be determined directly using DSC, but must be calibrated using external methods such as X-ray diffraction (XRD) or density measurements. In addition, the determination of the enthalpy or heat of fusion is not trivial and thus error-prone; hence, values from 60 to 260 J g−1 are quoted for polypropylene in the literature. It is therefore of great relevance to devise a consistent method to determine the heat of fusion. To determine the heat of fusion for polypropylene, a sample set with a broad range of crystallinities is produced using cooling rates between 1 and ≈3500 K min−1. The melting enthalpy of the samples is determined using DSC measurements. The determination of the melting enthalpy based on XRD measurements is discussed in detail, validated using Fourier-transform infrared spectroscopy (FTIR), and compared with values quoted in the open literature. Although two different approaches are used to determine the enthalpy of fusion, a value of 170 ± 3 J g−1 is determined.
CRIS-Team Scopus Importer:2019-11-19
Keywords: differential scanning calorimetry; Fourier-transform infrared spectroscopy; heat of fusion; polypropylenes; X-ray diffraction

On the failure of silicone breast implants: New insights by mapping the mechanical properties of implant shells - Schubert, Dirk W.; Kaschta, Joachim; Horch, Raymund E.; Walter, Bastian; Daenicke, Jonas (Polymer International, 2014)
This review summarizes the knowledge on rupture (in vivo as well as under laboratory conditions) of gel-filled silicone breast implants, which has been an open question since the first implantation in 1962. We present recent progress which has been made by a mapping of the mechanical properties of the shell material together with a statistical failure analysis by means of a Weibull fit. Reference implants and intact as well as ruptured explants are tested after several years in vivo using tensile tests. Up to 110 dumbbell-shaped specimens per implant are measured allowing a detailed mapping of the mechanical properties of the silicone shell. Therefore, it is possible to illustrate the results of the tensile tests by mapping the measured values of the implants in the form of a contour plot revealing novel insights. The contour plots clearly display that the mechanical behaviour (e.g. stress at break) varies significantly over the shell. Additionally, a map is proposed which clearly shows separated clusters for different manufacturers and product categories. © 2013 Society of Chemical Industry
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-TM.onthef

On the Preparation, Characterisation, Modelling and Simulation of Magneto-Sensitive Elastomers - Walter, Bastian; Saxena, Prashant; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (Proceedings of the Second Seminar on the Mechanics of Multifunctional Materials, 2014)
UnivIS-Import:2015-07-08:Pub.2014.tech.FT.FT-TM.onthep

On the Preparation, Characterization, Modeling and Simulation of Magneto-Sensitive Elastomers - Walter, Bastian; Saxena, Prashant; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (14th International Conference on Electrorheological Fluids and Magnetorheological Suspensions, 2014)

On the stabilizing effects of neck-in, gravity, and inertia in Newtonian film casting - Bechert, Mathias; Schubert, Dirk W.; Scheid, Benoit (Physics of Fluids, 2016)
We investigate the influence of the reduction of width along the stretching direction, the so-called neck-in effect, on the draw resonance instability in Newtonian film casting using a linear stability analysis of a model of reduced dimensionality including gravity and inertia forces. Proper scaling reveals the aspect ratio, i.e., the ratio of the initial film half-width to the film length, together with the fluidity and the inlet velocity as independent, dimensionless control parameters. Moreover, we introduce the local Trouton ratio as a measure for the type of elongational deformation, which can be uniaxial, planar, or a combination of both. In the case of purely uniaxial or planar deformations, a one-dimensional model is sufficient. The influence of the control parameters on the draw resonance instability, including a threshold to unconditional stability, is visualized by several stability maps. Special cases of viscous-gravity and viscous-inertia models are analyzed separately due to their practical importance. Gravity appears to influence the aspect ratio at which the critical draw ratio is maximum and amplifies the stabilizing effect of the neck-in. Inertia increases the stabilization due to neck-in, eventually leading to a window of unconditional stability within the analyzed region of aspect ratios. The mechanism underlying the complete suppression of draw resonance is presented, using exclusively steady state analysis. Additionally, the stabilizing mechanisms of gravity and neck-in are revealed. Known alternative stability criteria are extended to the case of finite width and their validity is tested in the presence of inertia, gravity, and finite aspect ratios. (C) 2016 AIP Publishing LLC.

On the stabilizing effects of neck-in, gravity, and inertia in Newtonian film casting - Bechert, Mathias; Schubert, Dirk W.; Scheid, Benoit (Physics of Fluids, 2016)
We investigate the influence of the reduction of width along the stretching direction, the so-called neck-in effect, on the draw resonance instability in Newtonian film casting using a linear stability analysis of a model of reduced dimensionality including gravity and inertia forces. Proper scaling reveals the aspect ratio, i.e., the ratio of the initial film half-width to the film length, together with the fluidity and the inlet velocity as independent, dimensionless control parameters. Moreover, we introduce the local Trouton ratio as a measure for the type of elongational deformation, which can be uniaxial, planar, or a combination of both. In the case of purely uniaxial or planar deformations, a one-dimensional model is sufficient. The influence of the control parameters on the draw resonance instability, including a threshold to unconditional stability, is visualized by several stability maps. Special cases of viscous-gravity and viscous-inertia models are analyzed separately due to their practical importance. Gravity appears to influence the aspect ratio at which the critical draw ratio is maximum and amplifies the stabilizing effect of the neck-in. Inertia increases the stabilization due to neck-in, eventually leading to a window of unconditional stability within the analyzed region of aspect ratios. The mechanism underlying the complete suppression of draw resonance is presented, using exclusively steady state analysis. Additionally, the stabilizing mechanisms of gravity and neck-in are revealed. Known alternative stability criteria are extended to the case of finite width and their validity is tested in the presence of inertia, gravity, and finite aspect ratios.
Keywords: Linear stability analysis; Fluid mechanics; newtonian fluids; equations of fluid dynamics; Maxwell fluids; newtonian mechanics; thin films; viscoelastic fluid; resonance phenomena; trouton ratio

On the stabilizing effects of neck-in, gravity, and inertia in Newtonian film casting - Bechert, Mathias; Schubert, Dirk W.; Scheid, Benoit (Physics of Fluids, 2016)
We investigate the influence of the reduction of width along the stretching direction, the so-called neck-in effect, on the draw resonance instability in Newtonian film casting using a linear stability analysis of a model of reduced dimensionality including gravity and inertia forces. Proper scaling reveals the aspect ratio, i.e., the ratio of the initial film half-width to the film length, together with the fluidity and the inlet velocity as independent, dimensionless control parameters. Moreover, we introduce the local Trouton ratio as a measure for the type of elongational deformation, which can be uniaxial, planar, or a combination of both. In the case of purely uniaxial or planar deformations, a one-dimensional model is sufficient. The influence of the control parameters on the draw resonance instability, including a threshold to unconditional stability, is visualized by several stability maps. Special cases of viscous-gravity and viscous-inertia models are analyzed separately due to their practical importance. Gravity appears to influence the aspect ratio at which the critical draw ratio is maximum and amplifies the stabilizing effect of the neck-in. Inertia increases the stabilization due to neck-in, eventually leading to a window of unconditional stability within the analyzed region of aspect ratios. The mechanism underlying the complete suppression of draw resonance is presented, using exclusively steady state analysis. Additionally, the stabilizing mechanisms of gravity and neck-in are revealed. Known alternative stability criteria are extended to the case of finite width and their validity is tested in the presence of inertia, gravity, and finite aspect ratios.

On the viscosity maximum during uniaxial extension: Material property or measuring artifact? - Stary, Zdenek; Burghelea, Teodor; Münstedt, Helmut (AIP Conference Proceedings, 2013)
An experimental investigation of the viscosity maximum observed during uniaxial extension of a low density polyethylene is presented. For this purpose, traditional integral viscosity measurements on a Münstedt-type extensional rheometer are combined with local measurements based on the in-situ visualization of the sample under extension. For elongational experiments at intermediate constant strain rates local maximum of the extensional viscosity is systematically observed. Images of samples within this regime show that secondary necks develop along the sample at the moment when the maximum of the integral viscosity is observed. The emergence of a maximum of the integral elongational viscosity is, thus, related to the distinct non-uniformity of deformation states and most probably not to the rheological properties of the material. Moreover, the position of the viscosity maximum was found to be dependent on the initial geometry of the specimen. This indicates again that the appearance of the transient viscosity maximum is not a material property but an artifact caused by a geometrical non-uniformity of highly stretched specimens. © 2013 AIP Publishing LLC.
Created from Fastlane, Scopus look-up
Keywords: Elongational flow; Polymer melts; Rheology

On the wall slip of magnetorheological elastomers in parallel-plate rotational rheometry - Walter, Bastian; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (7th ECCOMAS Thematic Conference on Smart Structures and Materials, 2015)

On the wall slip phenomenon of elastomers in oscillatory shear measurements using parallel-plate rotational rheometry: I. Detecting wall slip - Walter, Bastian; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (Polymer Testing, 2017)
A systematic study is presented in order to reveal the occurrence of wall slip of pre-prepared elastomeric samples characterized with the use of rotational rheometry. To exclude effects that could be attributed to additional functional fillers, both an unfilled (primarily used) and lightly silica reinforced (complementary system) silicone rubber are evaluated. Cylindrical samples are prepared by casting using a standardized methodology and examined by means of a stress-controlled parallel-plate rotational rheometer. As a control test, samples are also cured within the rheometer (in situ), thereby fixing them to the measuring plates and firmly establishing their response in “no-slip” conditions. The experiments suggest that wall slip, postulated to be caused by an adhesive failure at the sample-plate interface, may occur if the deformation is sufficiently large and no cohesive failure is present. It is detected by an increase in the loss modulus that is related to the adhesive failure associated with local dynamic friction, resulting in increased dissipated energy. Direct (via raw waveform data and normalized Lissajous figures) and indirect (via fast-Fourier-transformation) analysis of the overall system response for a single steady state deformation cycle provided further insights into the mechanism of wall slip.
Keywords: Wall slip; Adhesive failure; Measuring artifact; Large amplitude oscillatory shear; Silicone rubber; Parallel-plate rotational rheometry

On the wall slip phenomenon of elastomers in oscillatory shear measurements using parallel-plate rotational rheometry: II. Influence of experimental conditions - Walter, Bastian; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (Polymer Testing, 2017)
The use of parallel-plate rotational rheometry to characterize ex situ pre-prepared samples of rubber-like polymers is motivated by, for example, the investigation of magneto-rheological elastomers. When exceeding a critical excitation amplitude in oscillatory shear experiments, these elastomeric samples are prone to slip at the sample-plate contact interface. This phenomenon, known as wall slip, starts to occur at the sample's outer rim and leads to an imperfect force transfer onto the sample. This results in a systematic error of measured rheological material quantities. A thorough investigation is presented to reveal how this phenomenon is affected by selected experimental conditions, namely the static axial preload and measuring frequency. For this purpose disc-shaped samples composed of an unfilled silicone rubber are prepared by casting and examined by means +of a controlled stress rotational rheometer equipped with a serrated rotor configuration. The oscillatory strain sweep experiments suggest that wall slip, exclusively present at the serrated rotor surface, is significantly influenced by the static preload. In contrast, only a slight frequency dependence is observed within the examined experimental conditions. Further insights into the wall slip mechanism were attained by two novel methodologies. It is shown that it is possible to produce a master curve for the various applied preloads. This demonstrates that the physical mechanism behind wall slip is independent of the axial force. Furthermore, we derive an empirical model for the criterion governing the onset of wall slip. This links the critical stress at which wall slip is initiated to the static friction condition and geometrical aspects of the rotor configuration. From this it is anticipated that the conditions for reliable experiments involving ex situ pre-prepared samples composed of low damping elastomers can, in the future, be estimated a priori</em
Keywords: Wall slip; Adhesive failure; Measuring artifact; Large amplitude oscillatory shea; Silicone rubber; Parallel-plate rotational rheometry

Optimization of Fiber Laydown During the Fiber Spinning Process by Utilizing the Coanda-Effect - Bier, Alexander; Büchler, Julian; Schubert, Dirk W. (Macromolecular Materials and Engineering, 2023)
The laydown of aerodynamically stretched fibers during fiber spinning is a key feature of the non-woven quality. The desired properties of the produced non-woven are mostly determined by the mechanical properties of the single fiber and the homogeneity of the spunbond. While the former is studied widely, the homogeneity is mostly studied by simulations and not experimentally. Cloudiness or formation of non-wovens is a known phenomenon that describes deviations from the ideal laydown. Thin areas have a huge impact on the mechanical properties of the spunbond; And subsequently, the investigation of the fiber laydown is of great interest. This work presents an experimental approach to optimize the fiber laydown of a pilot plant fiber spinning device consisting of two aerodynamic stretching devices (aspirators) that stretch eight single fibers each. Due to fiber accumulation on the lay-down belt under each of the aspirators, a metal rod is placed in-between to deflect the fibers into the center utilizing the Coanda-effect to achieve a broad homogeneous fiber distribution.
CRIS-Team Scopus Importer:2023-12-22
Keywords: aerodynamic stretching; Coanda-effect; fiber laydown; Fiber spinning; non-woven

Optimization of polycaprolactone‑ based nanofiber matrices for the cultivation of corneal endothelial cells - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas A. (Nature Medicine, 2021)
Posterior lamellar transplantation of the eye’ s cornea (DSAEK, DMEK) currently is the gold standard for treating patients with corneal endothelial cell and back surface pathologies resulting in functional impairment. An artificial biomimetic graft carrying human corneal endothelium could minimize the dependency on human donor corneas giving access to this vision‑restoring surgery to large numbers of patients, thus reducing current long waiting lists. In this study, four groups of electrospun nanofibrous scaffolds were compared: polycaprolactone (PCL), PCL/collagen, PCL/gelatin and PCL/chitosan. Each of the scaffolds were tissue‑engineered with human corneal endothelial cells (HCEC‑B4G12) and analyzed with regard to their potential application as artificial posterior lamellar grafts. Staining with ZO‑1 and Na+/K+‑ATPase antibodies revealed intact cell functionalities. It could be shown, that blending leads to decreasing contact angle, whereby a heterogeneous blend morphology could be revealed. Scaffold cytocompatibility could be confirmed for all groups via live/dead staining, whereby a significant higher cell viability could be observed for the collagen and gelatine blended matrices with 97 ± 3% and 98 ± 2% living cells respectively. TEM images show the superficial anchoring of the HCECs onto the scaffolds. This work emphasizes the benefit of blended PCL nanofibrous scaffolds for corneal endothelial keratoplast

Optimization of polycaprolactone - based nanofiber matrices for the cultivation of corneal endothelial cells - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas A. (Scientific Reports, 2021)

Optimized human platelet lysate as novel basis for a serum‐, xeno‐, and additive‐free corneal endothelial cell and tissue culture - Thieme, Daniel; Reuland, Lynn; Lindl, Toni; Kruse, Friedrich E.; Fuchsluger, Thomas A. (Journal of Tissue Engineering and Regenerative Medicine, 2017)
The expansion of donor‐derived corneal endothelial cells (ECs) is a promising approach for regenerative therapies in corneal diseases. To achieve the best Good Manufacturing Practice standard the entire cultivation process should be devoid of nonhuman components. However, so far, there is no suitable xeno‐free protocol for clinical applications. We therefore introduce a processed variant of a platelet lysate for the use in corneal cell and tissue culture based on a Good Manufacturing Practice‐grade thrombocyte concentrate. This processed human platelet lysate (phPL), free of any animal components and of anticoagulants such as heparin with a physiological ionic composition, was used to cultivate corneal ECs in vitro and ex vivo in comparison to standard cultivation with fetal calf serum (FCS). Human donor corneas were cut in quarters while 2 quarters of each cornea were incubated with the respective medium supplement. Three fields of view per quarter were taken into account for the analysis. Evaluation of phPL as a medium supplement in cell culture of immortalized EC showed a superior viability compared with FCS control with reduced cell proliferation. Furthermore, the viability during the expansion of primary cells is significantly (3‐fold ±0.5) increased with phPL compared with FCS standard medium. Quartering donor corneas was traumatic for the endothelium and therefore resulted in increased EC loss. Interestingly, however, cultivation of the quartered pieces for 2 weeks in 0.1‐mg/ml pHPL in Biochrome I showed a 21 (±10) % EC loss compared with 67 (±12) % EC loss when cultivated in 2% FCS in Biochrome I. The cell culture protocol with pHPL as FCS replacement seems to be superior to the standard FCS protocols with respect to EC survival. It offers a xeno‐free and physiological environment for corneal endothelial cells. This alternative cultivation protocol could facilitate the use of EC for human corneal cell therap
Keywords: neal endothelial cells; donor cornea; eye bank; primary corneal endothelial cells; processed human platelet lysate; regenerative medicine; serum‐free

Organic Electronics on Paper - Eder, F.; Klauk, Hagen; Halik, Marcus; Zschieschang, Ute; Schmid, Günter; Dehm, C. (Applied Physics Letters, 2004)

Organic Thin Film Transistors with Printed Gate Electrodes - Zschieschang, Ute; Klauk, Hagen; Halik, Marcus; Schmid, Günter; Radlik, Wolfgang; et al. (IEEE International Conference on Neural Networks - Conference Proceedings, 2002)

Oscillations of the electrical resistance induced by shear deformation in molten carbon black composites - Krückel, Johannes; Stary, Zdenek; Schubert, Dirk W. (Polymer, 2013)
The time-dependent electrical resistance of polymethylmethacrylate containing carbon black was monitored under oscillatory shear in the molten state. The electrical signal measured was oscillating exactly at the doubled frequency of the oscillatory shear deformation. Moreover, the experimental results gave a hint to the development of conductive structures in polymer melts under shear deformation. It was shown that the flow induced destruction of conductive paths dominates over the flow induced build-up in the beginning of the shear deformations. However, for longer times both competitive effects reach a dynamic equilibrium and only the thermally induced build-up of pathways influences the changes in the composite resistance during the shear. Moreover, the oscillating electrical response depends clearly on the deformation amplitude applied. Furthermore, a simple physical model describing the behaviour of conductive pathways under shear deformation was derived and utilized for the description of the experimental data.
Keywords: Polymer composites; Electrical resistance; Rheology

Overcoming interface losses in organic solar cells by applying low temperature, solution processed aluminum-doped zinc oxide electron extraction layers - Stubhan, Tobias; Litzov, Ivan; Li, Ning; Salinas Batallas, Michael; Steidl, Matthias; Sauer, Gerhard; Forberich, Karen; Matt, Gebhard; Halik, Marcus; Brabec, Christoph (Journal of Materials Chemistry A, 2013)
Intrinsic zinc oxide (ZnO) is widely used as an electron extraction layer (EEL) for inverted polymer solar cells. Despite the excellent device performance, a major drawback for large area production is its low conductivity. Using microscopic simulations, we derived a technically reasonable threshold value of 10−3 S cm−1 for the conductivity required to overcome transport limitations. For conductivity values typical for ZnO we observed the interface layer thickness restriction at only a few tens of nanometers, either as a fill factor drop due to serial resistance, eventually accompanied by a second diode behavior, or by the need for light soaking. Higher conductive aluminum-doped zinc oxide (AZO), which was introduced earlier, meets the desired conductivity threshold, however, at the cost of high temperature processing. High annealing temperatures (>150 °C) significantly improve the electrical properties of ZnO, but prohibit processing on plastic substrates or organic active layers. Here we report on AZO layers from a sol–gel precursor, which has been already reported to give sufficiently high conductivities at lower processing temperatures (<150 °C). We investigate the influence of different precursor compositions on the electrical properties of the thin films and their performance in inverted poly(3-hexylthiophene):[6,6]-phenyl-C61-butyric acid methyl ester (P3HT:PCBM) solar cells. Low temperature AZO layers with thicknesses up to 680 nm maintained comparable performance to devices with thin AZO layers.
Keywords: Aluminum-doped zinc oxide; Annealing temperatures; High-temperature processing; Inverted polymer solar cells; Microscopic simulation; Organic active layers; Poly (3-hexylthiophene); Processing temperature Engineering controlled terms: Aluminum; Electric properties; Extraction; Processing; Sol-gels; Solar cells; Temperature Engineering main heading: Zinc oxide

Patient-tailored silicone plug for HeartMate 3™ left ventricular assist device explantation - Elbayomi, Mohamed; Tandler, Rene; Ebel, Nina; Schubert, Dirk W.; Werner, Siegfried; Kondruweit, Markus; Weyand, Michael; Heim, Christian (Journal of Artificial Organs, 2023)
Patient-tailored silicone plug for HeartMate 3™ left ventricular assist device explantation in two successive males proceeded successfully. Given medical therapeutic advancements, FDA-approved plug systems designed by LVAD manufacturers themselves will be necessary for the near future to provide a safe and simple device explantation alternative that fulfills all regulatory standards.
CRIS-Team Scopus Importer:2023-05-05
Keywords: Case report; HeartMate 3™; Ventricular assist device explantation

Patient-Tailored Silicone Plug for HeartMate 3 (TM) Left Ventricular Assist Device Explantation - Heim, Christian; Ebel, Nina; Schubert, Dirk W.; Werner, Siegfried; Kondruweit, Markus; Tandler, R.; Weyand, Michael (JOURNAL OF HEART AND LUNG TRANSPLANTATION, 2019)
CRIS-Team WoS Importer:2019-04-04

Pentacene Organic Transistors and Ring Oscillators on Glass and on Flexible Polymeric Substrates - Klauk, Hagen; Halik, Marcus; Zschieschang, Ute; Eder, F.; Schmid, Günter; Dehm, C. (Applied Physics Letters, 2003)

Perpendicular and In‐Plane Conductivity of Poly(methyl methacrylate) Composite Films Filled with Carbon‐Based Fillers Prepared from Solution Casting Process - Xu, Huagen; Schubert, Dirk W. (Macromolecular Materials and Engineering, 2020)
In this study, poly(methyl methacrylate) (PMMA)/carbon black (CB), PMMA/carbon fiber (CF), and PMMA/carbon nanotube (CNT) conductive composite films with different filler concentrations are prepared using the solution casting technique. Both perpendicular and in‐plane direction conductivity of all the binary composite films are investigated, percolation thresholds (ϕc) of both directions of PMMA/CB, PMMA/CF, and PMMA/CNT composite films are investigated and the experimental data are fitted using McLachlan’s equation. For all the three investigated films, the perpendicular ϕc,⊥ and in‐plane ϕc,∥ with different fillers show totally different behaviors. Pristine CB, CF, and CNT as well as PMMA/CB, PMMA/CF, and PMMA/CNT composite films are discussed. The gravity effect of the fillers is found to be most significant in the PMMA/CB system. A schematic diagram of PMMA composite films with CB, CF, and CNT as filler prepared from solution casting process is presented to explain the distribution gradient of the fillers in the perpendicular direction of the film after solution casting. A power law behavior is revealed for different filler types (CB, CF, CNT) correlating the exponent t for McLachlan’s equation and corresponding ϕc for in‐plane and perpendicular direction
Keywords: carbon nanotubes; carbon black; carbon fillers; conductive polymer films; percolation threshold

Phase structure, rheology and electrical conductivity of co-continuous polystyrene/polymethylmethacrylate blends filled with carbon black - Esper, Julian Duane; Scherzer, Selina; Stary, Zdenek; Pavlova, Ewa (Composites Science and Technology, 2015)
In this work the effect of carbon black concentration on the rheology, electrical conductivity and morphology development of PS/PMMA co-continuous blends during quiescent annealing is investigated. In the blends studied carbon black is preferentially localized in the PS. The specific interfacial length, which is taken as a measure of fineness of blends morphology, increases linearly with the carbon black content in the blends after melt mixing. However, significant suppression of the structure coarsening during annealing is observed in systems with more than 3 vol.% of carbon black, in which the filler structures induce pronounced flow restrictions. The final change in the flow behaviour of the blend induced by annealing is a result of competition between morphology coarsening and particle structure formation and it depends on the concentration of carbon blac
Keywords: Annealing; Polymer-matrix composites; Electrical properties; Scanning electron microscopy; Rheology

Phosphonate- and Carboxylate-Based Self-Assembled Monolayers for Organic Devices: A Theoretical Study of Surface Binding on Aluminum Oxide with Experimental Support - Bauer, Thilo; Schmaltz, Thomas; Lenz, Thomas; Halik, Marcus; Meyer, Bernd; Clark, Timothy (ACS Applied Materials and Interfaces, 2013)
We report a computational study on the chemical bonding of phosphonates and carboxylates to aluminum oxide surfaces and how the binding properties are related to the amount of water in the experimental environment. Two different surface structures were used in the calculations in order to model representative adsorption sites for the phosphonates and carboxylates and to account for the amorphous nature of the hydroxylated AlOx films in experiment. For the phosphonates, we find that the thermodynamically preferred binding mode changes between mono-, bi-, and tridentate depending on the surface structure and the amount of residual water. For the carboxylates, on the other hand, monodentate adsorption is always lower in energy at all experimental conditions. Phosphonates are more strongly bound to aluminum oxide than carboxylates, so that carboxylates can be replaced easily by phosphonates. The theoretical findings are consistent with those obtained in adsorption, desorption, and exchange reactions of n-alkyl phosphonic and carboxylic acids on AlOx surfaces. The results provide an atomistic understanding of the adsorption and help to optimize experimental conditions for self-assembly of organic films on aluminum oxide surfaces.

Photoactive self-assembled monolayers for optically switchable organic thin-film transistors - Salinas Batallas, Michael; Halik, Marcus (Applied Physics Letters, 2013)
We investigate the photoconductive and photovoltaic effects in organic thin-film transistors with thin hybrid dielectrics composed of aluminum oxide and self-assembled monolayers (SAMs). By using SAM molecules with an electro-optical functionality tuning of the photoinduced charge transfer at the interface of semiconductor and SAM upon illumination with laser light can be achieved. Control of the threshold voltage by the SAM composition enables the optical operation of the transistors without applying a gate voltage and affects the dynamics of photoinduced charge transfer.

Physical characterizations and biological properties of PHP/PCL electrospun fibermats - Ding, Yaping; Roether, Judith; Schubert, Dirk W.; Boccaccini, Aldo R. (European Polymer Federation, 2015)

Physical foaming of fluorinated ethylene-propylene (FEP) copolymers in supercritical carbon dioxide: single-film fluoropolymer piezoelectrets - Voronina, O.; Wegener, Michael; Wirges, Werner; Gerhard, Reimund; Zirkel, Larissa; Münstedt, Helmut (Applied Physics A-Materials Science & Processing, 2008)
Cellular polymer foams with significant piezoelectric activity were prepared from fluorinated ethylene-propylene (FEP) copolymers. The required void structure is obtained by saturation of FEP films with supercritical carbon dioxide and a subsequent heat treatment for controlled inflation. After bipolar electric charging of the voids and evaporation of electrodes, the FEP films show piezoelectric d33 coefficients up to 50 pC N. The present physical foaming process generates cellular efficients up to 50 pC/N. The present physical foaming process generates cellular fluoropolymer piezoelectret films with usually only one single void across the film thickness.
EAM Import::2019-03-12

Polyaniline based polymers in tissue engineering applications: a review - Rai, Ranjana; Roether, Judith; Boccaccini, Aldo R. (Progress in Biomedical Engineering, 2022)
A number of electrically conducting polymers, such as polyaniline (PANi), as well as functionalized aniline copolymers and composites, which are simultaneously biodegradable and conductive, have been applied for developing electrically conductive scaffolds for tissue engineering (TE) in recent years. The rationale behind these scaffolds is to induce ‘electroactivity’ in scaffolds, as many research works have shown that an intrinsic electrical activity leads to both increased regeneration rates and improved healing of damaged tissues. PANi is the conductive polymer of choice because it is economical and easy to process with a variety of methods. The resultant PANi based biomaterials have shown biocompatibility, conductivity, suitable processability, positive cellular response, as well as an intrinsic antibacterial effect in numerous research studies. The analysis of the literature has revealed that PANi based scaffolds have been investigated for TE applications including skin/wound healing, bone, cartilage, nerve/spinal cord, vascular, skeletal muscle repair and for the treatment of infertility. Although PANi based materials find widespread applications in other sectors, they are still far away from being commercially exploited as scaffolds for TE despite positive research results. This review aims to discuss and critically assess the current state of PANi based TE scaffolds for different applications. A future perspective for utilizing PANi based biomaterials for applications in TE is discussed, including recent considerations about potential cytotoxic effects.
CRIS-Team Scopus Importer:2022-11-25
Keywords: antibacterial; biocompatibility; conductivity; polyaniline; tissue engineering

Polyethylene-naphthalate (PEN) ferroelectrets: cellular structure, piezoelectricity and thermal stability - Fang, Peng; Qiu, Xunlin; Wirges, Werner; Gerhard, Reimund; Zirkel, Larissa (IEEE Transactions on Dielectrics and Electrical Insulation, 2010)
Cellular polyethylene-naphthalate (PEN) ferroelectrets are useful as soft and flexible electromechanical transducer materials. Improved cellular PEN foams are prepared by means of a + inflation + stretchingprocess and investigated with respect to their structure and their applications-relevant properties. It is found that most of the cellular voids have heights below 8 extgreekmm. The polymer walls do not allow sufficient gas exchange between the voids and the ambient atmosphere, when the cellular films are exposed to atmospheric pressures between a millibar and a few bars. As expected for ferroelectrets, a threshold voltage for charging is observed: A reasonable piezoelectric coefficient d_3_3 is only found when the charging voltage is higher than 4 kV. Furthermore, d_3_3 increases with charging voltage and reaches saturation at approximately 8 kV. Annealing after charging or charging at elevated temperatures may enhance the thermal stability of the PEN ferroelectrets. The d_3_3 of properly annealed samples is stable up to the respective annealing temperatures, but the annealing process reduces the piezoelectric activity of charged ferroelectret films to some extent. Samples charged at suitable elevated temperatures show much better thermal stability than those charged at room temperature, but the charging temperature should be limited to values below the material's glass-transition temperature Tg. Furthermore, the relevant elastic modulus c_3_3 of PEN ferroelectrets may decrease upon thermal treatment.
EAM Import::2019-03-08

Poly(Glycerol Sebacate) Films Modified by Thermal Proteins for Cardiac Tissue Engineering - Tallawi, Marwa; Rai, Ranjana; Costa, Marina; Roether, Judith; Schubert, Dirk W.; Boccaccini, Aldo R. (Biomedical Engineering, 2013)
Scaffolds for cardiac tissue engineering must be designed to achieve adequate degradation kinetics and mechanical properties. In this study, bulk modification of poly(glycerol sebacate) (PGS) with different concentrations of thermal proteins (TP) was investigated to tailor the degradation properties of PGS. TP are poly-amino acids formed by heating a mixture of amino acids with minimal proportions of glutamic or aspartic acid. The degradation study of TP-PGS was performed in vitro in phosphate buffered saline (PBS) solution over a 21 day period. Results showed that the degradation rate of PGS increased with increasing content of TP. After 21 days in PBS, degradation weight loss values of 9.40% ± 0.07, 7.3% ± 0.8 and 6.0% ± 0.4 were determined for PGS-TP-2g, PGS-TP-0.01g and PGS-control, respectively. The studies also showed that TP altered the mechanical properties and surface hydrophilicity of PGS.
Keywords: Thermal proteins; degradation; poly(glycerol sebacate); cardiac tissue engineering

Poly(Glycerol Sebacate)/Poly(Butylene Succinate-Butylene Dilinoleate) Fibrous Scaffolds for Cardiac Tissue Engineering - Tallawi, Marwa; Zebrowski, David; Rai, Ranjana; Roether, Judith; Schubert, Dirk W.; El Fray, Miroslawa; Engel, Felix; Aifantis, Katerina E.; Boccaccini, Aldo R. (Tissue Engineering - Part C: Methods, 2015)
The present article investigates the use of a novel electrospun fibrous blend of poly(glycerol sebacate) (PGS) and poly(butylene succinate-butylene dilinoleate) (PBS-DLA) as a candidate for cardiac tissue engineering. Random electrospun fibers with various PGS/PBS-DLA compositions (70/30, 60/40, 50/50, and 0/100) were fabricated. To examine the suitability of these fiber blends for heart patches, their morphology, as well as their physical, chemical, and mechanical properties were measured before examining their biocompatibility through cell adhesion. The fabricated fibers were bead-free and exhibited a relatively narrow diameter distribution. The addition of PBS-DLA to PGS resulted in an increase of the average fiber diameter, whereas increasing the amount of PBS-DLA decreased the hydrophilicity and the water uptake of the nanofibrous scaffolds to values that approached those of neat PBS-DLA nanofibers. Moreover, the addition of PBS-DLA significantly increased the elastic modulus. Initial toxicity studies with C2C12 myoblast cells up to 72 h confirmed nontoxic behavior of the blends. Immunofluorescence analyses and scanning electron microscopy analyses confirmed that C2C12 cells showed better cell attachment and proliferation on electrospun mats with higher PBS-DLA content. However, immunofluorescence analyses of the 3-day-old rat cardiomyocytes cultured for 2 and 5 days demonstrated better attachment on the 70/30 fibers containing well-aligned sarcomeres and expressing high amounts of connexin 43 in cellular junctions indicating efficient cell-to-cell communication. It can be concluded, therefore, that fibrous PGS/PBS-DLA scaffolds exhibit promising characteristics as a biomaterial for cardiac patch applications.

Poly(glycerol sebacate)(butylene succinate-dilinoleate) blends as candidate materials for cardiac tissue engineering - Göken, Mathias; Merle, Benoit; Boccaccini, Aldo R.; Aifantis, K.; Tallawi, Marwa; Rai, Ranjana; R-Gleixner, M.; Roerick, Olaf; Weyand, Michael; Roether, Judith; Schubert, Dirk W.; Kozlowska, A.; et al. (Macromolecular Symposia, 2013)
Poly (glycerol sebacate) (PGS) and poly (butylene succinate‐dilinoleate) (PBS‐DLA) are biodegradable polymers with potential application in cardiac tissue engineering. In the present study novel blends comprising PGS prepolymer and PBS‐DLA were prepared with varying compositions (70/30, 60/40, 50/50, 40/60, 30/70 and 0/100 in weight percentage). The physical, chemical, and mechanical properties of the PGS/PBS‐DLA blends were measured and compared. By adding PBS‐DLA to PGS the need for curing PGS prepolymer was eliminated, as the blended films are chemically stable. With increasing amount of PBS‐DLA the hydrophobicity of the blend system increased reaching values close to that of neat PBS‐DLA films. Furthermore, addition of PBS‐DLA significantly affected the mechanical properties of the blends, i.e. the elastic modulus of the blends was enhanced with increasing PBS‐DLA addition from 1.2 MPa to 54 MPa. At the same time, PBS‐DLA addition led to decreased degradation rate of the films. Furthermore the PBS‐DLA counteracted the acidity of the free carboxylic groups on the free end chains of the PGS prepolymer. In vitro cytocompatibility studies indicated high biocompatibility. Taken together the results confirm that the novel PGS/PBS‐DLA matrices exhibit promising characteristics as a biomaterial for application in cardiac regeneration approaches.
Keywords: myoblasts; poly (butylene succinate-dilinoleate); cardiac tissue engineering; mechanobiology; substrate stiffness

Poly(glycerol sebacate){Poly(butylene succinate-dilinoleate) Blends as Candidate Materials for Cardiac Tissue Engineering - Tallawi, Marwa; Rai, Ranjana; Ramsperger-Gleixner, Martina; Roerick, Olaf; Weyand, Michael; Roether, Judith; Schubert, Dirk W.; Kozlowska, A.; El Fray, Miroslawa; Merle, Benoit; Göken, Mathias; Aifantis, K.; et al. (WILEY-V C H VERLAG GMBH, 2013)
Poly (glycerol sebacate) (PGS) and poly (butylene succinate-dilinoleate) (PBS-DLA) are biodegradable polymers with potential application in cardiac tissue engineering. In the present study novel blends comprising PGS prepolymer and PBS-DLA were prepared with varying compositions (70/30, 60/40, 50/50, 40/60, 30/70 and 0/100 in weight percentage). The physical, chemical, and mechanical properties of the PGS/PBS-DLA blends were measured and compared. By adding PBS-DLA to PGS the need for curing PGS prepolymer was eliminated, as the blended films are chemically stable. With increasing amount of PBS-DLA the hydrophobicity of the blend system increased reaching values close to that of neat PBS-DLA films. Furthermore, addition of PBS-DLA significantly affected the mechanical properties of the blends, i.e. the elastic modulus of the blends was enhanced with increasing PBS-DLA addition from 1.2 MPa to 54 MPa. At the same time, PBS-DLA addition led to decreased degradation rate of the films. Furthermore the PBS-DLA counteracted the acidity of the free carboxylic groups on the free end chains of the PGS prepolymer. In vitro cytocompatibility studies indicated high biocompatibility. Taken together the results confirm that the novel PGS/PBS-DLA matrices exhibit promising characteristics as a biomaterial for application in cardiac regeneration approaches.
Keywords: cardiac tissue engineering; mechanobiology; myoblasts; poly (butylene succinate-dilinoleate); substrate stiffness

Poly(glycerol sebacate){Poly(butylene succinate-dilinoleate) Blends as Candidate Materials for Cardiac Tissue Engineering - Tallawi, Marwa; Rai, Ranjana; Ramsperger-Gleixner, Martina; Roerick, Olaf; Weyand, Michael; Roether, Judith; Schubert, Dirk W.; Kozlowska, A.; El Fray, M.; Merle, Benoit; Göken, Mathias; Aifantis, K.; et al. (Macromolecular Symposia, 2013)
Poly (glycerol sebacate) (PGS) and poly (butylene succinate-dilinoleate) (PBS-DLA) are biodegradable polymers with potential application in cardiac tissue engineering. In the present study novel blends comprising PGS prepolymer and PBS-DLA were prepared with varying compositions (70/30, 60/40, 50/50, 40/60, 30/70 and 0/100 in weight percentage). The physical, chemical, and mechanical properties of the PGS/PBS-DLA blends were measured and compared. By adding PBS-DLA to PGS the need for curing PGS prepolymer was eliminated, as the blended films are chemically stable. With increasing amount of PBS-DLA the hydrophobicity of the blend system increased reaching values close to that of neat PBS-DLA films. Furthermore, addition of PBS-DLA significantly affected the mechanical properties of the blends, i.e. the elastic modulus of the blends was enhanced with increasing PBS-DLA addition from 1.2 MPa to 54 MPa. At the same time, PBS-DLA addition led to decreased degradation rate of the films. Furthermore the PBS-DLA counteracted the acidity of the free carboxylic groups on the free end chains of the PGS prepolymer. In vitro cytocompatibility studies indicated high biocompatibility. Taken together the results confirm that the novel PGS/PBS-DLA matrices exhibit promising characteristics as a biomaterial for application in cardiac regeneration approache
Keywords: cardiac tissue engineering; mechanobiology; myoblasts; poly (butylene succinate-dilinoleate); substrate stiffness

Polylactide/organoclay nanocomposites: The effect of organoclay types on the structure development and the kinetic of cold crystallization - Abdolrsaouli, Mehdi Haji; Babaei, Amir; Kaschta, Joachim; Nazockdat, Hossein (Journal of Vinyl & Additive Technology, 2019)
Polylactide (PLA)/organoclay composites were prepared by melt compounding with 4 phr of two different types of organoclays (cloisite 20A and cloisite 30B). Structure development and nonisothermal kinetic of cold crystallization of PLA/organoclay nanocomposites were examined by using of X-ray diffraction technique, transmission electron microscopy, melt viscoelastic measurements, and differential scanning calorimetry. XRD results demonstrated that the melt intercalation of PLA chains into the cloisite 30B and cloisite 20A galleries was achieved to the same extent. However, it was shown that, PLA/cloisite 20A sample exhibited a significant viscosity upturn and a pronounced nonterminal low frequency storage modulus whose values were greater than those of PLA/cloisite 30B nanocomposite. A detailed analysis of the linear melt viscoelastic properties for the filled and unfilled samples at low frequencies was conducted by fitting the complex viscosity and storage modulus data with Carreau-Yasuda and Fractional Zener models, respectively. The glass transition, cold crystallization, melting temperature, and degree of crystallinity of virgin PLA and PLA/organoclay nanocomposites were inspected. Subsequently, the cold crystallization kinetics was analyzed by Avrami, Jezioney, and Lauritzen-Hoffman kinetic models. It was shown that, the crystallization rate followed Avrami equation with the exponent n around 2.4. From Lauritzen-Hoffman equation and Kissinger model, the nucleation parameter K-g and activation energy were estimated, respectively. J. VINYL ADDIT. TECHNOL., 25:48-58, 2019. (c) 2018 Society of Plastics Engineers
CRIS-Team WoS Importer:2019-02-21

Polymer-functionalised nanograins of Mg-doped amorphous calcium carbonate via a flow-chemistry approach - Demmert, Benedikt; Schinzel, Frank; Schüßler, Martina; Mondeshki, Mihail; Kaschta, Joachim; Schubert, Dirk W.; Jacob, Dorrit E.; Wolf, Stephan (Materials, 2019)
Calcareous biominerals typically feature a hybrid nanogranular structure consisting of calcium carbonate nanograins coated with organic matrices. This nanogranular organisation has a beneficial effect on the functionality of these bioceramics. In this feasibility study, we successfully employed a flow-chemistry approach to precipitate Mg-doped amorphous calcium carbonate particles functionalized by negatively charged polyelectrolytes-either polyacrylates (PAA) or polystyrene sulfonate (PSS).We demonstrate that the rate of Mg incorporation and, thus, the ratio of the Mg dopant to calcium in the precipitated amorphous calcium carbonate (ACC), is flow rate dependent. In the case of the PAA-functionalized Mg-doped ACC, we further observed a weak flow rate dependence concerning the hydration state of the precipitate, which we attribute to incorporated PAA acting as a water sorbent; a behaviour which is not present in experiments with PSS and without a polymer. Thus, polymer-dependent phenomena can affect flow-chemistry approaches, that is, in syntheses of functionally graded materials by layer-deposition processes.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Amorphous calcium carbonate; Biomaterials; Flow-chemistry; Microfluidics; Nanoceramics

Polymer Gate Dielectric Pentacene TFTs and Circuits on Flexible Substrates - Klauk, Hagen; Halik, Marcus; Zschieschang, Ute; Schmid, Günter; Radlik, Wolfgang; Brederlow, R.; Briole, S.; Parcha, C.; Thewes, R.; Weber, Werner (Technical Digest - International Electron Devices Meeting, 2002)

Polymer gate dielectrics and conducting polymer contacts for high-performance organic thin film transistors - Halik, Marcus; Klauk, Hagen; Zschieschang, Ute; Schmid, Günter; Radlik, Wolfgang; Weber, Werner (Advanced Materials, 2002)

Polymer/metal oxide hybrid dielectrics for low voltage field-effect transistors with solution-processed, high-mobility semiconductors - Held, Martin; Schießl, Stefan; Miehler, Dominik; Gannott, Florentina; Zaumseil, Jana (Applied Physics Letters, 2015)
Transistors for future flexible organic light-emitting diode (OLED) display backplanes should operate at low voltages and be able to sustain high currents over long times without degradation. Hence, high capacitance dielectrics with low surface trap densities are required that are compatible with solution-processable high-mobility semiconductors. Here, we combine poly(methyl methacrylate) (PMMA) and atomic layer deposition hafnium oxide (HfOx) into a bilayer hybrid dielectric for field-effect transistors with a donor-acceptor polymer (DPPT-TT) or single-walled carbon nanotubes (SWNTs) as the semiconductor and demonstrate substantially improved device performances for both. The ultra-thin PMMA layer ensures a low density of trap states at the semiconductor-dielectric interface while the metal oxide layer provides high capacitance, low gate leakage and superior barrier properties. Transistors with these thin (łeq70 nm), high capacitance (100–300 nF/cm2) hybrid dielectrics enable low operating voltages (<5 V), balanced charge carrier mobilities and low threshold voltages. Moreover, the hybrid layers substantially improve the bias stress stability of the transistors compared to those with pure PMMA and HfOx dielectrics.
EAM Import::2019-03-08

Polymers for myocardial tissue engineering - Roether, Judith; Jawad, H.; Rai, Ranjana; Ali, N. N.; Harding, S. E.; Boccaccini, Aldo R. (CRC Press, 2013)
Cardiovascular disease (CVD) is the leading cause of death in the industrialized world (Lloyd-Jones et al. 2010). Heart attacks are the main cause of death in patients with CVD, although damage to heart muscle can also occur from infection, drugs, alcohol, chemotherapeutic agents, or because of congenital conditions. According to available statistical information (www.bhf.org.uk), approximately 30% of patients suffering from heart attacks each year die suddenly before reaching hospital. In the remaining patients who survive the initial acute event, the damage sustained to the heart may eventually develop heart failure. A heart attack, known as myocardial infarction (MI), occurs when one or more of the blood vessels supplying the heart suddenly occlude. These vessels are the coronary arteries, and when blocked abruptly, there is a sudden decrease in the supply of nutrients and oxygen to the portion of heart muscle supplied by the artery. If blood flow is not restored rapidly, the result is irreversible cell death within the affected part of the heart muscle.
CRIS-Team Scopus Importer:2022-08-05

Polypropylene/styrene-butadiene-styrene nanocomposites: Mechanical properties - Mubarak, Y. A.; Schubert, Dirk W.; Abu-Halimeh, Rachael (International Journal of Mechanical and Mechanics Engineering, 2018)
Keywords: Tensile strength.; Fumed silica; Nanocomposites; Impact strength; Styrene-butadiene-styrene; Polypropylene

Polytetrafluoroethylene (PTFE) as a Suture Material in Tendon Surgery - Polykandriotis, Elias; Himmler, Marcus; Mansouri, Shirin; Ruppe, Florian; Grüner, Jasmin; Bräuer, Lars; Schubert, Dirk W.; Horch, Raymund E. (Journal of Visualized Experiments, 2022)
With the evolution of suture materials, there has been a change in paradigms in primary and secondary tendon repair. Improved mechanical properties allow more aggressive rehabilitation and earlier recovery. However, for the repair to hold against higher mechanical demands, more advanced suturing and knotting techniques must be assessed in combination with those materials. In this protocol, the use of polytetrafluoroethylene (PTFE) as a suture material in combination with different repair techniques was investigated. In the first part of the protocol, both linear tension strength and elongation of knotted against not-knotted strands of three different materials used in flexor tendon repair were evaluated. The three different materials are polypropylene (PPL), ultra-high molecular weight polyethylene with a braided jacket of polyester (UHMWPE), and polytetrafluoroethylene (PTFE). In the next part (ex vivo experiments with cadaveric flexor tendons), the behavior of PTFE using different suture techniques was assessed and compared with PPL and UHMWPE. This experiment is comprised of four steps: harvesting of the flexor tendons from fresh cadaveric hands, transection of the tendons in a standardized manner, tendon repair by four different techniques, mounting, and measurement of the tendon repairs on a standard linear dynamometer. The UHMWPE and PTFE showed comparable mechanical properties and were significantly superior to PPL in terms of linear traction strength. Repairs with four- and six-strand techniques proved stronger than two-strand techniques. Handling and knotting of PTFE are a challenge due to very low surface friction but fastening of the four- or six-strand repair is comparatively easy to achieve. Surgeons routinely use PTFE suture material in cardiovascular surgery and breast surgery. The PTFE strands are suitable for use in tendon surgery, providing a robust tendon repair so that early active motion regimens for rehabilitation can be applied.
CRIS-Team Scopus Importer:2022-11-18

Polyurethane/silver-nanocomposites with enhanced silver ion release using multifunctional invertible polyesters - Peukert, Wolfgang; Damm, Cornelia; Triebel, Christian; Vasylyev, Serhiy; Stara, Hana; Özpinar, Celal; Münstedt, Helmut; Hausmann, Sebastian (Journal of Materials Chemistry, 2011)
Nano-silver composites with a thermoplastic polyurethane as the matrix were prepared by two different routes. Using the so-called in situ preparation, silver nanoparticles were obtained by a thermal reduction of silver acetate during melt mixing. In addition, a more sophisticated ex situ preparation method was developed. Here, the silver nanoparticles are synthesized in an invertible polyester resulting in much smaller particle sizes. The particles obtained are surrounded by the polyester cage, which stabilizes them with respect to agglomeration. Hence, an incorporation of those particles into a polymer melt with common techniques like extrusion leads to an even distribution. This is due to the fact that the invertible polyester and the polymer matrix are entirely miscible which was proven with DSC measurements. The silver ion release of the composites prepared was measured with anodic stripping voltammetry. At a constant weight percentage of silver in the polymer, the composite with the ex situ silver nanoparticles exhibits a silver ion release which is about two orders of magnitude higher than the release from the composite with the in situ silver nanoparticles. This observation is explained by the higher specific surface area of the smaller particles and a higher coefficient of diffusion for silver ions. A concentration of only 0.07 wt% silver nanoparticles, prepared with the ex situ method, exhibits a high enough release of silver ions to achieve antimicrobial properties. © 2011 The Royal Society of Chemistry.
Keywords: nanoparticle; polymer; thermal; reduction; ex-situ

Positive effect of wrapping poly caprolactone/polyethylene glycol fibrous films on the mechanical properties of 45S5 bioactive glass scaffolds - Shi, Quan; Li, Zhi-Yong; Liverani, Liliana; Roether, Judith; Chen, Qiang; Boccaccini, Aldo R. (International Journal of Applied Ceramic Technology, 2018)
Keywords: electrospinning; mechanical properties; 45S5 bioactive glass scaffold; bone tissue engineering; poly caprolactone/polyethylene glycol film

Positive temperature coefficient (PTC) materials based on amorphous poly(methyl methacrylate) with ultrahigh PTC intensity, tunable switching temperature and good reproducibility - Luo, Xiaoling; Schubert, Dirk W. (Materials Today Communications, 2022)
Positive temperature coefficient (PTC) materials based on amorphous polymers usually suffer from low intensity owing to their relatively small volume thermal expansion. Herein, graphene nanoplatelets (GNPs) and carbon fibers (CF) with large aspect ratios were introduced into amorphous poly(methyl methacrylate) (PMMA) via melting mixing followed by hot pressing to improve the PTC characteristics of the conductive composites. The binary PMMA/GNPs composites showed good reproducibility while the PMMA/CF composites were superior in PTC intensity and their switching temperature (positive to negative temperature coefficient) could be tuned by varying the CF concentrations. When the both binary composites were connected in series, their strengths could be fostered and their weaknesses could be circumvented. The ternary composite exhibited a superior PTC intensity of 7.17, outperforming most of the reported PTC materials. These composites have great potential for applications as temperature sensors and current limiting devices.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Amorphous polymer; Carbon fibers; Graphene nanoplatelets; Positive temperature coefficient

Potent method of extracting glyphosate from water using superparamagnetic nanoparticles - Park, Hyoungwon; Sarcletti, Marco; Halik, Marcus (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2019-08-23

Practical Mapping Of The Draw Resonance Instability In Film Casting - Bechert, Mathias; Schubert, Dirk W.; Scheid, Benoit (Book of Abstracts, 2016)

Practical mapping of the draw resonance instability in film casting of Newtonian fluids - Bechert, Mathias; Schubert, Dirk W. (Bifurcations and Instabilities in Fluid Dynamics, 2015)

Practical mapping of the draw resonance instability in film casting of Newtonian fluids - Bechert, Mathias; Schubert, Dirk W.; Scheid, Benoit (European Journal of Mechanics B-Fluids, 2015)
The influence of viscosity and inlet velocity on the draw resonance instability of film casting processes is quantitatively analysed. By linear stability analysis of a Newtonian model including inertia and gravity effects, stability curves for different control parameter values are calculated numerically. For this purpose, we propose a scaling law which separates the fluidity, i.e. the reciprocal viscosity and the inlet velocity into two independent dimensionless parameters. This new scaling evidences a minimum of stability, separating two regimes of opposite behaviour: one for which increasing the inlet flow rate has a destabilizing effect due to viscosity and one for which increasing the inlet flow rate has a stabilizing effect due to gravity and inertia; increasing the fluidity has always a stabilizing effect. By fitting the stability curves with an appropriate postulated function, we are able to construct correlations between the critical draw ratio, the fluidity and the inlet velocity. For the first time regimes of negligible inertia or negligible gravity effects are revealed as well as a regime of unconditional stability. The proposed correlations for each of these regimes can further be used as an analytical solvable criterion for determining the onset of draw resonance in film casting. (C) 2015 Elsevier Masson SAS. All rights reserved.
Keywords: Draw resonance; Film casting; Stability map

Pre-Crosslinking with Hydrogel Microparticles Enhances the Printability of Alginate-Based Inks - Hazur, Jonas; Röder, Jonas; Czwalinna, Jonas; Schubert, Dirk W.; Boccaccini, Aldo R. (Macromolecular Materials and Engineering, 2023)
The main challenge in extrusion-based bioprinting is to develop inks which must comprise a manifold of characteristics before, during, and after printing. To tackle the challenge of good shape fidelity and printability of low concentration inks, in this study hydrogel microparticles (HMPs) are proposed to produce internally pre-crosslinked inks. Alginate (Alg) and oxidized alginate (OA)-based HMPs are fabricated and used as Ca2+-releasing reservoirs. OA HMPs are used to demonstrate the versatility of this approach and to show its suitability also for chemically modified alginate. Embedded in either fresh Alg or OA solution, HMPs are used to pre-crosslink the inks. Rheological measurements revealed that HMP pre-crosslinking increases the yield stress and viscosity while reducing the loss angle of bioinks. Moreover, printing experiments reveal that being able to tailor rheological properties is an effective tool to improve printability. Furthermore, pre-crosslinking significantly alters the hydogel internal microstructure. In vitro studies show that NIH/3T3 cells proliferate in HMP pre-crosslinked bioinks modified with gelatin. Altogether, a low-cost and easy to use setup to prepare HMPs is presented and for the first time, the possibility of using such HMPs as pre-crosslinking agent to tailor the printability of alginate-based bioinks is demonstrated.
CRIS-Team Scopus Importer:2023-08-18
Keywords: alginate; bioprinting; cross-linking; gelatin; oxidized alginate

Prediction of steady-state viscous and elastic properties of polyolefin melts in shear and elongation - Rolón-Garrido, Víctor; Resch, Julia; Wolff, Friedrich; Kaschta, Joachim; Münstedt, Helmut; Wagner, Manfred (Rheologica Acta, 2011)
The linear and nonlinear steady-state viscosities and elastic compliances were measured in shear and elongational flows for two low-density polyethylenes, a linear polypropylene, and two metallocene catalyzed polyethylenes (one linear and one long-chain branched) by Wolff et al. (Rheol Acta 49:95-103, 2010) and Resch (dissertation, 2010). Comprehensive data of this type are rarely found in the literature, and comprehensive modeling of both viscous and elastic effects is even rarer. In this contribution, the reliability of a modeling approach proposed by Laun (J Rheol 30(3):459-501, 1986) and based on the damping function concept is tested. The strain hardening seen for the long-chain branched polymers and its absence in the case of the linear polymer, the stronger decrease of the tensile compliance in comparison to the shear compliance with increasing stress, as well as the extended linear-viscoelastic regime of the shear viscosity in contrast to the shear compliance are correctly modeled. While the modeling of the nonlinear response in shear can be achieved with only one material parameter for most of the polymers considered here, the nonlinear modeling in elongation is achieved with two parameters. The same parameter values are shown to describe viscous as well as elastic properties of the melts, and thus the relations of Laun can be used to test the consistency of viscosity and compliance measurements.
Keywords: Rheology; Creep experiments; Shear flow; Elongational flow; Damping function; Strain hardening; Low-density polyethylene; Polymer melts

Preparation and characterization of 45S5 bioactive glass-based scaffolds loaded with PHBV microspheres with daidzein release function - Macias-Andres, Victor I.; Li, Wei; Aguilar-Reyes, Ena A.; Ding, Yaping; Roether, Judith; Harhaus, Leila; Leon-Patino, Carlos A.; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part A, 2017)
Keywords: 45S5 bioactive glass; Bone tissue engineering; Daidzein; Drug delivery; PHBV; Scaffold

Preparation and characterization of electrosprayed daidzein-loaded PHBV microspheres - Scheithauer, Ellen Corinna; Li, Wei; Ding, Yaping; Harhaus, Leila; Roether, Judith; Boccaccini, Aldo R. (Materials Letters, 2015)
Given that hormone therapy of osteoporosis with estrogen and progesterone may have potential negative side effects, there is a strong need of developing alternative solutions. Possible therapy alternatives involve the use of phytoestrogens such as daidzein. In this study, daidzein-loaded poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) microspheres were prepared using electrospraying. The obtained microspheres had uniform surface morphology, and narrow particle size distribution with mean particle size of 4.8 μm. Daidzein was determined to be in amorphous state in the PHBV microspheres by differential scanning calorimetry analysis. Encapsulated daidzein was released with a low initial burst release (7.6% at 1 h) followed by a sustained release over a period of 3 days. The developed PHBV microspheres with daidzein delivery function have potential applications in the treatment of osteoporosis and for bone tissue engineerin
Keywords: Bone tissue engineering; Daidzein; Drug delivery; Electrospraying; Osteoporosis; PHBV microspheres

Preparation and Characterization of Electrospun Blend Fibrous Polyethylene Oxide:Polycaprolactone Scaffolds to Promote Cartilage Regeneration - Mirzaei, Zeynab; Kuth, Sonja; Schubert, Dirk W.; Detsch, Rainer; Roether, Judith; Blunk, Torsten; Kordestani, Soheila S.; Boccaccini, Aldo R. (Advanced Engineering Materials, 2020)
Fibrous scaffolds can be used to mimic the structure of cartilage extracellular matrix aiming at cartilage regeneration through optimal utilization of such scaffolds and chondrogenic cells. Herein, different types of fibrous structures are manufactured through electrospinning of blends of polyethylene oxide (PEO) and polycaprolactone (PCL), and the physical and chemical characteristics of the produced fiber mats are investigated. The amount of PEO influenced hydrophilicity, biodegradability, and mechanical properties of the blend fibers. To assess the cytotoxicity and biocompatibility of the scaffolds as well as the effect of fiber orientation, in vitro cell culture studies with a chondrogenic cell line (ATDC5) are conducted. The results show no cytotoxicity of the developed fibrous structures. A promising fibrous scaffold technology is presented with potential applications in cartilage tissue engineering.
CRIS-Team WoS Importer:2020-05-29

Preparation and characterization of PHBV microsphere/45S5 bioactive glass composite scaffolds with vancomycin releasing function - Li, Wei; Ding, Yaping; Rai, Ranjana; Roether, Judith; Schubert, Dirk W.; Boccaccini, Aldo R. (Materials Science and Engineering C, 2014)
PHBV microsphere/45S5 bioactive glass (BG) composite scaffolds with drug release function were developed for bone tissue engineering. BG-based glass-ceramic scaffolds with high porosity (94%) and interconnected pore structure prepared by foam replication method were coated with PHBV microspheres (nominal diameter = 3.5 μm) produced by water-in-oil-in-water double emulsion solvent evaporation method. A homogeneous microsphere coating throughout the porous structure of scaffolds was obtained by a simple dip coating method, using the slurry of PHBV microspheres in hexane. Compressive strength tests showed that the microsphere coating slightly improved the mechanical properties of the scaffolds. It was confirmed that the microsphere coating did not inhibit the bioactivity of the scaffolds in SBF. Hydroxyapatite crystals homogeneously grew not only on the struts of the scaffolds but also on the surface of microspheres within 7 days of immersion in SBF. Vancomycin was successfully encapsulated into the PHBV microspheres. The encapsulated vancomycin was released with a dual release profile involving a relatively low initial burst release (21%) and a sustained release (1 month), which is favorable compared to the high initial burst release (77%) and short release period (4 days) measured on uncoated scaffolds. The developed bioactive composite scaffold with drug delivery function has thus the potential to be used advantageously in bone tissue engineering. © 2014 Elsevier B.V. All rights reserved.
Keywords: Bioglass; drug delivery; PHBV; scaffold; tissue engineering; vancomycin

Preparation and characterization of PHBV microsphere/45S5 bioactive glass composite scaffolds with vancomycin releasing function - Li, Wei; Ding, Yaping; Rai, Ranjana; Roether, Judith; Schubert, Dirk W.; Boccaccini, Aldo R. (Materials Science and Engineering C, 2014)
PHBV microsphere/45S5 bioactive glass (BG) composite scaffolds with drug release function were developed for bone tissue engineering. BG-based glass-ceramic scaffolds with high porosity (94%) and interconnected pore structure prepared by foam replication method were coated with PHBV microspheres (nominal diameter = 3.5 μm) produced by water-in-oil-in-water double emulsion solvent evaporation method. A homogeneous microsphere coating throughout the porous structure of scaffolds was obtained by a simple dip coating method, using the slurry of PHBV microspheres in hexane. Compressive strength tests showed that the microsphere coating slightly improved the mechanical properties of the scaffolds. It was confirmed that the microsphere coating did not inhibit the bioactivity of the scaffolds in SBF. Hydroxyapatite crystals homogeneously grew not only on the struts of the scaffolds but also on the surface of microspheres within 7 days of immersion in SBF. Vancomycin was successfully encapsulated into the PHBV microspheres. The encapsulated vancomycin was released with a dual release profile involving a relatively low initial burst release (21%) and a sustained release (1 month), which is favorable compared to the high initial burst release (77%) and short release period (4 days) measured on uncoated scaffolds. The developed bioactive composite scaffold with drug delivery function has thus the potential to be used advantageously in bone tissue engineerin
Keywords: tissue engineering; vancomycin; PHBV; scaffold; drug delivery; Bioglass

Preparation and characterization of vancomycin releasing PHBV coated 45S5 Bioglass®-based glassceramic scaffolds for bone tissue engineering - Li, Wei; Nooeaid, Patcharakamon; Roether, Judith; Schubert, Dirk W.; Boccaccini, Aldo R. (Journal of the European Ceramic Society, 2014)
Porous 45S5 Bioglass®-based glass-ceramic scaffolds with high porosity (96%) and interconnected pore structure (average pore size 300μm) were prepared by foam replication method. In order to improve the mechanical properties and to incorporate a drug release function, the scaffolds were coated with a drug loaded solution, consisting of PHBV and vancomycin. The mechanical properties of the scaffolds were significantly improved by the PHBV coating. The bioactivity of scaffolds upon immersion in SBF was maintained in PHBV coated scaffolds although the formation of hydroxyapatite was slightly retarded by the presence of the coating. The encapsulated drug in coated scaffolds was released in a sustained manner (99.9% in 6 days) as compared to the rapid release (99.5% in 3 days) of drug directly adsorbed on the uncoated scaffolds. The obtained drug loaded and bioactive composite scaffolds represent promising candidates for bone tissue engineering applications. © 2013 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2014.tech.IW.LM.prepar
Keywords: 45S5 Bioglass; Drug release; Mechanical properties; PHBV; Scaffold

Preparation and characterization of vancomycin releasing PHBV coated 45S5 Bioglass®-based glass-ceramic scaffolds for bone tissue engineering - Li, Wei; Nooeaid, Patcharakamon; Roether, Judith; Schubert, Dirk W.; Boccaccini, Aldo R. (Journal of the European Ceramic Society, 2014)
Porous 45S5 Bioglass®-based glass–ceramic scaffolds with high porosity (96%) and interconnected pore structure (average pore size 300 μm) were prepared by foam replication method. In order to improve the mechanical properties and to incorporate a drug release function, the scaffolds were coated with a drug loaded solution, consisting of PHBV and vancomycin. The mechanical properties of the scaffolds were significantly improved by the PHBV coating. The bioactivity of scaffolds upon immersion in SBF was maintained in PHBV coated scaffolds although the formation of hydroxyapatite was slightly retarded by the presence of the coating. The encapsulated drug in coated scaffolds was released in a sustained manner (99.9% in 6 days) as compared to the rapid release (99.5% in 3 days) of drug directly adsorbed on the uncoated scaffolds. The obtained drug loaded and bioactive composite scaffolds represent promising candidates for bone tissue engineering applications.
Keywords: Drug release; 45S5 Bioglass®; PHBV; Mechanical properties; Scaffold

Preparation and soft lithographic printing of nano-sized ITO-dispersions for the manufacture of electrodes for TFTs - Straue, Nadja; Rauscher, Martin; Walther, Sabine; Faber, Hendrik; Roosen, Andreas (Journal of Materials Science, 2009)

Preparation of magnetorheological elastomers and their slip-free characterization by means of parallel-plate rotational rheometry - Walter, Bastian; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (Smart Materials and Structures, 2017)
A systematic study is presented to highlight a methodology of sample preparation and subsequent slip-free characterization of magnetorheological (MR) elastomers in parallel-plate rotational rheometry. Focusing on the magnetic field-dependent nonlinear viscoelastic behavior an array of oscillatory strain sweep measurements is conducted with samples cured within the rheometer. The examined nonlinear material response (i.e. the amplitude dependence of the storage and loss moduli) as a function of the applied magnetic field is found to be qualitatively similar to the amplitude dependence of particle reinforced elastomers (i.e. the Payne effect). Therefore, the experimental data (both moduli) is decomposed similar to that for reinforced elastomers and a phenomenological model is formulated for both the storage and loss modulus to account for the physical mechanisms governing the nonlinear material characteristics. Parameter identification suggests that the material response at low magnetic fields is dominated by the polymeric network whereas the strong magneto-reinforced microstructure governs the linear and nonlinear viscoelastic behavior at high magnetic fields. The overall experimental outcome further suggests that the underlying concept of the phenomenological model for particle reinforced elastomers (i.e. destruction and reformation of the filler network) can be transfered to magnetorheological materials. Consequently, the proposed phenomenological model can be applied to quantify and further analyze the nonlinear response characteristics of MR elastomers (i.e. the amplitude dependence of the storage and loss modulus as a function of the applied magnetic field) that is closely linked to microstructural changes of the magnetizable particle network.
Keywords: Magnetorheological Elastomers (MREs); Field-Responsive Materials; Large Amplitude Oscillatory Shear (LAOS); Magnetorheometry; Magneto-Induced Payne Effect

Probing structure changes in magneto-rheological fluids and elastomers based on an injection moldable liquid silicone - Kaschta, Joachim; Musialek, Matthias; Böse, Holger; Schubert, Dirk W. (8th Annual European Rheology Conference, 2013)

Problematik der biofilm-Besiedlung von Biomaterialien bei der Translation in den klinischen Einsatz am Beispiel von Brustimplantaten - Horch, Raymund E.; Arkudas, Andreas; Schmitz, Marweh; Beier, Justus; Schultz, Gregory; Schubert, Dirk W. (14th BIONANO-MATERIALS, 2013)

Processing and characterisation of alginate-based hydrogels for the application in 3-D Bio Platting - Detsch, Rainer; Zehnder, Tobias; Sarker, Bapi; Kaschta, Joachim; Schubert, Dirk W.; Boccaccini, Aldo R. (14th BIONANO-MATERIALS, 2013)

Production of polyamide 11 microparticles for Additive Manufacturing by liquid-liquid phase separation and precipitation - Dechet, Maximilian; Goblirsch, Anja; Romeis, Stefan; Zhao, Meng; Lanyi, Franz; Kaschta, Joachim; Schubert, Dirk W.; Drummer, Dietmar; Peukert, Wolfgang; Schmidt, Jochen (Chemical Engineering Science, 2019)
Within this contribution liquid-liquid phase separation (LLPS) and precipitation from ethanol was studied as an approach to produce polyamide 11 (PA11) powders for selective laser sintering (SLS). To this end, the cloud point and solution temperature curve of the PAll-ethanol system was determined experimentally via turbidity measurements. The proper range of system composition and temperature for particle formation was deduced. The dependence of particle characteristics on process parameters (polymer concentration, stirring conditions and temperature regime) during LLPS and precipitation was assessed and the products were characterized with respect to their size and morphology. Furthermore, structural, rheological and thermal characteristics were analyzed and correlated with process parameters. Molecular weight distributions were determined. After removal of fines and dry coating with hydrophobic fumed silica, an optimized PA11 powder with mean particle size of 91 mu m showing good flowability for SLS was obtained. SLS processability of this optimized PA11 powder was demonstrated by building multilayered test specimens in a laser sintering machine. With this contribution, we present a comprehensive workflow for the process development, product characterization and product application of a SLS powder manufactured via precipitation. (C) 2018 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-02-21

Progress on Electrospun Composite Fibers Incorporating Bioactive Glass: An Overview - Ghorbani, Farnaz; Reiter, Theresa; Liverani, Liliana; Schubert, Dirk W.; Boccaccini, Aldo R.; Roether, Judith (Advanced Engineering Materials, 2023)
Electrospinning is a promising approach for the development of fibrous tissue engineering (TE) scaffolds suitable for hard and soft tissues. Apart from physicomechanical properties, electrospun fibers are required to incorporate bioactive cues to control cellular functions, including facilitating biomineralization and osteogenic differentiation in case of bone TE, as well as vascularization, to support successful tissue regeneration. In recent years, bioactive glass (BG) addition to electrospun biopolymer fibers has shown promising results in enhancing the properties of fibers, including the improvement of biological performance. In this article, a comprehensive overview of BG-containing electrospun polymer composite fibers is presented, identifying the parameters that affect the mechanical properties as well as the biological response in vivo and in vitro. Subsequently, the effects of BG addition on the properties of the scaffolds are discussed. Recent developments in the fields of bone regeneration, wound healing, and drug delivery using BG-containing electrospun fibrous scaffolds are described in detail. Essential aspects related to BG-polymer composite fibers for translational research in TE are highlighted for future research in this field.
CRIS-Team WoS Importer:2023-02-03

Properties of sintered glass-ceramics prepared from plasma vitrified air pollution control residues - Roether, Judith; Daniel, D. J.; Rani, D. Amutha; Deegan, D. E.; Cheeseman, Christopher R.; Boccaccini, Aldo R. (Journal of Hazardous Materials, 2010)
Air pollution control (APC) residues, obtained from a major UK energy from waste (EfW) plant, processing municipal solid waste, have been blended with silica and alumina and melted using DC plasma arc technology. The glass produced was crushed, milled, uni-axially pressed and sintered at temperatures between 750 and 1150 °C, and the glass-ceramics formed were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Mechanical properties assessed included Vickers's hardness, flexural strength, Young's modulus and thermal shock resistance. The optimum sintering temperature was found to be 950 °C. This produced a glass-ceramic with high density (∼2.58 g/cm3), minimum water absorption (∼2%) and relatively high mechanical strength (∼81 ± 4 MPa). Thermal shock testing showed that 950 °C sintered samples could withstand a 700 °C quench in water without micro-cracking. The research demonstrates that glass-ceramics can be readily formed from DC plasma treated APC residues and that these have comparable properties to marble and porcelain. This novel approach represents a technically and commercially viable treatment option for APC residues that allow the beneficial reuse of this problematic waste. © 2009 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.proper
Keywords: Air pollution control residues; Energy from waste; Glass-ceramics; Hazardous waste treatment; Plasma vitrification

Quality monitoring of PE-X semi-finished products - Heiduk, I.; Falk, M.; Schubert, Dirk W.; Kaschta, Joachim (Kunststoffe International, 2015)

Quality Monitoring of PE-X Semi-Finished Products - Heiduk, Ines; Falk, Martin; Schubert, Dirk W.; Kaschta, Joachim (Kunststoffe International, 2015)
In industrial production monitoring, fast, reliable results are required to evaluate product quality. Suitable test methods must be available for this purpose. The time-consuming method previously used to determine the degree of crosslinking of PE-X pipes can now be replaced by rapid rheological measurements

Quantitative Determination and Comparison of the Surface Binding of Phosphonic Acid, Carboxylic Acid, and Catechol Ligands on TiO2 Nanoparticles - Zeininger, Lukas; Portilla Berlanga, Luis; Halik, Marcus; Hirsch, Andreas (Chemistry - A European Journal, 2016)
The adsorption, desorption, co-adsorption, and exchange behavior of phosphonic acid, carboxylic acid, and catechol derivatives on the surface of titanium oxide (anatase) nanoparticles are investigated. Thermogravimetric analysis provides a facile and fast-track quantitative determination of the wet-chemical monolayer adsorption constants and grafting densities of ten adsorbates, all under neutral pH conditions. This characterization protocol allows straightforward quantification of the relevant thermodynamic data of ligand adsorption and a comparison of ligand adsorption strengths. The reported procedure is proposed as a universal tool and it should be applicable to many other colloidal metal oxide materials. Moreover, the determined values for the adsorption constants and the monolayer grafting densities provide a toolbox for the assessment of the adsorbates' behavior in desorption, exchange, and co-adsorption equilibria. This versatile evaluation procedure will help to identify optimal monolayer-surface combinations and to evaluate critical parameters, such as monolayer robustness, ligand exchange rates, or targeted mixed assembly of functionalities.

Rapid Enrichment of Submicron Particles within a Spinning Droplet Driven by a Unidirectional Acoustic Transducer - Peng, Tao; Fan, Cui; Zhou, Mingyong; Jiang, Fengze; Drummer, Dietmar; Jiang, Bingyan (Analytical Chemistry, 2021)
Efficient and rapid particle enrichment at the submicron scale is essential for research in biomedicine and biochemistry. Here, we demonstrate an acoustofluidic method for submicron particle enrichment within a spinning droplet driven by a unidirectional transducer. The unidirectional transducer generates intense sound energy with relatively low attenuation. Droplets placed offset in the wave propagation path on a polydimethylsiloxane film undergo strong pressure gradients, deforming into an ellipsoid shape and spinning at high speed. Benefitting from the drag force induced by the droplet spin and acoustic streaming and the radial force induced by the droplet compression and expansion, the submicron particles in the liquid droplet quickly enrich toward the central area following a spiral trajectory. Through numerical calculations and experimental processes, we have demonstrated the possible mechanism responsible for particle enrichment. The application of biological sample processing has also been exploited. This study anticipates that the strategy based on the spinning droplet and particle enrichment method will be highly desirable for many applications.
CRIS-Team Scopus Importer:2021-10-22

Rare-earth ion doped up-conversion materials for photovoltaic applications - Wang, Hao; Batentschuk, Miroslaw; Osvet, Andres; Pinna, Luigi; Brabec, Christoph (Advanced Materials, 2011)
With the aim of utilizing the infrared region of solar radiation to improve solar cell performance, significant progress, including theoretical analysis and experimental achievement, has been made in the field of up-conversion for photovoltaic applications. This Research News article reviews recent progress in the development of rear-earth (RE) ion doped up-conversion materials for solar cell applications. In addition, new trends for RE-ion-doped phosphors are briefly discussed, among them trivalent RE-ion-doped up-conversion materials for organic solar cell applications. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: nonlinear optical materials; phosphors; photovoltaic devices; rare earth ions

Realization of a 5-stage Divider Circuitry in p-type Polymer Transistor Technology - Lackner, C.; Klauk, Hagen; Gut, W.; Halik, Marcus; Spilka, R.; Zschieschang, Ute; Tanda, A.; Eder, F.; Rohde, D.; Ostermann, T.; Schmid, Günter (Technical Digest - International Electron Devices Meeting, 2005)

Real-time monitoring of magnetic nanoparticle-assisted nanoplastic agglomeration and separation from water - Groppe, Philipp; Wintzheimer, Susanne; Eigen, Andreas; Gaß, Henrik; Halik, Marcus; Mandel, Karl (Environmental Science: Nano, 2022)
Nanoplastics are one of the main modern concerns in water pollution and are suspected to have severe negative impacts on their surrounding ecosystems. The use of superparamagnetic iron oxide nanoparticles (SPIONs) as remediation agents is a suggested approach to address this issue. Their nanoparticulate and switchable magnetic properties enable a homogeneous distribution while magnetic collectability is feasible. However, uncertainties regarding an incomplete collection from treated water remain, which would pose another environmental burden. Herein, the nanoplastic remediation approach via SPIONs is investigated by utilizing magnetic particle spectroscopy (MPS) as an advanced qualitative characterization method. This work focuses on the influence of concentration ratio and colloidal stability of nanoparticles on the overall remediation process. Herein, MPS enables the in situ real-time monitoring of the agglomeration events and illustrates that high colloidal stability of the SPIONs prevents the formation of large, destabilized agglomerates and thus their successful magnetic removal. Furthermore, it is shown that at high SPION concentrations, nanoparticle residuals are left in dispersion after collection of formed agglomerates, while at low concentrations nanoplastic leftovers are found. Colloidal stability and concentration-dependence of the agglomeration process are recognized as key aspects to focus on when developing future particle-based materials for nanoplastic remediation from water.
CRIS-Team WoS Importer:2022-06-17

Recycling and Reprocessing of Thermoplastic Polyurethane Materials towards Nonwoven Processing - Wölfel, Bastian; Seefried, Andreas; Allen, Vincent; Kaschta, Joachim; Holmes, Christopher; Schubert, Dirk W. (Polymers, 2020)
Thermoplastic Polyurethane (TPU) is a unique tailorable material due to the interactions of hard and soft segments within the block-copolymer chain. Therefore, various products can be created out of this material. A general trend towards a circular economy with regards to sustainability in combination with TPU being comparably expensive is of high interest to recycle production as well as post-consumer wastes. A systematic study investigating the property changes of TPU is provided, focusing on two major aspects. The first aspect focuses on characterizing the change of basic raw material properties through recycling. Gel permeation chromatography (GPC) and processing load during extrusion indicate a decrease in molar mass and consequently viscosity with an increasing number of recycling cycles. This leads to a change in morphology at lower molar mass, characterized by differential scanning calorimetry (DSC) and visualized by atomic force microscope (AFM). The change in molar mass and morphology with increasing number of recycling cycles has an impact on the material performance under tensile stress. The second aspect describes processing of the recycled TPU to nonwoven fabrics utilizing melt blowing, which are evaluated with respect to relevant mechanical properties and related to molecular characteristics. The molar mass turns out to be the governing factor regarding mechanical performance and processing conditions for melt blown product
Keywords: recycling; reprocessing; TPU; thermoplastic elastomers; TPE; thermoplastic; polyurethane; elastomers; nonwoven; processing; melt blown; molar mass; mechanical properties; methylendiphenylisocyanate; MDI; polytetramethylene glycol; PTMG; morphology; structure; phase separation; sustainability; circular economy

Recycling and reprocessing of TPU materials in the context of Nonwoven processing - Wölfel, Bastian (POLYCHAR 27 - 27th Annual World Forum on Advanced Materials, 2019)
Thermoplastic Polyurethane (TPU) is a unique tailorable material due to the interactions of hard and soft segments within the block-copolymer chain. Therefore, it is of interest to create various products out of this material. A systematic study investigating the property changes of reprocessed TPU from a raw material perspective. The reprocessing procedure is outlined in Figure 1. Gel permeation chromatography (GPC) utilizing Dimethylacetamid (DMAc), processing load during repeated extrusion and rotating plate rheology indicate a decrease in viscosity and molar mass with increasing number of cycles. Frequency sweeps suit to an apparent change in morphology at lower molar mass. Two proposed morphologies, which contribute to the change in rheology data, are given. Changes in morphology detected in molten state can also be retrieved via differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The change in molar mass and morphology with an increasing number of cycles has an impact on material performance regarding self-adhesion and under tensile stress. Subsequent processing of the recycled TPUs to non-woven fabrics using melt blowing is also evaluated and related to molecular characteristics. The molar mass is also the governing factor regarding mechanical performance and processing conditions for melt blowing. This becomes apparent through the examination of the obtained non-wovens via tensile and tear strength, as well as DSC, TGA and GP

Regenerating bone with bioactive glass scaffolds: A review of in vivo studies in bone defect models - El-Rashidy, Aiah A.; Roether, Judith; Harhaus, Leila; Kneser, Ulrich; Boccaccini, Aldo R. (Acta Biomaterialia, 2017)
Keywords: 3D scaffolds; Animal model; Bioactive glass; Bone defects; Bone regeneration; In vivo

Region-selective Deposition of Core–Shell Nanoparticles for 3 D Hierarchical Assemblies by the Huisgen 1,3-Dipolar Cycloaddition - Etschel, Sebastian; Portilla Berlanga, Luis; Kirschner, Johannes; Drost, Martin; Marbach, Hubertus; Tykwinski, Rik; Halik, Marcus (Angewandte Chemie International Edition, 2015)
A method for the region-selective deposition of nanoparticles (NPs) by the Huisgen 1,3-dipolar cycloaddition is presented. The approach enables defined stacking of various oxide NPs in any order with control over layer thickness. Thereby the reaction is performed between a substrate, functionalized with a self-assembled monolayer of an azide-bearing phosphonic acid (PA) and aluminum oxide (AlOx) NPs functionalized with an alkyne bearing PA. The layer of alkyne functionalized AlOx NPs is then used as substrate for the deposition of azide-functionalized indium tin oxide (ITO) NPs to provide a binary stack. This progression is then conducted with alkyne-functionalized CeO2 NPs, yielding a ternary stack of NPs with three different NP cores. The stacks are characterized by AFM and SEM, defining the region-selectivity of the deposition technique. Finally, these assemblies have been tested in devices as a dielectric to form a capacitor resulting in a dramatic increase in the measured capacitance.

Region-Selective Self-Assembly of Functionalized Carbon Allotropes from Solution - Wang, Zhenxing; Mohammadzadeh, Saeideh; Schmaltz, Thomas; Kirschner, Johannes; Khassanov, Artöm; Eigler, Siegfried; Mundloch, Udo; Backes, Claudia; Steinrück, Hans-Peter; Magerl, Andreas; Hauke, Frank; Hirsch, Andreas; et al. (Acs Nano, 2013)
Approaches for the selective self-assembly of functionalized carbon allotropes from solution are developed and validated for 0D-fullerenes, 1D-carbon nanotubes and 2D-graphene. By choosing the right molecular interaction of self-assembled monolayers (serving the surface) with the functionalization features of carbon materials, which provide the solubility but also serve the driving force for assembly, we demonstrate a region-selective and self-terminating assembly of the materials. Active layers of the carbon allotropes can be selectively deposited in the channel region of thin-film transistor (TFT) devices by this approach. As an example for a 0D system, molecules of C functionalized octadecylphosphonic acids are used to realize self-assembled monolayer field-effect transistors (SAMFETs) based on a selective molecular exchange reaction of stearic acid in the channel region. For noncovalently functionalized single-walled carbon nanotubes (SWCNTs) and graphene oxide (GO) flakes, the electrostatic Coulomb interactions between the functional groups of the carbon allotropes and the charged head groups of a SAM dielectric layer are utilized to implement the selective deposition. © 2013 American Chemical Societ

Relationship Between Molecular Structure and Electrical Performance of Oligothiophene Organic Thin Film Transistors - Halik, Marcus; Klauk, Hagen; Zschieschang, Ute; Schmid, Günter; Ponomarenko, S.; Kirchmeyer, S.; Weber, Werner (Advanced Materials, 2003)

Reliable determination of the cross-link density in crosslinked polyethylenes by a new rheologicial measurement - Kaschta, Joachim; Falk, M.; Heiduk, I.; Walter, Lisa; Schubert, Dirk W. (Abstracts, 2016)

Remediation of charged organic pollutants—binding motifs for highly efficient water cleaning with nanoparticles - Eigen, Andreas; Schmidt, Victoria; Sarcletti, Marco; Freygang, Selina; Hartmann-Bausewein, Andreas; Schneider, Vanessa; Zehetmeier, Anna; Mauritz, Vincent; Müller, Lukas; Gaß, Henrik; Rockmann, Linda; Crisp, Ryan; et al. (Nano Select, 2023)
Many charged organic molecules behave as persistent and hazardous pollutants with harmful effects on human health and ecosystems. They are widely distributed related to their charged molecular structure that provides water solubility. In order to track the fate and behavior of such pollutants, charged dyes with specific absorption in the visible spectra serve as convenient model compounds. We provide a platform of smart adsorbers that efficiently remediate positively and negatively charged dyes (crystal violet and Amaranth) from water. Metal oxide nanoparticles serve as a core with an intrinsically large surface area. The surface potential was tuned towards positive or negative by decorating the cores with self-assembled monolayers of dedicated long-chained phosphonic acid derivatives. Selective remediation of the dyes was obtained with corresponding oppositely charged core-shell nanoparticles. Mixed dye solution can be cleaned by a cascade approach or by applying both particle systems simultaneously. The removal efficiency was determined as a function of particle concentration via UV-spectroscopy. The results of remediation experiments at different pH values and using superparamagnetic iron oxide nanoparticle cores lead to a simple process with recycling capabilit

Research on melt spun PMMA composites with aligned carbon fibers - Qu, Muchao; Schubert, Dirk W. (Proceedings of the 17th European Conference on Composite Materials ECCM17 - 17th European Conference on Composite Materials, 26-30th June 2016, Munich, Germany, 2016)
Keywords: Carbon fibers; High concentration; Conductive composites; Melt spun; Highly orientation

Resilience of silicone breast implants – new insights by mapping the mechanical properties of implant - Daenicke, Jonas; Schubert, Dirk W.; Horch, Raymund E.; Walter, Bastian (Polychar 22nd, 2014)

Resilience of Silicone Breast Implants – New Insights by Mapping the Mechanical Properties of Implant Shells - Schubert, Dirk W.; Horch, Raymund E.; Daenicke, Jonas; Walter, Bastian (14th BIO NANO-MATERIALS, 2013)

Resistance of silicone breast explants under cyclic compressive load as a function of implantation time and explant mass - von Hanstein, Harald; Horch, Raymund E.; Schubert, Dirk W. (Polymer Testing, 2020)
15 micro-textured silicone breast explants are investigated in cyclic compression tests regarding their mechanical behavior. Initially a maximum load of 2.5 kN was applied to the explants in a repetitive way until failure happened. Finally the results are shown on the one hand as a correlation between the number of endured loading cycles and the implantation time. On the other hand the correlation to the explants’ mass was analyzed and described by using a power la
Keywords: Silicone breast explant; cyclic load; implantation time; explant mass; compresssion test; mechanical behavior

Resolution of Virtual Depth Sectioning from Four-Dimensional Scanning Transmission Electron Microscopy - Terzoudis-Lumsden, E. W.C.; Petersen, T. C.; Brown, H. G.; Pelz, Philipp; Ophus, C.; Findlay, S. D. (Microscopy and Microanalysis, 2023)
One approach to three-dimensional structure determination using the wealth of scattering data in four-dimensional (4D) scanning transmission electron microscopy (STEM) is the parallax method proposed by Ophus et al. (2019. Advanced phase reconstruction methods enabled by 4D scanning transmission electron microscopy, Microsc Microanal25, 10-11), which determines the scattering matrix and uses it to synthesize a virtual depth-sectioning reconstruction of the sample structure. Drawing on an equivalence with a hypothetical confocal imaging mode, we derive contrast transfer and point spread functions for this parallax method applied to weakly scattering objects, showing them identical to earlier depth-sectioning STEM modes when only bright field signal is used, but that improved depth resolution is possible if dark field signal can be used. Through a simulation-based study of doped Si, we show that this depth resolution is preserved for thicker samples, explore the impact of shot noise on the parallax reconstructions, discuss challenges to making use of dark field signal, and identify cases where the interpretation of the parallax reconstruction breaks down.
CRIS-Team Scopus Importer:2023-08-04
Keywords: 3D imaging; 4D-STEM; depth sectioning; parallax; scattering matrix

Resonance phenomena in oscillatory shear rheometry: Influence of material parameters - Redel, Michael; Walter, Bastian; Kaschta, Joachim; Steinmann, Paul; Schubert, Dirk W. (Nordic Polymer Days 2018, 2018)
Rheological measurements are an established method for the characterisation of dynamic mechanical polymer properties. In current literature, possible restrictions to thesemeasurements by the phenomenon of resonance were evaluated by Stettin [1]. However, this paper is quiet about the influence of material parameters like stiffness or damping on the resonance phenomenon Therefore, an unfilled silicone elastomer, free of material particle interactions, is used. The cylindrical specimen are cured in a rheometer binding them firmly to the rotor. This has proven to prevent occurrence of for example wall slip [2]. The experiments conducted are frequency sweeps by means of a parallel-plate rheometer with a smooth geometry surface. Consequently, the influence of the setup, which was detected by Stettin [1], can be neglected. Resulting resonance frequencies are analysed concerning the material's damping and stiffness. Change in these parameters is realised by variation of mixture as well as addition of an additive. The resulting resonance frequencies show an explicit dependency of complex shear modulus |G*| as a measure of the stiffness. The resulting dependence in double logarithmic plot is compared with resonance frequency calculations based on oscillatory theories. Contribution of varying damping, realised by changing loss factor tan(δ), is detectable as an additional shift in resonance frequency and also discussed. Intriguingly, the wavedata of the stress response after resonance, obtained via fast Fourier transformation, differs from the expected sinusoidal signal. The change in wavedata and aberration from the sinusoidal excitation is explained by the phenomenon of vibration isolation. Furthermore, it is correlated with the material’s parameters reasoning the different experimental outcomes caused by the change in composition. A guideline to avoid the influence of resonance on oscillatory measurements is lastly presented

Ressourcenschonende Verpackungen aus PET durch reaktive Extrusion mit niedermolekularen Substanzen - Härth, Michael; Kaschta, Joachim; Schubert, Dirk W. (Würzburger Tage 2014, 2014)

Revealing correlations of bonding area and pilling behaviour of polypropylene nonwovens using a novel objective test method, - Leucker, Karsten; Schubert, Dirk W. (Polychar 26 World Forum on Advanced Materials, 2018)

Revealing critical model parameters for predicting the bioprintability of hydrogel systems - Schrüfer, Stefan; Schubert, Dirk W. (16th Biennial - Bayreuther Polymer Symposium, 2019)

Revealing electrical and mechanical performances of highly oriented electrospun conductive nanofibers of biopolymers with tunable diameter - Munawar, Muhammad; Schubert, Dirk W. (International Journal of Molecular Sciences, 2021)
The present study outlines a reliable approach to determining the electrical conductivity and elasticity of highly oriented electrospun conductive nanofibers of biopolymers. The highly oriented conductive fibers are fabricated by blending a high molar mass polyethylene oxide (PEO), polycaprolactone (PCL), and polylactic acid (PLA) with polyaniline (PANi) filler. The filler‐matrix interaction and molar mass (M) of host polymer are among governing factors for variable fiber di-ameter. The conductivity as a function of filler fraction (φ) is shown and described using a McLach-lan equation to reveal the electrical percolation thresholds (φc) of the nanofibers. The molar mass of biopolymer, storage time, and annealing temperature are significant factors for φc. The Young’s modulus (E) of conductive fibers is dependent on filler fraction, molar mass, and post‐annealing process. The combination of high orientation, tunable diameter, tunable conductivity, tunable elas-ticity, and biodegradability makes the presented nanofibers superior to the fibers described in pre-vious literature and highly desirable for various biomedical and technical applications.
Created from Fastlane, Scopus look-up
Keywords: Biomed-ical; Electrical percolation threshold; Fiber diameter; Orientation; Young’s modulus

Revealing key parameters to minimize the diameter of polypropylene fibers produced in the melt electrospinning process - Daenicke, Jonas; Lämmlein, Michael; Steinhübl, Felix; Schubert, Dirk W. (e-polymers, 2019)
This study deals with the subject of optimizing the melt electrospinning process of polypropylene with the aim of producing nanoscale fibers. A feasibility study with two polypropylene types and different additives to adapt the material composition is performed. The polypropylene types are of different molar masses to adapt the viscosity to the process. The used additives, sodium stearate and Irgastat® P 16, have a positive effect on the electrical conductivity of the polymer melt. In addition, process parameter optimization is done by varying the climate chamber temperature, using different collector voltages and varying the nozzle-collector distance. A strong influence of the climate chamber temperature has been proven and leads to a desired temperature of 100°C. The fiber diameter is dependent on process parameters, material melt viscosity and electrical conductivity. With optimized process and material parameters, the fiber diameter could be minimized to a median value of 210 n
Keywords: melt electrospinning; polypropylene; sodium stearate; nanofibers; process optimizing

Revealing Novel Power Laws and Quantization in Electrospinning Considering Jet Splitting—Toward Predicting Fiber Diameter and Its Distribution Part II Experimental - Schubert, Dirk W.; Allen, Vincent; Dippel, Ursula (Advanced Engineering Materials, 2021)
Blends of poly‐ϵ‐caprolactone (PCL) with two different molar masses are deliberately varied to change viscosity independent of polymer concentration enabling to separate viscosity and a direct concentration dependence of the fiber diameter in the electrospinning process. Multiple distributions as a result of jet splitting are determined and analyzed. The existence of essentially two modes in fiber diameter frequency distribution, the base mode and the split mode, is revealed, whereas the scaling laws for each mode can be validated according to the latest theory. Finally, the theoretical predicted upper limit 22" role="presentation">2√2 of the ratio of standard deviation of fiber diameter and average fiber diameter is validated.
Keywords: distribution; electrospinning; fiber diameter; jet splitting; power laws

Revealing Novel Power Laws and Quantization in Electrospinning considering Jet Splitting - Towards Predicting Fiber Diameter and its distribution - Schubert, Dirk W. (Macromolecular Theory and Simulations, 2019)
A novel physical model is proposed relating fiber diameter and its distribution to various process parameters. Power laws are derived taking into consideration, applied voltage, viscosity, charge density, surface tension, and jet splitting. It is recommended how researchers should analyze their data to separate various effects. In particular, it is possible to predict not only the fiber diameter but also its distribution. A review of available theories or models for electrospinning is given, from which the weaknesses become evident. As a consequence a novel theory is given to predict the fiber diameter resulting from electrospinning and its distribution. In particular, scaling laws are predicted based on fundamental physics and revealing some peaks in the fiber diameter distribution are not “experimental failure”, but are physical consequences of jet splitting, appearing as an indication of quantization of the fiber diameter. The key approach is the separation of electrospinning into a flow-dominated and a drying-dominated regime, where jet-splitting occurs at the transition from the one to the other regime. A clear recommendation is given for analyzing experimental data to challenge the predicted scaling laws. The work opens a door towards the design of the electrospinning fiber diameter and its distribution due to the separation of effects considering charge density, adjustable by salts, and surface tension, adjustable by surfactants, which are linked by viscosity.
CRIS-Team Scopus Importer:2019-05-02
Keywords: distribution; electrospinning; fiber diameter; jet splitting; power laws

Revealing novel power laws and qunatization in electrospinning considering jet splitting - towards predicting fiber diameter and its distribution - Schubert, Dirk W. (16th Biennial - Bayreuther Polymer Symposium, 2019)
Keywords: electrospinning

Revealing the effects of aerosol deposition on the substrate-film interface using NaCl coating - Khansur, Neamul H.; Eckstein, Udo; Li, Yizhe; Hall, David A.; Kaschta, Joachim; Webber, Kyle Grant (Journal of the American Ceramic Society, 2019)
Aerosol deposition is a feasible method of fabricating dense ceramic films at room temperature by the impact consolidation of submicron‐sized particles on ceramic, metal, glass, and polymer substrates at a rapid rate. Despite the potential usefulness of the aerosol deposition process, there are issues, such as deposition mechanisms and structure of the film‐substrate interface, that are not well understood. We have used complementary structural and microstructural analysis to capture the state of the substrate surface after the aerosol deposition process. The results reveal that modification of the substrate surface by the ejected submicron‐sized particles is essential for the formation of anchoring layer, thereby, a change in internal residual stress state and surface free energy of the substrate is required to deposit film using AD process. Our analysis also suggests that the adhesion between the metal substrate and ceramic particles is possibly contributed by both physical bonding and mechanical interlocki
Keywords: stress; thick films; X-ray methods

Revealing the effects of aerosol deposition on the substrate‐film interface using NaCl coating - Khansur, Neamul Hayet; Eckstein, Udo; Li, Yizhe; Hall, David A.; Kaschta, Joachim; Webber, Kyle Grant (Journal of the American Ceramic Society, 2019)
Aerosol deposition is a feasible method of fabricating dense ceramic films at room temperature by the impact consolidation of submicron‐sized particles on ceramic, metal, glass, and polymer substrates at a rapid rate. Despite the potential usefulness of the aerosol deposition process, there are issues, such as deposition mechanisms and structure of the film‐substrate interface, that are not well understood. We have used complementary structural and microstructural analysis to capture the state of the substrate surface after the aerosol deposition process. The results reveal that modification of the substrate surface by the ejected submicron‐sized particles is essential for the formation of anchoring layer, thereby, a change in internal residual stress state and surface free energy of the substrate is required to deposit film using AD process. Our analysis also suggests that the adhesion between the metal substrate and ceramic particles is possibly contributed by both physical bonding and mechanical interlocking.<br
Keywords: stress; thick films; X‐ray methods

Reversal phenomena of molten immiscible polymer blends during creep-recovery in shear - Pan, Yamin; Liu, Xian Hu; Kaschta, Joachim; Liu, Chuntai; Schubert, Dirk W. (Journal of Rheology, 2017)
In this work, the creep- recovery behavior of immiscible poly (styrene)/poly (methyl methacrylate) blends and their pure components in the molten state were systematically investigated. A stationary plateau in the recoverable compliance of pure components is observed. Unexpectedly, for immiscible polymer blends, the recoverable compliances show different phenomena. For blends with a fine co-continuous morphology, the recoverable compliances exhibit a one-reversal phenomenon, whereas a two-reversal phenomenon is found in the blends with a sea-island morphology. Moreover, these reversal behaviors become less pronounced with decreasing temperature, increasing creep stress, increasing annealing time, or incorporation of nanoparticles. Three competitive effects, i.e., the recovery of oriented polymer matrix, the interfacial tension which drives the deformed droplets to their equilibrium shape, and the phase coarsening process, are used here to explain the different behaviors. (C) 2017 The Society of Rheology.

Review on Electrospun Conductive Polymer Composites Strain Sensors - Wang, Xin; Gao, Qingsen; Schubert, Dirk W.; Liu, Xianhu (Advanced Materials Technologies, 2023)
The rapid development of wearable smart devices with the ability to detect physiological activity has contributed to a huge demand for smart strain sensors. However, conventional strain sensors have significant limitations about stretchability. Electrospun strain sensors show great potential for application in the field of wearable strain sensors due to their light weight, good elasticity, stretchability, and ease of processing. In this review, the effects of materials, processing methods, and microstructures of electrospun strain sensors from conductive polymer composites on wearable strain sensors are summarized and discussed. The purpose of this review is to critically review the progress of electrospinning process-based strain sensors and to predict promising future directions.
CRIS-Team Scopus Importer:2023-04-21
Keywords: electrospun technology; health monitoring; intelligent electronic devices; wearable strain sensors

Revitalized β‐form crystal during the remelting and recrystallization processes in isotactic polypropylene/glass fiber composites - Qin, Yijing; Zhang, Liying; Guo, Xiaobei; Dai, Kun; Schubert, Dirk W.; Zheng, Guoqiang; Liu, Chuntai (Polymer Crystallization, 2018)

Rheological and Biological Impact of Printable PCL-Fibers as Reinforcing Fillers in Cell-Laden Spider-Silk Bio-Inks - Schaefer, Natascha; Andrade Mier, Mateo S.; Sonnleitner, David; Murenu, Nicoletta; Ng, Xuen Jen; Lamberger, Zan; Büchner, Margitta; Trossmann, Vanessa T.; Schubert, Dirk W.; Scheibel, Thomas; Lang, Gregor (Small Methods, 2023)
The development of bio-inks capable of being 3D-printed into cell-containing bio-fabricates with sufficient shape fidelity is highly demanding. Structural integrity and favorable mechanical properties can be achieved by applying high polymer concentrations in hydrogels. Unfortunately, this often comes at the expense of cell performance since cells may become entrapped in the dense matrix. This drawback can be addressed by incorporating fibers as reinforcing fillers that strengthen the overall bio-ink structure and provide a second hierarchical micro-structure to which cells can adhere and align, resulting in enhanced cell activity. In this work, the potential impact of collagen-coated short polycaprolactone-fibers on cells after being printed in a hydrogel is systematically studied. The matrix is composed of eADF4(C16), a recombinant spider silk protein that is cytocompatible but non-adhesive for cells. Consequently, the impact of fibers could be exclusively examined, excluding secondary effects induced by the matrix. Applying this model system, a significant impact of such fillers on rheology and cell behavior is observed. Strikingly, it could be shown that fibers reduce cell viability upon printing but subsequently promote cell performance in the printed construct, emphasizing the need to distinguish between in-print and post-print impact of fillers in bio-inks.
CRIS-Team Scopus Importer:2023-07-07
Keywords: bio-inks; bio-printing; biofabrication; composites; fibers; silk

Rheological and electrical behavior of poly(methyl methacrylate)/carbon black composites as investigated by creep recovery in shear - Liu, Xian Hu; Pan, Yamin; Zheng, Guoqiang; Schubert, Dirk W. (Composites Science and Technology, 2016)
The rheological and electrical behavior of poly(methyl methacrylate) (PMMA)/carbon black (CB) composites has been studied as a function of CB concentration by simultaneous electrical and rheological measurements during creep and creep-recovery experiments in the linear and nonlinear regimes. The creep compliance and recoverable compliance were strongly influenced by the CB concentration in the linear regime, especially above the percolation threshold. The creep compliance remained almost unchanged in the linear and nonlinear regimes, but the recoverable compliance was strongly influenced by the creep stress. The electrical conductivity increased under low creep deformation, but under high creep deformation, the electrical conductivity decreased rapidly at the beginning of the creep experiment. After a sufficiently long creep time under shear, the electrical conductivity again increased. The results provide a deeper insight into structural changes in conductive polymer composites induced by shear deformation.
Keywords: Deformation; Electrical properties; Polymer-matrix composites; Rheology

Rheological and Electrical Behavior of Poly(methylmethacrylate)/Carbon Black Composites As Investigated by Creep Recovery in Shear - Liu, Xian Hu; Pan, Yamin; Zheng, Guoqiang; Schubert, Dirk W. (Book of Abstracts, 2016)

Rheological and electrical properties of polymethylmethacrylate filled with graphite - Liu, Xian Hu; Krückel, Johannes; Schubert, Dirk W. (10th Annual European Rheology Conference, 2015)

Rheological and thermo-mechanical properties of Polylactide/Poly(methylmethacrylacte) blends - Hao, Xiaoqiong; Kaschta, Joachim; Schubert, Dirk W. (10th Annual European Rheology Conference, 2015)

Rheological examination and 3D bioprinting of pre-gelled alginate hydrogels - Hazur, Jonas; Kaschta, Joachim; Bednarzig, Vera; Boccaccini, Aldo R.; Schubert, Dirk W.; Detsch, Rainer (Nordic Polymer Days 2018, 2018)
lginate hydrogels are from special interest in wound healing, drug delivery and tissue engineering applications, due to their biocompatibility and similarity to the extracellular matrices in tissues [1]. In this project, bioprinting of pre-crosslinked medical grade alginate gels via an internal gelation method using D-(+)-Gluconic acid-lactone in combination with CaCO3 was implemented and the rheological characteristics of the gels were examined. By parameter optimization, it was possible to print 3D porous structures with a height of 5 mm and a pore size of 1.1 mm with those gels. Surprisingly, the stirring process during cross-linking turned out to play a major role for the absolute value of complex viscosity (|η*|), as well as for the homogeneity of the gels. A significant increase of |η*| as well as of the storage modulus was obtained, when the gels were not stirred, leading to gels without viscous flow and therefore to less defined printed structures. Apart from that, the temperature during pre-crosslinking plays an important role on the homogeneity. At lower temperatures than room temperature, the gels showed a more uniform gelation process, compared to those at 20 °C. Furthermore, the concentration and temperature dependence of the alginate solutions were rheologically characterized. The shear dependent viscosities were superposable for both temperature and concentration and appropriate fitting functions in the investigated regions were derive

Rheological monitoring of the cross-link density for polyethylene materials cross-linked using different cross-linking technologies - Kaschta, Joachim; Heiduk, I.; Falk, M.; Schubert, Dirk W. (Book of Abstracts, 2016)

Rheological properties of electron beam-irradiated polypropylenes with different molar masses - Auhl, Dietmar; Stadler, Florian; Münstedt, Helmut (Rheologica Acta, 2012)
Electron beam-irradiated polypropylene undergoes chain scission initiated by the loss of a proton. The resulting macroradicals can lead to branched molecules. However, the understanding of the influence of irradiation on the branching of polypropylene is still scarce. Therefore, this paper investigates structure-property relationships in such irradiated polymers. In general, irradiation yields long-chain branches, which develop from a star-like into a tree-like branching architecture with increasing dose. These conclusions can be drawn from the relation between the zero shear-rate viscosity η 0 and the weight average molar mass M w as well as from the elongational behavior. © 2012 Springer-Verlag.
Created from Fastlane, Scopus look-up
Keywords: Electron beam irradiation; Elongational rheology; Long-chain branching; Polypropylene; Zero shear-rate viscosity

Rheological properties of LDPE/LLDPE-blends in the molten state in shear and elongation - Kaschta, Joachim; Dörgens, Anna; Schubert, Dirk W. (10th Annual European Rheology Conference, 2015)

Rheological study of the reaction kinetics in a poly(ethylene terephthalate) melt - Härth, Michael; Kaschta, Joachim; Schubert, Dirk W. (Polymer Degradation and Stability, 2015)
Time dependent measurements of the zero shear viscosity are applied to study the thermal stability of a commercial poly(ethylene terephthalate). Firstly, the factors influencing the experimental results, like moisture content and type of atmosphere (air or nitrogen) are briefly reviewed. Secondly, the time dependent viscosity is studied on dry samples in nitrogen atmosphere at various temperatures, as these conditions are commonly used for the rheological material characterization. All viscosity curves show a characteristic maximum which strongly depends on time and temperature. This maximum reflects the changes in molar mass resulting from the various chemical reactions. A simplified kinetic model, based on one build-up and one degradation reaction, is derived and used to analyze the experimental data. This model enables to determine the activation energy of flow (65 kJ mol(-1)) and the activation energy resulting from the temperature dependence of the molar mass maximum (120 kJ mol(-1)). Kinetic constants and corresponding activation energies of the chemical reactions are determined as well. The comparison with literature shows that the activation energies are similar to those found for the polymerization process. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Poly(ethylene terephthalate); Rheology; Reaction kinetics; Thermal degradation; Activation energy

Rheological Study on the Molar Mass Build-Up and Degradation in a PET Melt - Härth, Michael; Schubert, Dirk W. (Polychar 21st, 2013)

Rheologisches Verhalten magnetorheologischer Fluide und Elastomere auf Basis von Flüssigsilikon - Kaschta, Joachim; Walter, Bastian; Musialek, Matthias; Schubert, Dirk W. (Geesthachter Polymertage: Praktische Rheologie von Polymeren – Grundlagen und Anwendungen, 2014)

Rheology and conductivity of carbon fibre composites with defined fibre lengths - Stary, Zdenek; Krückel, Johannes; Weck, Constantin; Schubert, Dirk W. (Composites Science and Technology, 2013)
Rheological and electrical properties of polymer composites containing conductive fillers are influenced not only by the total content of the filler but also by the shape and dimensions of filler particles markedly. However, separate treatment of these two effects is often not feasible in composites prepared by melt mixing as the filler concentration affects the flow behaviour of the melt and, thus, has an effect on the final particles geometry. In this work, composites with polymethylmethacrylate matrix and short carbon fibres with defined lengths independent on the fibre concentration were prepared and their rheology and the electrical conductivity were investigated. A pronounced influence of the fibre length on the rheological and electrical properties of the composites was confirmed. Increasing the length of the fibres the rheological quantities were affected more significantly and simultaneously the percolation threshold was shifted to lower fibre volume fractions. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon fibres; Polymer-matrix composites; Electrical properties; Rheology

Rheology and Electrical Properties of Carbon Fibre Composites with Defined Filler Geometry - Stary, Zdenek; Weck, Constantin; Krückel, Johannes; Schubert, Dirk W. (Book of Abstracts, 2013)

Rheology and Processing - Schubert, Dirk W. (Polychar 23rd, 2015)

Role of Fiber Thickness and Surface Treatment of Electrospun Polycaprolactone Matrices on the Growth of Different Breast Cancer‐Associated Cells - Sivakumar, Sankaranarayanan; Schmid, Rafael; Wieland, Annalena; Strissel, Pamela; Strick, Reiner; Fischer, Lena; Thievessen, Ingo; Kataev, Elmar; Arkudas, Andreas; Horch, Raymund E.; Schubert, Dirk W.; Kengelbach-Weigand, Annika (Advanced Materials Interfaces, 2022)
Cancer models mimicking the tumor microenvironment are necessary to successfully develop and predict responses of oncological drugs. In this study, electrospun polycaprolactone (PCL) matrices are tested for the development of an in vitro breast cancer model. The effects of fiber thickness and plasma-treatment of the matrices on in vitro growth of breast cancer-associated cells, namely breast cancer cells MDA-MB-231, primary adipose-derived stem cells (ADSCs) and primary endothelial progenitor cells (EPCs) are evaluated. Surface treatment of the matrices by air-plasma leads to increased oxygen/carbon ratio and hydrophilicity. WST-8 analysis reveals that the proliferation of all three cell types increased exponentially over 12 d on all matrices. MDA-MB-231 and ADSC show a higher proliferation on nanofibers due to enhanced cellular adhesion compared to microfibers. In contrast, EPCs show a significantly higher proliferation on microfibers than on nanofibers at day 12 which can further be significantly improved by air-plasma treatment. Cross-sectioning analysis shows that cells grow on the surface of nanofibers, while microfibers have considerable cellular infiltration. These findings suggest that the electrospun PCL matrices are a suitable tool for the development of breast cancer models containing several cell types, which can ultimately lead to designing novel tumor therapies.<br

Schwann Cells Promote Myogenic Differentiation of Myoblasts and Adipogenic Mesenchymal Stromal Cells on Poly-ɛ-Caprolactone-Collagen I-Nanofibers - Cai, Aijia; Zheng, Zengming; Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas A.; Weisbach, Volker Günter; Horch, Raymund E.; Arkudas, Andreas (Cells, 2022)
For the purpose of skeletal muscle tissue engineering, different cell types have been investigated regarding their myogenic differentiation potential, including co-cultured myoblasts and adipogenic mesenchymal stromal cells (Mb/ADSC). As neural cells enhance synaptic junction formation, the aim of this study was to co-culture Schwann cells (SCs) with Mb/ADSC on biocompatible electrospun aligned poly-ε-polycaprolacton (PCL)-collagen I-nanofibers. It was hypothesized that SCs, as part of the peripheral nervous system, promote the myogenic differentiation of Mb/ADSC co-cultures. Mb/ADSC were compared to Mb/ADSC/SC regarding their capacity for myogenic differentiation via immunofluorescent staining and gene expression of myogenic markers. Mb/ADSC/SC showed more myotubes after 28 days of differentiation (p ≤ 0.05). After 28 days of differentiation on electrospun aligned PCL-collagen I-nanofibers, gene expression of myosin heavy chains (MYH2) and myogenin (MYOG) was upregulated in Mb/ADSC/SC compared to Mb/ADSC (p ≤ 0.01 and p ≤ 0.05, respectively). Immunofluorescent staining for MHC showed highly aligned multinucleated cells as possible myotube formation in Mb/ADSC/SC. In conclusion, SCs promote myogenic differentiation of Mb/ADSC. The co-culture of primary Mb/ADSC/SC on PCL-collagen I-nanofibers serves as a physiological model for skeletal muscle tissue engineering, applicable to future clinical application
Keywords: ADSC; myoblasts; myogenic differentiation; mesenchymal stem cells; nanofibers; Schwann cells

Selective Laser Sintering of Polyetheretherketone for bone substitutes - Pohle, D.; Rechtenwald, T.; Kaschta, Joachim; Münstedt, H. (Proceedings of the 10th International Conference on Polymers in Medicine and Surgery, 6.-8. September, Cambridge, 2004)
LFT Import::2019-08-05 (1114)

Self-Assembled Monolayer Dielectrics for Low-Voltage Carbon Nanotube Transistors with Controlled Network Density - Schießl, Stefan; Gannott, Florentina; Etschel, Sebastian; Schweiger, Manuel; Grünler, Saeideh; Halik, Marcus; Zaumseil, Jana (Advanced Materials Interfaces, 2016)

Self-Assembled Monolayer Exchange Reactions as a Tool for Channel Interface Engineering in Low-Voltage Organic Thin-Film Transistors - Lenz, Thomas; Schmaltz, Thomas; Novak, Michael; Halik, Marcus (Langmuir, 2012)
In this work, we compared the kinetics of monolayer self-assembly long-chained carboxylic acids and phosphonic acids on thin aluminum oxide surfaces and investigated their dielectric properties in capacitors and low-voltage organic thin-film transistors. Phosphonic acid anchor groups tend to substitute carboxylic acid molecules on aluminum oxide surfaces and thus allow the formation of mixed or fully exchanged monolayers. With different alkyl chain substituents (n-alkyl or fluorinated alkyl chains), the exchange reaction can be monitored as a function of time by static contact angle measurements. The threshold voltage in α,α′-dihexyl-sexithiophene thin-film transistors composed of such mixed layer dielectrics correlates with the exchange progress and can be tuned from negative to positive values or vice versa depending on the dipole moment of the alkyl chain substituents. The change in the dipole moment with increasing exchange time also shifts the capacitance of these devices. The rate constants for exchange reactions determined by the time-dependent shift of static contact angle, threshold voltage, and capacitance exhibit virtually the same value thus proving the exchange kinetics to be highly controllable. In general, the exchange approach is a powerful tool in interface engineering, displaying a great potential for tailoring of device characteristics.

Self-Assembled Monolayer Field-Effect Transistors based on Oligo-9,9’-dioctylfluorene Phosphonic Acids - Gothe, Bastian; de Roo, Tjaard; Will, Johannes; Unruh, Tobias; Mecking, Stefan; Halik, Marcus (Nanoscale, 2017)
The use of functional oligomers of pi-conjugated oligofluorenes led to a region-selective assembly of amorphous monolayers which exhibit robust lateral charge transport pathways in self-assembled monolayer field-effect transistors over long distances and even in mixed monolayers of semiconducting and insulating molecules. This oligomer concept might stimulate a new molecular design of self-assembling semiconducting materials.

Self-Assembled Monolayer Field-Effect Transistors (SAMFETs) and their application in organic integrated circuits - Zhao, Baolin; Gothe, Bastian; Halik, Marcus (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2019-08-23

Self-Healing Cs3Bi2Br3I6 Perovskite Wafers for X-Ray Detection - Daum, Manuel; Deumel, Sarah; Sytnyk, Mykhailo; Afify, Hany A.; Hock, Rainer; Eigen, Andreas; Zhao, Baolin; Halik, Marcus; These, Albert; Matt, Gebhard; Brabec, Christoph; Tedde, Sandro F.; et al. (Advanced Functional Materials, 2021)
Self-healing of defects imposed by external stimuli such as high energy radiation is a possibility to sustain the operational lifetime of electronic devices such as radiation detectors. Cs3Bi2Br3I6 polycrystalline wafers are introduced here as novel X-ray detector material, which not only guarantees a high X-ray stopping power due to its composition with elements with high atomic numbers, but also outperforms other Bi-based semiconductors in respect to detector parameters such as detection limit, transient behavior, or dark current. The polycrystalline wafers represent a size scalable technology suitable for future integration in imager devices for medical applications. Most astonishingly, aging of these wafer-based devices results in an overall improvement of the detector performance—dark currents are reduced, photocurrents are increased, and one of the most problematic properties of X-ray detectors, the base line drift is reduced by orders of magnitude. These aging induced improvements indicate self-healing effects which are shown to result from recrystallization. Optimized synthetic conditions also improve the as prepared X-ray detectors; however, the aged device outperforms all others. Thus, self-healing acts in Cs3Bi2Br3I6 as an optimization tool, which is certainly not restricted to this single compound, it is expected to be beneficial also for many further polycrystalline ionic semiconductors.
CRIS-Team Scopus Importer:2021-08-27
Keywords: bismuth halides; lead-free perovskites; photoconductors; self-healing; X-ray detection

Self-reinforcing and toughening isotactic polypropylene via melt sequential injection molding - Jiang, Jing; Liu, Xianhu; Lian, Meng; Pan, Yamin; Chen, Qiang; Liu, Hu; Zheng, Guoqiang; Guo, Zhanhu; Schubert, Dirk W.; Shen, Changyu; Liu, Chuntai (Polymer Testing, 2018)
Polymer material exhibits a trade-off between toughness and stiffness, therefore, it remains difficult to develop a strategy that simultaneously realizes improved mechanical strength and toughness. Inspired by the bamboo-like structure, an efficient and simple melt sequential injection molding is proposed to fabricate a controllable skin-core structure of iPP samples with self-reinforcement and toughness. With increasing the melt injection number, the shear layers containing shish-kebabs are progressively thickened, resulting in an effective improvement of mechanical properties. The tensile strength increased from 35.1 to 55.3 MPa for the melt injection number from one to four, meanwhile the toughness was enhanced from 23.1 to 53.6 kJ/m2. A simple theoretical model was derived and utilized to describe the experimental data. Theoretically calculated tensile strength of sample with entirely shish-kebabs can even reach 222.9 MPa via this technology, which is much higher than that of most engineering plastics and polymer composites. This work not only provides an efficient way to fabricate high-performance general plastics for engineering purposes but also a new opportunity to understand the fundamental issues about the mechanism of the self-reinforced polymers.
Keywords: Fracture toughness; Injection molding; Strength; Modelling; Polymers

Semi-empirical description for the draw resonance behavior of polypropylene - Kunzelmann, Peter; Danzer, Stefan; Schubert, Dirk W. (Book of Abstracts, 2013)

Semi-Empirical Equations for the description of Rheotens experiments - Kunzelmann, Peter; Danzer, Stefan; Schubert, Dirk W. (9th Annual European Rheology Conference, 2014)

Semi-empirical equations for the description of rheotens measurements Semi-empirische gleichungen zur beschreibung von rheotens messungen - Kunzelmann, Peter; Danzer, Stefan; Schubert, Dirk W. (Zeitschrift Kunststofftechnik, 2013)
Keywords: Critical draw ratio; Polypropylene; Draw resonance; Rheotens

Semi-empirical equations for the description of rheotens measurements Semi-empirische gleichungen zur beschreibung von rheotens messungen - Kunzelmann, Peter; Danzer, Stefan; Schubert, Dirk W. (Zeitschrift Kunststofftechnik, 2014)
Keywords: Critical draw ratio; Polypropylene; Draw resonance; Rheotens

Semi-empirical equations for the description of rheotens measurements Semi-empirische gleichungen zur beschreibung von rheotens messungen - Kunzelmann, Peter; Danzer, Stefan; Schubert, Dirk W. (Zeitschrift Kunststofftechnik, 2014)
Keywords: Critical draw ratio; Polypropylene; Draw resonance; Rheotens

Semimetallic TiO2 Nanotubes - Hahn, Robert; Schmidt-Stein, Felix; Salonen, Jarno; Thiemann, Stefan; Song, Yanyan; Kunze, Julia; Lehto, Vesa-Pekka; Schmuki, Patrik (Angewandte Chemie International Edition, 2009)
Orchestrating conductors: A carbo-thermal reduction treatment of a TiO_2 nanotube layer in acetylene converts the tube walls into highly conductive and stable oxy carbide compounds. The resulting semimetallic TiO_2 nanotube layers (TiOxCy) are electrode materials with properties that differ from other TiO_2 nanotubes (see picture). They have a high oxygen overpotential and can be used as a catalyst support, for example, for methanol oxidation.
EAM Import::2019-03-13

Shear and Elongational Flow Properties of Long-Chain Branched Poly(ethylene terephthalates) and Correlations to Their Molecular Structure - Härth, Michael; Kaschta, Joachim; Schubert, Dirk W. (Macromolecules, 2014)
Reactive processing with low-molar-mass modifiers is a well-known method to create long-chain branched (LCB) structures in a poly(ethylene terephthalate) (PET) melt. However, less is known about the elongational flow properties of LCB-PET. Therefore, the aim of this contribution is (a) to generate LCB molecules and (b) to evaluate the influence of the branching level on the transient elongational behavior. For this purpose, a commercial, linear PET and different contents (0.1-0.3 wt %) of the tetrafunctional modifier pyromellitic dianhydride (PMDA) were reactively processed. All samples were analyzed by size exclusion chromatography coupled with a light scattering device and characterized by shear and elongational rheometry. It was found that the molar mass distribution of the modified materials exhibit a high molar mass shoulder, leading to an increase of the weight-average molar mass and a broadening of the molar mass distribution. Moreover, the Mark-Houwink plot of the modified materials displays deviations from the power law toward lower intrinsic viscosities, which indicate the existence of LCB molecules. The shear viscosity shows a pronounced shear thinning behavior and a remarkable increase at low frequencies compared to the linear PET. Considering the transient elongational viscosity, a distinguished strain hardening is observed, which increases with increasing PMDA content and with increasing strain rate. From the results of the rheological and molecular characterization and by considering the chemical reaction mechanisms, it can be concluded that the PET modified with high PMDA contents has a treelike branch-on-branch architecture, which is well-known from low-density polyethylene melts.

Shear and elongational flow properties of peroxide-modified wood/low-density polyethylene composite melts - Harnnarongchai, Wanlop; Kaschta, Joachim; Schubert, Dirk W.; Sombatsompop, Narongrit (Polymer Composites, 2012)
Adding fillers to a polymer melt may result in a strain softening behavior in elongational flow in long-chain branched materials, showing strain-hardening behavior when compared with unfilled one. To improve the strain-hardening properties in wood/LDPE composites, the effect of peroxide concentration on both the molecular architecture and molar mass distribution, and the rheological quantities in shear and elongation is studied. Addition of wood flour increases the viscosity according to a logarithmic mixing rule, as expected from the large particle size and the filler fractions used. The peroxide has multiple effects on the molar architecture of the polymer. First, a gel fraction of cross-linked material is formed, the concentration of gel being dependent of the amount of peroxide used. Second, a higher molar mass component is detected, leading to higher value of Mw and to a broader molar mass distribution. Finally, the degree of long-chain branching unexpectedly decreases with increasing peroxide content. The changes in molecular architecture are hardly influenced by addition of the wood flour. The peroxide treatment leads to an improved strain-hardening behavior, detected by elongational viscosity and melt strength measurements. However, the addition of wood flour decreases the amount of strain hardening.

Shear Induced Changes of Carbon Black Structures in Conductive Polymer Composites - Schubert, Dirk W.; Krückel, Johannes; Stary, Zdenek (Polychar 21st, 2013)

Shear induced electrical behaviour of conductive polymer composites - Stary, Zdenek; Krückel, Johannes; Schubert, Dirk W. (International Conference on Novel Trends in Rheology V, 2013)
Keywords: Composites; Oscillatory shear; Electrical resistance

Shear induced electrical behaviour of conductive polymer composites - Stary, Zdenek; Krückel, Johannes; Schubert, Dirk W. (International Conference on Novel Trends in Rheology V, 2013)
Keywords: Composites; Oscillatory shear; Electrical resistance

Shear-induced rheological and electrical properties of molten poly(methyl methacrylate)/carbon black nanocomposites - Liu, Xianhu; Li, Chaohui; Pan, Yamin; Schubert, Dirk W.; Liu, Chuntai (Composites Part B-Engineering, 2019)
In this work, the rheological and electrical behavior of carbon black (CB) filled poly(methyl methacrylate) (PMMA) nanocomposites in the molten state as a function of CB concentration were investigated by simultaneous electrical and rheological measurements. Shear deformations applied during a stress amplitude sweep caused both changes in the linear viscoelastic behavior and electrical conductivity. The storage modulus increased with measuring time for all PMMA nanocomposites. However, the changes in the time-dependent behavior of storage modulus decreased above the percolated CB concentrations for all investigated nanocomposites, which was in good agreement with the changes in the time-dependent electrical conductivity. The different behaviors can be explained by the agglomeration of CB particles and the decrease of averaged force on a single CB particle.
CRIS-Team WoS Importer:2019-04-18

Shear rheology of nanofiber reinforced alginate solutions for bioprinting - Schrüfer, Stefan; Küng, Florian; Schubert, Dirk W. (Deutsche Gesellschaft für Biomaterialien - Annual Meeting, 2018)
Keywords: shear rheology; nanofiber; bioprinting

Simple Approach for Spreading Dynamics of Polymeric Fluids - Härth, Michael; Schubert, Dirk W. (Macromolecular Chemistry and Physics, 2012)
The spreading of an axisymmetric drop on partially and completely wetted substrates is investigated from the theoretical and experimental point of view. In particular, novel physical models considering the capillary force, the gravitational force, and a viscous friction force simultaneously are derived. The models enable the analytical mathematical description of the drop radius as a function of the spreading time, which is useful for practical applications. Moreover, the construction of a master curve for the partial wetting scenario is proposed. The theoretical models are experimentally verified, using different polymer films as substrates and polydimethylsiloxanes of different viscosities as liquids. The comparison shows that theory and experiment are consistent.
Keywords: drop spreading; fluoropolymers; gravitational and capillary force; modelling; slicon oil

Simple approximate solution for modeling the spreading of a drop in the partial wetting case - Härth, Michael; Schubert, Dirk W. (Book of Abstracts, 2012)

Simple fabrication technique for multilayered stratified composite scaffolds suitable for interface tissue engineering - Liverani, Liliana; Roether, Judith; Nooeaid, Patcharakamon; Trombetta, Marcella; Schubert, Dirk W.; Boccaccini, Aldo R. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2012)
A straightforward method for manufacturing stratified scaffolds with potential application in osteochondral tissue engineering is reported. The method integrates three different techniques widely used for scaffold fabrication: sponge replica method, freeze-drying and electrospinning. 45S5 Bioglass® was used for the fabrication of the rigid bioactive substrate intended to be in contact with bone tissue, chitosan and alginate based solutions were used for building the interface between the Bioglass®-based scaffold and the soft cartilage side of the construct. Finally a chitosan-based electrospun nanofibrous membrane was selected for the upper layer of the scaffold. In this design, the intermediate layer has multiple functions providing adherence between the other scaffold components, preventing delamination and acting as a soft coating for the rigid Bioglass® substrate. Morphological analysis, bioactivity tests in simulated body fluid (SBF), as well as mechanical and wettability tests were performed on all samples to assess the optimal stratified scaffold combination. The best results, in terms of resistance to layer delamination, preservation of the bioactivity and improvement of the mechanical properties, were obtained using a chitosan solution and the freeze gelation technique for fabrication of the intermediate layer. Key results are discussed in the context of the potential application of these novel scaffolds in osteochondral tissue engineering.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.simple
Keywords: Composites; Tissue engineering; Scaffolds; Electrospinning; Chitosan; Bioactive glass

Simple Model for the Spreading of Inks in Bioprinting—Revealing Relevant Scaling Laws—Part I Theory - Schubert, Dirk W. (Macromolecular Theory and Simulations, 2021)
A model taking into consideration viscosity and evaporation is suggested to describe the spreading kinetics of struts in bioprinting. Scenarios resulting by complete and partial wetting are discussed and described. Applicable fit functions and predictive scaling laws are given, relating viscosity of bioinks, process parameters such as print speed and throughput to the strut width. The approach is primarily based on 1D spreading.
Created from Fastlane, Scopus look-up
Keywords: 3D printing; bioprinting; scaling laws; shape fidelity; strut spreading; viscosity

Simple Model to Predict the Effect of Take-up Pressure on Fibre Diameter of PET Melt Spinning - Qin, Yijing; Schubert, Dirk W. (27th Annual World Forum on Advanced Materials (POLYCHAR 27), 2019)

Simple Model to Predict the Effect of Take-up Pressure on Fibre Diameter of PET Melt Spinning - Qin, Yijing; Schubert, Dirk W. (Polymer, 2019)
A simplified mathematical model was given based on the actual experimental data from a laboratory-scale poly (ethylene terephthalate) (PET) melt spinning. PET fibres were produced using three virgin and two recycled PET materials at two different processing temperatures of 270 °C and 280 °C. Filament emerging from a spinneret was drawn by high-velocity air moving through an aspirator, where six take-up pressures were used. It was proved that the model with only two adjustable parameters could effectively predict the variation of PET fibre diameter as a function of take-up pressure, and one of the parameters could be estimated using the zero shear viscosity of material
Keywords: Poly (ethylene terephthalate); melt spinning; Model

Simulating ’Soft’ Electronic Devices - Clark, Timothy; Halik, Marcus; Hennemann, Matthias; Jäger, Christof (2013)
A combination of classical molecular dynamics simulations and very large scale semiempirical molecular orbital calculations has been used to simulate field-effect transistors in which both the dielectric layer and the semiconductor are incorporated in a self-assembled monolayer of suitable functionalized alkylphosphonic acids. In such simulations, both the dynamics of the flexible organic molecules and the electronic properties of the molecular aggregates must be taken into account. First steps towards realistic simulations of such devices are described.

Simulating the effective electric conductivity of polymer composites with high aspect ratio fillers - Nilsson, Fritjof; Krückel, Johannes; Schubert, Dirk W.; Chen, Fei; Unge, Mikael; Gedde, Ulf; Hedenqvist, Mikael (Composites Science and Technology, 2016)
Three simulation models have been developed for predicting the electrical conductivity and the electrical percolation threshold of field-grading polymer composites intended for high voltage applications. The three models are based on finite element modelling (FEM), percolation threshold modelling (PTM) and electrical networks modelling (ENM). A Monte Carlo algorithm was used to construct the geometries, with either soft-core (overlapping) or hard-core/soft-shell (non-overlapping) fibres. Conductivity measurements on carbon-fibre/PMMA composites with well-defined fibre aspect ratios were used for experimental validation. The average fibre orientations were calculated from scanning electron micrographs. The soft-core PTM model with experimental fibre orientations and without adjustable parameters gave accurate (R = 0.984) predictions of the electrical percolation threshold as a function of aspect ratio. The corresponding soft-core ENM model, with close-contact conductivity calculated with FEM, resulted in good conductivity predictions for the longest fibres, still without the use of any adjustable parameters. The hard-core/soft-shell versions of the models, using the shell thickness as an adjustable parameter, gave similar but slightly poorer results.
Keywords: Carbon-fibre; Composites; Electrical conductivity; Field-grading; Simulation

Simulating the effective electric conductivity of polymer composites with high aspect ratio fillers - Nilsson, Fritjof; Schubert, Dirk W.; Chen, Fei (Composites Science and Technology, 2016)
Three simulation models have been developed for predicting the electrical conductivity and the electrical percolation threshold of field-grading polymer composites intended for high voltage applications. The three models are based on finite element modelling (FEM), percolation threshold modelling (PTM) and electrical networks modelling (ENM). A Monte Carlo algorithm was used to construct the geometries, with either soft-core (overlapping) or hard-core/soft-shell (non-overlapping) fibres. Conductivity measurements on carbon-fibre/PMMA composites with well-defined fibre aspect ratios were used for experimental validation. The average fibre orientations were calculated from scanning electron micrographs. The soft-core PTM model with experimental fibre orientations and without adjustable parameters gave accurate (R2 = 0.984) predictions of the electrical percolation threshold as a function of aspect ratio. The corresponding soft-core ENM model, with close-contact conductivity calculated with FEM, resulted in good conductivity predictions for the longest fibres, still without the use of any adjustable parameters. The hard-core/soft-shell versions of the models, using the shell thickness as an adjustable parameter, gave similar but slightly poorer result

Simulating the electric conductivity of the conductive polymer composites - Yang, Guanda; Nilsson, Fritjof; Schubert, Dirk W. (15th Bayreuth Polymer Symposium, 2017)

Simulating the electric conductivity of the conductive polymer composites - Yang, Guanda; Nilsson, Fritjof; Schubert, Dirk W. (54th Nordic Polymer Days, 2017)

Simulating the electric conductivity of the conductive polymer composites - Yang, Guanda; Schubert, Dirk W. (Workshop on Italian-Nordic Polymer Future, 2017)

Simulation of charge transport in organic semiconductors: A time-dependent multiscale method based on nonequilibrium Green's functions - Leitherer, Susanne; Jager, C. M.; Krause, Andreas; Halik, Marcus; Clark, Timothy; Thoss, Michael (Physical Review Materials, 2017)
In weakly interacting organic semiconductors, static disorder and dynamic disorder often have an important impact on transport properties. Describing charge transport in these systems requires an approach that correctly takes structural and electronic fluctuations into account. Here, we present a multiscale method based on a combination of molecular-dynamics simulations, electronic-structure calculations, and a transport theory that uses time-dependent nonequilibrium Green's functions. We apply the methodology to investigate charge transport in C-60-containing self-assembled monolayers, which are used in organic field-effect transistors.

Simulations of electrical conductivity in PMMA/Carbon Fibre composites - Nilsson, Fritjof; Krückel, Johannes; Schubert, Dirk W.; Gedde, Ulf; Hedenqvist, Mikael (Nordic Polymer Days, 2015)

Simultaneous Biaxial Stretching of Polypropylene Resins of Varying Tacticity Part II: Film Morphology and Properties - Capt, L.; Rettenberger, Stefan; Münstedt, Helmut; Kamal, M. R. (International Polymer Processing, 2022)
The simultaneous biaxial stretching behavior of three Ziegler-Natta-based isotactic polypropylene resins of varying isotacticity was studied using a laboratory film stretcher that simulates closely stretching conditions encountered in the commercial process. The effect of isotacticity on the final morphology and end film properties was associated with the effect of isotacticity on the thermal properties of the resin. The results showed that the degree of undermelting, oT(um) = T-m-T, determines the phase composition of the polymer before stretching and the morphology and orientation of the stretched films. The size and orientation of the crystallites in the stretching plane is mostly determined by the degree of undermelting. The elongation at break was correlated with the residual crystallinity of the film before stretching, and the elastic modulus was correlated with the final degree of crystallinity and the density of tie chains.
CRIS-Team WoS Importer:2022-03-25

Simultaneous electrical and rheological investigations on conductive polymer composites - Krückel, Johannes; Stary, Zdenek; Schubert, Dirk W. (Book of Abstracts, 2012)

Size Effect of Silica Particles on the Rheological Properties of Polyactide - Hao, Xiaoqiong; Kaschta, Joachim; Schubert, Dirk W. (9th Annual European Rheology Conference, 2014)

Size matters-in vitro behaviour of human fibroblasts on textured silicone surfaces with different pore sizes - Juia, Tolksdorf; Horch, Raymund E.; Grüner, Jasmin; Schmid, Rafael; Kengelbach-Weigand, Annika; Schubert, Dirk W.; Werner, Siegfried; Schneidereit, Dominik; Friedrich, Oliver; Ludolph, Ingo (Journal of Materials Science: Materials in Medicine, 2020)
Capsular contracture remains a challenge in plastic surgery and represents one of the most common postoperative complications following alloplastic breast reconstruction. The impact of the surface structure of silicone implants on the foreign body reaction and the behaviour of connective tissue-producing cells has already been discussed. The aim of this study was to investigate different pore sizes of silicone surfaces and their influence on human fibroblasts in an in vitro model. Four different textures (no, fine, medium and coarse texture) produced with the salt-loss technique, have been assessed in an in vitro model. Human fibroblasts were seeded onto silicone sheets and evaluated after 1, 4 and 7 days microscopically, with viability assay and gene expression analysis. Comparing the growth behaviour and adhesion of the fibroblasts on the four different textures, a dense cell layer, good adhesion and bridge-building ability of the cells could be observed for the fine and medium texture. Cell number and viability of the cells were increasing during the time course of experiments on every texture. TGFß1 was lowest expressed on the fine and medium texture indicating a trend for decreased fibrotic activity. For silicone surfaces produced with the salt-loss technique, we were able to show an antifibrotic effect of smaller sized pores. These findings underline the hypothesis of a key role of the implant surface and the pore size and pore structure in preventing capsular contracture.<br
Keywords: Silicone Surface; hand surgery; implants; Biocompatibility Studies

Smoothly Tunable Surface Properties of Aluminum Oxide Core-Shell Nanoparticles By A Mixed-Ligand Approach - Portilla Berlanga, Luis; Halik, Marcus (ACS Applied Materials and Interfaces, 2014)
We present a facile solution-based procedure for tailoring the surface properties of aluminum oxide nanoparticles (AlOx-NPs) by the formation of tunable core-shell systems with self-assembled monolayers. By employing chained molecules with a phosphonic acid anchor group and either hydrophobic or hydrophilic chains the surface properties of the nanoparticles change dramatically. So, the solubility can be tuned orthogonal from trifluorotoluene (CF3-C6H5) for hydrophobic shell to water (H2O) for hydrophilic functionalization respectively. Spray coated films of those functionalized nanoparticles exhibited superhydrophobic or superhydrophilic properties. The surface properties can be tuned smoothly by the formation of a mixed ligand monolayer from corresponding stoichiometric mixtures of the ligands. The core-shell nanoparticles were investigated by means of thermogravimetric analysis, TGA; Fourier transform infrared spectroscopy, FTIR; and static contact angle goniometry, SCA. The effect of different dipole moments of the SAM molecules in mixed shell nanoparticles to their stability in dispersions was studied by zeta potential measurements.

Sobetirome rescues α-synuclein-mediated demyelination in an in vitro model of multiple system atrophy - Meszaros, Lisa; Himmler, Marcus; Schneider, Yanni; Arnold, Philipp; Dörje, Frank; Schubert, Dirk W.; Winkler, Jürgen (European Journal of Neuroscience, 2023)
Multiple system atrophy (MSA) is a rare and rapidly progressive atypical parkinsonian disorder characterized by oligodendroglial cytoplasmic inclusions containing α-synuclein (α-syn), demyelination, inflammation and neuronal loss. To date, no disease-modifying therapy is available. Targeting α-syn-driven oligodendroglial dysfunction and demyelination presents a potential therapeutic approach for restricting axonal dysfunction, neuronal loss and disease progression. The present study investigated the promyelinogenic potential of sobetirome, a blood–brain barrier permeable and central nervous system selective thyromimetic in the context of an in vitro MSA model. Oligodendrocyte precursor cells (OPCs) were obtained from transgenic mice overexpressing human α-syn specifically in oligodendrocytes (MBP29 mouse line), a well-described MSA model, and non-transgenic littermates. mRNA and protein expression analyses revealed a substantial rescue effect of sobetirome on myelin-specific proteins in control and α-syn overexpressing oligodendrocytes. Furthermore, myelination analysis using nanofibres confirmed that sobetirome increases both the length and number of myelinated segments per oligodendrocyte in primary murine α-syn overexpressing oligodendrocytes and their respective control. These results suggest that sobetirome may be a promising thyromimetic compound targeting an important neuropathological hallmark of MSA.
CRIS-Team Scopus Importer:2023-12-22
Keywords: MSA; myelin; oligodendrocytes; sobetirome; thyromimetics; α-synuclein

Soft–matrices based on Fibrous Proteins for Biofabrication - Silva Lourenco, Rauqel; Sarker, Bapi; Singh, Raminder; Cicha, Iwona; Roether, Judith; Kaschta, Joachim; Detsch, Rainer; Garlichs, Christoph; Schubert, Dirk W.; Boccaccini, Aldo R. (14th BIONANO-MATERIALS, 2013)

Soft-matrices based on silk fibroin and alginate for tissue engineering - Silva, Raquel; Singh, Raminder; Sarker, Bapi; Papageorgiou, Dimitrios G.; Juhasz, Judith A.; Roether, Judith; Cicha, Iwona; Kaschta, Joachim; Schubert, Dirk W.; Chrissafis, Konstantinos; Detsch, Rainer; Boccaccini, Aldo R. (International Journal of Biological Macromolecules, 2016)
Keywords: Alginate; Endothelial cells; Silk fibroin; Soft-matrix; Tissue engineering

Solar spectral conversion for improving the photosynthetic activity in algae reactors - Wondraczek, Lothar; Batentschuk, Miroslaw; Schmidt, Markus A.; Borchardt, Rudolf; Scheiner, Simon; Seemann, Benjamin; Schweizer, Peter; Brabec, Christoph (Nature Communications, 2013)
Sustainable biomass production is expected to be one of the major supporting pillars for future energy supply, as well as for renewable material provision. Algal beds represent an exciting resource for biomass/biofuel, fine chemicals and CO storage. Similar to other solar energy harvesting techniques, the efficiency of algal photosynthesis depends on the spectral overlap between solar irradiation and chloroplast absorption. Here we demonstrate that spectral conversion can be employed to significantly improve biomass growth and oxygen production rate in closed-cycle algae reactors. For this purpose, we adapt a photoluminescent phosphor of the type Ca SrEuS, which enables efficient conversion of the green part of the incoming spectrum into red light to better match the Q peak of chlorophyll b. Integration of a Ca SrEuS backlight converter into a flat panel algae reactor filled with Haematococcus pluvialis as a model species results in significantly increased photosynthetic activity and algae reproduction rate. © 2013 Macmillan Publishers Limited. All rights reserved.

Sol-gel coatings for solar cover glass: Influence of surface structure on dust accumulation and removal - Zimmermann, Thomas; Stauch, Claudia; Bittel, Laura; Jüngling, Natalie; Muhamettursun, Mahmut; Halik, Marcus; Niessner, Jennifer; Wintzheimer, Susanne; Lyons, Alan; Löbmann, Peer; Mandel, Karl (Solar Energy, 2024)
Soiling of solar cover glass is a major cause for efficiency loss of solar photovoltaic modules. Anti-soiling coatings can be used to reduce the rate of soiling and lower cleaning costs. The efficiency of these coatings has been demonstrated in laboratory and field tests, but the mechanisms and relevant parameters are still not well understood. In this article, we present a study on the influence of surface structure of hydrophilic sol–gel coatings on their anti-soiling performance in terms of both, dust accumulation and subsequent indoor tests for dust removal by wind. The surface structure of the films originates from the addition of colloidal silica particles of different sizes to the sols used for film preparation. In the dust deposition experiments, standardized test dust and dust collected from solar installations were used. Repeated tests were conducted under controlled humidity. In the case of dust deposition, the accumulation of dust particles larger than ∼10 µm is strongly reduced, in relation to bare glass, by the anti-soiling effect of all coatings regardless of their surface structure. For the dust removal via wind, coatings that bear a smoother surface structure are cleaned more easily than coatings with a rougher surface structure. Additionally, larger and rounder dust particles are removed more easily from coatings with a rougher surface structure (structure height over ∼40 nm), while smaller and more irregularly shaped dust particles are removed more easily from coatings with a smoother surface structure.
CRIS-Team Scopus Importer:2024-01-05
Keywords: Anti-dust; Anti-soiling; Clean surfaces; PV module efficiency increase; Sol–gel coatings for photovoltaics; Structure

Solution-processed single-crystalline organic transistors on patterned ultrathin gate insulators - Tsurumi, J.; Amin, Atefeh Y.; Okamoto, T.; Mitsui, C.; Takimiya, K.; Matsui, Hiroyuki; Halik, Marcus; Takeya, Jun (Organic Electronics, 2014)
Single-crystalline organic transistors of 3,11-didecyl-dinaphtho[2,3-d:2′,3′-d′]benzo[1,2-b:4,5-b′]dithiophene (C10-DNBDT-NW) and 2,9-didecyl-dinaphtho[2,3-b:2′,3′-f]thieno[3,2-b]thiophene (C10-DNTT) were fabricated by solution processes on top of the patterned hybrid ultrathin gate dielectrics consisting of 3.6 nm-thick aluminum oxide and self-assembled monolayers (SAMs). Due to the excellent crystallinity of the channel films, bottom-gate and top-contact field-effect transistors exhibited the average field-effect mobility of 3.7 cm2/V s and 4.3 cm2/V s for C10-DNBDT-NW and C10-DNTT, respectively. These are the first successful devices of solution-processed single-crystalline transistors on ultrathin gate dielectrics with the mobility above 1 cm2/V s, opening the way to develop low-power-consumption and high-performance printed circuits.

Solvent effects on the vibronic one-photon absorption profiles of dioxaborine heterocycles - Wang, Y.-H.; Halik, Marcus; Wang, C.-K.; Marder, S. R.; Luo, Y. (Journal of Chemical Physics, 2005)

Solving complex nanostructures with ptychographic atomic electron tomography - Pelz, Philipp; Griffin, Sinéad M.; Stonemeyer, Scott; Popple, Derek; DeVyldere, Hannah; Ercius, Peter; Zettl, Alex; Scott, Mary C.; Ophus, Colin (Nature Communications, 2023)
Transmission electron microscopy (TEM) is essential for determining atomic scale structures in structural biology and materials science. In structural biology, three-dimensional structures of proteins are routinely determined from thousands of identical particles using phase-contrast TEM. In materials science, three-dimensional atomic structures of complex nanomaterials have been determined using atomic electron tomography (AET). However, neither of these methods can determine the three-dimensional atomic structure of heterogeneous nanomaterials containing light elements. Here, we perform ptychographic electron tomography from 34.5 million diffraction patterns to reconstruct an atomic resolution tilt series of a double wall-carbon nanotube (DW-CNT) encapsulating a complex ZrTe sandwich structure. Class averaging the resulting tilt series images and subpixel localization of the atomic peaks reveals a Zr11Te50 structure containing a previously unobserved ZrTe2 phase in the core. The experimental realization of atomic resolution ptychographic electron tomography will allow for the structural determination of a wide range of beam-sensitive nanomaterials containing light elements.
CRIS-Team Scopus Importer:2023-12-15

Solving the mystery of kinking - Kremser, Thomas; Gläss, Liesa; Roth, Stefan; Schubert, Dirk W. (Kunststoffe International, 2017)
The flexibility of infusion lines is a key product feature for their application. However, adverse pressure may cause kinking that can interfere with treatment safety. New test methods characterize the kinking behavior of hoses, and are able to predict the behavior over several days within hour

Sonochemical processing and characterization of composite materials based on soy protein and alginate containing micron-sized bioactive glass particles - Silva Lourenco, Rauqel; Bulut, Buse; Roether, Judith; Kaschta, Joachim; Schubert, Dirk W.; Boccaccini, Aldo R. (Journal of Molecular Structure, 2014)
Novel composite hydrogels based on the combination of natural polymers; namely alginate and soy protein isolate, and bioactive glass (BC) particles (mean size: 2 pm) were developed. For this purpose a sono-chemical approach was used and homogeneous composite hydrogels, incorporating two concentrations of BC particles, were successfully obtained. Further physico-chemical characterization was performed in order to evaluate the influence of each component on hydrogel properties. The water uptake ability, weight loss, protein release, as well as FTIR, SEM and DMTA characterization were carried out. The bio-mineralization process in simulated body fluid (SBF) was followed over time and the results demonstrated that the composite materials have the ability to form a surface apatite layer after 7 days in SBF. The design of novel composite hydrogels based on soy protein, alginate and BC can be a suitable approach for bone regeneration applications. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Alginate; Soy isolate protein; Bioactive glass; Hydrogel; Tissue engineering

Soy protein isolate/bioactive glass composite membranes: Processing and properties - Tansaz, Samira; Schulte, M.; Kneser, U.; Mohn, D.; Stark, W.; Roether, Judith; Cicha, Iwona; Boccaccini, Aldo R. (European Polymer Journal, 2018)
Keywords: Clotting assay; Cytocompatibility; Bioactive glass; Soy protein isolate; Wound dressing

Spatially Resolved Bottom-Side Fluorination of Graphene by Two-Dimensional Substrate Patterning - Bao, Lipiao; Zhao, Baolin; Lloret, Vicent; Halik, Marcus; Hauke, Frank; Hirsch, Andreas (Angewandte Chemie International Edition, 2020)
Patterned functionalization can, on the one hand, open the band gap of graphene and, on the other hand, program demanding designs on graphene. The functionalization technique is essential for graphene-based nanoarchitectures. A new and highly efficient method was applied to obtain patterned functionalization on graphene by mild fluorination with spatially arranged AgF arrays on the structured substrate. Scanning Raman spectroscopy (SRS) and scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDS) were used to characterize the functionalized materials. For the first time, chemical patterning on the bottom side of graphene was realized. The chemical nature of the patterned functionalization was determined to be the ditopic scenario with fluorine atoms occupying the bottom side and moieties, such as oxygen-containing groups or hydrogen atoms, binding on the top side, which provides information about the mechanism of the fluorination process. Our strategy can be conceptually extended to pattern other functionalities by using other reactants. Bottom-side patterned functionalization enables utilization of the top side of a material, thereby opening up the possibilities for applications in graphene-based devices.
CRIS-Team Scopus Importer:2020-03-31
Keywords: ditopic functionalization; fluorination; graphene; substrate patterning

Spray-coatable ionogels based on silane-ionic liquids for low voltage, flexible, electrolyte-gated organic transistors - Thiemann, Stefan; Sachnov, Swetlana; Gruber, Mathias; Gannott, Florentina; Spallek, Stefanie; Schweiger, Manuel; Krückel, Johannes; Kaschta, Joachim; Spiecker, Erdmann; Wasserscheid, Peter; Zaumseil, Jana (Journal of Materials Chemistry C, 2014)
We introduce a new type of silane-based ionogels that are produced by gelation of the ionic liquid 3-methyl-1-(3-(triethoxysilyl)propyl)-imidazolium bis(trifluoromethylsulfonyl)imide ([(EtO)3SiPMIM][TFSI]) with tetramethylorthosilane and formic acid. In the obtained ionogels the cations are involved in the network formation while the anions can move freely. The ionogels show advantageous properties for application in flexible electronics, such as low modulus, solution processability and high specific capacitance. Spray-coated ionogels were used as high capacitance gate dielectrics for organic (poly[3-hexylthiophene], P3HT) electrolyte-gated transistors (EGTs) that operated at very low voltages (<2 V) with high on/off ratios in air over weeks. Devices fabricated on polymer foil remained functional during repeated bending cycles with strains up to 2.3%.

Spreading Dynamics of Polymeric Fluids - Schubert, Dirk W.; Härth, Michael (Final Program and Book of Abstracts, 2011)
Spreading of fluids plays a key role in many processes and in research & development. For example, in the lubrication industry, he lubricating oil is evaluated by its spreading kinetic of a respective drop on a plane test surface. The time scale of the spreading dynamics depends not only on the interfacial tensions and the viscosity but also on the volume of the spreading fluid. For total and partial wetting scenarios novel models are developed from physical principals to describe the spreading kinetics detailed and consider gravity, interfacial energies and viscose friction simultaneosly. From mathematical perturbation calculations useful equations are derived [1] for practical application, like the following on

Spreading Kinetics on Completely Wettable Surface – Transition from Spherical Cap to Pancakes Shape - Albrecht, Michael; Härth, Michael; Schubert, Dirk W. (Abstracts, 2012)

Stability Analysis in Fiber Spinning of Polymer Melts using Simple Polymer Models - Bechert, Mathias; Schubert, Dirk W. (Abstracts, 2012)

Steady states in extensional flow of strain hardening polymer melts and the uncertainties of their determination - Münstedt, Helmut; Stary, Zdenek (Journal of Rheology, 2013)
The existence of a plateau, a maximum or even an overshoot of the elongational viscosity of polymer melts as a function of time or extension, respectively, is a hot topic of scientific discussions. Although not essential for the relation of elongational properties to applications, the feature is crucial for a verification of various theories. From a critical review of sophisticated comparative stressing and creep experiments on a low density polyethylene (LDPE), the existence of a pronounced stationary elongational viscosity becomes very probable. These conclusions are supported by investigations on a long-chain branched polypropylene. For an LDPE of higher molar mass with stress maxima caused by local necking within the sample, the maximum viscosities agree with the corresponding steady-state viscosities obtained from creep experiments performed by the same rheometer. The decisive role of the uniformity of the sample deformation for the accuracy of elongational experiments is pointed out. From the findings presented, it becomes evident that a careful control of the sample uniformity is the basic condition for a critical assessment of differing results from the various experimental methods found in the literature. © 2013 The Society of Rheology.
Created from Fastlane, Scopus look-up
Keywords: Elongation; Polymer melts; Sample uniformity; Steady state; Viscosity maximum

Stereoscopic analysis of silicone breast implant shells damaged by surgical instruments - Schmitz, Marweh; Schubert, Dirk W.; Horch, Raymund E. (Plastic and Reconstructive Surgery, 2016)

Stereoscopic Analysis of Silicone Breast Implant Shells Damaged by Surgical Instruments - Schmitz, Marweh; Schubert, Dirk W.; Horch, Raymund E. (Plastic and Reconstructive Surgery, 2016)

Sterilization effects on the physical properties and cytotoxicity of poly (glycerol sebacate) - Rai, Ranjana; Tallawi, Marwa; Roether, Judith; Detsch, Rainer; Barbani, Niccoletta; Rosellini, Elisabeth; Kaschta, Joachim; Schubert, Dirk W.; Boccaccini, Aldo R. (Materials Letters, 2013)
The influence of conventional sterilization methods such as gamma irradiation, ethylene oxide treatment and steam exposure on the physical properties of poly(glycerol sebacate) (PGS) was investigated. Scanning electron microscope (SEM) observations, attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) and Raman spectra demonstrated that the applied sterilization methods do not induce adverse surface modifications. The sterilized samples also maintained their thermal and mechanical properties post-sterilization. In addition, gamma sterilized PGS films did not induce any toxicity when films were in contact with murine fibroblast 313 cells. PGS is compatible for all the sterilization methods used in this study, which is of relevance for the wider application of PGS in medical devices. (C) 2013 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.steril
Keywords: Biocompatibility; Biopolymers; Gamma irradiation; Poly(glycerol sebacate); Sterilization

Strain hardening of various polymer melts - Münstedt, Helmut (AIP Conference Proceedings, 2023)
Various strain-hardening features of polymer melts in uniaxial extension are described. Of special interest is the dependence of strain hardening on elongational rate. Long-chain branched polyethylene, commercial polystyrenes and their blends with high molar mass components exhibit strain hardening becoming more pronounced with increasing strain rate. For linear polypropylenes, strain hardening is not found within the experimental window. Adding a small amount of a linear polyethylene with ultrahigh molar mass (UHMWPE) results in strain hardening increasing with decreasing rate. Rouse times are used to qualitatively interpret the experimental results on polystyrene. The non strain hardening behavior of linear PP and HDPE can be made plausible by the Rouse model. But for a qualitative understanding of the rate dependence of strain hardening of the PP/UHMWPE blend, the existence of a separate phase of the minor component and special deformation processes at the interface with the matrix have to be postulated.
CRIS-Team Scopus Importer:2023-07-21

Strain Sensing, Electromagnetic Shielding, and Antimicrobial Performance of Triple Hierarchic Fabric Coated with Agnws and Polydopamine - Qu, Muchao; Luo, Ziying; Chen, Hongji; Qin, Yijing; Yang, Guanda; Nilsson, Fritjof; Han, Lei (2025)
https://cris.fau.de/converis/publicweb/Publication/319020054
Keywords: fabric; Silver Nanowires; Polydopamine; strain sensors; electromagnetic shielding

Strengthening mechanism of PDLLA coated titania foam - Fiedler, Thomas; Fisher, M.; Roether, Judith; Belova, I. V.; Samtleben, T.; Bernthaler, T.; Murch, G. E.; Boccaccini, Aldo R. (Mechanics of Materials, 2014)
This paper addresses the numerical analysis of the mechanical properties of titania foam intended for use in tissue engineering scaffolds. Special focus is given to a PDLLA coating that has been shown to distinctly increase the mechanical strength of the scaffold. Micro-computed tomography (μCT) data of a real scaffold are obtained and converted into numerical calculation models. Finite element simulations are performed alternately with and without the PDLLA coating. In addition, a strut model containing a single micro-crack is analysed. Numerical results indicate that filling the crack with PDLLA significantly increases the strength of the strut by attenuating stress concentrations. © 2013 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2014.tech.IW.LM.streng
Keywords: Biomaterial; Composite material; Finite element analysis; Micro-computed tomography; Micro-structure

Stress relaxation amplitude of hydrogels determines migration, proliferation, and morphology of cells in 3-D culture - Hazur, Jonas; Endrizzi, Nadine; Schubert, Dirk W.; Boccaccini, Aldo R.; Fabry, Ben (Biomaterials Science, 2021)
The viscoelastic behavior of hydrogel matrices sensitively influences the cell behavior in 3-D culture and biofabricated tissue model systems. Previous reports have demonstrated that cells tend to adhere, spread, migrate and proliferate better in hydrogels with pronounced stress relaxation. However, it is currently unknown if cells respond more sensitively to the amplitude of stress relaxation, or to the relaxation time constant. To test this, we compare the behavior of fibroblasts cultured for up to 10 days in alginate and oxidized alginate hydrogels with similar Young's moduli but diverging stress relaxation behavior. We find that fibroblasts elongate, migrate and proliferate better in hydrogels that display a higher stress relaxation amplitude. By contrast, the cells' response to the relaxation time constant was less pronounced and less consistent. Together, these data suggest that it is foremost the stress relaxation amplitude of the matrix that determines the ability of cells to locally penetrate and structurally remodel the matrix on a molecular level, which subsequently leads to better spreading, faster migration, and higher cell proliferation. We conclude that the stress relaxation amplitude is a central design parameter for optimizing cell behavior in 3-D hydrogels.
CRIS-Team WoS Importer:2021-12-10

Structural Analysis of Chain Extended Poly(ethylene terephthalate) from Rheological Data - Härth, Michael; Majewski, Jürgen; Schubert, Dirk W. (13th Bayreuth Polymer Symposium, 2013)

Structural Investigations of Self-Assembled Monolayers for Organic Electronics: Results from X-ray Reflectivity - Khassanov, Artöm; Steinrück, Hans-Georg; Schmaltz, Thomas; Magerl, Andreas; Halik, Marcus (Accounts of Chemical Research, 2015)
Self-assembled monolayers (SAMs) have been established as crucial interlayers and electronically active layers in organic electronic devices, such as organic light emitting diodes (OLEDs), organic photovoltaics (OPVs), organic thin film transistors (OTFTs), and nonvolatile memories (NVMs). The use of self-assembling functionalized organic molecules is beneficial due to mainly three advantages compared with common thin film deposition approaches. (1) Molecular self-assembly occurs with surface selectivity, determined by the interaction between the functional anchor group of the organic molecules and the target surface. (2) The film thickness of the resulting layers is perfectly controllable on the angstrom scale, due to the self-terminating film formation to only a single molecular layer. And finally, (3) the wide variability in the chemical structure of such molecules enables different SAM functionalities for devices, ranging from electrical insulation to charge storage to charge transport. The SAM approach can be further expanded by employing several functionalized molecules to create mixed SAMs with consequently mixed properties. The function of SAMs in devices depends not only on the chemical structure of the molecules but also on their final arrangement and orientation on the surface. A reliable and nondestructive in-depth characterization of SAMs on nonconductive oxide surfaces is still challenging because of the very small thickness and the impracticality of methods such as scanning tunneling microscopy (STM) and X-ray photoelectron spectroscopy (XPS). In this Account, we illustrate how X-ray reflectivity (XRR) provides analytical access to major questions of SAM composition, morphology, and even formation by means of investigations of pure and mixed SAMs based on phosphonic acids (PAs) of various chain structures on flat alumina (AlOx) surfaces. XRR is an analytical method that provides access to spatially averaged structural depth profiles over a relatively large area of several square micrometers. The key outcome of XRR, the surface-normal electron density profile of the SAMs, leads to precise information on the SAM thickness with subangstrom resolution and allows for the determination of molecular tilt angles and packing densities. We have systematically increased the chemical complexity of PA molecules and the resulting SAMs, utilizing XRR to provide insight into the SAM structures. In SAMs composed of functionalized molecules or complex chain structures, the distribution of electron rich and electron poor signatures is detected and thus the molecular order within the SAM is determined. In mixed SAMs of two different molecular species, electron density profiles reveal the morphology and how the surface-normal structure changes if one component of the mixed SAM is altered. Furthermore, XRR was applied to investigate in situ the self-assembly of functionalized PA molecules from solution by tracking the monolayer growth over time. Even though the results provided by XRR on in-plane molecular arrangement are limited, it presents excellent information on the molecular scale along the surface normal and in addition allows for drawing conclusions on the intermolecular interactions within the SAM.

Structure changes of aligned carbon nanotubes in thermoplastics below percolation revealed by impedance spectroscopy - Qu, Muchao; Terasa, Maik-Ivo; Adelung, Rainer; Schubert, Dirk W. (Applied Nanosciene, 2018)
Keywords: Impedance spectroscopy; Melt spinning; Below percolation; Aligned CNTs

Studies on Recycled Polyester - Qin, Yijing; Qu, Muchao; Kaschta, Joachim; Allen, Vincent; Schubert, Dirk W. (Textile Science and Clothing Technology, 2019)
In this chapter, poly(ethylene terephthalate) (PET) melt-spun fibres from five different PET materials were fabricated by a capillary rheometer, which was equipped with an air aspirator for aerodynamic stretching. Two recycled PET of coloured rPET-A and clear rPET-B from waste PET bottle flakes were used, and three virgin PET with different grades of the bottle-grade vPET-2, fibre-grade vPET-1 and fibre-grade vPET-3 were chosen as reference benchmark. During the extrusion process, two processing temperatures of 270 and 280 °C in the capillary rheometer were applied, combined with six different take-up pressures from 0.5 to 3.0 bar for fibre stretching during the spinning process. An empirical equation was given, to predict the water content of PET materials under the specific drying temperature and drying time. Afterwards, the characteristics of the raw materials and drawn PET fibres were discussed comprehensively from the perspective of thermal behaviour, molar mass characteristic, rheological properties, surface morphology, diameter, tenacity and elongation at break. rPET-B and vPET-1 materials yielded optimal spinnability and demonstrated to be the most suitable materials to fabricate fibres with a desirable tenacity, an outstanding elongation at break and an excellent fibre fineness. Crystallinity and orientation of fibres from these two materials were explored to give a potential explanation for the higher tenacity. Furthermore, performance-reliability plots were applied, and a semi-empirical equation was suggested for the first time relating the tenacity and elongation at break of fibres. This study proves the possibility to produce PET fibres from bottle-grade recycled co-polymer PET material, which have similar properties as fibres produced from fibre-grade virgin homo-polymer PET. All the specific information of the five investigated PET materials, especially rPET-B and vPET-1, can provide guidance for melt spinning process in the futur
Keywords: Recycled PET Virgin PET Melt spinning Thermal behaviour Viscosity Surface morphology Mechanical property Semi-empirical equation

Study on the spinnability and mechanical properties of aspirator aided melt-spun binary blends polypropylene fibers - Qu, Muchao; Qin, Yijing; Zhu, Kai; Schubert, Dirk W.; Lu, Dong; Wu, Siman; Xie, Zixin; Han, Lei; Gao, Qun; Bier, Alexander; Du, Canyi (Polymers For Advanced Technologies, 2021)
In this study, polypropylene (PP) binary blends with obviously different molecular weight were produced and melt spun using a capillary rheometer aided with an aspirator for aerodynamic stretching for the first time. A comprehensive processing map on the spinnability of all the seven PP blends regarding to three extrusion speeds and six take-up pressures was originally presented. According to a detailed investigation on the diameter information and tensile properties of all the PP fibers (modulus, tenacity, elongation at break), the optimum processing parameters of the advanced technology of aspirator for preparing PP fibers were revealed: processing temperature at 250°C, extrusion speed at 0.075 mm/s and take-up pressure at 1.5 bar. Most importantly, the reliability of a novel mathematic model was verified to predict PP fiber diameters in this study, which provides practical guidance for the research or mass production of PP blend fibers in the academia and industry.
CRIS-Team Scopus Importer:2021-08-27
Keywords: binary blends; mechanical properties; melt spinning; modeling; polypropylene

Superalloy IN625 with cellular microstructure - Fabrication route and mechanical properties - Quadbeck, Peter; Kaschta, Joachim; Singer, Robert (Advanced Engineering Materials, 2004)
Cellular microstructures are of special interest for applications in filtering, heat transfer or acoustic absorption. In the present paper a new route for the preparation of such structures from superalloys will be presented. Polyoxymethylene (POM) is used as space holder which can be injection molded into any desired shape. Densification of the cell walls and struts is achieved by supersolidus liquid phase sintering (SLPS).

Superior sensitive, high-tensile flexible fabric film strain sensor - Wang, Xin; Liu, Xian Hu; Ge, Xiao; Schubert, Dirk W. (Composites Part A-Applied Science and Manufacturing, 2023)
Developing strain sensor with higher sensitivity and larger monitoring range is urgently needed for meeting the increasing potential applications of high-performance sensors in intelligent electronics, motion signal analysis and human monitoring. Herein, via an advanced and efficient method about embedding silver nanowires on electrospun thermoplastic polyurethane fabric film modified with carbon black, a high-performance flexible strain sensor is fabricated. The strain sensor exhibits excellent electrical response abilities of the superior sensitivity (gauge factor >16,000) with strain of 360%, an ultra-wide strain range (0.1% to 200%) and outstanding durability and reliability (>10,000 cycles) under cyclic stretching-recovering operating. Furthermore, mathematical fitting models about variation of resistance (ΔR/R0) and gauge factor upon the applied strains during the stretching process are proposed, which can quantitatively describe and analysis the variation of conductive pathways and inter-particles distance under the external stimuli. It is expected that such fitting models can be used to predict conductive sensing behaviors of flexible strain sensors for actual manufacturing and improvement of products.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Electrospinning; Fitting models; Silver nanowires; Strain sensor

Superoleophilic Magnetic Iron Oxide Nanoparticles for Effective Hydrocarbon Removal from Water - Sarcletti, Marco; Vivod, Dustin; Luchs, Tobias; Rejek, Tobias; Portilla Berlanga, Luis; Müller, Lukas; Dietrich, Hanno; Hirsch, Andreas; Zahn, Dirk; Halik, Marcus (Advanced Functional Materials, 2019)
Various hydrocarbons are efficiently extracted from water by using a new sorbent material based on covalently functionalized magnetic nanoparticles. The functionalization of the magnetite nanoparticles with a self‐assembled monolayer of hexadecylphosphonic acid renders the nanoparticles oleophilic and the magnetic nature of magnetite allows for simple extraction of the hydrocarbon‐soaked sorbent. The sorbent material is capable of extracting single contaminants such as alkanes and aromatics and complex hydrocarbon mixtures such as crude oils in high extraction rates of up to 14 times the sorbent volume. Experimental results are explained by molecular dynamics simulations on the adsorption of single components from a hydrocarbon‐water mixture to the alkylphosphonic acid layer on the nanoparticles. The core–shell sorbent material is highly stable and therefore, reusable over several successive extraction cycles without degradation. The extraction performance is determined at different water temperatures, different water sources, and different magnetic core materials and evaluated compared to heptadecanoic acid functionalized magnetite. The new sorbent material provides the opportunity for an efficient, reliable, inexpensive, and environmental friendly removal of hydrocarbons from wate
Keywords: magnetic nanoparticles; functionalized nanoparticles; oil extraction; water remediation; phosphonic acids

Suppression of Hysteresis Effects in Organohalide Perovskite Solar Cells - Hou, Yi; Scheiner, Simon; Tang, Xiaofeng; Gasparini, Nicola; Richter, Moses; Li, Ning; Schweizer, Peter; Chen, Shi; Chen, Haiwei; Ramírez Quiroz, César Omar; Du, Xiaoyan; Matt, Gebhard; et al. (Advanced Materials Interfaces, 2017)
Thin-film solar cell based on hybrid perovskites shows excellent light-to-power conversion efficiencies exceeding 22%. However, the mixed ionic-electronic semiconductor hybrid perovskite exhibits many unusual properties such as slow photocurrent instabilities, hysteresis behavior, and low-frequency giant capacitance, which still question us so far. This study presents a direct surface functionalization of transparent conductive oxide electrode with an ultrathin ≈2 nm thick phosphonic acid based mixed C60/organic self-assembled monolayer (SAM) that significantly reduces hysteresis. Moreover, due to the strong phosphonates bonds with indium tin oxide (ITO) substrates, the SAM/ITO substrates also exhibit an excellent recyclability merit from the perspective of cost effectiveness. Impedance studies find the fingerprint of an ion-based diffusion process in the millisecond to second regime for TiO2-based devices, which, however, is not observed for SAM-based devices at these low frequencies. It is experimentally demonstrated that ion migration can be considerably suppressed by carefully engineering SAM interfaces, which allows effectively suppressing hysteresis and unstable diode behavior in the frequency regime between ≈1 and 100 Hz. It is suggested that a reduced density of ionic defects in combination with the absence of charge carrier accumulation at the interface is the main physical origin for the reduced hysteresis.

Supraparticles with a Mechanically Triggerable Color-Change-Effect to Equip Coatings with the Ability to Report Damage - Wenderoth, Sarah; Eigen, Andreas; Wintzheimer, Susanne; Prieschl, Johannes; Hirsch, Andreas; Halik, Marcus; Mandel, Karl (Small, 2022)

Surface Modification of SPIONs in PHBV Microspheres for Biomedical Applications - Idris, Maizlinda Izwana Binti; Zaloga, Jan; Detsch, Rainer; Roether, Judith; Unterweger, Harald; Alexiou, Christoph; Boccaccini, Aldo R. (Scientific Reports, 2018)
Surface modification of superparamagnetic iron oxide nanoparticles (SPIONs) has been introduced with lauric acid and oleic acid via co-precipitation and thermal decomposition methods, respectively. This modification is required to increase the stability of SPIONs when incorporated in hydrophobic, biodegradable and biocompatible polymers such as poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV). In this work, the solid-in-oil-in-water (S/O/W) emulsion-solvent extraction/evaporation method was utilized to fabricate magnetic polymer microspheres incorporating SPIONs in PHBV. The prepared magnetic PHBV microspheres exhibited particle sizes <1 mu m. The presence of functional groups of lauric acid, oleic acid and iron oxide in the PHBV microspheres was confirmed by Fourier Transform Infrared spectroscopy (FTIR). X-ray diffraction (XRD) analysis was performed to further confirm the success of the combination of modified SPIONs and PHBV. Thermogravimetric analysis (TGA) indicated that PHBV microspheres were incorporated with SPIONs(Lauric) as compared with SPIONs(Oleic). This was also proven via magnetic susceptibility measurement as a higher value of this magnetic property was detected for PHBV/SPIONs(Lauric) microspheres. It was revealed that the magnetic PHBV microspheres were non-toxic when assessed with mouse embryotic fibroblast cells (MEF) at different concentrations of microspheres. These results confirmed that the fabricated magnetic PHBV microspheres are potential candidates for use in biomedical applications.
Keywords: biomedical materials; cell culture; superparamagnetic iron oxide nanoparticles

Surface Modifications of Polyetheretherketone (PEEK): Results from the Literature and Special Studies of Copper-Coated Films - Münstedt, Helmut; Grossmann, Joern (Polymers, 2022)
For some challenging applications of the high-performance thermoplastic polyetheretherketone (PEEK) in engineering or medical fields, the bonding to other materials is important. In these cases, modifications of the inert polymer surface are often necessary. Results from the literature with respect to sandblasting, corona discharge, plasma treatment, excimer-laser irradiation, and chromium-sulfuric-acid etching are described and discussed. Our own detailed studies of these methods under well-defined experimental conditions are reported, which make their comparability possible and support the assessment for certain applications. PEEK films coated with copper are of special interest due to their potential for flexible electronics. Copper foils glued by an epoxy resin and copper layers from physical vapor deposition are compared with respect to their mechanical adhesion. Surface properties were characterized with respect to roughness, contact angle, and oxygen-to-carbon (O/C) ratio. The latter has been found to be the most decisive parameter for good adhesion. It was shown that an enhancement of the O/C ratio can be achieved in several ways. The advantages and disadvantages of the methods applied are discussed under various aspects of applications.
CRIS-Team Scopus Importer:2022-12-02
Keywords: bonding properties; copper layers; polyetheretherketone; surface analysis; surface treatment

Suture-ability of patch grafts for ocular surface reconstruction - Küng, Florian; Fuchsluger, Thomas; Schubert, Dirk W. (Polychar, 2017)

Suture retension test method for opthalmological materials - Voigt, Monika; Thieme, Daniel; Küng, Florian; Schubert, Dirk W.; Kruse, Friedrich; Fuchsluger, Thomas (Deutsche Gesellschaft für Biomaterialien, 2018)
Keywords: biomaterialien; espinning suture retension

Synergistic effects between carbon nanotube and anisotropy-shaped Ni in polyurethane sponge to improve electromagnetic interference shielding - Cheng, Haoran; Pan, Yamin; Wang, Tiecheng; Zhou, Yang; Qin, Yijing; Liu, Chuntai; Shen, Changyu; Liu, Xianhu (Science China Materials, 2023)
Ingenious microstructural design and suitable multicomponent strategy remain challenging for efficient absorption-dominated electromagnetic interference (EMI) shielding materials with light weight, low filling levels and thin sample thickness. Herein, a flexible waterborne polyurethane (WPU)/dielectric carbon nanotube (CNT)/magnetic anisotropic Ni (chain or flower) EMI shielding composite sponge based on the unique shielding capsule structure was constructed by a dip-coating process. The results show that increasing the Ni (flower or chain) filler content significantly improves the electrical conductivity and EMI shielding properties of composites. The EMI shielding performances of WPU/CNT/8 wt% Ni flower-melamine foam (MF) and WPU/CNT/8 wt% Ni chain-MF are 42.8 and 46.7 dB, respectively, which exceed those of the composite sponge with only CNTs. The synergistic effect between CNTs and Ni (flower or chain) means that the main EMI shielding mechanism of the composite sponge comes from the absorption process. Importantly, owing to the protection of the WPU layer, the composites exhibit excellent EMI shielding effectiveness (SE) even under severe physical and chemical degradation. This research provides a simple synergistic approach for the design of novel, lightweight, and efficient EMI shielding composites, which show great promise for applications in portable and wearable electronic devices. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-04-28
Keywords: anisotropy-shaped Ni; carbon nanotubes; electrical properties; electromagnetic interference shielding; polymer-matrix composites

Synthesis and Characterization of New Long-Wavelength-Absorbing Oxonol Dyes from the 2,2-Difluoro-1,3,2-dioxaborine Type - Halik, Marcus; Hartmann, Horst (Chemistry - A European Journal, 1999)

Synthesis and Characterization of Novel Ethylene-graft-Ethylene/Propylene Copolymers - Stadler, Florian; Arikan, Burçak; Kaschta, Joachim; Kaminsky, Walter; Münstedt, Helmut (Macromolecules, 2011)
A sequential metallocene-catalyzed synthesis of ethylene/propylene macromers, which are subsequently incorporated into growing polyethylene chains, leads to comb-like polymers. After the synthesis, a Soxhlet extraction ensures the purity of the sample. The GPC-MALLS analysis reveals narrowly distributed samples with a non-negligible degree of branching. The comb polymers show a very high viscosity, which significantly differs from conventional long-chain branched metallocene polyethylenes (LCB-mPE) but is in agreement with findings on comb model polymers. The zeroshear rate viscosity eta(o) lies significantly above the relation between M(w) and eta(o) for linear and for conventional LCB-mPE. The thermorheological behavior is complex and differs from that observed for LCB-mPE but also does not resemble an LDPE-like thermorheological behavior.

Synthesis, Morphology and Thermal Properties of Electrospun PHB/PCL/Silica Hybrid Fibermats with and without Calcium Addition - Ding, Yaping; Roether, Judith; Schubert, Dirk W.; Boccaccini, Aldo R. (13th Bayreuth Polymer Symposium, Bayreuth, 2013)

Tailored modification of flow behavior and processability of polypropylene powders in SLS by fluidized bed coating with in-situ plasma produced silica nanoparticles - Gomez Bonilla, Juan Sebastian; Trzenschiok, Holger; Lanyi, Franz; Schubert, Dirk W.; Bück, Andreas; Schmidt, Jochen; Peukert, Wolfgang (30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019, 2019)
The processability of selective laser sintering (SLS) powders and the characteristics of the generated parts depend amongst others on the flowability. To increase the flowability, SLS powders are usually functionalized with flowing agents. Flowing agents are typically applied by dry particle coating. The optimization of the process parameters necessary to achieve a homogenous coating avoiding segregation is still empirical. In this contribution, an alternative process to particle dry coating is presented. This process integrates the synthesis of silica nanoparticles via plasma enhanced chemical vapor deposition (PECVD) and coating of polymer host particles in a fluidized bed in a single process. The influence of the treatment time on the packing density and flow behavior of the powders is investigated. Test specimen are produced to assess the influence of the treatment on the processability of the powders and the mechanical properties of the produced parts. © Solid Freeform Fabrication 2019: Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019. All rights reserve
Keywords: Additives; Coatings; Compressive strength; Fluidized bed process; Laser heating; Nanoparticles; Plasma CVD; Plasma enhanced chemical vapor deposition; Polypropylenes; Powders; Selective laser sintering; Silica; Silica nanoparticles; Sintering; Synthesis (chemical); Alternative process; Dry-particle coating; Fluidized bed coating; Homogenous coatings; Packing density; Process parameters; Selective laser sintering (SLS); Fluidized beds

Tailoring elastic properties of PLGA/TiO2 biomaterials - Fiedler, Thomas; Belova, I. V.; Murch, G. E.; Roether, Judith; Boccaccini, Aldo R. (Computational Materials Science, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.tailor

Targeted Printing of Cells: Evaluation of ADA-PEG Bioinks for Drop on Demand Approaches - Karakaya, Emine; Bider, Faina; Frank, Andreas; Teßmar, Jörg; Schöbel, Lisa; Forster, Leonard; Schrüfer, Stefan; Schmidt, Hans-Werner; Schubert, Dirk W.; Blaeser, Andreas; Boccaccini, Aldo R.; Detsch, Rainer (Gels, 2022)
A novel approach, in the context of bioprinting, is the targeted printing of a defined number of cells at desired positions in predefined locations, which thereby opens up new perspectives for life science engineering. One major challenge in this application is to realize the targeted printing of cells onto a gel substrate with high cell survival rates in advanced bioinks. For this purpose, different alginate-dialdehyde—polyethylene glycol (ADA-PEG) inks with different PEG modifications and chain lengths (1–8 kDa) were characterized to evaluate their application as bioinks for drop on demand (DoD) printing. The biochemical properties of the inks, printing process, NIH/3T3 fibroblast cell distribution within a droplet and shear forces during printing were analyzed. Finally, different hydrogels were evaluated as a printing substrate. By analysing different PEG chain lengths with covalently crosslinked and non-crosslinked ADA-PEG inks, it was shown that the influence of Schiff’s bases on the viscosity of the corresponding materials is very low. Furthermore, it was shown that longer polymer chains resulted in less stable hydrogels, leading to fast degradation rates. Several bioinks highly exhibit biocompatibility, while the calculated nozzle shear stress increased from approx. 1.3 and 2.3 kPa. Moreover, we determined the number of cells for printed droplets depending on the initial cell concentration, which is crucially needed for targeted cell printing approaches.<br
Keywords: bioprinting; drop on demand; sodium alginate; polyethylene glycol; shear stress

Technologies for Multilayered Scaffolds Suitable for Interface Tissue Engineering - Nooeaid, Patcharakamon; Roether, Judith; Weber, Eva; Schubert, Dirk W.; Boccaccini, Aldo R. (Advanced Engineering Materials, 2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.techno

The evaluation of physical properties and in vitro cell behavior of PHB/PCL/sol-gel derived silica hybrid scaffolds and PHB/PCL/fumed silica composite scaffolds - Ding, Yaping; Yao, Qingqing; Li, Wei; Schubert, Dirk W.; Boccaccini, Aldo R.; Roether, Judith (Colloids and Surfaces B: Biointerfaces, 2015)
PHB/PCL/sol-gel derived silica hybrid scaffolds (P5S1S) and PHB/PCL/fumed silica composite scaffolds (P5S1N) with a 5:1 organic/inorganic ratio were fabricated through a combination of electrospinning and sol-gel methods and dispersion electrospinning, respectively. In contrast to the silica nanoparticle aggregates appearing on the fiber surface of P5S1N, smooth and uniform fibers were obtained for P5S1S. The fiber diameter distribution, tensile strength, thermal gravimetric analysis (TGA), and cellular behavior of both types of scaffolds were characterized and studied. The tensile strength results and TGA indicated that the interfacial interaction between the organic and the inorganic phase was enhanced in P5S1S over the nanocomposite scaffolds, and cells exhibited significantly higher alkaline phosphate activity (ALP) for P5S1S, which makes P5S1S hybrid scaffolds candidate materials for bone tissue engineering applications.
Keywords: Bone tissue engineering; Electrospinning; Hybrid; Nanoparticle; Silica; Sol-gel

The Impact of Self-Assembled Monolayer Thickness in Hybrid Gate Dielectrics for Organic Thin-Film Transistors - Jedaa, Abdesselam; Burkhardt, Martin; Zschieschang, Ute; Klauk, Hagen; Habich, Dana; Schmid, Günter; Halik, Marcus (Organic Electronics, 2009)
We have investigated the electrical characteristics of hybrid dielectrics with a thickness of 6 nm or less that are composed of a plasma-grown aluminum oxide (AlOx) layer and a self-assembled monolayer (SAM) of an aliphatic phosphonic acid. The impact of the quality of the AlOx layer on the insulating properties of the double-layer dielectrics was assessed by comparing two different oxidation procedures, and the influence of the thickness of the organic SAM was evaluated by employing molecules with five different chain lengths. In order to decouple the relative contributions of the oxide and the SAM to the performance of the double-layer dielectrics we have also performed cyclic voltammetry measurements on indium tin oxide (ITO)/SAM devices without AlOx layer. Finally, we have evaluated how the quality of the AlOx layer and the thickness of the SAM affect the performance of low-voltage organic thin-film transistors (TFTs) that employ the thin AlOx/SAM dielectrics as the gate dielectric. The results confirm the important role of the SAM in determining the breakdown voltage, in limiting the current density, and in compensating the somewhat lower quality of AlOx layers produced under mild plasma conditions.

The influence of boron nitride shape and size on thermal conductivity, rheological and passive cooling properties of polyethylene composites - Wang, Yiding; Zhang, Wenrui; Feng, Mingjie; Qu, Muchao; Cai, Zhenghao; Yang, Guanda; Pan, Yamin; Liu, Chuntai; Shen, Changyu; Liu, Xianhu (Composites Part A-Applied Science and Manufacturing, 2022)
The shape and particle size of the filler are highly relevant to the composite's performance and application. We herein report the role of boron nitride (BN) shapes and sizes for polyethylene composites on the rheological properties, thermal conductivity (TC) and passive cooling via melt blending. Fillers with large sizes are adverse to form a rheological network in the composites, but they are beneficial to high thermal conductivity and their maximum increase (1.535 Wm−1K−1) relative to the matrix is 256%. Additionally, due to the high solar reflectance (90%) and thermal emittance (85%), the composites endow a cooling performance of 4 °C at daytime and 10 °C at night compared to the contrast temperature in the device. This work is helpful to provide guidance for the optimization of BN fillers for applications in the fields of thermal management and passive cooling.
CRIS-Team Scopus Importer:2022-08-12
Keywords: A. Polymer-matrix composites (PMCs); B. Rheological properties; B. Thermal properties; Passive cooling

The influence of nanoparticles and their functionalization on the dielectric properties of biaxially oriented polypropylene for power capacitors - Streibl, Maximilian; Werner, Siegfried; Kaschta, Joachim; Schubert, Dirk W.; Moos, Ralf (IEEE Transactions on Dielectrics and Electrical Insulation, 2020)
In this work, eleven commercially available nanoparticles are benchmarked against each other according to their potential for an application in a polypropylene (PP) based nanocomposite for thin film power capacitors. Biaxially oriented films containing a fixed concentration of 5 wt%. Al2O3, TiO2, SiO2, or POSS nanoparticles with different surface functionalization were analyzed by dielectric spectroscopy and dielectric breakdown measurements. Two particle systems emerged to increase both the dielectric breakdown strength and the reliability of the films combined with low dielectric losses. The effects of the particles were in agreement with the multicore model of Tanaka et al. The particle dispersion was analyzed on SEM images. A correlation between agglomerates and zeta potential in isopropanol was found yielding a quick analysis tool for the tendency of nanoparticles to form clusters during processing with PP. To assure comparability between the films, the real particle content was determined by incineration. The surface roughness of the film has a large influence on the breakdown behavior and was, therefore, also monitored.
CRIS-Team Scopus Importer:2020-04-14
Keywords: dielectric breakdown; dielectric films; dielectric losses; dielectric materials; nanocomposites

The morphology of integrated self-assembled monolayers and their impact on devices – A computational and experimental approach - Novak, Michael; Jäger, Christof; Rumpel, Armin; Kropp, Henning; Peukert, Wolfgang; Clark, Timothy; Halik, Marcus (Organic Electronics, 2010)
We report on a combined experimental and computational study on self-assembled monolayers (SAMs). The dielectric properties of SAMs based on n-alkyl phosphonic acids in large area thin film devices (organic field-effect transistors with good hole mobilities up to 0.3 cm² V−1 s−1 at −1 V and capacitors) depend on their chain length, but not consistently to theoretical pictures of tunneling through saturated n-alkanes. An unexpected saturation of current density with increasing chain length was obtained in devices, what impact on the leakage current in transistors and current density in capacitors. This is attributed to different self-assembled monolayer morphology ranging from an amorphous state for short alkyl chains to a quasi-crystalline state for longer alkyl chains. Molecular dynamics (MD) simulations provide a deeper insight into the nature of the three-dimensional intermolecular interactions and support the proposed SAM morphology. The change in morphology leads to a reduced effective SAM thickness in devices, which could be described by a Simmons approach quantitatively. The morphological aspect of self-assembled molecules is of enormous importance beyond the applications of SAMs in low-voltage, high mobility organic transistors because of it’s relevance for the hole field of molecular scale electronics. It demonstrates that even small changes in the molecular design can change the molecular interactions and monolayer assembly.

The mutual influence of surface energy and substrate temperature on the saturation mobility in organic semiconductors - Sarcletti, Marco; Schmaltz, Thomas; Halik, Marcus (Organic Electronics, 2014)
We report on a mutual correlation between the substrate temperature during semiconductor deposition and the surface energy of the gate dielectric on the charge carrier mobility in bottom gate top contact organic field effect transistors (OFETs) with N,N′-diphenyl-3,4,9,10-perylene tetracarboxylic diimide (DP-PDI) as organic semiconductor. The gate dielectric consists of a thin gate aluminum oxide and a self-assembled monolayer (SAM) with which the surface energy of the hybrid dielectric is tuned. The substrate temperature during evaporation of the DP-PDI semiconductor was systematically varied to obtain the best charge carrier mobility for each SAM. We found that the optimum substrate temperature correlates with the surface energy. Devices with low surface energy reach best mobility at higher substrate temperatures than devices with a higher surface energy.

Theoretical and experimental study of the dynamic percolation behaviour of carbon black filled polymethylmethacrylate prior and after shear - A novel three phase approach - Krückel, Johannes; Schubert, Dirk W. (European Polymer Journal, 2014)
The time-dependent increase of the electrical conductivity (dynamic percolation) of carbon black filled polymethylmethacrylate under quiescent conditions was studied theoretically and experimentally. Therefore, a three phase model based on two different aggregate sizes is proposed leading to manageable fit functions, which are able to describe the experimental data. In order to test the model, the time-dependent electrical conductivity of the composites was monitored prior and after a short shear step. It was found that the shear step leads to a significant change in the conductivity and influences the aggregation kinetics of the system which is in agreement with our physical model proposed. Moreover, it could be shown, that the model has a much higher accuracy in describing the experimental data compared to the existing aggregation models where only one aggregate size is considered. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Dynamic percolation; Conductive composites; Aggregation model; Electrical conductivity

The potential of molecular self-assembled monolayers in organic electronic devices - Halik, Marcus; Hirsch, Andreas (Advanced Materials, 2011)
Functionalized molecules that organize to self-assembled monolayers (SAMs) are gaining importance in organic electronic devices. They are fully compatible with flexible substrates, are amenable to low-cost processing, and show reliable film-forming behavior. Highly integrated devices, such as sensor arrays or memories, have also been demonstrated. Starting from auxiliary layers, which improve and modify surfaces and interfaces in traditional thin-film devices, the applications of SAMs develop towards molecular scale electronics, including active molecular device layers and multifunctional SAMs, which fulfill several layer functions of a device within one monolayer. Mixed SAMs make new and tunable device features possible, by stoichiometric control of the composition of different SAM-forming molecules. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

The relationship between exponent t in McLachlan equation and electronic percolation thresholds of solution cast films - Xu, Huagen; Qu, Muchao; Chen, Baoquan; Yang, Qiancheng; Schubert, Dirk W. (Journal of Polymer Research, 2022)
To better understand the relationship between the exponent t in McLachlan's GEM equation and the percolation threshold of conductive polymer composites, in this work, a series of percolation threshold and exponent t pairs were obtained from the percolation curves of different carbon-based fillers utilizing the McLachlan equation. In particular, pairs derived perpendicular and in-plane to the films for binary composite films with carbon fiber of different aspect ratios (AR) as well as pairs derived perpendicular for ternary composite films with different polymer blends and different polymer blend ratios for both carbon black and carbon nanotubes filler were investigated. In these systems, the exponent t for all three fillers is different from the value of 2.0 often referred to as “universal”. Scanning electron microscopy was used to reveal the microscopic morphology of different shape fillers in the solution cast composite films. A schematic diagram was used to illustrate the differences in the conductive pathways formed by different conductive fillers.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Carbon-based fillers; Conductive polymer composite films; Exponent t; McLachlan GEM equation; Percolation thresholds

The relationship between threshold voltage and dipolar character of self-assembled monolayers in organic thin-film transistors - Salinas Batallas, Michael; Jäger, Christof; Yousefi Amin, Atefeh; Dral, Pavlo; Meyer-Friedrichsen, Timo; Hirsch, Andreas; Clark, Timothy; Halik, Marcus (Journal of the American Chemical Society, 2012)
We report a quantitative study that describes and correlates the threshold voltage of low-voltage organic field-effect transistors with the molecular structure of self-assembled monolayer dielectrics. We have observed that the component of the dipole moment of such self-assembled molecules perpendicular to the surface correlates linearly with the threshold voltage shift in devices. The model was validated using three different organic semiconductors (pentacene, α,α′-dihexylsexithiophene, and fullerene-C ) on six different self-assembled monolayers. The correlation found can help optimize future devices, by tuning the dipole moments of the molecules that constitute the self-assembled monolayer. © 2012 American Chemical Society.

The remediation of nano-/microplastics from water - Sarcletti, Marco; Park, Hyoungwon; Wirth, Janis; Englisch, Silvan; Eigen, Andreas; Drobek, Dominik; Vivod, Dustin; Friedrich, Bernhard; Tietze, Rainer; Alexiou, Christoph; Zahn, Dirk; Apeleo Zubiri, Benjamin; et al. (Materials Today, 2021)
Nano-/microplastics (NP) is a human-made emerging contaminant with worldwide occurrence. The small size (below one micrometer), the different chemical nature and the persistence make NP to potential hazards with suspect probability of tissue penetration and inflammation or as accumulator for toxins. A strategy to stop the spill of novel NP is the remediation from waste water or rivers as prominent distributors. We have developed core–shell superparamagnetic iron oxide nanoparticles (SPIONs) that attract NP and glue them to larger agglomerates which then can be removed from water by applying an external magnetic field. The shell molecules provide two interaction motifs towards NP. The tuned surface potential of the functionalized SPIONs attract complementary charged NP efficiently and the n-alkyl chain is dedicated to preferential interaction towards organic NP rather than inorganic particles. Structural analytics and molecular dynamics simulation support the proposed concept. Systematic remediation experiments with different NP (chemical structures, sizes and mixtures), from different waters – including river water – and with different SPION core materials indicate a universal validity of the concept, with best remediation performance for mixed NP. We suggest a method for broadband remediation of various NP with simple materials and processes, which both have the potential to be up-scaled.<br

Thermal and Morphological Properties of Polypropylene/Styrene-Butadiene-Styrene Nanocomposites - Mubarak, Yousef; Abu-Halimeh, Rachael; Schubert, Dirk W. (Polymer-Plastics Technology and Engineering, 2018)
Polypropylene/styrene-butadiene-styrene fumed silica nanocomposites were mixed in a twin screw Brabender Plasticorder, the weight percent of the SBS was varied at (0, 5, 10, 20, and 40), and the fumed silica content was varied at (0, 0.05, 0.1, 0.5, 1, and 2) wt%. The thermal and morphological properties of these nanocomposites were studied using a differential scanning calorimetry and a polarized light microscopy. It has been found that the addition of styrene-butadiene-styrene or fumed silica nanoparticles alone to polypropylene did not change the melting temperature while the existence of both elements changed the melting temperature of polypropylene slightly. Also, increasing the percentage of fumed silica nanoparticles leads to an increase in the crystallization temperature while styrene-butadiene-styrene increment has no effect. The melting peaks obtained by the differential scanning calorimetry revealed that increasing the styrene-butadiene-styrene content reduces the percentage crystallinity as a result of increasing the amorphous portion. The addition of styrene-butadiene-styrene to polypropylene has a very slight effect on the relative percentage crystallinity when calculations are performed based on the quantity of polypropylene within the composite. Although fumed silica nanoparticles aided and accelerating the nucleation step but it could not increase the percentage crystallinity of polypropylene beyond the percentage crystallinity of neat polypropylen
Keywords: polypropylene; styrene-butadiene-styrene; Fumed silica; nanocomposites

Thermal-Induced Percolation Phenomena and Elasticity of Highly Oriented Electrospun Conductive Nanofibrous Biocomposites for Tissue Engineering - Munawar, Muhammad; Schubert, Dirk W. (International Journal of Molecular Sciences, 2022)
Highly oriented electrospun conductive nanofibrous biocomposites (CNBs) of polylactic acid (PLA) and polyaniline (PANi) are fabricated using electrospinning. At the percolation threshold (φc), the growth of continuous paths between PANi particles leads to a steep increase in the electrical conductivity of fibers, and the McLachlan equation is fitted to identify φc. Annealing generates additional conductive channels, which lead to higher conductivity for dynamic percolation. For the first time, dynamic percolation is investigated for revealing time-temperature superposition in oriented conductive nanofibrous biocomposites. The crystallinity (χc) displays a linear dependence on annealing temperature within the confined fiber of CNBs. The increase in crystallinity due to annealing also increases the Young’s modulus E of CNBs. The present study outlines a reliable approach to determining the conductivity and elasticity of nanofibers that are highly desirable for a wide range of biological tissue applications.<br

Thermal stabilization of polypropylene by renewable antioxidants - Kröner, Richard; Kaschta, Joachim; Heiduk, Ines; Dorfmüller, Daniel; Falk, Martin; Schubert, Dirk W. (2023)
The thermal stability of recycled polypropyl- ene should be increased by using renewa- ble stabilizers known as antioxidants. These chemical compounds delay the degradation and aging of polymers by offering a hydrogen atom to the radical generated during thermal decomposition, so that the radical does not react with the polymer chain [1]. In this work the use of Irganox 1010 (industry standard), lignin and α-tocopherol (vitamin E) in polypropylene is investigated [2-4]. To assess the effectiveness of the stabilizers, the oxidation induction time (OIT) is determined according to standard (EN ISO 11357-6) [5]. The oxidation induction time is the time a polymer can resist at 200 °C until degradation occurs after the change from nitrogen to oxygen atmosphere. The objective is to increase that time to more than 10 minutes. By adding different amounts of antioxidant, a critical concentration c* is cal- culated at which the objective is achieved. A linear relationship between concentration and thermal stability is found for all systems, except for the addition of α-tocopherol. The highest thermal stability is achieved by α-to- copherol and α-tocopherol succinate, whose structures are formed on the basis of BHA (2, 6-di-tert-butyl-4-methoxyphenol) instead of BHT (2, 6-di-tert-butyl-4-methylphenol), as it is the case for the other stabilizers [4]. Compared to the industry standard (Irganox 1010) the efficiency of α-tocopherol is ten times higher in the relevant concentration level, making Vi- tamin E the most suitable antioxidant found in this research. The wood component lignin also shows good stabilization effects, but requires the tenfold concentration c* than Irganox 1010. Furthermore, the stabilized samples are ana- lysed with regard to their rheological proper- ties. At a temperature of 250 °C, that is equal to the processing temperature in the industry, degradation occurs during the measurement, so the unstabilized sample (pure PP) shows a lower viscosity compared to the stabilized sampl

Thermodynamically Consistent Model to Predict the Magneto-Rheological Behavior of Magneto-Sensitive Elastomers - Saxena, Prashant; Walter, Bastian; Kaschta, Joachim; Fey, Tobias; Steinmann, Paul; Schubert, Dirk W. (9th Annual European Rheology Conference, 2014)

Thermorheological behavior of various long-chain branched polyethylenes - Stadler, Florian; Kaschta, Joachim; Münstedt, Helmut (Macromolecules, 2008)
To analyze the thermorheological behavior of various polyethylenes, the relaxation spectra were shifted. Not only linear and short-chain branched PE but also the classical high-pressure LDPE were found to be thermorheologically simple, i.e., the activation energy E(a) is independent of the relaxation strength or the relaxation time, respectively. However, for the long-chain branched metallocene catalyzed polyethylenes investigated a significant dependence of the activation energy E(a) on the relaxation time is detected. At shorter relaxation times E(a) is very close to that of linear PE, but it increases with longer times. The lower E(a) values are assumed to be due to linear molecules and the higher ones to different species of long-chain branched molecules. These findings offer the possibility to use the analysis of the thermorheological complexity to get an insight into the branching structure of polyethylenes. For the LCB-mPE investigated, it can be concluded that they are a mixture of linear and long-chain branched chains.

Thermorheological Behavior of Various Short- and Long-Chain Branched Polyethylenes and Their Correlations with the Molecular Structure - Keßner, Ute; Kaschta, Joachim; Stadler, Florian; Le Duff, Cécile; Drooghaag, Xavier; Münstedt, Helmut (Macromolecules, 2010)
This paper deals with the characterization of a broad range of linear polyethylenes (PE) by means of thermorheology. It is demonstrated, in which way the thermorheological behavior can be related to the comonomer type and content of copolymers. In the first part of this paper, well-established analytical and theological methods are applied to distinguish linear and branched samples. The resolution limit of these methods is demonstrated by the investigation of a blend from a linear-low density PE (LLDPE) and a branched low density PE (LDPE). Special attention is paid to nuclear-magnetic resonance (NMR) spectroscopy in order to reliably determine the comonomer type and content of the samples chosen. The main focus of this paper lies on thermorheological investigations and correlations with the molecular structure. The comparatively high sensitivity of such investigations is highlighted: even small amounts of long-chain branches (LCB) are revealed. The activation energy (E(u)) of linear samples increases with growing comonomer length and content, respectively. As such, thermorheology is demonstrated to be an interesting theological "tool" to get an insight into branching structures. Moreover, the experimental effort is relatively small as solely usual dynamic-mechanical experiments at different temperatures are required.

The role of conductive pathways in the conductivity and rheological behavior of poly(methyl methacrylate)-graphite composites - Liu, Xian Hu; Pan, Yamin; Hao, Xiaoqiong; Dai, Kun; Schubert, Dirk W. (Journal of Applied Polymer Science: Applied Polymer Symposium, 2016)
Up to now, research on the dynamic process of conductive network formation has tended to focus on composite particles with one‐dimensional geometry, such as carbon black and carbon nanotubes. However, studies on this subject based on fillers with two‐dimensional structure, such as graphite, are rare in the literature. In this work, the dynamic percolation and rheological properties of poly(methyl methacrylate) (PMMA)–graphite composites under an electric field were investigated. The activation energies of conductive network formation and polymer matrix mobility were calculated from the temperature dependence of the percolation time and the zero‐shear viscosity. It was found that the activation energy calculated from the zero‐shear viscosity was not influenced by the electric field in the concentration range investigated, but the electric field had an effect on the activation energy calculated from the percolation time. This finding emphasizes that the electrical and rheological properties have different physical origins
Keywords: self-assembly; conducting polymers; rheology; composites; amorphous

Time- and temperature-dependent crosslinking behaviour of a silicone resin - Wolff, Friedrich; Kugler, Christoph; Münstedt, Helmut (Rheologica Acta, 2012)
The crosslinking behaviour of a silicone resin which is interesting from a technical point of view was investigated by means of rheology. In order to accelerate the crosslinking process, zinc acetylacetonate and aluminium acetylacetonate were applied as latent catalysts. The effect of the type of catalyst, its concentration, and the temperature on crosslinking was determined by isothermal dynamic-mechanical measurements. A radial gradient in crosslinking causes the gel point to be reached earlier at the outer edge of the sample in the rheometer. This radial gradient is averaged when measuring G′ and G''. Therefore, since the physically well-defined state of critical gelation (gel point) could not be obtained from the data, the time at which a distinct crosslinking state is reached was determined by the crossover of the moduli G′ and G''. For this distinguished point, the denotation gelation index GI is introduced. The gelation indices measured at different temperatures follow an Arrhenius-type relationship. Activation energies between 89 and 126 kJ/mol were determined. They were found to be dependent on the type of catalyst used but independent of its concentration. The activation energies of the crosslinking processes enable the calculation of the gelation index at temperatures not measured directly.
EAM Import::2019-03-12

Time-Temperature Superposition in Highly Oriented Electrospun Conductive Nanofibers of Biodegradable - Munawar, Muhammad (31st Annual Conference of the European Society for Biomaterials (ESB 2021), together with the 43rd Annual Congress of the Iberian Society of Biomechanics and Biomaterials (SIBB), Porto, 2021)

TiO2-PLLA nanocomposite coatings and free-standing films by a combined electrophoretic deposition-dip coating process - Chavez-Valdez, Alejandra; Arizmendi-Morquecho, Ana; Moreno Bello, Karla; Roether, Judith; Kaschta, Joachim; Boccaccini, Aldo R. (Composites Part B-Engineering, 2014)
TiO2/PLLA nanocomposites were prepared using a two-step process involving electrophoretic deposition (EPD) and dip coating (DC). EPD was carried out first to obtain porous TiO2 nanostructured coatings while subsequent dip coating was performed using different concentrations of PLLA in dichloromethane (DCM) to obtain nanocomposite materials. According to SEM images, cracks in the TiO2 nanostructured coatings, developed upon drying, were filled with the polymer which led to improvement of the flexibility of the nanocomposite coatings. Similarly, a surface modification from hydrophilic to hydrophobic was obtained with the addition of the polymer. FTIR analysis showed characteristic bands of both materials, TiO2 and PLLA, both on the coating surface and at the interphase between the nanocomposite coating and the substrate. Hardness measurements showed a maximum value of 1.4 GPa for TiO2-10 wt% PLLA composite. For DMTA tests, detached layers were used and the storage and loss moduli were determined. TiO2-PLLA nanocomposite coatings showed higher values of storage modulus at higher temperature in comparison to pure PLLA samples. Also, there was a shift in the glass transition temperature (T-g) with increasing TiO2 content. In conclusion, the EPD-DC combined technique proposed here enables the fabrication of nanostructured coatings and free-standing layers in which the quantity of PLLA can be changed according to the intended application, i.e. it is possible to fabricate coatings with tailored degradability and suitable mechanical properties with low additions of PLLA or free standing films with increased flexibility, biodegradability and biocompatibility with high amounts of PLLA. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Nanostructures; Particle-reinforcement; Mechanical properties; Surface properties; Electrophoretic deposition

TiO2-PLLA nanocomposite coatings and free-standing films by a combined electrophoretic deposition-dip coating process - Chavez-Valdez, Alejandra; Arizmendi-Morquecho, Ana; Moreno, K. J.; Roether, Judith; Kaschta, Joachim; Boccaccini, Aldo R. (Composites Part B-Engineering, 2014)
TiO2/PLLA nanocomposites were prepared using a two-step process involving electrophoretic deposition (EPD) and dip coating (DC). EPD was carried out first to obtain porous TiO2 nanostructured coatings while subsequent dip coating was performed using different concentrations of PLLA in dichloromethane (DCM) to obtain nanocomposite materials. According to SEM images, cracks in the TiO2 nanostructured coatings, developed upon drying, were filled with the polymer which led to improvement of the flexibility of the nanocomposite coatings. Similarly, a surface modification from hydrophilic to hydrophobic was obtained with the addition of the polymer. FTIR analysis showed characteristic bands of both materials, TiO2 and PLLA, both on the coating surface and at the interphase between the nanocomposite coating and the substrate. Hardness measurements showed a maximum value of 1.4 GPa for TiO2–10 wt% PLLA composite. For DMTA tests, detached layers were used and the storage and loss moduli were determined. TiO2–PLLA nanocomposite coatings showed higher values of storage modulus at higher temperature in comparison to pure PLLA samples. Also, there was a shift in the glass transition temperature (Tg) with increasing TiO2 content. In conclusion, the EPD–DC combined technique proposed here enables the fabrication of nanostructured coatings and free-standing layers in which the quantity of PLLA can be changed according to the intended application, i.e. it is possible to fabricate coatings with tailored degradability and suitable mechanical properties with low additions of PLLA or free standing films with increased flexibility, biodegradability and biocompatibility with high amounts of PLLA.
Keywords: B. Mechanical properties; B. Surface properties; A. Nanostructures; A. Particle-reinforcement; Electrophoretic deposition

Toughening and functionalization of bioactive ceramic and glass bone scaffolds by biopolymer coatings and infiltration: a review of the last 5 years - Philippart, Anahi; Boccaccini, Aldo R.; Fleck, Claudia; Schubert, Dirk W.; Roether, Judith (Expert Review of Medical Devices, 2015)
Inorganic scaffolds with high interconnected porosity based on bioactive glasses and ceramics are prime candidates for applications in bone tissue engineering. These materials however exhibit relatively low fracture strength and high brittleness. A simple and effective approach to improve the toughness is to combine the basic scaffold structure with polymer coatings or through the formation of interpenetrating polymer-bioactive ceramic microstructures. The polymeric phase can additionally serve as a carrier for growth factors and therapeutic drugs, thus adding biological functionalities. The present paper reviews the state-of-the art in the field of polymer coated and infiltrated bioactive inorganic scaffolds. Based on the notable combination of bioactivity, improved mechanical properties and drug or growth factor delivery capability, this scaffold type is a candidate for bone and osteochondral regeneration strategies. Remaining challenges for the improvement of the materials are discussed and opportunities to broaden the application potential of this scaffold type are also highlighted.
Keywords: bioactive glasses; bioceramics; bone tissue engineering; calcium phosphates; composite materials; drug delivery; growth factors; hydroxyapatite; scaffolds

Toward strain resistant flexible organic thin film transistors - Jedaa, Abdesselam; Halik, Marcus (Applied Physics Letters, 2009)
We suggest a molecular design for small molecules as polycrystalline organic semiconductors in flexible organic thin film transistor applications, providing an improved stability during substrate bending. A stable operation of alkyl-substituted sexithiophens was obtained under strain up to ±2.5%. The stability relates to the flexibility of the alkyl chain substitution, scales with their chain length, and outperforms those of pentacene devices. These findings were independent from the underlying dielectric layer.

Transcutaneous Energy Transfer System for Cardiac-Assist Devices by Use of Inhomogeneous Biocompatible Core Material - Fazeli Khalili, Hossein; Kirchner, Jens; Bartunik, Max; Werner, Siegfried; Ebel, Nina; Schubert, Dirk W.; Weyand, Michael; Fischer, Georg (IEEE Transactions on Magnetics, 2021)
A novel magnetic liquid silicone rubber composite core design applicable to wireless power transfer (WPT) for medical applications is presented. As a case study, the integration of WPT, including the proposed cores for the coils, with ventricular assist devices (VADs) was investigated. This facilitates transferring 4.6 W of power wirelessly through the skin-layer, which thus allows to disposal of the transcutaneous cable that connects the extracorporal batteries to the implanted blood pump. To enhance the coupling coefficient and consequently increase the WPT efficiency, the geometry of the cores was optimized. This reduces the temperature increase in the implant area. The field and thermal simulations were carried out with CST software. The electrical properties of the proposed design as obtained by simulation were validated by measurements. The simulation results perfectly coincide with the measured results. Finally, a new optimized design with additional high permeability core inserts is introduced to further increase the coupling coefficient. The results indicate that the coupling coefficient is increased from 0.31 to 0.52 with the optimized design compared to the case without cores. Moreover, by fixing the initial temperature as 37 °C, the maximum temperature is decreased from 38.19 °C to 37.27 °C, while keeping the transferred power fixed. Its high magnetic conductivity, biocompatibility, low-loss property, flexibility and Qi-standard compatibility make the proposed WPT design an excellent candidate for the wireless-powering of heart assist devices such as VAD

Transparency and suture ability of alginate hydrogel reinforced nano-fiber scaffolds - Stafiej, Piotr; Schubert, Dirk W. (Europe Africa Conference 2017 of the Polymer Processing Society, 2017)

Transparency of nanofiber reinforced alginate hydrogels for corneal wound healing - Stafiej, Piotr; Küng, Florian; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Association for Research in Vision and Ophthalmology, 2017)

Transparency of suture able polycaprolactone nanofiber hydrogel compounds for medical application in the eye - Stafiej, Piotr; Fuchsluger, Thomas; Schubert, Dirk W. (54th Nordic Polymer Days, 2017)

Transparency of suture able polycaprolactone nanofiber hydrogel compounds (NFHC) for medical application in ophthalmology - Stafiej, Piotr; Küng, Florian; Fuchsluger, Thomas; Schubert, Dirk W. (Deutsche Gesellschaft für Biomaterialien 2017, 2017)

Trion Electroluminescence from Semiconducting Carbon Nanotubes - Jakubka, Florian; Grimm, Stefan; Zakharko, Yuriy; Gannott, Florentina; Zaumseil, Jana (ACS nano, 2014)
Near-infrared emission from semiconducting single-walled carbon nanotubes (SWNTs) usually results from radiative relaxation of excitons. By binding an additional electron or hole through chemical or electrochemical doping, charged three-body excitons, so-called trions, are created that emit light at lower energies. The energy difference is large enough to observe weak trion photoluminescence from doped SWNTs even at room temperature. Here, we demonstrate strong trion electroluminescence from electrolyte-gated, light-emitting SWNT transistors with three different polymer-sorted carbon nanotube species, namely, (6,5), (7,5) and (10,5). The red-shifted trion emission is equal to or even stronger than the exciton emission, which is attributed to the high charge carrier density in the transistor channel. The possibility of trions as a radiative relaxation pathway for triplets and dark excitons that are formed in large numbers by electron-hole recombination is discussed. The ratio of trion to exciton emission can be tuned by the applied voltages, enabling voltage-controlled near-infrared light sources with narrow line widths that are solution-processable and operate at low voltages (<3 V).
EAM Import::2019-03-13

Tunable Composition of Mixed Self-Assembled Shell-by-Shell Structures on Nanoparticle Surfaces - Eigen, Andreas; Stiegler, Lisa; Gradl, Susanne; Schneider, Vanessa; Wedler, Vincent; Gaß, Henrik; Müller, Lukas; Sarcletti, Marco; Heinrich, Markus; Hirsch, Andreas; Halik, Marcus (Advanced Materials Interfaces, 2022)
The formation of mixed shell-by-shell (SbS) systems with tunable shell compositions is demonstrated by using molecular self-assembly driven by chemical recognition motifs. Aluminum oxide nanoparticles (AlOx-NPs) act as template surface for a self-assembled monolayer (SAM) of either partially fluorinated fluoroalkyl or alkyl chained phosphonic acid derivatives or defined stoichiometric mixtures of those. By providing an equimolar mixture of corresponding fluoroalkyl and alkyl-chained amphiphiles in water, the stoichiometry of underlaying mixed SAM on the NP-surface preferentially directs the composition of the secondary self-assembly. The composition of the shell-by-shell assemblies is studied by high performance liquid chromatography and fluorescence spectroscopy. The concept allows the formation of NP-templated vesicle-like bilayer structures, even consisting of orthogonal chain structures in tunable composition driven by chemical recognition and hydrophobic segregation.
Created from Fastlane, Scopus look-up
Keywords: hydro-; fluoro-; lipophilic/phobic; nanoparticles; self-assembly; shell-by-shell architectures; surface chemistry

Tuning the molecular order of C60-based self-assembled monolayers in field-effect transistors - Schmaltz, Thomas; Khassanov, Artöm; Steinrück, Hans-Peter; Magerl, Andreas; Hirsch, Andreas; Halik, Marcus (Nanoscale, 2014)
The control of order in organic semiconductor systems is crucial to achieve desired properties in electronic devices. We have studied the order in fullerene functionalized self-assembled monolayers by mixing the active molecules with supporting alkyl phosphonic acids of different chain length. By adjusting the length of the molecules, structural modifications of the alignment of the C60 head groups within the SAM can be tuned in a controlled way. These changes on the sub-nanometre scale were analysed by grazing incidence X-ray diffraction and X-ray reflectivity. To study the electron transport properties across these layers, self-assembled monolayer field-effect transistors (SAMFETs) were fabricated containing only the single fullerene monolayer as semiconductor. Electrical measurements revealed that a high 2D crystalline order is not the only important aspect. If the fullerene head groups are too confined by the supporting alkyl phosphonic acid molecules, defects in the crystalline C60 film, such as grain boundaries, start to strongly limit the charge transport properties. By close interpretation of the results of structural investigations and correlating them to the results of electrical characterization, an optimum chain length of the supporting alkyl phosphonic acids in the range of C10 was determined. With this study we show that minor changes in the order on the sub-nanometre scale, can strongly influence electronic properties of functional self-assembled monolayers.

Tuning the molecular order of C60-based self-assembled monolayers in field-effect transistors - Schmaltz, Thomas; Khassanov, Artöm; Steinrueck, Hans-Georg; Magerl, Andreas; Hirsch, Andreas; Halik, Marcus (Nanoscale, 2014)
The control of order in organic semiconductor systems is crucial to achieve desired properties in electronic devices. We have studied the order in fullerene functionalized self-assembled monolayers by mixing the active molecules with supporting alkyl phosphonic acids of different chain length. By adjusting the length of the molecules, structural modifications of the alignment of the C60 head groups within the SAM can be tuned in a controlled way. These changes on the sub-nanometre scale were analysed by grazing incidence X-ray diffraction and X-ray reflectivity. To study the electron transport properties across these layers, self-assembled monolayer field-effect transistors (SAMFETs) were fabricated containing only the single fullerene monolayer as semiconductor. Electrical measurements revealed that a high 2D crystalline order is not the only important aspect. If the fullerene head groups are too confined by the supporting alkyl phosphonic acid molecules, defects in the crystalline C60 film, such as grain boundaries, start to strongly limit the charge transport properties. By close interpretation of the results of structural investigations and correlating them to the results of electrical characterization, an optimum chain length of the supporting alkyl phosphonic acids in the range of C10 was determined. With this study we show that minor changes in the order on the sub-nanometre scale, can strongly influence electronic properties of functional self-assembled monolayer

Tuning the Molecular Order of C60 Functionalized Phosphonic Acid Monolayers - Rumpel, Armin; Novak, Michael; Walter, Johannes; Braunschweig, Björn; Halik, Marcus; Peukert, Wolfgang (Langmuir, 2011)
Mixed self-assembled monolayers (SAM) of alkyl phosphonic acids and C60 functionalized octadecyl phosphonic acids (C60C18–PA) are deposited on alumina substrates from solution and are shown to form wellordered structures with an insulating layer of alkyl chains and a semiconducting layer that comprises mainly C60. Such an ordered structure is a necessity for the application of SAMs in organic transistors but is difficult to obtain since C60C18–PA without additional support do self-assemble in dense packaging but not in a well-ordered fashion. To avoid disordering of the SAM and to gain a better control of the interfacial properties we have investigated the stabilizing effects of fluorinated dodecyl phosphonic acids (FC12–PA) on the C60C18–PA monolayer. Vibrational sum-frequency (SFG) spectroscopy, ellipsometry, X-ray photoelectron spectroscopy, and electrical measurements were applied to study the mixed monolayers. Here, we make use of the differently labeled PA to determine surface coverages and molecular properties of the two species independently. Adsorption of FC12–PA gives rise to vibrational bands at 1344 cm-1 and 1376 cm-1 in SFG spectra, while a pronounced vibrational band centered at 1465 cm-1 is attributable to C60 vibrations. The coexistence of the bands is indicative for the presence of a mixed monolayer that is composed of both molecular species. Furthermore, a pronounced maximum in SFG intensity of the C60 band is observed for SAMs, which are deposited from solutions with  75% C60C18–PA and  25% FC12–PA. The intensity maximum originates from successful stabilization of C60 modified C60C18–PA by FC12–PA and a significantly improved molecular order. Conclusions from SFG spectra are corroborated by electric measurements that show best performance at these concentrations. Our results provide new information on the morphology and composition of C60 modified SAMs and establish a route to fabricate well-defined layers for molecular scale organic electronics.
Keywords: Thickness; Nonlinear optics; Layers; Monolayers

Tuning the molecular order of C-60 functionalized phosphonic acids - Rumpel, Armin; Novak, Michael; Walter, Johannes; Braunschweig, Björn; Halik, Marcus; Peukert, Wolfgang (2012)

Twisted lamellae in water-assisted injection molded high density polyethylene - Liu, Xian Hu; Pan, Yamin; Peng, Cheng; Hao, Xiaoqiong; Zheng, Guoqiang; Liu, Chuntai; Schubert, Dirk W.; Shen, Changyu (Materials Letters, 2016)
A distinct skin-core-water-channel structure was formed in water-assisted injection molded low molecular weight high density polyethylene. A large number of well-developed banded spherulites were observed in core region. Two types of shish-kebabs, i.e., shish-kebabs without and with twisted lamellae, were appeared in both skin and water-channel region. The results imply that the formation mechanisms of twisted lamellae in banded spherulites and shish-kebabs are different, but both depend on the level of applied shear stress. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Banded spherulites; Microstructure; Twisted lamellae; X-ray techniques

Two-photon 3D lithography: Materials and applications - Kuebler, S. M.; Braun, K. L.; Stellacci, F.; Bauer, C. A.; Halik, Marcus; Zhou, W.; Yu, T.; Ober, C. K.; Marder, S. R.; Perry, J. W. (Conference Proceedings - Lasers and Electro-Optics Society Annual Meeting-LEOS, 2004)

Two-Photon Absorption in Linear Bis-dioxaborine Compounds - the impact of correlation induced oscillator strength redistribution - Zojer, E.; Wenseleers, W.; Halik, Marcus; Grasso, C.; Barlow, S.; Perry, J. W.; Marder, S. R.; Bredas, J. L. (ChemPhysChem, 2004)

Ultralow-power organic complementary circuits - Klauk, Hagen; Zschieschang, Ute; Pflaum, Jens; Halik, Marcus (Nature, 2007)

Ultrasonic elasticity determination of 45S5 Bioglass®-based scaffolds: Influence of polymer coating and crosslinking treatment - Li, Wei; Pastrama, Maria-Ioana; Ding, Yaping; Zheng, Kai; Hellmich, Christian; Boccaccini, Aldo R. (Journal of the Mechanical Behavior of Biomedical Materials, 2014)
Highly porous 45S5 Bioglass-based scaffolds with interconnected pore structure are promising candidates for bone tissue engineering due to their bioactivity, biocompatibility, osteogenic and angiogenic effects. In the present study, to ensure the mechanical competence of the 45S5 Bioglass-based scaffolds, their stiffness was adjusted by applying polymer coatings and further crosslinking treatment. A non-destructive ultrasonic technique was used to determine the stiffness of the scaffolds. The stiffness of uncoated scaffolds was shown to increase by applying polymer coatings, and a further increase was achieved by crosslinking the used polymer coatings. All uncoated and polymer-coated scaffolds were confirmed to exhibit stiffness values in the range of reported values in the literature for cancellous bone. A statistical evaluation of combined multiscale ultrasound-nanoindentation measurements indicated that the stiffness of the coated scaffold is directly dependent on the stiffness of the polymer coating.
Keywords: Bioglass®; Elasticity; Polymer coating; Scaffold; Ultrasound

Universal and anisotropic simulation platform for the study of electrical proberties of conductive polymer composites - Yang, Guanda; Nilsson, Fritjof; Schubert, Dirk W. (AIP Conference Proceedings, 2019)
In order to carry out a study on the synergistic relationship of variables which could affect the electrical properties of CPC, a universal and anisotropic platform of simulation, containing three simulation modules are explored. The simulation modules are: finite element modelling (FEM), percolation threshold modeling (PTM) and electrical networks modelling (ENM
Keywords: mathematical modeling; conductive polymer composites; finite-element analysis; electrical circuits; electrical properties and parameters

Universal and anisotropic simulation platform for the study of electrical properties of conductive polymer composites - Yang, Guanda; Nilsson, Fritjof; Schubert, Dirk W. (AIP Conference Proceedings, 2019)
In order to carry out a study on the synergistic relationship of variables which could affect the electrical properties of CPC, a universal and anisotropic platform of simulation, containing three simulation modules are explored. The simulation modules are: finite element modelling (FEM), percolation threshold modeling (PTM) and electrical networks modelling (ENM

Untersuchung der mechanischen Eigenschaften Gel gefüllter Silikon Brustimplantate bei Druckbelastung und deren Auswirkung auf das Hüllenmaterial - von Hanstein, Harald (Gemeinsame Jahrestagung der Plastischen Chirurgie, 2017)

Up-conversion semiconducting MoO 3:Yb/Er nanocomposites as buffer layer in organic solar cells - Wang, Hao; Stubhan, Tobias; Osvet, Andres; Litzov, Ivan; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2012)
The spectral sensitivity of organic solar cells can be sensitized in the near-IR and IR by incorporating Yb/Er-doped MoO up-conversion nanocomposites. Poly-3-hexyl thiophene (P3HT) and [6,6] phenyl C butyric acid methyl ester (PC BM) were chosen for the active layer. Yb/Er-doped MoO nanoparticles with dual functionality were solution processed as charge selective interface layer. On the one hand, the electrical functionality of MoO as hole extraction layer is demonstrated. On the other hand, up-conversion emission from Yb sensitized Er dopants in the MoO nanoparticles is observed. Since the photocurrent generated from up-conversion with 975 nm excitation was found to be in competition with photocurrent contributions from a charge transfer complex absorbing also in the near IR, up-conversion from a Yb/Er doped MoO layer within an organic solar cell is proven spectroscopically and demonstrated by analyzing the photocurrent response of the Yb/Er doped cell and the undoped cell to the excitation intensity. The concept to integrate up-conversion functionality into metal oxide (MOx) based charge extraction layer suggests a promising and practical pathway for improving the near IR and IR sensitivity of thin film solar cells. © 2012 Elsevier B.V.
Keywords: Interface layer; Organic solar cell; Solution-processable; Up-conversion semiconducting MoO 3

Use of oleophilic magnetite nanoparticles as efficient sorbent for water contaminants - Sarcletti, Marco; Vivod, Dustin; Luchs, Tobias; Rejek, Tobias; Portilla, Luis; Hirsch, Andreas; Zahn, Dirk; Halik, Marcus (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2019-08-23

Using a fast hybrid pixel detector for dose-efficient diffraction imaging beam-sensitive organic molecular thin films - Wu, Mingjian; Stroppa, Daniel G.; Pelz, Philipp; Spiecker, Erdmann (JPhys Materials, 2023)
We discuss the benefits and showcase the applications of using a fast, hybrid-pixel detector (HPD) for 4D-STEM experiments and emphasize that in diffraction imaging the structure of molecular nano-crystallites in organic solar cell thin films with a dose-efficient modality 4D-scanning confocal electron diffraction (4D-SCED). With 4D-SCED, spot diffraction patterns form from an interaction area of a few nm while the electron beam rasters over the sample, resulting in high dose effectiveness yet highly demanding on the detector in frame speed, sensitivity, and single-pixel count rate. We compare the datasets acquired with 4D-SCED using a fast HPD with those using state-of-the-art complementary metal-oxide-semiconductor (CMOS) cameras to map the in-plane orientation of π-stacking nano-crystallites of small molecule DRCN5T in a blend of DRCN5T: PC71BM after solvent vapor annealing. The high-speed CMOS camera, using a scintillator optimized for low doses, showed impressive results for electron sensitivity and low noise. However, the limited speed restricted practical experimental conditions and caused unintended damage to small and weak nano-crystallites. The fast HPD, with a speed three orders of magnitude higher, allows a much higher probe current yet a lower total dose on the sample, and more scan points cover a large field of view in less time. A lot more faint diffraction signals that correspond to just a few electron events are detected. The improved performance of direct electron detectors opens more possibilities to enhance the characterization of beam-sensitive materials using 4D-STEM techniques.
CRIS-Team Scopus Importer:2023-10-20
Keywords: 4D-STEM; electron detector; electron microscopy; molecular crystal; organic materials

Using Supercritical Carbon Dioxide for Physical Foaming of Advanced Polymer Materials - Wolff, Friederich; Zirkel, Larissa; Sarah, Betzold; Jakob, Matthias; Verena, Maier; Nachtrab, Frank; Ceron Nicolat, Bruno; Fey, Tobias; Münstädt, Helmut (International Polymer Processing, 2011)
Foams from high performance polymers find more and more interest. The processes to generate them can be difficult, however. It is shown how physical foaming with CO2 can be used as a first step to assess the potentials of such materials. For investigations of such kind an autoclave on a laboratory scale which allows pressure variations up to 300 bars and temperatures up to 300 degrees C was set up. The samples are saturated with supercritical carbon dioxide (s.c. CO2) which acts as a foaming agent. Depending on the process and material parameters different foam characteristics and cell morphologies were obtained and characterised. The potential of this method is demonstrated for two different classes of advanced polymer materials, thermoplastic fluoropolymers (PEP), and a silicone resin. In the case of the fluoropolymer, previously prepared films were foamed and the effects of various process parameters on the foam characteristics were investigated. Besides the general potential of foams from fluoropolymers, they are candidates for polymeric piezoelectric materials with a relatively high temperature stability. Silicone polymers possess some properties superior to common organic polymers. First results on the foaming behaviour of a silicone resin are presented.

Various features of melt strain hardening of polymeric materials in uniaxial extension and their relation to molecular structure: review of experimental results and their interpretation - Münstedt, Helmut (Rheologica Acta, 2023)
Strain hardening of polymer melts is able to improve the uniformity of items in processing operations with elongational deformation. Of particular interest in this aspect is the dependence of strain hardening on elongational rate. In its first part, the paper presents a review on melt strain hardening obtained in uniaxial extensional experiments. Its dependence on elongational rate is of particular interest insofar as besides non-strain-hardening polymers, strain hardening increasing or decreasing with rate can be found. Results on linear polymers like polystyrene (PS), polypropylene (PP), high-density polyethylene (HDPE), and linear low-density polylethylene (LLDPE) in dependence on molecular parameters are discussed, as well as those of various blends. Particularly interesting are the strain-hardening features of certain HDPEs and LLDPEs, which could be understood by the assumption of a non-homogeneous chemical structure of the samples. Blends of various compositions of a linear and a long-chain branched PP throw light on the complex relation between branching structure and rate dependence of strain hardening. In the second part of the paper, the different strain-hardening behavior of linear polymers is interpreted by assessing the Rouse times as decisive physical quantity. For blends of certain linear species like HDPE and PP and those of linear with long-chain branched polymers, the existence of separate phases in the molten state is postulated. The assumptions are discussed in the light of the various studies on miscibility of linear and branched polyolefins from the literature. Graphical Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-08-04
Keywords: Dependence on strain rate; Linear and branched polymers; Melt strain hardening; Models; Polymer blends; Uniaxial elongation

Vascularization of Poly-ε-Caprolactone-Collagen I-Nanofibers with or without Sacrificial Fibers in the Neurotized Arteriovenous Loop Model - Kratzer, Simon; Arkudas, Andreas; Himmler, Marcus; Schubert, Dirk W.; Schneidereit, Dominik; Bauer, Julian; Friedrich, Oliver; Horch, Raymund E.; Cai, Aijia (Cells, 2022)
Electrospun nanofibers represent an ideal matrix for the purpose of skeletal muscle tissue engineering due to their highly aligned structure in the nanoscale, mimicking the extracellular matrix of skeletal muscle. However, they often consist of high-density packed fibers, which might impair vascularization. The integration of polyethylene oxide (PEO) sacrificial fibers, which dissolve in water, enables the creation of less dense structures. This study examines potential benefits of poly-ε-caprolactone-collagen I-PEO-nanoscaffolds (PCP) in terms of neovascularization and distribution of newly formed vessels compared to poly-ε-caprolactone -collagen I-nanoscaffolds (PC) in a modified arteriovenous loop model in the rat. For this purpose, the superficial inferior epigastric artery and vein as well as a motor nerve branch were integrated into a multilayer three-dimensional nanofiber scaffold construct, which was enclosed by an isolation chamber. Numbers and spatial distribution of sprouting vessels as well as macrophages were analyzed via immunohistochemistry after two and four weeks of implantation. After four weeks, aligned PC showed a higher number of newly formed vessels, regardless of the compartments formed in PCP by the removal of sacrificial fibers. Both groups showed cell influx and no difference in macrophage invasion. In this study, a model of combined axial vascularization and neurotization of a PCL-collagen I-nanofiber construct could be established for the first time. These results provide a foundation for the in vivo implantation of cells, taking a major step towards the generation of functional skeletal muscle tissue.<br
Keywords: vascularization of nanofiber scaffolds; neurotization; neoangiogenesis; EPI loop model; AV loop model; PCL-collagen I-nanofiber scaffolds; polyethylene oxide

Vascular Tissue Engineering: Effects of Integrating Collagen into a PCL Based Nanofiber Material - Bertram, Ulf; Steiner, Dominik; Poppitz, Benjamin; Dippold, Dirk; Köhn, Katrin; Beier, Justus; Detsch, Rainer; Boccaccini, Aldo R.; Schubert, Dirk W.; Horch, Raymund E.; Arkudas, Andreas (BioMed Research International, 2017)
The engineering of vascular grafts is a growing field in regenerative medicine. Although numerous attempts have been made, the current vascular grafts made of polyurethane (PU), Dacron (R), or Teflon (R) still display unsatisfying results. Electrospinning of biopolymers and native proteins has been in the focus of research to imitate the extracellular matrix (ECM) of vessels to produce a small caliber, off-the-shelf tissue engineered vascular graft (TEVG) as a substitute for poorly performing PU, Dacron, or Teflon prostheses. Blended poly-epsilon-caprolactone (PCL)/collagen grafts have shown promising results regarding biomechanical and cell supporting features. In order to find a suitable PCL/collagen blend, we fabricated plane electrospun PCL scaffolds using various collagen type I concentrations ranging from 5% to 75%. We analyzed biocompatibility and morphological aspects in vitro. Our results show beneficial features of collagen I integration regarding cell viability and functionality, but also adverse effects like the loss of a confluent monolayer at high concentrations of collagen. Furthermore, electrospun PCL scaffolds containing 25% collagen I seem to be ideal for engineering vascular grafts.

Velocity measurements on a polypropylene melt during extrusion through a flat coat-hanger die - Grieß, Hans Jürgen; Burghelea, Teodor; Münstedt, Helmut (Polymer Engineering and Science, 2012)
An experimental investigation of various flow regimes observed during the extrusion of a polypropylene melt through a flat coat-hanger die by laser-Doppler velocimetry (LDV) is presented. LDV measurements of the velocity profiles across the gap of the die at various locations along the die reveal three different extrusion regimes. At small wall shear stresses, the velocity profiles can be fitted by symmetrical curves with the velocities becoming zero at the die walls. These profiles are not uniformly distributed along the die. An increase of the wall shear stress reveals a second flow regime characterized by a uniform distribution of the velocity profiles along the die. As the wall shear stress is increased even further, a third flow regime characterized by wall slip on the glass windows is observed. This flow regime is systematically characterized by measurements of the slip velocities at various temperatures and throughputs. The maximum velocities along the die are taken to assess the uniformity of flow which decisively influences the thickness of the extruded film. By measuring velocity profiles, at different throughput, and temperatures, the conditions for constant velocities along the die were determined. © 2011 Society of Plastics Engineers.
Created from Fastlane, Scopus look-up

Verarbeitungstechnologien für Geopolymere: 3D-Druck und mechanische Bearbeitung - Toniolo, Nicoletta; Bednarzig, Vera; Roether, Judith; Rost, Harald; Boccaccini, Aldo R. (Keramische Zeitschrift, 2019)
CRIS-Team Scopus Importer:2019-06-21

Versagen von Silikonbrustimplantaten - Neuartige Kartierung und Aufdeckung von Produkt-Clustern - Daenicke, Jonas; Walter, Bastian; Horch, Raymund E.; Kaschta, Joachim; Schubert, Dirk W. (Plastische Chirurgie, 2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-TM.versag

Versatile bioactive and antibacterial coating system based on silica, gentamicin, and chitosan: Improving early stage performance of titanium implants - Ballarre, Josefina; Aydemir, T.; Liverani, Liliana; Roether, Judith; Goldmann, Wolfgang; Boccaccini, Aldo R. (Surface & Coatings Technology, 2019)
The aim of this work is to develop and characterize a multifunctional and dual surface coating system for titanium orthopedic implants by applying two different cost-effective, scalable, and non-complex coating technologies (spray and electrophoretic deposition). The first deposit is formed by a sprayed hybrid sol-gel layer combined with bioactive glass particles (45S5, BG), and the outer part of the dual coating consists of a chitosan-gelatin/silica (Si) - antibiotic (gentamicin, Ge) composite layer applied by electrophoretic deposition. The application of sol-gel enclosed BG drops onto the surface was done to enhance the bioactivity of the double-layered surface coating system. After the BG is dissolved, thus generating a calcium‑silicon rich medium, the re-deposition of hydroxyl‑carbonate apatite occurs. Regarding the antibacterial inhibition properties, antibacterial activity to both strains used (S. aureus and E. coli) was obtained for the chitosan/gelatin/Si[sbnd]Ge nanoparticle coatings on titanium substrates, showing a large inhibition area around the samples. Both the bare Ti samples and the coatings with chitosan/gelatin matrix did not successfully inhibit bacterial growth. As expected, the presence of silica-based glasses and coatings based on amorphous silica enhanced cell viability. The deposition of BG was done with the aim of extending the bioactive effect of the system, considering the presence of a porous degradable organic layer deposited on top, which was shown to be partially degraded after 7 days. The sol gel sprayed BG layer combined with chitosan/gelatin biopolymers filled with Si[sbnd]Ge nanoparticles presents a suitable technology to generate bioactive and antibacterial surfaces to enhance Ti implant performance.
CRIS-Team Scopus Importer:2019-12-13
Keywords: Antibacterial effect; Bioactive glass; Bioactivity; Electrophoretic deposition; Silica-gentamicin nanoparticles; Titanium

Very Facile Polarity Umpolung and Noncovalent Functionalization of Inorganic Nanoparticles: A Tool Kit for Supramolecular Materials Chemistry - Zeininger, Lukas; Petzi, Stefanie; Schönamsgruber, Jörg; Portilla Berlanga, Luis; Halik, Marcus; Hirsch, Andreas (Chemistry - A European Journal, 2015)
The facile assembly of shell-by-shell (SbS)-coated nanoparticles [TiO2 -PAC16 ]@shell 1-7 (PAC16 = hexadecylphosphonic acid), which are soluble in water and can be isolated as stable solids, is reported. In these functional architectures, an umpolung of dispersibility (organic apolar versus water) was accomplished by the noncovalent binding of ligands 1-7 to titania nanoparticles [TiO2 -PAC16 ] containing a first covalent coating with PAC16. Ligands 1-7 are amphiphilic and form the outer second shell of [TiO2 -PAC16 ]@shell 1-7. The tailor-designed dendritic building blocks 3-5 contain negative and positive charges in the same molecule, and ligands 6 and 7 contain a perylenetetracarboxylic acid dimide (PDI) core (6/7) as a photoactive reporter component. In the redox and photoactive system [TiO2 -PAC16 ]@shell 7, electronic communication between the inorganic core to the PDI ligands was observed.

Viscoelastic and electrical behavior of poly(methyl methacrylate)/carbon black composites prior to and after annealing - Pan, Yamin; Liu, Xian Hu; Kaschta, Joachim; Hao, Xiaoqiong; Liu, Chuntai; Schubert, Dirk W. (Polymer, 2017)
Keywords: Carbon black; Creep-recovery; Polymer nanocomposites; Viscoelastic properties

Viscoelastic properties of a silicone resin during crosslinking - Wolff, Friedrich; Kugler, Christoph; Münstedt, Helmut (Rheologica Acta, 2011)
Viscoelastic properties of a silicone resin crosslinked at various extents were characterised by means of rheology. The influence of temperature on the viscoelastic properties of the material as-delivered and in a state pre-crosslinked approximately to the gel point has been investigated by dynamic-mechanical measurements. While the glass transition temperature is increased by the crosslinking, no changes of the free volume fraction at Tg and its thermal expansion coefficient were observed. Taking the different glass transition temperatures into account, it could be shown that the corresponding WLF-parameters are the same. Themolar mass and, hence, the viscosity of the material can be increased by a heat treatment. The dependence of the zero shear-rate viscosity on the weight average molar mass indicates that the existence of entanglements of the polymer molecules is not very probable.
EAM Import::2019-03-12

Viscoelastic properties of suspended cells measured with shear flow deformation cytometry - Gerum, Richard; Mirzahossein, Elham; Eroles, Mar; Elsterer, Jennifer; Mainka, Astrid; Bauer, Andreas; Sonntag, Selina; Winterl, Alexander; Bartl, Johannes; Fischer, Lena; Abuhattum, Shada; Goswami, Ruchi; et al. (eLife, 2022)
Numerous cell functions are accompanied by phenotypic changes in viscoelastic prop-erties, and measuring them can help elucidate higher level cellular functions in health and disease. We present a high-throughput, simple and low-cost microfluidic method for quantitatively measuring the elastic (storage) and viscous (loss) modulus of individual cells. Cells are suspended in a high-viscosity fluid and are pumped with high pressure through a 5.8 cm long and 200 µm wide microflu-idic channel. The fluid shear stress induces large, ear ellipsoidal cell deformations. In addition, the flow profile in the channel causes the cells to rotate in a tank-treading manner. From the cell deformation and tank treading frequency, we extract the frequency-dependent viscoelastic cell properties based on a theoretical framework developed by R. Roscoe [1] that describes the deformation of a viscoelastic sphere in a viscous fluid under steady laminar flow. We confirm the accuracy of the method using atomic force microscopy-calibrated polyacrylamide beads and cells. Our measurements demonstrate that suspended cells exhibit power-law, soft glassy rheological behavior that is cell-cycle-dependent and mediated by the physical interplay between the actin filament and intermediate filament networks.
CRIS-Team Scopus Importer:2022-10-28

Viscosity and Softening Behavior of Alkali Zinc Sulfophosphate Glasses - Da, Ning; Krolikowski, Sebastian; Nielsen, Karsten H.; Kaschta, Joachim; Wondraczek, Lothar (Journal of the American Ceramic Society, 2010)
We report on the softening properties and viscosity of glasses from the system ZnO–Na_2O–SO_3–P_2O5 for low-temperature sealing applications. Up to a ratio of network-forming ions PO_43-:SO_42- of about 2:1, a gradual substitution of P_2O5 by SO_3 results in decreasing glass transition and softening temperatures. At the same time, decreasing kinetic fragility is observed, noteworthy even for decreasing the total amount of network former from 44 at.% to 39 at.%. Thermomechanical and calorimetric analyses reveal a distinct SO_42–promoted relaxation phenomenon at temperatures significantly below the macroscopic glass transition temperature, which is interpreted as a result of the formation of an increasingly interconnected assembly of SO_42- and PO_43- units with increasing SO_3 content.
EAM Import::2019-03-12

Viscous and elastic properties of polylactide melts filled with silica particles: Effect of particle size and concentration - Hao, Xiaoqiong; Kaschta, Joachim; Schubert, Dirk W. (Composites Part B-Engineering, 2016)
Mixing of inorganic particle into polymer material is widely used to tailor polymer with desired physical properties and processibility, in which the size and concentration of the former play a critical role in polymer processing. In this study, rigid spherical silica particle with varying size (average diameter of 7 nm, 40 nm, and 9 mu m) were used to reinforce polylactide (PLA) by melt compounding. The dependence of rheological properties of PLA/silica composites on the silica size and concentration were examined by dynamical mechanical and creep-recovery experiments. Our results demonstrate that mixing of silica particles into PLA matrix could increase the thermal stability of PLA. Oscillatory shear tests in the linear viscoelastic regime revealed a strong concentration-dependent behavior for the storage, loss moduli, and complex viscosity of the PLA/silica composites by the addition of nanosilica, while these properties were slightly affected by the addition of microsilica at low frequency range. A linear relationship between the silica concentration and the logarithmic form of zero shear viscosity (log eta(0)) of the composites is found when the concentration is below the rheological percolation threshold, whereas the growth rate is inversely influenced by the silica particle size. Creep-recovery experiments indicated that the elastic properties of PLA were more sensitive by the addition of silica than the viscous properties. Even for microsilica, a remarkable enhancement of the elastic properties was found at low silica concentration. A model based on the radius of gyration of polymer matrix R-g and the mean distance between particles D is proposed to describe the interactions between polymer matrix and particles. When D is larger than 2R(g), the particles-polymer interactions are suggested to be responsible for the rheological properties. On the other side, when D is smaller than R-g, a silica network structure will be formed and the rheological properties of the composites are dominated by the interactions of particle-particle and particle-polymer. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Particle-reinforcement; Polymer-matrix composites (PMCs); Elasticity; Rheological properties

Wafer-Scale Organic Complementary Inverters Fabricated with Self-Assembled Monolayer Field-Effect Transistors - Zhao, Baolin; Gothe, Bastian; Sarcletti, Marco; Zhao, Yuhan; Rejek, Tobias; Liu, Xinxin; Park, Hyoungwon; Strohriegl, Peter; Halik, Marcus (Advanced Electronic Materials, 2020)
Self-assembled monolayers (SAMs) of π-conjugated molecules can achieve robust charge transport by the formation of ordered 2D layers at the desired regions, which enable their application for organic integrated circuits. Here, the self-assembled monolayer field-effect transistor concept is applied as a scalable method to realize fully integrated complementary inverters by stepwise semiconductor deposition. Two-component stacked bilayer ambipolar transistors are fabricated by semiconducting self-assembled monolayers (n-SAM or p-SAM) as the bottom layer and a complementary thin-film semiconductor layer on top. The integrated complementary metal-oxide-semiconductor like (CMOS-like) inverter achieves proper logic performances. The nanometer-thin monolayers exhibit effective charge transport and their flat, homogeneous surfaces benefit the interconnected growth of the top layer. Furthermore, by controlling the solution-based and region-selective deposition of p- and n-type SAMs, fully integrated CMOS inverters are realized on wafer scale by photolithography for the first time. The CMOS inverters show a nearly 100% yield with a gain up to 48, and noise margin 3.68 V (73.6% of VDD/2). The strategy of semiconducting SAMs for digital logic gates demonstrates a reliable approach for sophisticated large-area circuits.
CRIS-Team Scopus Importer:2020-08-14
Keywords: organic complementary metal-oxide-semiconductor inverters; organic field-effect transistors; p-n heterojunction structures; self-assembled monolayers

Wall slip of magnetorheological elastomers in parallel-plate rotational rheometry - Walter, Bastian; Pelteret, Jean-Paul; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul (7. TA Anwendertreffen Rheologie - Erlangen, 2015)

Ways to more potent capacitors for high-voltage DC transmission technology based on polymer nanocomposites and blends - Werner, Siegfried; Kaschta, Joachim; Schubert, Dirk W. (VDE High Voltage Technology, 2021)
To evaluate possible improvements of thin film capacitors, biaxial oriented films based on nanocomposites of PP and hydrophobic silica as well as polymer blends of PP and ENC were investigated. Therefore, the films were produced on a pilot scale stretching line, metallized and wound to capacitors. On scanning electron microscope (SEM) images the PP/ENC blends showed a layer like structure and the particles a homogeneous distribution throughout the film. The morphology of the PP matrix investigated by differential scanning calorimetry (DSC) was comparable for all films. Additionally, the degradation by compounding and processing was investigated using high temperature gel permeation chromatography (HT-GPC). A pronounced reduction of the molecular weight was found for the nanocomposites, as the particles were added in an additional compounding step. The suitability of the compounds for an application as capacitor films was evaluated determining dielectric strength and voltage endurance of the films as well as the reduction in capacitance and the increase in loss factor of the capacitors during an endurance test based on IEC 61071. It was revealed that the degradation of the molecular weight determined by HT-GPC was the governing factor for all four parameters. Among the different compounds the blend of PP and ENC was the most promising as it showed low degradation and a better voltage endurance than the PP reference. Nanoparticles might still be a viable option, however the degradation during compounding has to be reduced significantly.
CRIS-Team Scopus Importer:2021-03-12

Wear and corrosion behaviors of high-power laser surface-cleaned 304L stainless steel - Park, Hyoungwon; Jong Yoo, Hyun; Park, Changkyoo (Optics and Laser Technology, 2024)
In this study, the influence of laser surface cleaning (LSC) on the wear and corrosion behaviors of 304L stainless steel (SS304L) is discussed. A kilowatt-level (1140 W) Nd:YAG laser with different hatch distances and repetition times is applied to remove the corrosion layer of SS304L, and its corresponding effects on SS304L are examined. Electron backscatter diffraction (EBSD) and kernel average misorientation (KAM) analyses of LSC-induced microstructural modifications reveal a smaller grain size and larger strain rate after the LSC process. In addition, an electron probe X-ray microanalyzer (EPMA) confirms the remaining local Cr-depletion regions even after a complete corrosion layer removal. These Cr-depletion regions are developed during the corrosion process, and an additional LSC process significantly reduces the Cr-depletion regions. Electrochemical tests are conducted to examine the corrosion behavior of the base metal and LSC specimens, and a larger corrosion resistance is achieved with fewer local depletion regions. Moreover, tribological tests reveal that a higher wear resistance is achieved after the LSC process owing to an increase in the surface microhardness.
CRIS-Team Scopus Importer:2023-08-11
Keywords: 304L stainless steel; Corrosion; Corrosion removal; Laser surface cleaning; Tribology

"Wer führt in (die) Zukunft“? Männer und Frauen in Führungspositionen der Wirtschaft in Deutschland – Die sechste Studie - Fifka, Matthias; Becker, Ingrid; Bischoff, S. (2016)
Keywords: Männer; Frauen; Führungspositionen; BWL; Zukunft; Führungskraft

Wet Chemical Synthesis of Graphene - Eigler, Siegfried; Enzelberger-Heim, Michael; Grimm, Stefan; Hofmann, Philipp; Kroener, Wolfgang; Geworski, Andreas; Dotzer, Christoph; Röckert, Michael; Xiao, Jie; Papp, Christian; Lytken, Ole; Steinrück, Hans-Peter; et al. (Advanced Materials, 2013)
A suitable technology for the preparation of graphene based on versatile wet chemistry is presented for the first time. The protocol allows the wet chemical synthesis of graphene from a new form of graphene oxide that consists of an intact hexagonal extgreeks-framework of C-atoms. Thus, it can be easily reduced to graphene that is no longer dominated by defects.

Wide Band-Gap Bismuth-based p-Dopants for Opto-Electronic Applications - Pecqueur, Sebastien; Maltenberger, Anna; Petrukhina, Marina; Halik, Marcus; Jäger, Arndt; Pentlehner, Dominik; Schmid, Guenter (Angewandte Chemie International Edition, 2016)

ZA-derived phonons in the Raman spectra of single-walled carbon nanotubes - Vierck, Asmus; Gannott, Florentina; Schweiger, Manuel; Zaumseil, Jana; Maultzsch, Janina (Carbon, 2017)
We report the observation of four Raman modes in individual, aligned single-walled carbon nanotubes, with frequencies between the RBM and D modes, and above the G(+/-) modes. By studying the diameter and excitation-energy dependence, we find that these strongly dispersive and comparatively intense modes share the lowest-frequency helical phonon branch as the origin, which can be derived from the out-of plane acoustic (ZA) phonon branch of graphene. This ZA phonon is observed due to a defect-assisted, double-resonant process, similar to the D mode; its two-phonon overtones and combinations with transverse optical (TO) phonons do not require defects. Our assignment is supported by a theoretical model based on sixth-nearest neighbour tight-binding and a force-constant approach. We present a complete theoretical evaluation of the diameter and excitation-energy dependence of the ZA, 2ZA, and TO +/- ZA modes, which fits very well to our experimental results and previous studies of the so-called region of intermediate frequency modes. (C) 2017 Elsevier Ltd. All rights reserved.

Zoledronic acid impregnated and poly (L-lactic acid) coated 45S5 Bioglass®-based scaffolds - Locs, Janis; Li, Wei; Sokolova, Marina; Roether, Judith; Loca, Dagnija; Boccaccini, Aldo R. (Materials Letters, 2015)
A new family of 45S5 Bioglass®-based scaffolds with local drug delivery capability was developed and characterized. The basic scaffold fabricated by the foam replica technique was impregnated with zoledronic acid and coated with poly(L-lactic acid) resulting in scaffolds with improved compressive strength in comparison with non-coated scaffolds and exhibiting the ability to deliver zoledronic acid in a controlled manner.
Keywords: Bioactive glass; Bisphosphonates; PLLA; Scaffolds

Correlation of Microstructure and Properties of Cold Gas Sprayed INCONEL 718 Coatings - Vassen, R.; Fiebig, J.; Kalfhaus, T.; Gibmeier, J.; Kostka, A.; Schrüfer, Stefan (Journal of Thermal Spray Technology, 2020)
In the cold gas spray process, deposition of particles takes place through intensive plastic deformation upon impact in a solid state at temperatures well below their melting point. The high particle impact velocities and corresponding peening effects can lead to high compressive residual stresses in cold spray coatings. This can be advantageous with regard to mechanical properties as fatigue life and hence, cold spray is an ideal process for repair applications. In this study, INCONEL 718 particles were cold sprayed by using nitrogen as propellant gas. The deposited coatings with different thicknesses were characterized using electron microscopy techniques to study grain refinement and precipitates in the coating. In addition, depth-resolved residual stress measurements have been performed by the incremental hole drilling method. The residual stress depth profiles in the coatings indicate compressive residual stresses of several hundred MPa which are hardly influenced by the coating thickness. In addition, large compressive stress levels are found in surface-near regions of the substrate due to the grit blasting process. Furthermore, a post-heat treatment analysis was performed to investigate its influence on residual stresses and bonding strength. These findings are used to develop a consistent explanation of the dependence of strength values on thickness.
Created from Fastlane, Scopus look-up
Keywords: Cold gas spraying; Electron microscopy; INCONEL 718; Incremental hole drilling method; Residual stress

Diagnostics of Cold-Sprayed Particle Velocities Approaching Critical Deposition Conditions - Mauer, G.; Singh, R.; Rauwald, K. -H.; Schrüfer, Stefan; Wilson, S.; Vassen, R. (Journal of Thermal Spray Technology, 2017)
In cold spraying, the impact particle velocity plays a key role for successful deposition. It is well known that only those particles can achieve successful bonding which have an impact velocity exceeding a particular threshold. This critical velocity depends on the thermomechanical properties of the impacting particles at impacting temperature. The latter depends on the gas temperature in the torch but also on stand-off distance and gas pressure. In the past, some semiempirical approaches have been proposed to estimate particle impact and critical velocities. Besides that, there are a limited number of available studies on particle velocity measurements in cold spraying. In the present work, particle velocity measurements were performed using a cold spray meter, where a laser beam is used to illuminate the particles ensuring sufficiently detectable radiant signal intensities. Measurements were carried out for INCONEL® alloy 718-type powders with different particle sizes. These experimental investigations comprised mainly subcritical spray parameters for this material to have a closer look at the conditions of initial deposition. The critical velocities were identified by evaluating the deposition efficiencies and correlating them to the measured particle velocity distributions. In addition, the experimental results were compared with some values estimated by model calculations.
Created from Fastlane, Scopus look-up
Keywords: cold spraying; critical velocity; deposition efficiency; Inconel 718; particle diagnostics; particle velocity